Circulating succinate changes during acute cold exposure are not related with brown adipose tissue in humans - Francisco J. Osuna-Prieto; Borja Martinez-Tellez; Guillermo Sánchez-Delgado; Francisco M. Acosta; Lucas Jurado-Fasoli; Joan Vendrell; Jonatan R. Ruiz; Sonia Fernández-Veledo (Journal of Physiology and Biochemistry, 2026)
Brown adipose tissue (BAT) activity in humans is linked to better glucose metabolism and cardiometabolic health. In mice, cold exposure increases circulating succinate and enhances BAT thermogenesis, but whether similar succinate responses occur in humans remains undetermined. We analysed data from 33 young (18–25 years), sedentary adults (20 women) from the ACTIBATE cohort (NCT02365129). Plasma succinate was measured enzymatically at baseline and 60 and 120 min during a personalized cooling protocol. BAT volume, activity, and radiodensity were assessed via static 18 F-fluorodeoxyglucose positron emission tomography–computed tomography ( 18 F-FDG PET-CT) at the end of the cold exposure. Circulating succinate changed over time during cold exposure, with no significant change at 60 min and a significant increase at 120 min versus baseline (+ 23.8%, P = 0.017), with substantial interindividual variability. Exploratory stratification by median baseline succinate revealed divergent temporal patterns: the low-baseline group showed increases at 60 min (+ 46%) and 120 min (+ 80.5%; both P ≤ 0.021), while the high-baseline group showed reductions at both timepoints (–31.4% and − 2.4%; both P ≤ 0.003). These profiles were not explained by phenotypic or BAT-related parameters. In the full cohort, changes in circulating succinate were not associated with BAT outcomes. Overall, our findings indicate that circulating succinate responses during acute cold exposure are highly heterogeneous and no associated with BAT PET/CT-derived parameters in humans.

Changes in circulating bile acid levels during cold exposure are associated with brown adipose tissue in humans: a secondary analysis from the ACTIBATE study - Lucas Jurado-Fasoli; Borja Martinez-Tellez; Isabelle Kohler; Jonatan R. Ruiz; Francisco J. Osuna-Prieto (Journal of Physiology and Biochemistry, 2026)
Cold exposure activates brown adipose tissue (BAT), a therapeutic target to mitigate cardiometabolic diseases. Emerging evidence suggests that bile acids may influence BAT activity through metabolic and endocrine signaling pathways. Characterizing changes in circulating bile acids during cold exposure may uncover new pathways to improve metabolic health in humans. We analysed 56 young (21.7 ± 2.3 years old), sedentary adults (43 women, 77%) from the ACTIBATE cohort (NCT02365129) before the intervention in whom plasma samples were available for bile acid analyses. Eighteen plasma bile acid species were analyzed using liquid chromatography-tandem mass spectrometry before (i.e., baseline), 60, and 120 min during a personalized cooling protocol. BAT volume, activity, and radiodensity were assessed via 18 F-fluorodeoxyglucose positron emission tomography-computed tomography scan ( 18 F-FDG PET-CT) at the end of the cooling protocol. During the 2-hour cold exposure, plasma levels of total, secondary, and conjugated bile acids decreased by 24–30% (all P < 0.001). In normal-weight participants, most reductions remained significant after adjustment for PET-CT time, and glycolithocholic acid (GLCA) showed consistent positive associations with BAT volume and glucose uptake, as well as an inverse association with radiodensity (|r|≤0.41, adj. FDR ≤ 0.25; R ≤ 0.34, P ≤ 0.038 in adjusted regression models). In participants with overweight or obesity, most bile-acid changes lost statistical significance after adjustment for PET-CT time, although lithocholic acid and its sulfated derivative remained positively correlated with BAT radiodensity (|r|≤0.53; adj. FDR ≤ 0.25). Acute cold exposure is associated with changes in circulating bile acids in humans, with patterns differing by body-weight status. In normal-weight individuals, GLCA displayed consistent associations with BAT volume and glucose uptake, suggesting a possible link between bile acid and BAT activation. Further studies are needed to confirm these observations and to clarify the physiological relevance of bile acid signaling in human thermogenic adaptation.

Gymnodinium catenatum blooms in the northern Gulf of California: From massive mortalities of seabirds and marine mammals to socioeconomic impacts - Ernesto García-Mendoza; Jennifer Medina-Elizalde; Mary Carmen Ruiz-de la Torre; Erick J. Núñez-Vázquez; Jose J. Bustillos-Guzmán; David Rivas; Frances M.D. Gulland; Andrew D. Turner; Miguel Matus-Hernández; Maggie Broadwater; Rigel Castañeda-Quezada; Kassandra Beltran-Solis; et al. (Harmful Algae, 2026)

Clinical outcomes of patients with brain metastases from primary esophageal cancer - Bianca Nolde-Lopez; Christina K. Cramer; Scott Isom; Anthony Naquin; Caio M.S.P. Rocha Lima; Ravi K. Paluri; Jimmy Ruiz; Fei Xing; Christopher T. Whitlow; Stephen B. Tatter; Adrian W. Laxton; Jaclyn J. White; et al. (Next Research, 2026)

Risks of mercury release from disturbance of blue carbon ecosystems - Fan Zhang; Jingrou Hu; Ana Carolina Ruiz-Fernández; Christian J. Sanders; Xinxin Li; Ruotong Chen; Kunshan Bao; Bigyan Neupane; Aidah Baloch; Yanhui Zheng; Oscar Serrano (Earth-Science Reviews, 2026)

Evolutionary history reveals spatial concentration of threatened evolutionary diversity in Agave across the Americas - Karen Y. Ruiz-Mondragón; Luis E. Eguiarte; Abisaí J. García-Mendoza; Erika Aguirre-Planter; Jorge Nieto Sotelo; Marcella Corcoran; Paul Rees; Amy Barker; Stuart Cable; Bryan Naqqi Manco; Dodly Prosper; Junel Blaise; et al. (Biological Conservation, 2026)

Tissue composition and thermal performance in native and invasive mussels from southern chile - Melissa Fernández; Roddy Jara; Oscar Varas; Diego Quintanilla-Ahumada; Pedro A. Quijón; Cristian Duarte; Pablo A. Oyarzún; Marcela Aldana; Roberto García-Huidobro; Gonzalo J. Ruiz-Tagle; José Pulgar (Marine Biology, 2026)

From Hazard Occurrence to Risk Assessment: Antimicrobial Resistance and Chemical Co-selection in Ready-to-Eat Vegetables: A Scoping Review - Jowenna X.F. Sim; Claire Hayward; Mark Drew; Fran Lopez-Ruiz; Sukhvinder Pal Singh; Nicholas J. Ashbolt; Barbara Drigo (Trends in Food Science & Technology, 2026)

Synergistic effect of process parameters influencing the physico-chemical properties of magnetic activated carbons from industrial chestnut wastes - M. Niubó; B. Ruiz; S. Rodríguez-Sánchez; E. Fuente; J.J. de Felipe; J. Lladó (Process Safety and Environmental Protection, 2026)

Microbially influenced uranium biomineralization and mineralogical changes in a U(VI)/carbon steel/bentonite system for repository safety assessment - Cristina Povedano-Priego; Miguel Angel Ruiz-Fresneda; Fadwa Jroundi; Lidia Lopez-Tercero; Laura Carmen Terrón-Camero; Marta Espinar-Solano; Ursula Alonso; Ana M. Fernández; Jesus J. Ojeda; Mohamed L. Merroun (Journal of Hazardous Materials, 2026)

Quantitative sustainability assessment of bioactive ingredients lipophilization - Francisco J. Ruiz; Susana Nieto; Maite Nuño; Rocio Villa; Pedro Lozano (Journal of Cleaner Production, 2026)

Characterisation of bituminite and testing reproducibility of vitrinite and bituminite reflectance measurements in organic‑carbon-rich intervals of the Kimmeridge Clay Formation: ICCP Identification of Dispersed Organic Matter Working Group round robin exercises - J. Kus; A.G. Borrego; B. Bielowicz; P. Crosdale; M.-E. Damoulianou; D. Flores; C. Fonseca; P.A. Gonçalves; P.C. Hackley; M. Hámor-Vidó; S. Henne; B. Holstein; et al. (International Journal of Coal Geology, 2026)

Thin films composed of hydrolyzed collagen and chitosan as sustainable dressings for medical use: Formulation and evaluation - K.L. Hernández-Ruiz; D.I. Sánchez-Machado; J. López-Cervantes; A.A. Quintero-Guerrero; O.N. Campas-Baypoli; J.R. González-Galaviz; L.Z. Rodríguez-Anaya; D. Servín de la Mora-López; L.A. Esquer-Núñez; T.J. Madera-Santana; P. Vázquez Loureiro (Food and Bioproducts Processing, 2026)

A novel approach against amitraz toxicity based on magnetic extraction using native β-cyclodextrin and β-cyclodextrin polymers attached to superparamagnetic nanoparticles for potential human cell protection - F. Franco-Campos; Y. Rodríguez-Carrasco; A. Riveros; C. Álamos; S. Guerrero; F. Melo; R. Sierpe; N. Yutronic; S. Oyarzún; J. Denardin; M.J. Ruiz; M.J. Kogan; et al. (Chemico-Biological Interactions, 2026)

Engaging European local communities in biodiversity genomics research: A five-step framework for scientists - Christian de Guttry; Chiara Bortoluzzi; Luísa S. Marins; Tinatin Chkhartishvili; Camilla R. De Pierri; Stefaniya Kamenova; Jennifer A. Leonard; Kay Lucek; Lada Lukić Bilela; Camila J. Mazzoni; Ann M. Mc Cartney; Svein-Ole Mikalsen; et al. (Biological Conservation, 2026)

Contemporary distribution of non-native coho salmon in South America - César Bugueño; Joseph A. Langan; J. Andrés Olivos; Javier Ciancio; Selim S. Musleh; Mauricio Cañas; Graciela Fabiano; Santiago Silveira; Martín Laporta; Tamara Contador; Bruno Ruiz; Carolina Araya; et al. (Biological Invasions, 2026)

Double-edged dispersal: animal-mediated transport in the Anthropocene - Andrew J. Abraham; Ethan S. Duvall; Eva Moracho; Maria J. Ruiz-López; Lola Gilbert; Diego Ellis-Soto; Tomos Prys-Jones; Emma-Liina Marjakangas (Trends in Ecology & Evolution, 2026)

Alpha-gal syndrome: Mechanisms, global epidemiology, and implications for meat science - Sara R. Hene; Jordan T. Looper; Karl J. Clark; Paulina Maldonado-Ruiz; Yoonseong Park; Priscilla Brenes; Michael D. Chao (Meat Science, 2026)

Impact of pre-harvest elicitors on the toxigenic mycobiota and mycotoxin risk in dried figs: A holistic safety assessment - Cristina Hidalgo; Santiago Ruiz-Moyano; Alicia Rodríguez; Margarita López Corrales; Josué Delgado; Manuel J. Serradilla (International Journal of Food Microbiology, 2026)

Predicting gas evolution during steam gasification of chars derived from biomass pyrolysis - M.N. Rivas-Márquez; R. Ruiz-Rosas; J.M. Rosas; J. Rodríguez-Mirasol; T. Cordero (Fuel, 2026)

Pre- and post-hatching effects on nestling growth and brood reduction - Juan J Soler; María D Barón; Antonio J García-Núñez; Ester Martínez-Renau; Magdalena Ruiz-Rodríguez; Gustavo Tomás; Manuel Martín-Vivaldi (Behavioral Ecology and Sociobiology, 2026)
Developmental trajectories are considered plastic phenotypic traits that allow animals to adjust their growth in response to environmental conditions. Plasticity in growth trajectories is likely mediated by parental effects occurring before and after offspring birth, but its relative contribution has rarely been explored in the wild. By swapping first, intermediate, and last hatched nestlings between nests of the European hoopoe ( Upupa epops ), a species with pronounced hatching asynchrony, we experimentally broke the natural association between laying and hatching order to explore their effects on nestling growth and survival. First-hatched nestlings grew faster and experienced the lowest probability of death and cannibalism regardless of their rank hierarchy in their nest of origin. Growth rate of intermediate nestlings was lower than that of first and last nestlings, but deficiencies were compensated for afterwards, and they showed an intermediate probability of death and cannibalism. Finally, most of the last-hatched nestlings showed deficient growth during the nestling period, and the highest probability of death and cannibalism. The hatching position of experimental nestlings in their nest of origin had little effect on their growth patterns in the nest of rearing, and did not affect their probability of death. These results suggest that post-hatching effects are responsible for nestling probability of death and cannibalism, while pre-hatching effects associated with egg-laying order may be partially responsible for the particularities of growth patterns among nestlings of different hatching order. We discuss the importance of these results under the hypothesis that animals should adjust pre- and post-hatching investment according to the fitness value of their offspring.

Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.

Spatial Partitioning of Microbial Functional Potential Suggests Complex Nitrogen Cycling in a Subterranean Estuary - Daniel Romano‐Gude; Nestor Arandia‐Gorostidi; Catalina Mena; Marc Diego‐Feliu; Bella Almillategui; Anna J. Székely; Stefan Bertilsson; Andrea G. Bravo; Jesus Carrera; Cristina Romera‐Castillo; Albert Folch; Jordi Garcia‐Orellana; et al. (Environmental Microbiology, 2026)
Subterranean estuaries (STEs) are key bioreactors regulating the quantity and chemical composition of groundwater‐derived nitrogen (N) reaching coastal ecosystems. Yet, the microbial controls on N‐cycling within these groundwater–seawater mixing zones remain poorly understood. We investigated the spatio‐temporal variations in microbial communities and their N‐cycling potential within an alluvial Mediterranean STE with high N concentration. We explored changes in microbial abundance, heterotrophic activity, taxonomic composition, and the abundance of N‐cycling genes across groundwater samples collected at several depths and distances from the shoreline in winter and summer. Microbial abundance, activity, and diversity varied strongly across hydrochemical zones according to physicochemistry and aquifer depth but showed limited seasonality. Functional predictions suggested a complex, spatially structured suite of N pathways encoded by diverse taxa occupying different STE zones, and quantitative‐PCR revealed niche partitioning between ammonia‐oxidizing archaea, prevalent in fresh‐groundwater, and bacterial denitrifiers enriched in deep‐saline layers. Multiple linear model predictions showed a stronger fit for NO 2 − and NH 4 + concentrations when using microbial properties than when using environmental variables, highlighting their importance for understanding N cycling in STEs. Our results suggest that the functional potential of the STE microbiome is complex and spatially structured across hydrochemical zones, explaining spatial variations in STE N‐cycling.

Optimizing Photogrammetry Parameters for 3D Reconstruction of Fresh Brain Specimens - Carlos A. Rueda-Pérez; María-Camila Valencia-Loaiza; Paula Vega-Cordoba; Juliana Tobón; Dylan S. Anaya; Andres Gonzalez-Leyton; Juan F. Mazo; Jesús D. Tarazona; Santiago Ruiz; Juan G. Martinez; Andrés Echeverri-Garcia; Catherine J. Gomez-Moreno; et al. (Neuroinformatics, 2026)
Photogrammetry has become an essential tool in medical and research fields for generating high-fidelity 3D models from 2D images. However, optimizing the imaging and processing parameters remains a challenge, particularly for fresh brain specimens, where repeated imaging is not feasible. This study systematically evaluates the impact of various Metashape alignment settings on 3D reconstruction outcomes, analyzing 12,600 configuration combinations and 63,000 alignments. Our results suggest that the optimal imaging setup consists of four photo sets: two captured at anatomical position (level with the brain and 30 cm above it at a 30° camera tilt) and two identical sets with the basal side facing upwards. The brain should be rotated 3° between shots, generating 120 images per set. Initial processing should be performed without masks using medium-precision alignment in Metashape. If alignment fails, we recommend generating one mask per image, delineating the brain’s borders, and applying masks to key points. Notably, higher image density only improves alignment reliability when masking is selected to detected features and may only increase processing time. We also observed variability in alignment results under identical conditions, suggesting an inherent stochastic component in Metashape. Consequently, unsuccessful alignments should be repeated before modifying imaging parameters. To our knowledge, this is the first study to systematically define an optimal imaging and processing parameters for 3D photogrammetry of fresh brains using a turntable. Future research should focus on determining the minimum number of images required to ensure high-quality reconstructions.

Boosting betalain bioaccessibility from prickly pear peel through pulsed electric fields (PEF) and pressurized liquid extraction (PLE) - Mara Calleja-Gómez; Noelia Pallarés; María Gaona-Ruiz; Francisco J. Barba; Celia Carrillo (Food Chemistry, 2026)

Occurrence and distribution of emerging contaminants in surface water and biota: An integrated analytical-statistical assessment - Enrique J. Díaz-Montaña; Sofía Dominguez-Gil; María G. Hinojosa; Ramón Aparcio-Ruiz; María T. Morales (Environmental Pollution, 2026)

Water Limits Radial Tree Growth More Than Light in an Everwet Subtropical Forest - Laura E. Boeschoten; Chris M. Smith‐Martin; Jose A. Medina‐Vega; Kristina J. Anderson‐Teixeira; Luis A. Esbrí Ruiz; Rebecca A. Montgomery; Monique Picón; Mukund P. Rao; Tana E. Wood; Xiangtao Xu; Jess K. Zimmerman; María Uriarte (Global Change Biology, 2026)
Everwet tropical forests, defined by the absence of a pronounced dry season, are globally significant carbon sinks, covering roughly 80% of Southeast Asian tropical forests, 30% of the Amazon basin, and 10% of the Congo Basin. Yet the climatic drivers of stem radial growth in these ecosystems remain understudied. The prevailing hypothesis is that growth is primarily light‐limited, as persistent cloud cover constrains photosynthesis. Evaluating this assumption is critical as climate projections for the humid tropics point towards rising atmospheric evaporative demand, episodic drought, and reduced cloud cover, conditions whose net effect on woody growth remains unresolved. To address this gap, we deployed automated point dendrometers on 35 trees in an everwet subtropical forest with 3500 mm mean annual precipitation and no pronounced rainfall seasonality, collecting 2 years of hourly radial stem growth data alongside concurrent measurements of soil moisture, vapor pressure deficit (VPD), and light availability. Contrary to the prevailing light‐limitation hypothesis, soil moisture and atmospheric evaporative demand were the primary determinants of both whether and how much growth occurred on any given day, even under these perennially wet conditions. Light availability and photoperiod enhanced growth magnitude when water was not limiting, but their effects were consistently smaller. Droughts occurring during the wetter, high‐growth months had the greatest negative impact on annual stem increment, potentially reducing annual growth to just 20% of current levels. These results challenge long‐standing assumptions of light‐limited stem growth in everwet forests, which is critical for improving model projections of forest responses to climate change. Broader validation across tropical forests, combined with direct physiological measurements of carbon uptake and storage, will be essential to evaluate our working hypothesis that radial growth in these everwet ecosystems is ultimately more constrained by water availability than by carbon supply.

Soil Microbial Diversity and Network Organization Respond to Land Use and Agricultural Inputs Worldwide - Zaki Saati‐Santamaría; Sergio Pérez‐Gorjón; Daniel Abel‐Schaad; Alberto Acedo‐Bécares; Francisca Alba‐Sánchez; Amanda Lucia Alves; Weronika Babinska‐Wensierska; Jorge Ariel Marfetán; Carolina Barroetaveña; Kara Barry; Francisco Beitia; Katerina Biniari; et al. (Global Change Biology, 2026)
Soil microbiomes are critical for ecosystem functioning, yet the global influences of climate and agricultural practices on their diversity and structure remain incompletely characterized. Here we analyzed 1921 soil samples from 33 countries worldwide across diverse biomes to assess how climate gradients and agricultural inputs, including pesticides and fertilizers, shape prokaryotic and fungal communities. We found that microbial diversity peaks at intermediate temperatures and differs markedly between natural and agricultural soils, with agriculture increasing microbial diversity while altering community composition and ecological guilds. Pesticide use selectively reduced bacterial diversity and shifted fungal guilds, decreasing ectomycorrhizal fungi while increasing saprotrophs, whereas fertilization reduced microbial network cohesion, with organic and inorganic fertilizers eliciting distinct community responses. These findings reveal that climatic factors and agricultural management jointly influence soil microbial diversity, community structure, and network connectivity, with implications for soil health and ecosystem resilience in managed landscapes. Overall, our results demonstrate that agricultural practices, including the use of pesticides and both organic and inorganic fertilizers, act as strong ecological filters that reshape soil microbiomes worldwide—enhancing apparent diversity but driving a functional shift toward less mutualistic, more fragmented, and potentially less resilient communities.

Uncovering the association between broad emotional dysregulation and emotional eating: A meta-analysis - Jara Mendia; Yolanda Quiles; Aitziber Pascual; Álvaro Ruiz; Javier Manchón; Susana Conejero; José J. Pizarro; Itziar Alonso-Arbiol (Appetite, 2026)

Contrasting provenance, fluxes and budgets for dissolved aluminium and barium in the Mediterranean; an integrating overview - Gert J. De Lange; Nieves Torres-Crespo; Francisca Martinez-Ruiz; Bernard Schnetger (Quaternary Science Reviews, 2026)

What do we know about tooth weathering? A neotaphonomic study on mammals from the Argentine Pampas - Rodrigo L. Tomassini; Claudia I. Montalvo; Dores Marin-Monfort; Iván Rey-Rodríguez; Yolanda Fernández-Jalvo; Fernando J. Fernández; Gabriel Nahuel-Ruiz; Marta S. Kin (Quaternary International, 2026)

The plant lipid contactome: emerging roles of inter-organelle contact sites in lipid metabolism - Carolina Huercano; Miriam Moya-Barrientos; Oliver Cuevas; Carlos Cardenas; Joaquín J. Salas; Victoria Sanchez-Vera; Noemi Ruiz-Lopez (Progress in Lipid Research, 2026)

Effect of drought and shading on lime yield, bioactive compounds (vitamin C and flavanones) and postharvest life - Ana Belén Mira-García; Vicente Agulló; Francisco J. Salar; Wenceslao Conejero; M. Carmen Ruiz-Sánchez (Postharvest Biology and Technology, 2026)

Nitrogen and sulfur co-limitation and stoichiometry modulate yield and nutrient use efficiency of bread wheat - Brent R. Jaenisch; Nicolas Giordano; Victor O. Sadras; Nathan O. Nelson; Mary J. Guttieri; Allan K. Fritz; Dorivar Ruiz Diaz; Romulo P. Lollato (Field Crops Research, 2026)

Serum metabolomics of diabetic dogs treated with daily administration of a commercially available lyophilized feces preparation - Jose D. J. Ruiz Romero; Patrick Barko; Jan S. Suchodolski; David A. Williams; Holly H. Ganz; Arnon Gal (Veterinary Research Communications, 2026)
Enteric microbial dysbiosis can contribute to the pathobiology of canine diabetes mellitus (DM) by interfering with host metabolism, promoting inflammation, and altering incretin hormone responses. Enriching and diversifying an unbalanced gastrointestinal microbiome with microbiome-based interventions such as lyophilized fecal preparations (LFP) can help improve gut function and glycemic control of diabetic dogs. This study aimed to determine the differences in the serum metabolomes, levels of interstitial glucose (IG), and 24-hour water intake of diabetic dogs treated with daily administration of LFP or placebo. A prospective, randomized, double-masked, placebo-controlled clinical trial was conducted using six DM dogs in the LFP group and six DM dogs in the placebo group. Dogs had physical examinations and 24-hour water intake assessments at admission, 2, 4, 6, and 8 weeks, with continuous IG monitoring performed throughout the study. Serum samples were collected longitudinally at baseline and during follow-up for untargeted metabolomic analysis. The marginal mean of IG after 8 weeks was lower in the LFP group (286 ± 22 mg/dL vs. 309 ± 22 mg/dL; p = 0.468), with the LFP group showing lower marginal mean IG at each time point except week five. Marginal mean log 24-hour water intake was significantly lower in the LFP group compared to placebo (mean difference − 0.24 ± 0.10, p = 0.024). Treatment groups significantly differed in metabolites with important roles in carbohydrate, protein, and lipid metabolism. Overall, our results show that LFP induced measurable metabolic alterations, with patterns generally consistent with a more favorable metabolic profile, but only minimal improvement in glycemic control.

Geospatial analysis of Andean microbialitic systems as analogues for the search for life on Mars - Micaela Della Vedova; Julia Jimeno-Alda; Francisco J. Ruiz-Sanchez; Luis R. Horta; Patricio G. Villafañe (Earth Science Informatics, 2026)

Impact of an online-guided physical activity intervention on cognition, resting-state brain connectivity, and the gut microbiome in healthy older adults—a randomized controlled trial - Simon J. Schrenk; Corinna Bang; Lena Best; Thomas Dost; Stefano Flor; Christiane Frahm; Christian Gaser; Rami Abou Hamdan; Marco Herbsleb; Christoph Kaleta; Fabian Kattlun; Hans-Josef Müller; et al. (GeroScience, 2026)
Introduction Physical activity may enhance cognition in older adults, yet evidence from randomized controlled trials (RCTs) on mechanistic pathways remains inconclusive. Methods This single-blinded RCT examined the effects of an 8-week, online-guided, multicomponent physical activity intervention on cognitive function, resting-state functional brain connectivity (rsFC), and the gut microbiome in 92 healthy older adults (M age = 66.35). Participants were randomized to a physical activity group performing moderate-to-vigorous-intensity aerobic, coordination, and balance exercises, or to an active control group engaging in progressive muscle relaxation and listening to aging-related podcasts. The primary outcome was change in visual processing speed (items/s) from pre- to post-assessment. Secondary outcomes included changes in additional cognitive measures, rsFC, cardiorespiratory fitness (CRF), and the gut microbiome. Results The primary outcome showed no significant between-group differences. However, exploratory analyses revealed potential improvements in inhibition ( η 2 = 0.061; p = 0.025) and visual memory ( η 2 = 0.047; p = 0.040) in the physical activity group. This group also showed a potential increase in rsFC between visual and dorsal attention networks ( η 2 = 0.101; p = 0.009). Visual memory gains correlated with improvements in rsFC ( p = 0.013). No between-group differences were observed in CRF or gut microbiome composition. Discussion While the primary outcome (visual processing speed) and predefined mechanistic pathways (e.g., gut microbiome composition) remained unaffected, this may partly reflect the sample’s high baseline fitness, which likely limited observable improvements. Exploratory findings suggest potential cognitive and associated rsFC benefits in memory and attention-related networks. The online format enabled a structured, scalable intervention while minimizing potential confounding from social interaction. Trial registration https://drks.de/search/de/trial/DRKS00028022 (date of registration: 14.02.2022).

Nicotinic acid treatment improves the developmental potential of equine oocytes for cloned embryo production - Jenin V. Cortez; Danton Cervi; Agustin J. Ruiz; Christopher G. Grupen (Theriogenology, 2026)

LA-COMET group: In vivo application of the comet assay in animal and plant models, including wild species - Gisela L. Poletta; Patricia Mussali-Galante; J. Alfredo Castillo-Ipiña; Guillermo Espinosa-Reyes; Ana Rosa Flores-Márquez; Donaji J. González-Mille; César A. Ilizaliturri-Hernández; Celeste Ruiz de Arcaute; Efraín Tovar-Sánchez; Juliana da Silva; Deidamia Franco; Ana Leticia García; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Ichnological response of macrobenthic fauna to Late Devonian anoxic pulses: New evidence from North America and a global synthesis - Javier Fernández-Martínez; Francisco J. Rodríguez-Tovar; Francisca Martínez-Ruiz; Thomas J. Algeo (Global and Planetary Change, 2026)

Long-term electrodialysis nutrient concentration from anaerobic membrane bioreactor effluents: Challenges for calcium sulfate precipitation - P. Ruiz-Barriga; S. Hernández-Cuenca; J. Serralta; R. Barat; A. Bouzas; J. Carrillo-Abad (Desalination, 2026)

Antimicrobial 3D printed implants for periprosthetic joint infections - Iván Yuste; Francis C. Luciano; Carmina Rodríguez; Bianca I. Ramirez; Chrysi Rapti; Brayan J. Anaya; Aikaterini Lalatsa; Almudena Ribed-Sánchez; Pablo Sanz-Ruiz; Elena González-Burgos; Dolores R. Serrano (Drug Delivery and Translational Research, 2026)
Periprosthetic joint infections (PJIs) remain a serious complication following hip and knee arthroplasty, affecting 1–5% of patients in developed countries and posing significant challenges to patients, clinicians, and healthcare systems. Conventional prophylactic strategies, such as antibiotic-loaded bone cement, suffer from limited post-implantation drug release and potential compromise of mechanical integrity. To overcome these limitations, we developed a personalized, 3D-printed implant designed to integrate with the acetabular component of joint prostheses. These implants deliver either monotherapy or a combination of amphotericin B (AmB) and vancomycin (VAN), targeting both fungal and bacterial pathogens. Fabricated via fused deposition modeling using a biocompatible polyvinyl alcohol–polyethylene glycol (PVA–PEG) matrix, the implants enable passive drug loading and rapid adhesion to prosthetic surfaces within 60 s, minimizing operative time. In vitro testing confirmed broad-spectrum antimicrobial activity against Candida spp. ( C. albicans , C. parapsilosis , C. glabrata , C. krusei ) and Staphylococcus spp. ( S. aureus , S. epidermidis ). VAN was released rapidly, while AmB exhibited sustained release for up to 10 h, with both maintaining saturation solubility for 48 h. Notably, AmB-loaded implants showed five-fold lower hemolytic toxicity compared to free drug. These results highlight the potential of 3D-printed, drug-eluting implants as a clinically viable solution for the prevention and early treatment of PJIs. Graphical abstract

Dietary supplementation of a plant-based diet with hydrolyzed microalgae–grape marc extracts: effect on oxidative status, intestinal functionality and microbiota in Sparus aurata juveniles - Alba Galafat; Isabel del Carmen Ruiz-Rodríguez; Alejandro Morcillo-Guillén; Anyell Caderno; Jorge García-Márquez; Isabel Maria Cerezo; Marta Román; Verónica de las Heras; Antonio J. Vizcaíno; Maria Isabel Sáez; Tomás F. Martínez; Amalia E. Morales; et al. (Frontiers in Marine Science, 2026)
The expansion of aquaculture and the rising cost of fishmeal have driven research into fish gut health and the replacement of marine-derived ingredients with alternative protein sources, within sustainable strategies aligned with the Blue Transformation. In this sense, the objective of this study was to evaluate the effect of including a functional ingredient based on hydrolyzed microalgae and grape marc extracts in feeds with high proportion of plant protein sources on growth, muscle composition, oxidative status, intestinal microbiota, and digestive functionality in gilthead seabream juveniles ( Sparus aurata ). Three experimental diets were formulated, all isoproteic (47%) and isolipidic (18%), namely: CT (control diet - a diet mimicking the commercial aquafeeds used for this species based on 20% fishmeal); PP (a plant-based diet replacing 60% of fishmeal with hydrolyzed vegetable protein); and PP-GG (the same PP diet supplemented with 2% of the microalgal-grape marc based nutraceutical, LB-Green Grape ). Results indicated a trend for improved growth performance and FCR in fish fed the PP-GG diet compared to PP group, although differences were not statistically significant. The inclusion of plant protein ingredients reduced muscle protein content, however, supplementation with microalgae and grape marc extract in the PP-GG diet partially mitigates this loss. Fishmeal replacement with vegetable proteins also affected lipid composition, with higher mono-unsaturated fatty acid content and increased poly-unsaturated fatty acid retention in PP and PP-GG groups. Additionally, PP diet posed an oxidative challenge, evidenced by higher lipid peroxidation, while this was significantly reduced in the PP-GG group, confirming the antioxidant effect of the nutraceutical ingredient. Digestive enzyme activities significantly increased in pancreatic enzymes of PP-GG group. Finally, although no significant differences in intestinal microbiota composition were observed, PP group showed increased bacterial diversity. In conclusion, dietary fortification with the nutraceutical based on microalgae and grape marc extracts improved growth, reduced oxidative damage, and enhanced digestive capacity in gilthead seabream juveniles, highlighting its potential as a nutritional strategy for sustainable aquaculture.

Distributed optical fibre sensing in physical oceanography: emergence and future prospects - Alberto C. Naveira Garabato; Carl P. Spingys; Andrew J. Lucas; Tiago S. Dotto; Christian T. Wild; Scott W. Tyler; Ted A. Scambos; Christopher B. Kratt; Giuseppe Cappelli; Ethan F. Williams; Mariona Claret; Hannah E. Glover; et al. (Ocean Science, 2026)
Distributed optical fibre sensing (DOFS) is a technology that enables continuous, real-time measurements of a range of environmental parameters along the length of a fibre optic cable. In this article, we review the recently emerged applications of DOFS techniques in physical oceanography and offer a perspective on the technology's potential for future growth within the field. The introduction of DOFS to physical oceanography is contextualised with a brief history of the technology, which spun off primarily from the use of seafloor-laid optical fibres for telecommunications purposes. The key components and underpinning physics of a DOFS system are outlined and, on their basis, the suite of variables that are observable with DOFS are discussed. The implementation factors of DOFS, which include trade-offs between measurement accuracy and spatio-temporal resolutions and ranges, are also examined. The physical oceanographic applications of DOFS to date are then illustrated with case examples of four distinct DOFS techniques: distributed temperature sensing (DTS), which can provide ocean temperature observations; distributed static strain sensing (DSS) and distributed acoustic sensing (DAS), which are sensitive to temperature, cable strain and strain-associated variables, such as pressure and ocean velocity; and ultra-long-range observations of ocean currents with optical interferometry. The forthcoming prospects of DOFS in physical oceanography are considered, and are proposed to include new fibre optic-based approaches to sense ocean salinity and measure through the water column. We conclude with reflections on the future role of DOFS within the Global Ocean Observing System, and highlight the opportunities provided by the existing world-wide network of seafloor-laid optical fibres.

The influence of age and captivity on cardiac structure and function in rhesus macaques - T. G. Dawkins; B. A. Curry; A. Drane; V. N. Rivas; Y. Ueda; J. A. Stern; D. Philips; J. Negron-Del Valle; Lauren Brent; James Higham; Angelina Ruiz-Lambides; Noah Snyder-Mackler; et al. (GeroScience, 2026)

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

Effects of UV-LED irradiation on decapod crustacean larval mortality, motility, and respiration: Implications for ballast water treatments and invasive species management - Á. Rodríguez-Ruiz; E. González-Ortegón; G.F. de Carvalho-Souza; J. Moreno-Andrés; E. Nebot; L. Romero-Martínez (Marine Pollution Bulletin, 2026)

Numerical simulation of color and acrylamide distribution during cookie baking: Coupling nonequilibrium multiphase transport, reaction kinetics and structural deformation - Chang Chen; Mauricio Espinal-Ruiz; Alyssa Francavilla; Iris J. Joye; Maria G. Corradini (Journal of Food Engineering, 2026)

Experimental Models to Study Polyglutamine Spinocerebellar Ataxias: From Mechanisms to Therapeutic Developments - Vanessa Ruiz-Esparza-Palacios; Fabiola V. Borbolla-Jiménez; Aranza Meza-Dorantes; Regina Villarreal-Ramírez; Bulmaro Cisneros; Jonathan J. Magaña (The Cerebellum, 2026)

Enhancing Community Pharmacists’ Professional Competencies and Sun-Safe Behaviors Through the FarmaSoludable Educational Program - Guillermo J. Pozuelo-Sánchez; Magdalena de Troya-Martín; Francisco Rivas Ruiz; Alba Rodriguez-Martinez; Andras Subert; Maria Alvarez de Sotomayor (Journal of Cancer Education, 2026)
This study examined the impact of a structured educational intervention on professional competencies in individualized photoprotection counselling and on personal sun-safe behaviors. A quasi-experimental pre–post study was conducted among community pharmacists in Seville, Spain, in 2024. The intervention consisted of a blended educational program comprising an online training course delivered by a multidisciplinary faculty and a one-day practical session. Professional counselling practices were assessed using the Counselling Habits in Individualized Photoprotection questionnaire, while personal habits, attitudes, and knowledge related to photoprotection were evaluated using the Habits, Attitudes, and Knowledge in Photoprotection questionnaire. Data were collected at baseline and after completion of the intervention, and analyses included descriptive and comparative pre–post statistics, with statistical significance set at p < 0.05. A total of 116 pharmacists completed the baseline professional assessment and 80 the post-intervention, while 125 and 85 pharmacists completed the personal behavior questionnaire, respectively. Professional competencies improved significantly, including identification of skin cancer risk factors (45.2% to 72.2%), promotion of skin self-examination (31.6% to 65.8%), and adaptation of counselling to occupational sun exposure ( p < 0.001). Knowledge scores increased from 6.03 to 7.07 ( p < 0.001). Personal sun-safe behaviors also improved, including sunscreen use, regular reapplication, and reduced sunburn frequency. Knowledge of early skin cancer detection criteria increased markedly (ABCDE rule: 61.5% to 100%; ugly duckling sign: 27.9% to 98.8%; p < 0.001). The FarmaSoludable educational program improved professional competencies and personal preventive behaviors, supporting pharmacists’ roles as behavioral role models and educators for community knowledge transfer.

Genetic testing for hereditary breast and ovarian cancer in the Murcian population using a comprehensive NGS panel - Y. Mestre Terkemani; L. Rosado Jiménez; A. García Aliaga; M. D. Sarabia Meseguer; M. Marín Vera; J. A. Macías Cerrolaza; P. Sánchez Henarejos; M. R. García Hernández; M. Zafra Poves; B. Alvarez Abril; E. García Torralba; C. B. López Sánchez; et al. (Familial Cancer, 2026)

Greenhouse-scale proximity-RFID system enabling flower-visit metrics for bumblebee pollination studies under climate change - A.R. Jiménez; M. Pilla; J. Serrano; F. Seco; L. Ruiz-Ruiz; M. Ormazabal; J.J. Guerrero; A.S. Prudencio; J.A. Martín Rodríguez; F. Pérez-Alfocea (Computers and Electronics in Agriculture, 2026)

Long-term forest structure trends in the peninsular Spain from lidar-optical sensors synergies - M. Tanase; J.P. Martini; P. Miranda; D. Garcia; V. Wilke; S. Miguel; C. Mihai; J. Diez; S. Natal; D. San Martin; P. Ruiz-Benito (Remote Sensing of Environment, 2026)

β-caryophyllene mitigates metabolic dysfunction in the testes of gerbils perinatally exposed to BPA - Stella Bicalho-Silva; Ana D. Martins; Rúben J. Moreira; Thalles F.R. Ruiz; Vitor Grigio; Pedro F. Oliveira; Sebastião R. Taboga; Patrícia S.L. Vilamaior; Marco G. Alves (Reproductive Toxicology, 2026)

Cattle excreta on Lotus tenuis-promoted grasslands: Exploring soil microbiome and nitrous oxide emissions in the Salado River Basin, Argentina - Amira Susana del V. Nieva; Mónica G. Pérez; Cristian J. Antonelli; Alejandro O. Costantini; Oscar A. Ruiz (European Journal of Soil Biology, 2026)

Effects of the Double-Ovsynch and Presynch–Ovsynch protocols on first-service conception rate in dairy cows with and without subclinical endometritis - Fernando Villaseñor-González; Dan Ponce-Aguilar; Héctor Raymundo Vera-Ávila; Felipe de Jesús Ruiz-López; Mario A. Espinosa-Martínez; Marina Durán-Aguilar; Luis J. Montiel-Olguín (Tropical Animal Health and Production, 2026)

Hierarchically structured cobalt-aluminium layered double hydroxides for photocatalytic CO₂ reduction using calcined cotton fiber templates - Marta Estrada-Ruiz; Daniel Cosano; Dolores Esquivel; Francisco J. Romero-Salguero; José R. Ruiz (Applied Clay Science, 2026)

Infestation by Phorid Flies Disrupts Behavior and Immune Function in Honey Bees Monitored by Radio-frequency Identification - Gloria Ruiz-Guzmán; Oliverio Delgado-Carrillo; Francisco J. Balvino-Olvera; María de Jesús Aguilar-Aguilar; Violeta Patiño-Conde; Paulo de Souza; Ulises Olivares-Pinto; Mauricio Quesada (Neotropical Entomology, 2026)
Honey bees ( Apis mellifera Linnaeus) are important pollinators in natural and agricultural ecosystems and play a key role in global food production. However, colonies are increasingly affected by multiple stressors, including emerging parasites, which can compromise their health and performance. Among these, phorid flies (Diptera: Phoridae) have been observed in association with weak or collapsing honey bee colonies in various regions in Mexico, yet their effects on honey bee behavior and immune function under field conditions remain poorly understood. In this study, we investigated the impact of a phorid fly infestation on the behavior, survival, and immune defense of A. mellifera under natural conditions. Using radio-frequency identification (RFID) technology, we monitored the daily activity of individually tagged bees from a healthy hive and a naturally infested hive. Additionally, we assessed the prevalence of coinfections and measured immune responses including prophenoloxidase (proPO), phenoloxidase (PO), lytic activity, and hemocyte counts. Our results showed that phorid fly infestation was associated with a reduction in the frequency and duration of foraging trips, nocturnal activity, and significant changes in immune function, particularly elevated proPO/PO activity and reduced total hemocyte counts. No significant differences were observed between adult and pupal stages in immune parameters, suggesting a consistent physiological response across developmental stages. While only one hive was infested and ultimately collapsed, these findings provide evidence that phorid flies can disrupt key behavioral and immune processes in honey bees. Further studies are needed to determine the broader implications of phorid infestations for colony health and resilience.

A Systematic Evaluation of CNN Configurations for Multiclass Oil Spill Classification in Hyperspectral Images - María Gema Carrasco-García; Javier González-Enrique; Juan Jesús Ruiz-Aguilar; Alberto Camarero-Orive; David Elizondo; Ignacio J. Turias Domínguez (Journal of Marine Science and Engineering, 2026)
Oil spills represent a severe threat to aquatic ecosystems, requiring rapid and reliable detection methods to support environmental response. Hyperspectral imaging (HSI) offers high spectral resolution for distinguishing hydrocarbon types, but its effective use depends on the performance and robustness of deep learning (DL) models, especially under data-limited conditions. This study presents a systematic evaluation of convolutional neural network (CNN) configurations for oil spill classification in visible-near-infrared (VNIR) hyperspectral data, examining the influence of architectural depth and hyperparameters such as the number of convolutional kernels, neuron density, and dropout rate. Two architectures were tested across 54 configurations and two training set sizes (259 and 518 samples). Results show that a compact architecture with an additional max pooling layer achieved near-perfect accuracy (>0.99) with reduced complexity and greater robustness, outperforming its deeper counterpart. Importantly, this study reveals that under small-sample scenarios, optimal performance can still be achieved by carefully balancing model capacity, favouring moderate convolutional depth and high neuron density, while avoiding over-regularisation. These findings provide practical guidance for designing efficient CNNs for UAV-based oil spill monitoring and lay the groundwork for future integration into local real-time processing pipelines and transfer learning applications.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Field-based assessment of carbon farming practices in Mediterranean olive groves: Emission reductions and sequestration outcomes - B. Ruiz-Carrasco; E. Pareja-Sánchez; J. Liétor; D. Vera; L. Fernández-Lobato; R. García-Ruiz (Journal of Cleaner Production, 2026)

Multispecies weed mapping using deep learning on UAV imagery for SSWM in maize and tomato - G. A. Mesías-Ruiz; I. Borra-Serrano; J. Dorado; A. I. de Castro; J. M. Peña (Precision Agriculture, 2026)
Purpose: Accurate identification and mapping of multiple weed species at early growth stages is a critical step toward operational site-specific weed management (SSWM), yet most UAV-based studies have so far been limited to broad weed categories or single dominant species. This study aimed to evaluate and compare deep learning models for multispecies weed classification, detection and mapping in maize and tomato fields using UAV-based RGB imagery. Methods: Three convolutional neural networks (Inception-ResNet-v2, EfficientNet-B0, YOLOv8) and two Vision Transformers (ViT-Base, Swin-T) were assessed for the classification of nine common weed species. The two best-performing classifiers were then implemented in object detection frameworks (YOLOv8m and DETA), and species-specific treatment maps were generated using adaptive economic weed thresholds applied to gridded density weed data. Results: Swin-T and YOLOv8 achieved the highest classification metrics, with weighted F1-scores of 98.1% and 97.0%, respectively. For object detection, YOLOv8m outperformed DETA, reaching a mean Average Precision of 0.93 and a recall of 0.94, while substantially reducing inference time. The multispecies treatment maps revealed over 70% of weed-free areas, indicating the potential benefits of cost-saving approaches compared to uniform full-field treatments. Conclusions: The proposed workflow enabled accurate multispecies weed classification, detection and mapping at early growth stages, providing valuable inputs for decision support systems and smart sprayers to gradually advance SSWM for a more selective, efficient and sustainable weed control.

Training intensity distribution for sprinter swimmers: suggestions for swimming coaches and scientists - Konstantinos Papadimitriou; Jesus J. Ruiz-Navarro; Francisco Cuenca-Fernández; Nikos V. Margaritelis (European Journal of Applied Physiology, 2026)

Controls on Seasonal Atmosphere‐Ecosystem Carbon Dioxide Exchanges in a Temperate Salt Marsh - Jesus Ruiz‐Plancarte; Jose D. Fuentes; Karen J. McGlathery (Global Change Biology, 2026)
Salt marshes play a vital role in the biogeochemistry of coastal zones, yet the biophysical controls on CO 2 exchange with the atmosphere, or net ecosystem exchange (NEE, positive upwards) remain poorly quantified. We investigated a Spartina alterniflora monoculture salt marsh on the eastern shore of Virginia, United States, by estimating half‐hourly NEE from March 2016 to February 2017 using the eddy‐covariance method. Maximum marsh–atmosphere CO 2 exchanges occurred during June and July when hourly averaged NEE values reached −10.0 ± 2.5 μmol CO 2 m −2 s −1 (mean ±1 standard deviation). During the most productive time of the year, a tidal inundation of 0.7 m reduced daytime CO 2 assimilation and nighttime CO 2 release to the atmosphere by 5.0 ± 1.2 μmol CO 2 m −2 s −1 and 3.0 ± 0.7 μmol CO 2 m −2 s −1 , respectively. Diffuse photosynthetically active radiation (PAR) conditions promoted quantum use efficiencies ( α ) of the ecosystem that were approximately three times greater than under direct PAR conditions ( α Cloudy = 0.012 ± 0.004 versus α Clear = 0.004 ± 0.001 mol CO 2 per (mol photons)). Under diffuse light, NEE increased more rapidly with PAR and photo‐saturation occurred at higher PAR levels compared to clear‐sky conditions. On average, under the influence of diffuse light, the assimilation of CO 2 increased by 30% relative to equivalent PAR levels under direct sunlight. During March 2016 to February 2017 the marsh exchanged −269.1 ± 9.1 g of carbon per m 2 with the atmosphere. The findings demonstrate that tides and light quality are key regulators of carbon cycling in tidal marshes. These factors should be incorporated into models of tidal marsh biogeochemistry, particularly as both are undergoing rapid changes due to sea level rise and atmospheric warming.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Arabidopsis trehalose phosphate synthaseII (tpsII) mutants are ABA-hypersensitive during early development while tps7 to tps11 show increased drought susceptibility consistent with anomalous stomatal closure and weak post-stress recovery responses - Daniela J. Bonilla-Córdoba; Andrea C. Ruiz-Castillo; Ismael Cisneros-Hernández; Norma Martínez-Gallardo; Enrique Ramírez-Chávez; Lino Sánchez-Segura; John Délano-Frier (Plant Science, 2026)

Carbon farming in Mediterranean olive groves: potential for carbon credits and policy implications - P. Domouso; E. Pareja-Sánchez; J. Lechuga-Puñal; A.J. García-Moreno; V. Ochoa-Esteban; R. García-Ruiz (Journal of Environmental Management, 2026)

Guidelines for producing integrated 210Pb and 14C age-models - Joan-Albert Sanchez-Cabeza; Marco A. Aquino-López; Maarten Blaauw; Ana Carolina Ruiz-Fernández; Johanna L.J. Jupin; Lysanna Anderson; Clarke A. Knight; Marie Rhondelle Champagne; Nicole K. Sanderson; Simon Goring; J. Andrés Christen (Earth-Science Reviews, 2026)

How air pollution and extreme temperatures affect emergency hospital admissions due to neurological diseases: A study in 10 Spanish provinces - M. Iriso; C. Linares; J. Díaz; R. Ruiz-Páez; M.A. Navas; J. López-Bueno (Atmospheric Environment, 2026)

The biomedical engineer’s pledge: overview and context - Antoni Ivorra; Txetxu Ausín; Laura Becerra-Fajardo; Antonio J. del Ama; Jesús Minguillón; Aracelys García-Moreno; Jordi Aguiló; Filipe Oliveira Barroso; Bart Bijnens; Oscar Camara; Sara Capdevila; Roger Castellanos Fernandez; et al. (Medical & Biological Engineering & Computing, 2026)
Although biomedical engineering (BME) is a profession with ethical responsibilities comparable to those in medicine, it has, until now, lacked a counterpart to the Hippocratic Oath. While professional societies have established codes of ethics for biomedical engineers, these documents lack the symbolic and ceremonial significance of an oath or pledge. By contrast, the recitation of the Hippocratic Oath, or its modern version, the “Physician’s Pledge,” serves as a powerful rite of passage for medical students, fostering a strong sense of ethical duty at the start of their professional journey. However, the content of the Hippocratic Oath includes elements specific to clinical practice and is not directly applicable to biomedical engineering. To fill this gap, we have created a “Biomedical Engineer’s Pledge,” comprising a preamble, ten promises, and a concluding statement, to inspire ethical awareness and establish a meaningful graduation tradition. Graphical abstract

Citral impairs intestinal changes caused by ulcerative colitis through modulation of antioxidant, anti-inflammatory and healing activities - Maycon T. Emílio-Silva; Vinícius P. Rodrigues; Antonio J. Ruiz-Malagon; Isabela G. Guidolin; Felipe L. Dario; Mariana M. Fioravanti; Alba Rodriguez-Nogales; Julio Gálvez; Clelia A. Hiruma-Lima (Inflammopharmacology, 2026)

Demographic Parameters of Iberian Killer Whales Between 2011 and 2023 - Ruth Esteban; Pauline Gauffier; Alfredo López; Francisco J. Gil‐Vera; Jörn Selling; Lilian Haristoy; Rocio Espada Ruiz; Pierre Guibert; André Días; Alfredo Rodrigues; Alejandro Onrubia; Mario Morcillo; et al. (Marine Mammal Science, 2026)
The Iberian killer whale subpopulation was assessed as critically endangered (CR) by the IUCN red list of threatened species based on the available information until 2011 on its low abundance, high newborn mortality, and dependency on the endangered Atlantic bluefin tuna. The present study focuses on updating the subpopulation demographic parameters between 2011 and 2023. Data were based on photo‐identification and stranding records. Abundance, survival, reproductive rates, and population growth were estimated through mark‐recapture models. Stranding records were used to estimate body size and calving seasonality. Sightings of newborn calves were also used for assessing seasonality. From 2011 through 2023, 26 stranding records were obtained, and 18,554 ID‐images were examined. This subpopulation showed a stable abundance, with 37 individuals in 2023, still qualifying for the IUCN CR category under criteria D. Calf survival rate has increased compared to pre‐2011, while adult survival has decreased, particularly for females. Reproductive rates were low, with an estimated interbirth interval of 8.3 years. The overall population growth rate was apparently stable at 0.46%. Most births occurred in the summer and fall. Iberian killer whales are generally smaller than the average body length of other killer whale populations throughout the world. The study emphasizes the need for long‐term monitoring and highlights new potential threats from fishing activities and recent disruptive interactions with recreational boats. The future of the subpopulation depends on recruitment and survival of juveniles and effective female reproduction.

Out of sight, but not out of mind: Key issues regarding seafloor macrolitter monitoring - Georg Hanke; Miquel Canals; Ryota Nakajima; Melanie Bergmann; Francois Galgani; Daoji Li; George Papatheodorou; Christopher Kim Pham; Diva J. Amon; Michela Angiolillo; Lene Buhl-Mortensen; Alessandro Cau; et al. (Marine Pollution Bulletin, 2025)

Cascading ecological impacts: from eutrophic coastal lagoon collapse to decline of Posidonia oceanica meadows in the Mediterranean - J. Jiménez-Casero; J.M. Ruiz; J. Bernardeau-Esteller; R. García-Muñoz; J.L. Sánchez-Lizaso; L. Marín-Guirao; M.D. Belando (Marine Pollution Bulletin, 2025)

Sustainable production of nanocrystalline cellulose from Sargassum spp. biomass via deep eutectic solvents: A comparative study of green methodologies - Alberto Elizalde-Mata; Emilio Guardado-Ruiz; M.E. Trejo-Caballero; Mar Lovi; Karla Juarez-Moreno; J. Luis López-Miranda; Miriam Estevez (Journal of Environmental Chemical Engineering, 2025)

Inflammatory dietary potential and gut microbiota in older adults with overweight or obesity and metabolic syndrome - Héctor Vázquez-Lorente; Adrián Hernández-Cacho; Jesús F. García-Gavilán; Jun Li; Miguel Ruiz-Canela; Clara Belzer; Jesús Vioque; Dolores Corella; Montserrat Fitó; Josep Vidal; Prokopis Konstanti; Isabel Moreno-Indias; et al. (Food Research International, 2025)

A comparative study of 3D CAD and fractal geometry models for analyzing mass transfer in shrimp during convective drying - K.H. Estévez-Sánchez; J. Del Rosario-Santiago; O. Cortés-Zavaleta; M. Sánchez-Cantú; H. Ruiz-Espinosa; M.A. García-Alvarado; C.E. Ochoa-Velasco; I.I. Ruiz-López (Food and Bioproducts Processing, 2025)

A simplified solution for mass transfer in elliptic cylinders: Application to the dry salting of shrimp - J. Del Rosario-Santiago; K.H. Estévez-Sánchez; H. Ruiz-Espinosa; O. Cortés-Zavaleta; J. Carrillo-Ahumada; C.E. Ochoa-Velasco; I.I. Ruiz-López (Food and Bioproducts Processing, 2025)

Elucidation of xenobiotics in textiles for infants using non-targeted approaches: The role of fabrics as a source of early-life exposure to potentially harmful chemicals - A. Domínguez-Liste; E. Linares-Ruiz; M.O. Schweiss; L. Papay-Ramírez; C. Freire; P. Pérez-Serrano; R. Quesada-Jiménez; F.M. Pérez-Carrascosa; V. Mustieles; J.P. Arrebola; J. Pérez-del-Palacio; O. Ballesteros; et al. (Environmental Research, 2025)

Enhanced cell immobilization in filamentous fungal pellets via surface modification and biocoating - Carlota Casas-Coronado; Francisco J. Ruiz-Castilla; Alberto Ramírez; Lara Lúquez-Caravaca; Laura Cano; Jaime Moreno-García (Bioresource Technology Reports, 2025)

The inoculation with Pseudomonas simiae WCS417 strain promotes growth and the induction of iron-deficiency responses in cucumber plants (Cucumis sativus L.) - Miguel A. Aparicio; Francisco J. Ruiz-Castilla; José Ramos; Francisco J. Romera; Carlos Lucena (Planta, 2025)
Main conclusion Inoculation with Pseudomonas simiae WCS417 improves cucumber growth under Fe deficiency conditions and induces iron-deficiency responses, making it a promising candidate for sustainable biofertilization strategies in dicot plants. Abstract Iron (Fe) deficiency poses a significant agronomic challenge in calcareous soils, particularly affecting dicot plants. Conventional production methods rely heavily on high-yielding varieties and the application of substantial amounts of agrochemicals, leading to considerable environmental concerns. In this context, leveraging the potential of beneficial rhizosphere microorganisms as biofertilizers represents a highly promising and environmentally sound alternative to chemical fertilizers. This study aims to investigate the efficacy of the nonpathogenic strain Pseudomonas simiae WCS417 in eliciting Fe deficiency responses in cucumber plants, along with its impacts on plant growth and Fe chlorosis. Conducted under hydroponic conditions, our experiments reveal compelling outcomes. Root inoculation of cucumber plants with P. simiae significantly enhances plant growth while concurrently mitigating Fe chlorosis symptoms over successive cultivation days. The inoculation with this bacterium induces acidification in the subapical zone of cucumber roots, facilitating Fe solubility in the rhizosphere. Additionally, P. simiae triggers the upregulation of Fe-related genes in inoculated plants, even under Fe sufficiency. In conclusion, P. simiae emerges as a potent enhancer of Fe deficiency responses in cucumber plants. Its ability to promote growth, enhance Fe solubility through rhizosphere acidification, and alleviate Fe chlorosis underscores its potential as an effective biofertilizer for a sustainable Fe nutrition of dicot plants.

Linking genomic and proteomic signatures to brain amyloid burden: insights from GR@ACE/DEGESCO - Raquel Puerta; Itziar de Rojas; Pablo García-González; Clàudia Olivé; Oscar Sotolongo-Grau; Ainhoa García-Sánchez; Fernando García-Gutiérrez; Laura Montrreal; Juan Pablo Tartari; Ángela Sanabria; Vanesa Pytel; Carmen Lage; et al. (Functional & Integrative Genomics, 2025)

Airborne bacterial communities present in particulate matter (PM2.5 and PM10) samples collected during different seasons in Temuco City in Chile - Tay Ruiz-Gil; Joaquín I. Rilling; Marco Campos; So Fujiyoshi; Fumito Maruyama; Jacquelinne J. Acuña; Milko A. Jorquera (Aerobiologia, 2025)

Babesia spp. in Domestic Animals from Rural Areas of Cauca Department: Previous Exposure and Molecular Detection Among Canines, Bovines and Equines - Carlos Ramiro Silva-Ramos; Juan Andrés Niño Rodríguez; Juliana Gil-Mora; Paola Betancourt-Ruiz; Heidy- C. Martínez-Díaz; Elkin Forero-Becerra; J. Manuel Matiz-González; Eliana Bolaños; Luz-Adriana Olaya-M; Efraín Benavides; Marylin Hidalgo (Acta Parasitologica, 2025)
Purpose Babesia species are tick-borne protozoan parasites which affect several animal species. Babesia spp. infections are significantly important for veterinary medicine, affecting a wide range of domestic animal species such as dogs, cattle, and horses. In Colombia, studies of Babesia spp. infections in domestic animals are scarce. Thus, the aim of the present study was to explore the circulation of these parasites among domestic canines, bovines and equines from the department of Cauca. Methods Between August and November, 2017, active domestic animal sampling of cattle was performed in eight rural areas of four municipalities of Cauca department. Serum and whole-blood samples were obtained from all specimens for serological and molecular tests. Immunofluorescence assays were performed on all serum samples to detect antibodies against Babesia spp., and DNA was extracted from whole-blood samples to perform a genus-specific PCR to identify the presence of Babesia spp. Results A total of 198 samples were collected: 52.5% from dogs, 32.3% from horses, and 15.2% from cattle. Seroprevalence rates showed that 58.1% of domestic animals were exposed to Babesia spp., with the highest rates among equines (65.6%). Molecular detection revealed that 17.7% had an active Babesia spp. infection, being more frequent among cattle (53.3%). Phylogenetic analysis indicated that Babesia bigemina was the primary species identified. Conclusion This study provides critical data on Babesia infections in domestic animals in Cauca department, revealing active infections and previous exposures among domestic animals from the region.

Biodiversity Genomics Research Practices Require Harmonising to Meet Stakeholder Needs in Conservation - Elena Buzan; Christian de Guttry; Chiara Bortoluzzi; Nathaniel R. Street; Kay Lucek; Anna Rosling; Lino Ometto; Alice Mouton; Luísa S. Marins; María José Ruiz‐López; José Melo‐Ferreira; Elisabet Ottosson; et al. (Molecular Ecology, 2025)
Biodiversity resilience relies on genetic diversity, which sustains the evolutionary potential of organisms in dynamic ecosystems. Genomics is a powerful tool for accurately estimating genetic diversity across genomes of species and populations. However, integration of genomic data into conservation efforts faces challenges due to the heterogeneity of approaches employed. Establishing common sets of standards for genomic data production and analysis is essential to consistently interpret results and clearly communicate outcomes to stakeholders. While the European Reference Genome Atlas (ERGA) community has contributed significantly to the standardisation of reference genome methodologies in synergy with other initiatives, there is now an urgent need to extend these principles to downstream analyses. ERGA aims to build on its experience to help establish harmonised approaches in applied biodiversity genomics research, aligned with ongoing efforts to define standardised metrics for measuring and reporting genetic diversity. Establishing consensus on best practices for genome‐wide data generation methods and applications will substantially increase accuracy, interpretability, and comparability, together with enhanced stakeholder capacities. By identifying key opportunities and challenges, as well as conducting preliminary stakeholder mapping and examining case studies, the goal is to build an inclusive framework that ensures the relevance and widespread adoption of these best practices: fostering trust and confidence in genomics research practices to meet stakeholder needs in biodiversity conservation. We call upon the broader research community to join efforts in establishing these approaches, recognising the importance of participation of end‐users, to foster the integration of genomic data into the toolkit for measuring and reporting genetic diversity.

First record of winter pregnant males of two pipefish species in a Mediterranean coastal lagoon - Adrián Guerrero‐Gómez; Antonio Zamora‐López; Antonio Andrés Herrero‐Reyes; Francisco J. Oliva‐Paterna; Jorge Madrid‐Ruiz; Víctor M. Álvarez‐Navarro; Rocío Peñalver; Mar Torralva (Journal of Fish Biology, 2025)
Syngnathus abaster Risso, 1827 and Syngnathus typhle L., 1758 are key components of fish assemblages in European transitional waters, with well‐documented reproductive cycles typically occurring from spring to autumn. However, recent warming trends in the western Mediterranean has raised questions about potential shifts in their breeding phenology. In January 2025, three pregnant S. abaster males and one S. typhle male were detected in the Mar Menor Coastal lagoon (western Mediterranean), representing the first recorded winter breeding event for both species. The size structure of S. abaster in winter 2025 also contrasted with colder winters, further supporting this interpretation. These findings may reflect a response to recent thermal anomalies and highlight the phenological plasticity of these species. To our knowledge, this is the first indication of potential phenological shifts in syngnathids from transitional waters, with implications for understanding how climate change may influence their reproductive dynamics.

Regional Emergence of Water‐Related Browning in a Greening World - Rene Orth; Jasper M. C. Denissen; Josephin Kroll; Sungmin O; Ana Bastos; Wantong Li; Diego G. Miralles; Melissa Ruiz‐Vásquez; Anne J. Hoek van Dijke; Andrew F. Feldman; Mirco Migliavacca; Lan Wang‐Erlandsson; et al. (Global Change Biology, 2025)
The Earth is greening in many regions under elevated atmospheric CO 2 concentrations, along with increasing temperature and land use changes. However, despite the continued rise in CO 2 , greening has stagnated or even reversed in some regions, suggesting a reduced capacity of the land surface to act as a carbon sink. Here, we show that declining water availability and rising atmospheric water demand have coincided with regional browning trends over recent decades in some tropical regions that have historically acted as prominent carbon sinks. A regression analysis considering a balanced set of water‐ and energy‐related variables alongside land cover change and climate extremes confirms that both water availability and atmospheric water demand are important contributors to inter‐annual variability in Leaf Area Index (LAI) there. Earth system models mostly reproduce the observed spatial extent of browning and concurrent related coinciding water changes in the multi‐model mean, but results from individual models differ strongly. Our findings provide a new constraint for related model development and highlight the need for enhanced monitoring and consideration of observation‐based water availability trends as an emerging driver of vegetation in future analyses and model development.

Longer time series with missing data improve parameter estimation in a state‐space model in coral reef fish communities - Alfonso Ruiz‐Moreno; Michael J. Emslie; Sean R. Connolly (Ecology, 2025)
Analysis of time series data is fundamental in ecology for understanding community dynamics, and the mechanisms driving such dynamics. However, ecological time series commonly contain missing values, which can arise due to methodological changes in monitoring programs, poor weather conditions, logistical constraints, or human error. State‐space models are a useful suite of techniques for analyzing ecological time series with missing data. Such models can estimate the unobserved true abundances as latent variables, even for putative census occasions that lack observations. Nevertheless, the impact of missing data on parameter accuracy and precision in these state‐space models remains poorly investigated, particularly in species‐rich systems. We evaluated the performance of a multivariate process‐based state‐space model for time series of varying lengths and sampling frequencies, using simulated data informed by empirical counts of reef fish communities from the Great Barrier Reef in Australia. We found that despite containing missing data, the models fitted to longer time series produced more accurate and precise parameter estimates compared to shorter, complete‐case time series. Additionally, higher spatial replication with uneven census intervals enhanced parameter precision more than maintaining census frequency at the expense of reducing the number of sites. Analysis of reef fish community data revealed attenuation in intrinsic population growth parameters and weaker intraspecific density dependence when modeling longer time series whose inter‐census intervals change, while estimates of variability in species' population growth parameters due to environmental fluctuations remained consistent regardless of sampling design. Nonetheless, analyses of shorter, complete‐case time series still produced reliable parameter estimates. Our findings highlight the robustness of Bayesian state‐space models to missing data, demonstrating that flexibility in long‐term monitoring programs does not compromise ecological inference from these models.

Role of wetlands in the Pampas of Argentina in global shorebird conservation - N. S. Martínez‐Curci; J. P. Isacch; J. L. Fernández; F. Bogel; J. Ruiz; J. G. Navedo (Conservation Biology, 2025)
Less than 10% of migratory bird species worldwide benefit from adequate protected area coverage throughout their annual cycles. This increases their vulnerability and exacerbates the global biodiversity crisis. The ongoing decline of shorebird populations, 60% of which are migratory, suggests critical gaps in current conservation strategies. One such gap is the spatial bias in surveys and monitoring efforts. Such efforts are heavily concentrated in the Global North, leaving regions in the Global South underrepresented. We assessed the importance of a vast inland region in southern South America, the Inland Pampas of Argentina, for shorebird conservation, as it supports thousands of wetlands but has been largely overlooked in shorebird research and conservation. We conducted shorebird counts in 134 wetlands across the region in January and June of 2021, 2022, and 2023. Seventeen species were recorded, including 3 of global conservation concern: white‐rumped sandpiper ( Calidris fuscicollis ), Hudsonian godwit ( Limosa haemastica ), and lesser yellowlegs ( Tringa flavipes ). Shorebird abundance peaked in January (maximum number of approximately 30,000 individuals) and was dominated by Nearctic migrants. In contrast, June assemblages were dominated by Neotropical species and Hudsonian godwits, indicating the region serves as an important oversummering site for the latter. In June, there was also an influx of godwits from other nonbreeding areas. Three wetlands had notably high numbers of shorebirds, including populations that met criteria for international importance. Because of the abundances we found, our results underscore the urgent need to expand research efforts to identify other high‐priority areas for shorebirds in the Global South. Neglecting these regions would bias global population assessments and risk omitting critical habitats from national and international conservation frameworks. Addressing these data gaps is essential not only for updating global priorities but also for promoting more inclusive and geographically balanced approaches to migratory shorebird conservation. The complete Spanish version of the manuscript is available as Supplemental Material (S2).

Decoupling mass transfer steps in fluoride electrosorption kinetics using a Rotating Packed Electrode - Jonathan J. Ruiz-Martinez; Emilia Morallon; Fernando F. Rivera-Iturbe; Rene Rangel-Mendez; Luis F. Chazaro-Ruiz (Journal of Water Process Engineering, 2025)

Histotaphonomic patterns as paleoenvironmental proxies in eolian deposits: Insights from Last Glacial Maximum mammals in the Argentine Pampas - María Dolores Marin‐Monfort; Mariana Garrone; Claudia I. Montalvo; Gabriel Nahuel‐Ruiz; Yolanda Fernández‐Jalvo; Rodrigo Tomassini; Fernando J. Fernández (Journal of Quaternary Science, 2025)
Eolian environments provide valuable information about arid climate intervals, yet the preservation of fossil bone microstructure, which can provide evidence of past environmental conditions in these settings, remains poorly understood. During the Last Glacial Maximum (LGM), eolian systems were more widespread than today across both hemispheres. In order to identify patterns associated with this type of environment, a series of LGM fossil specimens was selected from central Argentina, an area mantled by widespread eolian deposits. A combination of petrographic and scanning electron microscopy observations was employed, along with mineralogical (X‐ray diffraction, XRD) and elemental chemical composition (energy‐dispersive spectroscopy, EDS) analyses. Histological analysis revealed extensive bacterial bioerosion with superimposed generations, as well as radial and central microcracks, suggesting periodic environmental fluctuations. Mineral infillings, primarily carbonates and iron oxides, further reflect episodic changes in water availability over time. These taphonomic features support the interpretation of a depositional environment consistent with an interdune context characterized by alternating wet and dry conditions. The observed microstructural modifications highlight the relevance of histotaphonomic proxies for reconstructing environmental conditions in fossil‐bearing eolian deposits and provide a comparative framework for similar deposits worldwide.

The key mechanisms associated with the survival of Gulf toadfish, Opsanus beta , when in severe hypoxia - Anastasiya Plotnikova; Isabelle R. Nelson; Shara Y. Sookhoo; Jacob M. Belkin; Vanessa P. Lima; Ross D. Bronfman Bunch; Athena M. Santomero; Sophia A. Santomero; Emily C. Rodriguez; Jayda K. Rodriguez; Kathleen M. Davis; Amanda J. Kaplan; et al. (Journal of Fish Biology, 2025)
Florida's shallow seagrass beds experience daily diurnal fluctuations in environmental oxygen, leading to hypoxic episodes (PO 2 −1 , ~6 kPa) that have increased in frequency and intensity in recent decades. The native Gulf toadfish ( Opsanus beta ) have been shown to employ a suite of adaptive cardiovascular, ventilatory and metabolic adjustments to survive moderate hypoxia, but little is known of the mechanisms used to survive severe hypoxia. The objective of this study was to characterize the acute response of Gulf toadfish to severe hypoxia ( 2 ~0.4 kPa for 3 h followed by 1 h recovery). Heart rate, pulse pressure, caudal arterial blood pressure, ventilation frequency and ventilation amplitude were monitored and blood samples were taken from both groups and analysed for pH, glucose, lactate and other endpoints. Hypoxia‐exposed fish experienced a statistically significant 70% decrease in heart rate and a 32% decrease in ventilation frequency during hypoxia exposure. Moreover, plasma glucose concentrations increased 5‐fold and plasma lactate concentrations increased 6‐fold, with a minimal reduction in pH. Our findings support our hypothesis that Gulf toadfish are highly hypoxia tolerant and survive severe hypoxia by reducing energy expenditure and switching to anaerobic metabolism. It is important to understand how the Gulf toadfish deal with severe hypoxia due to the increasing prevalence of severe hypoxia in its natural environment.

The impact of data reduction on classical and Bayesian210Pb dating models - Marco A. Aquino-López; Nicole K. Sanderson; Maarten Blaauw; Joan-Albert Sanchez-Cabeza; Ana Carolina Ruiz-Fernández; J. Andrés Christen (Quaternary Geochronology, 2025)

Endogenous NO fluctuations in Arabidopsis leaves influence peroxisomal activities and ROS, NADPH, and H2S metabolism - Francisco J. Corpas; Salvador González-Gordo; María A. Muñoz-Vargas; Marta Rodríguez-Ruiz; Carmelo Ruiz-Torres; José M. Palma (Plant Science, 2025)

Cyclotides from Bolivian plants - J. Ruiz; U. Göransson; S. Gunasekera (Phytochemistry Letters, 2025)

Storage of Alperujo influences composting performance: Insights into gaseous emissions and functional metagenomics - Francisco J. Ruiz-Castilla; Marina Barbudo-Lunar; M. Carmen Gutiérrez; Carmen Michán; M. Ángeles Martín; José Alhama (Journal of Environmental Management, 2025)

Tracking chemical releases in wastewater systems: An integrated plant-wide model for publicly owned treatment works - David Perez; John D. Chea; Tarek Abichou; Raymond L. Smith; Gerardo J. Ruiz-Mercado (Journal of Environmental Management, 2025)

Pathological findings in four magellanic penguins (Spheniscus magellanicus) during surveillance in Chile, 2024 - C. Flores Olivares; V. Neira; G. Cerda; N. Ariyama; J. Ruíz; S. Marambio; M. Zamorano; R. Reyes; P. Oyarzún Ruiz; M. Seguel (Journal of Comparative Pathology, 2025)

Postmortem findings in two porpoises (Phocoena spinipinnis) stranded along the coast of Chile - C. Flores Olivares; V. Neira; N. Ariyama; J. Ruíz; S. Marambio; M. Zamorano; R. Reyes; P. Oyarzún Ruiz; M. Pérez; M. Saldías (Journal of Comparative Pathology, 2025)

Wheat crop models underestimate drought stress in semi-arid and Mediterranean environments - H. Webber; D. Cooke; C. Wang; S. Asseng; P. Martre; F. Ewert; B. Kimball; G. Hoogenboom; S. Evett; A. Chanzy; S. Garrigues; A. Olioso; et al. (Field Crops Research, 2025)

Croton draco Schltdl. & Cham is a Latin American plant from the family Euphorbiaceae with therapeutic potential and ecological interactions: A review - M.d.L. Grijalva-Delgado; J. López-Cervantes; D.I. Sánchez-Machado; O.N. Campas-Baypoli; K.L. Hernández-Ruiz; A.A. Quintero-Guerrero; M.d.R. Martínez-Macias (Biochemical Systematics and Ecology, 2025)

Improved spatial representation of precipitation and air surface temperature over highlands of the southern tropical Andes (Lake Titicaca region) during an austral summer using the WRF model - A. Llacza; J. Paredes; J. Llamocca; M. Saavedra; L. Fita; C. Ruiz; C. Junquas (Atmospheric Research, 2025)

Mechanochemical synthesis of multivariate UPO-3 (Cu-ZIF-9-ica) MOF for inactivation of antibiotic-resistant bacteria and irrigation-quality water production via heterogeneous photo-Fenton catalysis - Noelia Rodríguez-Sánchez; J. Enrique Domínguez-Santos; Biswajit Bhattacharya; Carsten Prinz; Inés Canosa; Amando Flores; Antonia Jiménez-Rodríguez; A. Rabdel Ruiz-Salvador; Franziska Emmerling; Menta Ballesteros (Chemosphere, 2025)

P28-28 Reproductive Impact Assessment of Endocrine-Disrupting Chemical Mixtures: A Comparative Approach Using In vitro Aquatic Models - N. Apú; J. Ruiz-Michelsen; F. Rommes; M. Alvarado-Arias; M. Méndez-Rivera; V. Lizano-Fallas (Toxicology Letters, 2025)

P18-56 Mitochondrial oxidative stress induced by cyclopiazonic acid in SH-SY5Y cells - C. Martínez-Alonso; Y. Rodríguez-Carrasco; J. Tolosa; M.J. Ruiz (Toxicology Letters, 2025)

Paleoclimatic implications of glacial fluctuations in the Sierra Nevada del Cocuy, northern Andes, Colombia, during the Lateglacial and Holocene - Jordan N. Herbert; Gordon R.M. Bromley; Meredith A. Kelly; Alice M. Doughty; Daniel Ruiz-Carrascal; Sergio A. Restrepo-Moreno; Santiago Noriega Londoño; Peter Galloway; Alan J. Hidy (Quaternary Science Reviews, 2025)

Exploring the future of probiotics with innovations in delivery systems and market insights - Alberto Ramírez; Andrés Bermúdez-Luque; Juan J. Román-Camacho; Francisco J. Martín-García; Jaime Moreno-García; Mine Güngörmüşler; Francisco J. Ruiz-Castilla (Food Bioscience, 2025)

From wild to domesticated: exploring selection signatures caused by domestication in Carica papaya - Mónica I. Jiménez-Rojas; Pedro J. Ruiz-Gil; Mauricio Heredia-Pech; Mariana Chávez-Pesqueira (Ecological Genetics and Genomics, 2025)

Short-term effects of chemical and noise pollution during heat and cold waves on emergency hospital admissions in Madrid - R Ruiz-Páez; JA López-Bueno; J Díaz; MA Navas; C. Linares (International Journal of Biometeorology, 2025)
Cold and heatwaves and air pollution have a joint, direct impact on population health. The aim of this study was to evaluate the combined impact of chemical air and noise pollution on hospital admissions during warm and cold months, with a breakdown by age group. We conducted a time-series study of unscheduled emergency admissions by specific causes in Madrid across the period 2013–2018. The independent variables were daily mean concentrations of PM 2.5 , PM 10 , NO 2 , tropospheric ozone, noise, and maximum and minimum temperatures. Relative and attributable risks were calculated using generalised linear models with a Poisson link. During the warm months, stronger associations were found between: ozone and admissions due to respiratory, circulatory and neurological causes; NO 2 and admissions due to respiratory diseases; and PM and admissions due to dementia and Alzheimer’s disease. Heat had a greater effect on admissions due to neurological diseases. During the cold months, no association was found with any chemical air pollutant, except for NO 2 and asthma-related admissions. By age, the greatest impacts were registered for PM, noise, cold and heat at ages ≥ 65 years, and for noise, NO 2 and cold at ages ≤ 14 years.

Resistance to Zabrotes subfasciatus (Boheman, 1833) (Coleoptera: Chrysomelidae) in common bean (Phaseolus vulgaris L.) and relationship with Fe and Zn content - Alexis Lamz-Piedra; Roberto R. Ruiz Santiago; María I. Gómez Jiménez; Luis Fernando Londono; Juan Miguel Bueno; Guadalupe I. Olivas-Orozco; Francisco J. Molina Corral; Marilyn Florido-Bacallao; Belkis Peteira Delgado-Oramas (International Journal of Tropical Insect Science, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Effectiveness of oral ivermectin, praziquantel, and fenbendazole against intestinal helminths in fighting birds - Roger I. Rodríguez–Vivas; Gabriela J. Flota–Burgos; José A. Rosado–Aguilar; Edwin J. Gutiérrez–Ruiz; Iris Trinidad–Martínez; Vanesa Evia–Pech; Gustavo Vázquez (Veterinary Parasitology, 2025)

Elucidating microplastic's seasonal occurrence in urban indoor and outdoor aerosol - J. Cárdenas-Escudero; S. Deylami; M. López Ochoa; J. Urraca Ruiz; D. Galán-Madruga; J.O. Cáceres (Science of The Total Environment, 2025)

Health-related compounds and Maillard reaction products in dry and steam roasted purple carrots (Daucus carota L.) - Laura Sáez-Escudero; Gracia Patricia Blanch; Francisco J. Morales; Marta Mesías; María Luisa Ruiz del Castillo (Food Chemistry, 2025)

Correction: Acute pancreatitis experimental models, advantages and disadvantages - Genaro J. Rosales-Muñoz; Verónica Souza-Arroyo; Leticia Bucio-Ortiz; Roxana U. Miranda-Labra; Luis E. Gomez-Quiroz; María Concepción Gutiérrez-Ruiz (Journal of Physiology and Biochemistry, 2025)

Acute pancreatitis experimental models, advantages and disadvantages - Genaro J. Rosales-Muñoz; Verónica Souza-Arroyo; Leticia Bucio-Ortiz; Roxana U. Miranda-Labra; Luis E. Gomez-Quiroz; María Concepción Gutiérrez-Ruiz (Journal of Physiology and Biochemistry, 2025)
Acute pancreatitis represents a severe health problem, not only because of the number of people affected but also because of the severity of its clinical presentation that can eventually lead to the death of patients. The study of the disease is complex, and we lack optimized models that can approach the clinical presentation in patients, in addition to the significant vulnerability of the organ itself. In the present work, we undertook the task of reviewing and analyzing the experimental methods most currently used for the induction of acute pancreatitis, emphasizing the advantages and disadvantages of each model and their delimitation based on experimental objectives. We aimed to provide an actual and quick-access guide for researchers interested in experimental acute pancreatitis.

Alterations in hepatic amino acid metabolism related to MASLD in individuals with obesity - Armando J. Pérez-Díaz; Inmaculada Ros-Madrid; María A. Martínez-Sánchez; Sara Rico-Chazarra; Alba Oliva-Bolarín; Andrés Balaguer-Román; Virginia E. Fernández-Ruiz; Carlos M. Martínez; José E. Yuste; Mercedes Ferrer-Gómez; Camilo J. Llamoza-Torres; María D. Frutos; et al. (Journal of Physiology and Biochemistry, 2025)

Direct and interactive effects of crop domestication and mineral fertilization over leaf traits: insights from squash, maize, and beans - Jorge Ruiz-Arocho; Nicholas Steinthal; Eric J. von Wettberg; Yolanda H. Chen (Genetic Resources and Crop Evolution, 2025)

Local inflammation at the salmon louse (Lepeophtheirus salmonis) attachment site contributes to copepodid rejection in coho salmon (Oncorhynchus kisutch) - Lene Sveen; Mark D. Fast; Torstein Tengs; Rachel A. Kline; Judit Aguilar Marti; Dominic Kurian; Gerrit Timmerhaus; Marianne Vaadal; Ross D. Houston; James E. Bron; Sean J. Monaghan; Haitham H. Mohammed; et al. (Cell and Tissue Research, 2025)
The study investigates the susceptibility of Atlantic salmon ( Salmo salar ) and Pacific salmon species (pink salmon, Oncorhynchus gorbuscha ; coho salmon, Oncorhynchus kisutch ; and chum salmon, Oncorhynchus keta ) to the parasitic salmon lice ( Lepeophtheirus salmonis ). The research had two main objectives: to characterize the morphology of the scaly skin in four salmonid species and to compare the cellular response at the louse attachment site in coho salmon and Atlantic salmon. Three consecutive challenge trials were conducted, with successful louse infestation only achieved across all four species in the third trial using mild anesthesia with tricaine methanesulfonate. Skin and fin samples were collected at 12, 24, 36, 48, 60, and 168 h post-infestation (hpi) for histological, proteomic, and spatial transcriptomic analyses. Results showed that chum salmon had significantly higher mucous cell coverage (30–40%) in the epithelium of scaly skin compared to Atlantic salmon (10%). At the louse attachment site in coho salmon, there was a greater influx of inflammatory cells at 36–48 hpi compared to Atlantic salmon. Proteomic analysis at 12 hpi and 36 hpi in coho salmon showed upregulation of neutrophil degranulation and formyl-methionyl-leucyl-phenylalanine signaling. Additionally, spatial transcriptomics at the attachment site showed local upregulation of inflammatory gene markers. These findings suggest that coho salmon mount a rapid and large-scale inflammatory response driven by neutrophils to louse attachment within the first 48 hpi. Overall, the study emphasizes the significance of local changes at the host-parasite interface for resistance mechanisms against salmon lice.

Extreme temperature events directly and indirectly mediate evolutionary adaptation of zooplankton metabolic rate - Thomas Ruiz; Martin J. Kainz (Limnology and Oceanography, 2025)
Under global warming, understanding the evolutionary adaptation of ectotherms resting metabolic rate (RMR) is critical for predicting long‐term populations' response to temperature increases. While several studies have evaluated metabolic rate evolution under different thermal context, most focused on space‐for‐time substitutions rather than assessment of populations' adaptation over time. Here, applying the method of resurrection ecology, we used sediment cores as an archive of populations' evolution and hatched ephippia from different sediment layers to examine the metabolic evolution of modern vs. ancient Daphnia longispina populations. Focusing on an oligotrophic subalpine lake, for which temperature has been monitored for almost a century, we were able to link population response to historical thermal contexts. We demonstrate that modern (2021) clonal lines exhibit a 60% higher RMR than ancient ones (1997) when measured at 20°C. The higher RMR correlated with reduced juvenile growth rates at 20°C but increased survival rates at high temperatures, with a higher thermal limit 2°C higher in modern populations. These findings reflect a trade‐off favoring survival over growth under warming and likely result from increased oxygen uptake capacities, which provide an advantage at high temperatures but constrain individual energy budgets at non‐stressful temperatures. Overall, this study suggests that survival at extreme weather events, such as heatwaves, may play an important role in shaping the RMR adaptation of Daphnia and, more generally, zooplankton populations.

Bycatch trend and its fate of the Spanish-owned tuna purse seiners fleet from the Atlantic and Indian oceans: Impacts of the implementation of good practices - Sergio Acevedo-Iglesias; Miguel Herrera; María Lourdes Ramos; José Carlos Báez; Jon Ruiz; Gonzalo Rodríguez-Rodríguez; Vanessa Rojo; Pedro J. Pascual-Alayón; Francisco J. Abascal (Marine Policy, 2025)

Differential diagnostic challenge of a cranial mediastinal mass involving the lung in a dog - G. Herrera-Torres; E. Mozos; M. Teresa Ruiz-Campillo; V. Molina-Hernández; M. José Bautista; I. Agulló-Ros; J. Morgaz; C. Pineda; J. Pérez (Journal of Comparative Pathology, 2025)

Liver lesions in sheep vaccinated against F. hepatica with and without naltrexone as immune modulator - M. Teresa Ruiz-Campillo; J. Pérez; G. Herrera-Torres; L. Miguel Flores-Velázquez; V. Molina-Hernández; Á. Martínez-Moreno; F. Javier Martínez-Moreno; R. Zafra; L. Buffoni; P. José Rufino-Moya (Journal of Comparative Pathology, 2025)

Effect of the oral administration of heat-killed Mycobacterium manresensis on intestinal health and immunology parameters of weaned piglets - C. Álvarez-Delgado; I. Ruedas-Torres; J. María Sánchez-Carvajal; K. Fristiková; M. Rodríguez-Ruiz; F. Larenas-Muñoz; J. Joaquín Cerón; F. José Pallarés; P. Joan Cardona; I. Magdalena Rodríguez-Gómez; L. Carrasco; J. Gómez-Laguna (Journal of Comparative Pathology, 2025)

Anoxic desulfurization of biogas rich in hydrogen sulfide through feedback control using biotrickling filters: Operational limits and multi-omics analysis - J. Brito; C. Frade-González; F. Almenglo; J.J. González-Cortés; A. Valle; M.C. Durán-Ruiz; M. Ramírez (Bioresource Technology, 2025)

Climate change effects on the spatial and temporal distribution of extreme precipitation in the Mid-Atlantic region - Majid Mirzaei; Adel Shirmohammadi; Alfredo Ruiz-Barradas; Lars J. Olson; Masoud Negahban-Azar (Urban Climate, 2025)

Setting the limit: cold rather than hot temperatures limit intertidal distribution of a coastal foundation species - Kerstin Wasson; Kim Cressman; Kathryn Beheshti; Erin C. Herder; Charlie Endris; Christopher D.G. Harley; Alicia Abadía-Cardoso; Rodrigo Beas-Luna; Joachim Carolsfeld; Andrew L. Chang; Jeffrey A. Crooks; Matthew C. Ferner; et al. (Marine Environmental Research, 2025)

Lignin hydrotreatment to aromatics products on metallic phosphides carbon-based catalysts produced from lignin - M. García-Rollán; S. Bertran-Llorens; M.A. Palazzolo; P.J. Deuss; H.J. Heeres; R. Ruiz-Rosas; J.M. Rosas; J. Rodriguez-Mirasol; T. Cordero (Fuel, 2025)

Tarwi okara (Lupinus mutabilis) native and modified by high-intensity ultrasound as a gluten-free bread improver - Claudia Huamaní-Perales; Julio Vidaurre-Ruiz; Dario M. Cabezas; María Jimena Correa; Juan J. Burbano; Juan Carlos Rodríguez-Soto; Ritva Repo-Carrasco-Valencia (Food Hydrocolloids, 2025)

From field to fork: the benefits of Trichoderma spp. in food quality and safety - Carlos García-Latorre; Santiago Ruiz-Moyano; Alicia Rodríguez; Rocío Velázquez; María J Poblaciones; Alejandro Hernández (Current Opinion in Food Science, 2025)

The tps5, tps10 and tps11 class II trehalose phosphate synthase mutants alter carbon allocation to starch and organic and amino acids at two different photoperiods in Arabidopsis - Andrea C. Ruiz-Castillo; Daniela J. Bonilla-Córdoba; Ismael Cisneros-Hernández; Norma Martínez-Gallardo; Enrique Ramírez-Chávez; John Délano-Frier (Planta, 2025)
Main conclusion Altered C and N allocation in response to short- and long photoperiods in class II TPS mutants suggest that they negatively regulate the TPS1-Tre6P metabolic regulator system in A. thaliana . Abstract The biological function of class II TPS genes remains largely enigmatic, although there is evidence that they may play an important regulatory role in plant stress responses as well as in development and growth. Recent findings indicated that part of biological function of TPSII proteins may be related to their capacity to associate with the SnRK1 regulator of metabolism in order to inhibit its nuclear activity. The results of the present study show that insertional mutants of the TPS5 , TPS10 and TPS11 class II TPS genes had a marked effect on the carbon allocation to non-structural carbohydrates, notably starch, and to organic and amino acids during both short- and long-day photoperiods. The results obtained in this study, which resembled those obtained previously in AhTPS1 overexpressing plants, suggest that these particular TPSII proteins may negatively regulate of C and N allocation to non-structural carbohydrates, organic and amino acids mediated by the TPS1-Tre6P central metabolic regulator system in A. thaliana plants. The effect observed was sometimes dependent on of the photoperiod employed and the mutant examined. The mechanism by means of which these TPS II proteins may specifically target TPSI activity and Tre6P levels in order to regulate C and N allocation in A. thaliana in response to short- and long-day photoperiods remains to be determined.

Integrated monitoring of dams and large ponds: the role of satellite radar interferometry and the European ground motion service - Antonio Miguel Ruiz-Armenteros; Miguel Marchamalo-Sacristán; Francisco Lamas-Fernández; Álvaro Hernández-Cabezudo; Alfredo Fernández-Landa; José Manuel Delgado-Blasco; Matus Bakon; Milan Lazecky; Daniele Perissin; Juraj Papco; Gonzalo Corral; José Luis García-Balboa; et al. (Applied Geomatics, 2025)
Satellite radar interferometry (InSAR) has become an invaluable tool for monitoring dams and large ponds, providing significant advantages when complemented with geotechnical and geodetic monitoring. InSAR uses radar signals from satellites to detect ground movements with millimeter precision by comparing phase differences between images taken at different times. This technique enables large-scale, continuous monitoring, which is critical for identifying potential structural problems and preventing catastrophic failures. Unlike traditional geotechnical and geodetic monitoring, which require extensive equipment and manual data collection, InSAR provides a non-intrusive, efficient solution that covers vast areas with high temporal frequency. The European Ground Motion Service (EGMS) exemplifies these advantages by providing standardized ground motion data across Europe, derived from Sentinel-1 satellite radar data. EGMS enables routine and comprehensive monitoring of ground stability and infrastructure integrity, assisting in the early detection of deformation patterns and supporting proactive maintenance and risk management. For dam managers, the integration of InSAR with traditional methods enhances the reliability of structural health assessments. Geotechnical sensors offer localized information on soil and material properties, while geodetic methods provide precise positional data; InSAR complements these by delivering comprehensive, continuous deformation maps. This synergy ensures robust monitoring and enhances the ability to predict and mitigate potential problems, significantly improving the effectiveness and efficiency of monitoring dams and large ponds, and contributing to safer and more resilient infrastructure management. This work presents several case studies from the SIAGUA project as examples, highlighting the practical applications and benefits of combining InSAR with traditional monitoring techniques.

Neuroimaging and immunofluorescence of the Pseudopus apodus brain: unraveling its structural complexity - S. Jiménez; R. Morona; M. J. Ruiz-Fernández; E. Fernández-Valle; D. Castejón; M. I. García-Real; J. González-Soriano; N. Moreno (Brain Structure and Function, 2025)
The present study provides an in-depth neuroanatomical characterization of the brain of Pseudopus apodus , combining magnetic resonance imaging (MRI) with histological analysis by immunofluorescence. In the telencephalon, the pallial regions showed distinct anatomical features, including a cortical structure, a dorsal ventricular ridge and the spherical nucleus, but prominent layering patterns, observable on histological slides, were not fully resolved by MRI. Subpallial structures, such as the nucleus accumbens and the basal ganglia, were delineated with histological clarity and further supported by MRI. In the hypothalamic and diencephalic regions, the dense and complex cellular composition made precise delineation of individual nuclei difficult by MRI, in contrast to the histological accuracy, however by MRI the identification of the major tracts running through these domains are clearly identifiable. Mesencephalic and rhombencephalic structures, including the optic tectum, isthmic nuclei, cerebellum, and reticular groups, were systematically described using a combination of histological and MRI techniques. In addition, immunofluorescence analysis of specific markers, such as Calretinin, ChAT, Isl1, Satb1, Serotonin and Tyrosine Hydroxylase, provided higher resolution of functional sub-regions, allowing precise identification of boundaries and facilitating comprehensive regional mapping, showing complex organizational arrangements, both in rostral regions, such as the dorsal ventricular crest, and in caudal regions, within the tegmental and posterior nuclei of the brain, including the ventral tegmental area, substantia nigra and raphe nuclei. These findings establish a robust neuroanatomical framework for Pseudopus apodus , contributing significantly to the understanding of reptile brain organization and providing valuable insights into the evolutionary adaptations underlying a limbless lizard neuroanatomy.

Dissipation of the insecticide profenofos in tropical agricultural soils (Berambadi catchment, South India): Insight from compound-specific isotope analysis (CSIA) - J. Masbou; C. Grail; S. Payraudeau; L. Ruiz; M. Sekhar; J. Riotte; G. Imfeld (Journal of Hazardous Materials, 2025)

The influence of pressure on the formation of macroscopic & microscopic gas hydrate structures and concentration efficiency in coffee solutions - R.M. Sutter; J. Busom Descarrega; V. Meunier; S. Ruiz; J. Doebelin; C. Milo; C. Rauh; C. Hartmann (Journal of Food Engineering, 2025)

How air pollution and extreme temperatures affect emergency hospital admissions due to various respiratory causes in Spain, by age group: A nationwide study - C. Linares; J. Díaz; M.A. Navas; R. Ruiz-Páez; M. Saez; M.A. Barceló; J.A. López-Bueno (International Journal of Hygiene and Environmental Health, 2025)

Reconstructing past sea-level changes from storm-built beach ridges - Alessio Rovere; Marta Pappalardo; Sebastian Richiano; Deirdre D. Ryan; Karla Rubio-Sandoval; Patricio Martin Ruiz; Alejandro Montes; Evan J. Gowan (Geomorphology, 2025)

Plasticized cellulose bioplastics with beeswax for the fabrication of multifunctional, biodegradable active food packaging - Pedro Florido-Moreno; José J. Benítez; Jaime González-Buesa; José M. Porras-Vázquez; Jesús Hierrezuelo; Montserrat Grifé-Ruiz; Diego Romero; Athanassia Athanassiou; José A. Heredia-Guerrero; Susana Guzmán-Puyol (Food Hydrocolloids, 2025)

Analysing the expansion of the circular economy in the European Union: How important is the regional context? - Marta García-Velasco Garzás; María J. Ruiz-Fuensanta (Ecological Economics, 2025)

Aqueous phase hydrogenolysis of glycerol with in-situ hydrogen generation over Ni catalysts supported on activated carbon: Effects of nickel loading and base addition - R. Raso; L. García; J. Ruiz; M. Oliva; J. Arauzo (Biomass and Bioenergy, 2025)

Soluble alpha-klotho and 25-hydroxivitamin D are not associated with brown adipose tissue metabolism in young healthy adults - Francisco J. Amaro-Gahete; Héctor Vázquez-Lorente; Guillermo Sanchez-Delgado; Jonatan R. Ruiz (Journal of Physiology and Biochemistry, 2025)
Background Soluble Alpha-Klotho (S-αklotho) protein and 25-Hydroxyvitamin D (25-OH-D) have emerged as potential modulators for activating and recruiting Brown Adipose Tissue (BAT). The present study aimed to investigate whether circulating S-αklotho and 25-OH-D levels are related to BAT volume, 18 Fluorine-Fluorodeoxyglucose ( 18 F-FDG) uptake, and BAT radiodensity in young healthy adults. Methods A total of 128 participants (68% women) aged 18–25 years old participated in this cross-sectional study. Serum levels of S-αklotho were determined by a solid-phase sandwich enzyme-linked immunosorbent assay kit and 25-OH-D serum levels were analyzed using a competitive chemiluminescence immunoassay, both in blood samples collected after an overnight fast. All participants underwent a personalized cold exposure to determine their BAT volume, 18 F-FDG uptake, and radiodensity, using a static positron emission tomography combined with computed tomography scan. Results After adjusting for multiple covariates, serum levels of S-αklotho (all R 2 ≤ 0.228 and P ≥ 0.364), 25-OH-D as continuous (all R 2 ≤ 0.242 and P ≥ 0.088) or by vitamin D status (all R 2 ≤ 0.767 and P ≥ 0.061) were not associated with either BAT volume and 18 F-FDG uptake, or BAT radiodensity. Conclusion Serum S-αklotho and 25-OH-D levels within the physiological range are not related to BAT-related variables in young healthy adults. Further studies are needed to fully understand the underlying mechanisms involved in BAT metabolism in humans. (ACTIBATE; ClinicalTrials.gov identifier: not applicable).

Quantifying physical activity during active commuting to school: A comparison of methodologies - P. Campos-Garzón; A.J. Lara-Sánchez; A. Queralt; J. Schipperijn; T. Stewart; Y. Barranco-Ruiz; P. Chillón; J.H. Migueles (Travel Behaviour and Society, 2025)

From fly ashes of lignocellulose waste combustion to sustainable activated carbons for VOCs removal - B. Ruiz; Alba Cabrera-Codony; R.P. Girón; Alba Anfruns; Maria J. Martín; I. Suárez-Ruiz; E. Fuente (Sustainable Chemistry and Pharmacy, 2025)

Designing cost-effective supply chains for plastics at the end-of-life - Baibhaw Kumar; Jean Pimentel; Natalia A. Cano-Londoño; Gerardo J. Ruiz-Mercado; Csaba T. Deak; Heriberto Cabezas (Journal of Cleaner Production, 2025)

A crustal-scale section of central and NW Iberia: Deformation mechanisms and transfer during the Alpine compression - I. DeFelipe; P. Ayarza; I. Palomeras; M. Ruiz; J. Andrés; M. Yenes; D. Martínez Poyatos; R. Carbonell (Gondwana Research, 2025)

Exploring automated tracking of chemicals through their conditions of use to support life cycle chemical assessment - John D. Chea; David E. Meyer; Raymond L. Smith; Sudhakar Takkellapati; Gerardo J. Ruiz‐Mercado (Journal of Industrial Ecology, 2025)
Modeling the fate of chemicals across their life cycle when considering all potential uses can be challenging because of the data gaps arising from issues like confidential business information (data accessibility) and complex processing schemes (involvement in formulations, reactions, and separations) across multiple industries, products, and applications. Thus, assessing chemicals for safety and/or sustainability requires developing an extensive knowledge of chemical releases along the various conditions of use (CoU) to identify potential impacts on human health and the environment. The first step in this process is mapping the flow of a chemical throughout its various downstream uses, which can be time‐intensive. Here, a chemical mapping methodology is developed to qualitatively assess the allocation of a chemical of interest from its manufacture through its CoU in consumer, commercial, and industrial products. The chemical flow mapping combines knowledge from searches of publicly available data sources based on the chemical's Chemical Abstracts Service number to determine viable chemical flow paths. Examples of data sources when applying this approach to chemicals in the United States include the Chemical Data Reporting database, the Toxics Release Inventory, the North American Industry Classification System, and the Chemical and Products Database. The methodology is demonstrated using case studies of methylene chloride and triphenyl phosphate. The value of this approach is its ability to be automated and enable rapid determination of the life cycle chemical flow for expedited chemical assessment.

Remarks on the diversity of Hysteromorpha Lutz 1931 (Digenea, Diplostomidae), with erection of a new species from South America - Tyler J. Achatz; Sean A. Locke; Florencia Arrascaeta; Martin M. Montes; Jorge Barneche; Alan Fecchio; Jeffrey A. Bell; Pablo Oyarzún-Ruiz; Geza T. R. Souza; Ricardo M. Takemoto; Vasyl V. Tkach (Systematic Parasitology, 2025)
Hysteromorpha Lutz, 1931 is a small but broadly distributed genus of diplostomoidean digeneans parasitic as adults primarily in cormorants, but also reported from some other fish-eating birds. Their metacercariae were found in a variety of freshwater fishes as second intermediate hosts. Prior to this study, the genus included only 3 nominal species, 2 of them distributed in the Old World and 1 in the New World. We obtained sequences of partial mitochondrial cox 1 gene and nuclear rDNA operon from new specimens collected in Europe, North and South America and used them for species comparisons and phylogenetic analysis. We also examined morphology of our newly collected specimens as well as museum specimens. Our analysis has demonstrated that at least 2 (likely 3) species of Hysteromorpha are distributed in the Americas. Hysteromorpha sp. previously sequenced from larval stages, clearly represents a new species named herein Hysteromorpha ostrowskiae n. sp. Achatz, Locke et Tkach. Morphology of adults of the new species was earlier described in sufficient detail under the name Hysteromorpha triloba (Rudolphi, 1819). Our analyses also suggest the presence of another unknown Hysteromorpha sp. in North America represented by cox 1 sequence from southeastern Canada (GenBank JF769473), but no morphological vouchers are available for this species.

Past and present bacterial communities in deglaciating northern latitude catchments reveal varied soil carbon sequestration potential - Saule Akhmetkaliyeva; Andrew P. Dean; Leon J. Clarke; Simon J. Cook; Sharon Ruiz Lopez; Robert B. Sparkes (Science of The Total Environment, 2025)

Economic estimation and impact of air pollution and temperature extremes on emergency hospital admissions in Spain - R. Ruiz-Páez; J. Díaz; J.A. López-Bueno; M. Saez; M.A. Barceló; M.A. Navas; C. Linares (Science of The Total Environment, 2025)

Historical increases in plant density increased vegetative maize biomass while breeding increased reproductive biomass and allocation to ear over stem - Ezequiel Saenz; Alejo Ruiz; Cintia Sciarresi; Kyle King; Mitchell Baum; Antonella Ferela; Gerasimos J.N. Danalatos; Brenda Gambin; George Kalogeropoulos; August Thies; Raziel A. Ordóñez; Slobodan Trifunovic; et al. (Field Crops Research, 2025)

Climate change impacts on two European crop rotations via an ensemble of models - E. Pohanková; P. Hlavinka; K.C. Kersebaum; C. Nendel; A. Rodríguez; J. Balek; J. Balkovič; M. Dubrovský; G. Hoogenboom; M. Moriondo; J.E. Olesen; J.W.M. Pullens; et al. (European Journal of Agronomy, 2025)

Triphenyl Acetic Glyceroate as a sustainable multifunctional additive for developing transparent, biodegradable, and flexible polylactide green alternative to polyethylene-based films for food packaging - Martina Ferri; Luca Lenzi; Micaela Degli Esposti; Laura Martellosio; José J. Benítez; Jesús Hierrezuelo; Montserrat Grifé-Ruiz; Diego Romero; Susana Guzmán-Puyol; José A. Heredia-Guerrero; Davide Morselli; Paola Fabbri (Chemical Engineering Journal, 2025)

Genome-wide analysis of ARF gene family and miR160 in avocado (Persea americana Mill.) and their roles in somatic embryogenesis from zygotic embryos - J. L. Lorenzo-Manzanarez; A. J. Enríquez-Valencia; C. A. Olivares-García; E. Ibarra-Laclette; O. Velázquez-López; E. Ruiz-May; V. M. Loyola-Vargas; A. F. Kú-González; M. A. Arteaga-Vázquez; M. Mata-Rosas (Planta, 2025)

Pericardium decellularization in a one-day, two-step protocol - P. López-Chicón; J. I. Rodríguez Martínez; C. Castells-Sala; L. Lopez-Puerto; L. Ruiz-Ponsell; O. Fariñas; A. Vilarrodona (Molecular and Cellular Biochemistry, 2025)

Nitric Oxide (NO) and Hydrogen Sulfide (H2S): New Potential Biotechnological Tools for Postharvest Storage of Horticultural Crops - Francisco J. Corpas; María A. Muñoz-Vargas; Salvador González-Gordo; Marta Rodríguez-Ruiz; José M. Palma (Journal of Plant Growth Regulation, 2025)
Storage and maintenance of horticultural products in optimal conditions for a reasonable period, once they have been harvested is a technological challenge. Diverse methods are generally used, i.e., low temperature but, in many cases, it may provoke undesirable collateral effects such as softening or promoting pathogens infections, thus causing their deterioration. Nitric oxide ( · NO) and hydrogen sulfide (H 2 S) are compounds generated endogenously by plants with signaling properties that mediate fruit development and ripening. Additionally, when these molecules are applied exogenously, they can provide benefits such as maintaining the quality of horticultural products and even prolonging their shelf-life once they are stored. This review provides a broad perspective of · NO and H 2 S metabolism in plant cells and, in addition, different plant models are described of how the exogenous application of either NO or H 2 S to horticultural products preserves nutritional quality during postharvest storage. Graphical Abstract

The combination of neurotropic B vitamins (B1, B6, and B12) is superior to individual B vitamins in promoting neurite growth in vitro - Melissa L. D. Rayner; Arnaud J. Ruiz; Christian Viel (In Vitro Cellular & Developmental Biology - Animal, 2025)

Effects of feed additives in the diet of male dairy beef calves on physiological status and rumen microbial fermentation pre- and postweaning - E. Romera-Recio; E. Ramos-Morales; A. Belanche; M. Hassan; P. Romero; A. Gómez; I. Rivelli; N. Llanes; J. Torra; D.R. Yáñez-Ruiz (Animal Feed Science and Technology, 2025)

Socioecological drivers of injuries and aggression in female and male rhesus macaques (Macaca mulatta) - Melissa A. Pavez-Fox; Erin R. Siracusa; Samuel Ellis; Clare M. Kimock; Nahiri Rivera-Barreto; Josue E. Negron-Del Valle; Daniel Phillips; Angelina Ruiz-Lambides; Noah Snyder-Mackler; James P. Higham; Delphine De Moor; Lauren J. N. Brent (Behavioral Ecology and Sociobiology, 2025)
Competition over access to resources, such as food and mates, is one of the major costs associated with group living. Two socioecological factors believed to drive the intensity of competition are group size and sex ratio. However, empirical evidence linking these factors to physical aggression and injuries is scarce. Here, we leveraged 10 years of data from free-ranging female and male rhesus macaques to test whether group size and adult sex ratio predicted the risk of inter and intrasexual aggression, as well as injury risk. We found evidence for an optimal group size at which the risk of intragroup aggression was minimized for both sexes. Despite male-male aggression being lowest in mid-sized groups, males in smaller groups experienced higher injury risk, suggesting within-group aggression might not be the main cause of male injury. Additionally, we found that sex ratio influenced aggression, but not injury risk. Specifically, female aggression toward other females was heightened during the birth season when groups had fewer available males, suggesting either female competition for male friends or exacerbated female-female competition due to the energetic costs of lactation. Male aggression towards females was higher in female-biased groups during the birth season and in male-biased groups during the mating season, which could reflect male competition with females over feeding opportunities and male coercion of females, respectively. Together, these findings provide insights into fitness costs (i.e., injury risk) of inter and intrasexual competition in primates in relation to key aspects of social organization. Significance statement While theory suggests that group size and sex ratio influence competition, studies linking these factors to aggression and injury rates are limited. Using long-term data on demography, aggression, and injury from a group-living primate, we show that both males and females experience aggression less often at intermediate group sizes. However, males in smaller groups faced higher injury risks. Although sex ratio did not predict injury risk, it did influence intra- and intersexual aggression, with patterns varying by reproductive season. Overall, our findings provide insights into how competition shapes intra and intersexual dynamics in relation to aspects of social organization.

How Old Is the Presence of the Canary Pine Forests in the Canary Islands? - C. A. Góis‐Marques; E. Martín‐González; J. M. Postigo‐Mijarra; M. C. Velasco‐Flores; C. Castillo Ruiz; M. Menezes de Sequeira (Journal of Biogeography, 2025)
Aim The Neogene fossil record of Pinus canariensis C.Sm ex DC. suggests a wider past distribution in Europe, but due to extirpation by past climatic events, today this taxon is restricted to the Canary Islands. Remarkably, the putative oldest P. canariensis fossil for the Canary Islands, found in Gran Canaria is 13.3–13.0 Ma. This palaeobiogeographical information has been cited as proof of the deep‐time presence of conifers, the genus Pinus L., P. canariensis and the pine forest ecosystems in the Canary Islands, but also to justify the long‐term evolution of P. canariensis within an active insular volcanic environment. Here we present a re‐evaluation of the oldest Pinus fossil from the Canary Island. Location Gran Canaria, Canary Islands, Spain. Taxon Pinus canariensis C.Sm ex DC. Methods We compiled a citation record for the mentions of the ‘bark fossil’ and conducted a review of the specimen. We compared it with extant P. canariensis and with pyroclasts. Results The analysis of the specimen demonstrates that it lacks morphological or anatomical characters to identify as a bark or even as a plant fossil. The specimen is best interpreted as a lapilli‐sized tube pumice, highly altered by mineral deposition promoted by the percolating hydrothermal water. Main Conclusions The oldest reliable Pinus fossils from the Canary Islands are 3.9–3.1 Ma and ca. 9 to 10 Ma younger than previously claimed. When did Pinus arrive at the Canary Islands is unknown, but this biogeographical question can be approached via focused volcano‐stratigraphical and palaeobotanical research in this Archipelago.

Continuous extraction of xylose to Dowtherm A via esterification with 1-napthalene boronic acid from bagasse acid hydrolysate - Peter J. van der Wal; Jean-Paul Lange; Sascha R.A. Kersten; M. Pilar Ruiz (Journal of Environmental Chemical Engineering, 2025)

Differentiation of microbial communities in coastal seawater before and during an Akashiwo sanguinea (Dinophyceae) bloom in the urban area of Antofagasta city (northern Chile) - Jingming Hu; Henry Camerón; Joaquín I. Rilling; Marco Campos; Tay Ruiz-Gil; Mariela A. Gonzalez; Gonzalo Gajardo; Karen Vergara; Leonardo Guzmán; Oscar Espinoza-González; Gonzalo Fuenzalida; Carlos Riquelme; et al. (Harmful Algae, 2025)

Raw milk at refrigeration temperature displays an independent microbiota dynamic regardless Listeria monocytogenes contamination - Alba Espí-Malillos; Inmaculada López-Almela; Pilar Ruiz-García; María Carmen López-Mendoza; Nerea Carrón; Pedro González-Torres; Juan J. Quereda (Food Research International, 2025)

Integrated biotechnological process based on submerged fermentation and sonotrode extraction as a valuable strategy to obtain phenolic enriched extracts from moringa leaves - María del Carmen Razola-Díaz; Soumi De-Montijo-Prieto; María José Áznar-Ramos; Beatriz Martín-García; María Jiménez-Valera; Alfonso Ruiz-Bravo; Eduardo J. Guerra-Hernández; Belén García-Villanova; Vito Verardo; Ana M Gómez-Caravaca (Food Research International, 2025)

Yield environment changes the ranking of soybean genotypes - Lucas J. Abdala; Santiago Tamagno; Alejo Ruiz; Raí A. Schwalbert; Adrián A. Correndo; Nicolas Martin (Field Crops Research, 2025)

Lignocellulosic pruning waste adsorbents to remove emerging contaminants from tyre wear and pharmaceuticals present in wastewater in circular economy scenario - J. Lladó; A.M. Díaz; N. Lopez-Vinent; S. Pérez; N. Montemurro; A. Cruz-Alcalde; C. Lao; E. Fuente; B. Ruiz (Bioresource Technology, 2025)

Oxidative electrochemical depolymerization of lignin using highly active self-standing electrocatalysts prepared by electrospinning of lignin - M. García-Rollán; M. Toscano-de los Riscos; R. Ruiz-Rosas; J.M. Rosas; J. Rodríguez-Mirasol; T. Cordero (Biomass and Bioenergy, 2025)

Higher plasma levels of endocannabinoids and analogues are correlated with a worse cardiometabolic profile in middle-aged adults - Carmen Rodríguez-García; Francisco J. Osuna-Prieto; Isabelle Kohler; Joaquin Sanchez-Gomez; Samuel Ruiz-Campos; Manuel J. Castillo; Francisco J. Amaro-Gahete; Borja Martínez-Tellez; Lucas Jurado-Fasoli (Journal of Physiology and Biochemistry, 2025)

Untangling the Complexity of Climate Change Effects on Plant Reproductive Traits and Pollinators: A Systematic Global Synthesis - Silvana Martén‐Rodríguez; Edson Jacob Cristobal‐Pérez; Martín Hesajim de Santiago‐Hernández; Guillermo Huerta‐Ramos; Lucero Clemente‐Martínez; Gary Krupnick; Orley Taylor; Martha Lopezaraiza‐Mikel; Francisco Javier Balvino‐Olvera; Eugenia M. Sentíes‐Aguilar; Sergio Díaz‐Infante; Armando Aguirre Jaimes; et al. (Global Change Biology, 2025)
Climate change is expected to affect the morphological, physiological, and life‐history traits of plants and animal pollinators due to more frequent extreme heat and other altered weather patterns. This systematic literature review evaluates the effects of climate change on plant and pollinator traits on a global scale to determine how species responses vary among Earth's ecosystems, climate variables, taxonomic groups, and organismal traits. We compiled studies conducted under natural or experimental conditions (excluding agricultural species) and analyzed species response patterns for each trait (advance vs. delay or no change for phenology, decrease vs. increase or no change for other traits). Climate change has advanced plant and animal phenologies across most Earth's biomes, but evidence for temporal plant–pollinator mismatches remains limited. Flower production and plant reproductive success showed diverse responses to warming and low water availability in Alpine and Temperate ecosystems, and a trend for increased or neutral responses in Arctic and Tropical biomes. Nectar rewards mainly experienced negative effects under warming and drought across Alpine and Temperate biomes, but scent emissions increased or changed in composition. Life form (woody vs. nonwoody species) did not significantly influence trait response patterns to climate change. Pollinator fecundity, size, life‐history, developmental, and physiological traits mostly declined with warming across biomes; however, animal abundance and resource acquisition traits showed diverse responses. This review identified critical knowledge gaps that limit our understanding of the impacts of climate change, particularly in tropical/subtropical biomes and southern latitudes. It also highlights the urgent need to sample across a greater range of plant families and pollinator taxa (e.g., beetles, wasps, vertebrates). The diversity of climate change effects should be assessed in the context of other anthropogenic drivers of global change that threaten critically important pollination interactions.

Challenges to Mediterranean Fagaceae ecosystems affected by Phytophthora cinnamomi and Climate Change: Integrated Pest Management perspectives - Carmen Morales-Rodríguez; Andrea Vannini; Bruno Scanu; Pablo González-Moreno; Silvia Turco; Mounira Inas Drais; Andrea Brandano; Mari Ángeles Varo Martínez; Angelo Mazzaglia; Antonio Deidda; Adrián Cidre; José Gomes-Laranjo; et al. (Current Forestry Reports, 2025)

Phylogeography of Labyrinthula species and strains shows high connectivity and low genetic variation across seagrass hosts and geographic locations in North America - Katrina M. Pagenkopp Lohan; Ruth DiMaria; Daniel L. Martin; A. Randall Hughes; Bradley J. Peterson; Katharyn E. Boyer; John J. Stachowicz; Pablo Jorgensen; Gregory M. Ruiz; Cliff Ross (Frontiers in Marine Science, 2025)
Seagrass wasting disease, caused by parasitic slime nets in the genus Labyrinthula , affects seagrasses globally with outbreaks occurring at local to regional scales. Though prior research showed variation in pathogenicity across strains, little is known about the broad-scale diversity and biogeography of Labyrinthula species. We used targeted amplicon-based high throughput sequencing (HTS) to examine the phylogeography of Labyrinthula species associated with two seagrass hosts ( Zostera marina , Thalassia testudinum ) collected from across North America, including locations in the USA and Mexico. After testing 189 seagrass blades from 16 locations across North America, Labyrinthula spp. were detected at 14 sites with PCR prevalence ranging from 20 - 100%. We generated 10,936,628 sequences for analyses, which yielded 25 unique Labyrinthula amplicon sequence variants (ASVs), which were phylogenetically grouped into three species of Labyrinthula . All three species detected were previously identified as pathogenic, indicating that Labyrinthula species capable of causing wasting disease are present across these regions, including in locations where disease outbreaks have not been reported. The highest strain level variation was detected in Florida, which is likely due to larger sample sizes from Florida compared to other sampling locations. Assessing the phylogeography of strains was limited by sample size in each location, but indicates that the genetic connectivity of strains appears high, with location and seagrass host being the most important factors explaining the variation in Labyrinthula strains detected. The high connectivity, but low overall species diversity of Labyrinthula , is consistent with a parasite that is a host generalist. Given the high connectivity of strains and broad geographic range of pathogenic Labyrinthula reported here, this study provides valuable insight regarding how parasite diversity impacts seagrass disease.

Promoting Workplace Health, Safety, and Well-Being Among Essential Agricultural Workers Through Vaccine-Preventable Infectious Diseases Training in the Rio Grande Valley - Anabel Rodriguez; David I Douphrate; Ana L Pineda Reyes; Susana Zavala; Andrea V. Cabrera Cruz; Maria D Alegria; Brian Ukaegbu; Annie J Keeney; Brenda Berumen-Flucker; Eva M Shipp; Shannon P Guillot-Wright; Maria E Fernandez-Esquer; et al. (Journal of Agromedicine, 2025)

Shortfalls in the protection of Important Shark and Ray Areas undermine shark conservation efforts in the Central and South American Pacific - Théophile L. Mouton; Adriana Gonzalez-Pestana; Christoph A. Rohner; Ryan Charles; Emiliano García-Rodríguez; Peter M. Kyne; Amanda Batlle-Morera; Giuseppe Notarbartolo di Sciara; Asia O. Armstrong; Enzo Acuña; Joanna Alfaro-Shigueto; Randall Arauz; et al. (Marine Policy, 2025)

Effect of different deficit irrigation regimens on soil moisture, production parameters of mango (Mangifera indica L.), and spectral vegetation indices in the Mediterranean region of Southern Spain - J.A. Sillero-Medina; J. González-Pérez; P. Hueso-González; J.J. González-Fernández; J.I. Hormaza-Urroz; J.D. Ruiz-Sinoga (Remote Sensing Applications: Society and Environment, 2025)

Influence of Triassic and Jurassic arc magmatism in Lower Jurassic Sierra de Santa Rosa Formation, northwestern México: Constraints from geochemistry and U-Pb geochronology - Jocelyn Galindo-Ruiz; Erik Ramírez-Montoya; Jayagopal Madhavaraju; Carlos M. González-León; Francisco J. Grijalva-Noriega; Luigi Solari; Rogelio Monreal; Inocente G. Espinoza-Maldonado (Marine and Petroleum Geology, 2025)

Evaluating the precise grapevine water stress detection using unmanned aerial vehicles and evapotranspiration-based metrics - V. Burchard-Levine; I. Borra-Serrano; J. M. Peña; W. P. Kustas; J. G. Guerra; J. Dorado; G. Mesías-Ruiz; M. Herrezuelo; B. Mary; L. M. McKee; A. I. de Castro; S. Sanchez-Élez; et al. (Irrigation Science, 2025)
Precise irrigation management requires accurate knowledge of crop water demand to adequately optimize water use efficiency, especially relevant in arid and semi-arid regions. While unoccupied aerial vehicles (UAV) have shown great promise to improve the water management for crops such as vineyards, there still remains large uncertainties to accurately quantify vegetation water requirements, especially through physically-based methods. Notably, thermal remote sensing has been shown to be a promising tool to evaluate water stress at different scales, most commonly through the Crop Water Stress Index (CWSI). This work aimed to evaluate the potential of a UAV payload to estimate evapotranspiration (ET) and alternative ET-based crop water stress indices to better monitor and detect irrigation requirements in vineyards. As a case study, three irrigation treatments within a vineyard were implemented to impose weekly crop coefficient (Kc) of 0.2 (extreme deficit irrigation), 0.4 (typical deficit irrigation) and 0.8 (over-irrigated) of reference ET. Both the original Priestley-Taylor initialized two-source energy balance model (TSEB-PT) and the dual temperature TSEB (TSEB-2T), which takes advantage of high-resolution imagery to discriminate canopy and soil temperatures, were implemented to estimate ET. In a first step, both ET models were evaluated at the footprint level using an eddy covariance (EC) tower, with modelled fluxes comparing well against the EC measurements. Secondly, in-situ physiological measurements at vine level, such as stomatal conductance (g st ), leaf (Ψ leaf ) and stem (Ψ stem ) water potential, were collected simultaneously to UAV overpasses as plant proxies of water stress. Different variants of the CWSI and alternative metrics that take advantage of the partitioned ET from TSEB, such as Crop Transpiration Stress Index (CTSI) and the Crop Stomatal Stress Index (CSSI), were also evaluated to test their statistical relationship against these in-situ physiological indicators using the Spearman correlation coefficient ( ρ ). Both TSEB-PT and TSEB-2T CWSI related similarly to in-situ measurements (Ψ leaf : ρ ~ 0.4; Ψ stem : ρ ~ 0.55). On the other hand, stress indicators using canopy fluxes (i.e. CTSI and CSSI) were much more effective when using TSEB-2 T (Ψ leaf : ρ = 0.45; Ψ stem : ρ = 0.62) compared to TSEB-PT (Ψ leaf : ρ = 0.18; Ψ stem : ρ = 0.49), revealing important differences in the ET partitioning between model variants. These results demonstrate the utility of physically-based models to estimate ET and partitioned canopy fluxes, which can enhance the detection of vine water stress and quantitatively assess vine water demand to better manage irrigation practices.

Random Mating in a Hybrid Zone Between Two Putative Climate‐Adapted Bird Lineages With Predicted Mitonuclear Incompatibilities - Lana M. Austin; J. Nevil Amos; Diana A. Robledo‐Ruiz; Jessica W. Zhou; Rohan H. Clarke; Alexandra Pavlova; Paul Sunnucks (Molecular Ecology, 2025)
Biochemical and evolutionary interactions between mitochondrial and nuclear genomes (‘mitonuclear interactions’) are proposed to underpin fundamental aspects of biology including evolution of sexual reproduction, adaptation and speciation. We investigated the role of pre‐mating isolation in maintaining functional mitonuclear interactions in wild populations bearing diverged, putatively co‐adapted mitonuclear genotypes. Two lineages of eastern yellow robin Eopsaltria australis —putatively climate‐adapted to ‘inland’ and ‘coastal’ climates—differ by ~7% of mitogenome nucleotides, whereas nuclear genome differences are concentrated into a sex‐linked region enriched with mitochondrial functions. Female‐specific selection and male‐mediated gene flow across the hybrid zone where the lineages coexist and interbreed can explain this pattern. It remains unknown whether lineage divergence is driven by intrinsic incompatibilities (particularly in females; Haldane's rule), extrinsic selection, both, or other drivers. We tested whether lineage divergence could be facilitated by non‐random mate‐pairing with respect to partners' mitolineage and/or mitonuclear genes encoded by the Z sex‐chromosome, which differ between the lineages. We used field‐, Z‐linked‐ and mitolineage data from two locations where lineages hybridise to test whether females mate disproportionately with (1) males of their own mitolineage and/or bearing similar Z‐linked variation, as might be expected if hybrids experience intrinsic incompatibilities, or (2) putatively locally‐adapted males, as might be expected under environmental selection. Comparing field observations with simulations provided no evidence of non‐random mating, thus drivers of observed population genetic patterns are consistent with reduced female gene flow likely acting post‐mating. Future tests of female‐biased mortality at different life stages and habitat selection may clarify mechanisms of selection.

A Neanderthal's specialised burning structure compatible with tar obtention - Juan Ochando; Francisco J. Jiménez-Espejo; Francisco Giles-Guzmán; Carlos Neto de Carvalho; Jose S. Carrión; Fernando Muñiz; Juan Manuel Rubiales; Pedro Cura; João Belo; Stewart Finlayson; Belen Martrat; Barend L. van Drooge; et al. (Quaternary Science Reviews, 2024)

Permian succession from Sierra La Flojera, Sonora, Mexico: Stratigraphy and correlation with Laurentia - Alejandra Montijo-González; Francisco Javier Cuen-Romero; Héctor Arturo Noriega-Ruiz; Miguel A. Torres-Martínez; Rogelio Monreal; Juan J. Avendaño-Pazos; Blanca Estela Buitrón-Sánchez (Journal of South American Earth Sciences, 2024)

Precursors consumption preferences and thiol release capacity of the wine yeasts Saccharomyces cerevisiae, Torulaspora delbrueckii, and Lachancea thermotolerans - J. Vicente; F. Kiene; D. Fracassetti; I. De Noni; R. Shemehen; A. Tarasov; A.V. Dobrydnev; D. Marquina; A. Santos; D. Rauhut; I. Belda; J. Ruiz (International Journal of Food Microbiology, 2024)

Enhanced extraction of bioactive compounds from tea waste for sustainable polylactide-based bioplastic applications in active food packaging - Maria A. Acquavia; José J. Benítez; Susana Guzmán-Puyol; José M. Porras-Vázquez; Jesús Hierrezuelo; Montserrat Grifé-Ruiz; Diego Romero; Angela Di Capua; Rocco Bochicchio; Saverio Laurenza; Giuliana Bianco; José A. Heredia-Guerrero (Food Packaging and Shelf Life, 2024)

Soil greenhouse gas fluxes partially reduce the net gains in carbon sequestration in mangroves of the Brazilian Amazon - Angelo F. Bernardino; Hermano M. Queiroz; Gabriel N. Nobrega; Gabriel C. Coppo; Christian J. Sanders; Antonio E.B. Silva; J. Boone Kauffman; Rodolfo F. Costa; Carla F. Pacheco; André Vassoler; Araiene P. Pereira; Francisco Ruiz; et al. (Environmental Research, 2024)

Elicitors: impact on the fungal pathogenicity and colonization in fruits - Cristina Hidalgo; Santiago Ruiz-Moyano; Manuel J Serradilla; Ana I Galván; Alicia Rodríguez (Current Opinion in Food Science, 2024)

Determination of neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio and systemic immune-inflammation index in dogs with leptospirosis - A. Durán-Galea; J. I. Cristóbal-Verdejo; B. Macías-García; P. Nicolás-Barceló; R. Barrera-Chacón; P. Ruiz-Tapia; M. C. Zaragoza-Bayle; F. J. Duque-Carrasco (Veterinary Research Communications, 2024)
Leptospirosis is a globally distributed zoonosis with multisystemic involvement in canine species, capable of causing a pulmonary hemorrhagic syndrome (LPHS) in the most severe cases. In humans, the neutrophil to lymphocyte ratio (NLR), platelets to lymphocytes (PLR) and systemic immune-inflammation index (SII) have been described as predictors of morbidity and mortality in various pathologies, but no such studies have been developed for canine leptospirosis. Hence, we aimed to assess the usefulness of NLR, PLR and SII in dogs affected with leptospirosis, focusing on those that died or survived after hospitalization, whether or not they developed LPHS. The leptospirosis group was composed by 36 dogs while the control group consisted of 32 healthy dogs. The NLR, associated with inflammation, demonstrated a threefold or greater increase in all leptospirosis groups compared to the control group (median 2.44 ± 1.66) (developing or not LPHS). Dogs that died (median 67.78 ± 158.67), developed LHPS (median 85.17 ± 143.77), or both developed LHPS and died (median 67.78 ± 155,14) had a lower PLR in comparison to the control group (median 101,82 ± 53,75) and the rest of groups, but no statistically significant differences were observed ( p > 0.05). The SII was higher in leptospirosis-affected dogs that survived (median 1356,92 ± 2726,29) and statistically significant differences were observed in those who did not develop LPHS (median 1770,41 ± 2630,77; p < 0.05) compared to the control group (median 555,21 ± 313,26). Our data shows that NLR may be used as inflammation indicator, while more studies are needed for PLR and SII in canine leptospirosis.

Impacts of the COVID-19 pandemic on the Spanish seafood sector - Sebastian Villasante; Arantza Murillas; Pablo Pita; Ana Tubío; Jose J. Pascual-Fernández; Guillherme Arangao; Joan Moranta; Marta Coll; Andrés Ospina-Alvarez; Silvia de Juan; Ana Ruiz-Frau; Raul Prellezo; et al. (Marine Policy, 2024)

V-ToCs (Venom Toxin Clustering): A tool for the investigation of sequence and structure similarities in snake venom toxins - Konstantinos Kalogeropoulos; Vlad Rosca; Carol O'Brien; Charlotte Risager Christensen; Rahmat Grahadi; Christoffer Vinther Sørensen; Max D. Overath; Diego Ruiz Espi; David E. Jenkins; Ulrich auf dem Keller; Andreas H. Laustsen; Thomas J. Fryer; et al. (Toxicon, 2024)

Tracking orbital and suborbital climate variability in the westernmost Mediterranean over the past 13,000 years: New insights from paleoperspectives on marine productivity responses - Ricardo D. Monedero-Contreras; Francisca Martínez-Ruiz; Francisco J. Rodríguez-Tovar; José M. Mesa-Fernández; Francesca Sangiorgi (Quaternary Science Reviews, 2024)

Reconstructing deep-sea oxygenation in the Western Alboran Sea Basin during Late Pleistocene-Holocene (last 37 kyrs): Insights from a multiproxy approach - Santiago Casanova-Arenillas; Francisca Martínez-Ruiz; Francisco J. Rodríguez-Tovar; José N. Pérez-Asensio; Ricardo Monedero-Contreras; Víctor Villasante-Marcos (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

The role of liquefaction in the evolution of shallow submarine canyon heads from a geotechnical perspective: A case study of the Garrucha Canyon (SE Mediterranean) - J. Nespereira; D. Casas; M. Yenes; S. Monterrubio; D. Casalbore; N. López-González; B. Alonso; M.E Martín; R. Ruiz; A. Tijera; S. Lafuerza; J. Llopart (Marine Geology, 2024)

The petrology of dispersed organic matter in sedimentary rocks: Review and update - P.A. Gonçalves; J. Kus; P.C. Hackley; A.G. Borrego; M. Hámor-Vidó; W. Kalkreuth; J.G. Mendonça Filho; H.I. Petersen; W. Pickel; M.J. Reinhardt; I. Suárez-Ruiz (International Journal of Coal Geology, 2024)

The antimycotic potential of Debaryomyces hansenii LRC2 on Iberian Pork Loins with low concentration preservatives - Helena Chacón-Navarrete; Marcos Gómez; María José Cardador; José Ángel Salatti-Dorado; Pilar Ruiz Pérez-Cacho; José Ángel Roldán-Casas; Lourdes Arce; Hortensia Galán-Soldevilla; Bibiano López; José Ramos; Francisco J. Ruiz-Castilla (Food Control, 2024)

Furanic jet fuels – Water-free aldol condensation of furfural and cyclopentanone - R. Baldenhofer; A. Smet; J.-P. Lange; S.R.A. Kersten; M.P. Ruiz (Biomass and Bioenergy, 2024)

Correction to: Comparison of linear and nonlinear models to estimate body weight of Pelibuey ewes from body measurements - Rafael J. Macedo-Barragán; Victalina Arredondo-Ruiz; Carlos Urban Haubi-Segura; Paola Estefanía Castillo-Zamora (Tropical Animal Health and Production, 2024)

Enhancing groundwater management with GRACE-based groundwater estimates from GLDAS-2.2: a case study of the Almonte-Marismas aquifer, Spain - C. Guardiola-Albert; N. Naranjo-Fernández; J. S. Rivera-Rivera; J. M. Gómez Fontalva; H. Aguilera; F. Ruiz-Bermudo; M. Rodríguez-Rodríguez (Hydrogeology Journal, 2024)
The Almonte-Marismas aquifer, southwestern Spain, is a critical ecohydrogeological system that features extensive groundwater monitoring. This study investigates the utility of gravity recovery and climate experiment (GRACE) satellite data, specifically obtained from the global land data assimilation system (GLDAS) version 2.2, for assessing groundwater storage variations in the Almonte-Marismas aquifer. The presented research emphasizes the practical application of readily available GLDAS products that do not require data preprocessing. The study validates the GLDAS-2.2-based ready-to-use groundwater storage (GWS) time series by correlating it with precipitation and piezometric information, highlighting its effectiveness in medium-scale aquifers. The results reveal a strong agreement between GLDAS-2.2-derived GWS anomalies and in-situ measurements, confirming GLDAS-2.2’s potential for assessing aquifer depletion. The study discusses the consistency of seasonal variations in groundwater levels and GLDAS-2.2 data, emphasizing their close alignment with precipitation and pumping activities. Importantly, the study introduces GLDAS-2.2-derived volumetric groundwater storage (VGWS) as a valuable calibration parameter for numerical groundwater flow models, enhancing their accuracy over time. Moreover, the analysis reveals disparities in annual recharge values between GLDAS-2.2-derived data and the soil-water mass balance. These variations suggest the importance of additional inputs to precipitation, possibly related to subsurface or lateral connections. Overall, this study contributes to the ongoing discourse on the practical applications of GLDAS-2.2-derived GWS data in groundwater management, offering insights into its effectiveness in diverse hydrogeological settings, particularly in areas that lack monitoring infrastructure.

Impacts of advanced metals recovery on municipal solid waste incineration bottom ash: aggregate characteristics and performance in portland limestone cement concrete - Kate D. Weiksnar; Ethan J. Marks; Margaret J. Deaderick; Isabella Meija-Ruiz; Christopher C. Ferraro; Timothy G. Townsend (Waste Management, 2024)

Harmful Ostreopsis cf. ovata blooms could extend in time span with climate change in the Western Mediterranean Sea - S. Fabri-Ruiz; E. Berdalet; C. Ulses; S. Somot; M. Vila; R. Lemée; J.-O. Irisson (Science of The Total Environment, 2024)

Short-term effects of fine particulate matter from biomass combustion and Saharan dust intrusions on emergency hospital admissions due to mental and behavioural disorders, anxiety and depression in Spain - R. Ruiz-Páez; J.A. López-Bueno; A. Padrón-Monedero; M.A. Navas; P. Salvador; C. Linares; J. Díaz (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Upwelling-induced inflow pulses in a tropical bay during mid-summer drought - Alexandre Tisseaux-Navarro; Braulio Juárez; J. Mauro Vargas-Hernández; Sergio Cambronero-Solano; Mario Espinoza; Amaia Ruiz de Alegría-Arzaburu; Juan Pablo Salazar-Ceciliano (Regional Studies in Marine Science, 2024)

Ecotoxicity assessment of sustainable magnesium phosphate cements (Sust-MPCs) using luminescent bacteria and sea urchin embryo-larval development tests - V. Muñoz-Ruiz; E. Cifrian; A. Alfocea-Roig; J. Santos; J. Formosa; J.M. Chimenos; A. Andres (Journal of Environmental Chemical Engineering, 2024)

Long-term annual estimation of forest above ground biomass, canopy cover, and height from airborne and spaceborne sensors synergies in the Iberian Peninsula - M.A. Tanase; M.C. Mihai; S. Miguel; A. Cantero; J. Tijerin; P. Ruiz-Benito; D. Domingo; A. Garcia-Martin; C. Aponte; M.T. Lamelas (Environmental Research, 2024)

Evaluating the utility of combining high resolution thermal, multispectral and 3D imagery from unmanned aerial vehicles to monitor water stress in vineyards - V. Burchard-Levine; J. G. Guerra; I. Borra-Serrano; H. Nieto; G. Mesías-Ruiz; J. Dorado; A. I. de Castro; M. Herrezuelo; B. Mary; E. P. Aguirre; J. M. Peña (Precision Agriculture, 2024)
Purpose High resolution imagery from unmanned aerial vehicles (UAVs) has been established as an important source of information to perform precise irrigation practices, notably relevant for high value crops often present in semi-arid regions such as vineyards. Many studies have shown the utility of thermal infrared (TIR) sensors to estimate canopy temperature to inform on vine physiological status, while visible-near infrared (VNIR) imagery and 3D point clouds derived from red–green–blue (RGB) photogrammetry have also shown great promise to better monitor within-field canopy traits to support agronomic practices. Indeed, grapevines react to water stress through a series of physiological and growth responses, which may occur at different spatio-temporal scales. As such, this study aimed to evaluate the application of TIR, VNIR and RGB sensors onboard UAVs to track vine water stress over various phenological periods in an experimental vineyard imposed with three different irrigation regimes. Methods A total of twelve UAV overpasses were performed in 2022 and 2023 where in situ physiological proxies, such as stomatal conductance (g s ), leaf (Ψ leaf ) and stem (Ψ stem ) water potential, and canopy traits, such as LAI, were collected during each UAV overpass. Linear and non-linear models were trained and evaluated against in-situ measurements. Results Results revealed the importance of TIR variables to estimate physiological proxies (g s , Ψ leaf , Ψ stem ) while VNIR and 3D variables were critical to estimate LAI. Both VNIR and 3D variables were largely uncorrelated to water stress proxies and demonstrated less importance in the trained empirical models. However, models using all three variable types (TIR, VNIR, 3D) were consistently the most effective to track water stress, highlighting the advantage of combining vine characteristics related to physiology, structure and growth to monitor vegetation water status throughout the vine growth period. Conclusion This study highlights the utility of combining such UAV-based variables to establish empirical models that correlated well with field-level water stress proxies, demonstrating large potential to support agronomic practices or even to be ingested in physically-based models to estimate vine water demand and transpiration.

Social acceptance of renewable energies: a meta-analytic review of 40 years of related literature - D. Rojas-Peña; C. Quintana-Rojo; M. A. Tarancón; M. J. Ruiz-Fuensanta (Environment, Development and Sustainability, 2024)

P25-21 Examining the impact of a realistic mixture of dietary contaminants on the intestinal barrier and compounds absorption - A. Araújo; H. Ramos; M. Ribeiro; Z. Martins; J. Marín-Sáez; R. Lopez-Ruiz; M. Faria; I. Ferreira (Toxicology Letters, 2024)

P02-07 Using microfluidic hepatic spheroid cultures for assessing effects of T2 mycotoxin - M. Taroncher; J.-M. de Hoyos-Vega; A.-M. Gonzalez-Suarez; Y. Rodriguez-Carrasco; M.-J. Ruiz; A. Revzin (Toxicology Letters, 2024)

Epidemics of Begomoviruses Transmitted by Bemisia tabaci in Habanero Peppers and the Efficacy of Botanical Insecticides - Ana L. Ruiz-Jiménez; Yomara J. Chan-May; Esaú Ruiz-Sánchez; Oscar A. Moreno-Valenzuela; Yereni Minero-García; Blancka Y. Samaniego-Gámez; Luis Latournerie-Moreno; Jacques Fils Pierre (Agricultural Research, 2024)

Sigma-1 Receptors Control Neuropathic Pain and Peripheral Neuroinflammation After Nerve Injury in Female Mice: A Transcriptomic Study - M. Carmen Ruiz-Cantero; José M. Entrena; Antonia Artacho-Cordón; Miguel Á. Huerta; Enrique Portillo-Salido; Francisco R. Nieto; José M. Baeyens; Michael Costigan; Rafael González-Cano; Enrique J. Cobos (Journal of Neuroimmune Pharmacology, 2024)

Weed species classification with UAV imagery and standard CNN models: Assessing the frontiers of training and inference phases - G.A. Mesías-Ruiz; I. Borra-Serrano; J.M. Peña; A.I. de Castro; C. Fernández-Quintanilla; J. Dorado (Crop Protection, 2024)

Boosting nutrient recovery from AnMBR effluent by means of electrodialysis technology: Operating parameters assessing - P. Ruiz-Barriga; J. Serralta; A. Bouzas; J. Carrillo-Abad (Journal of Environmental Management, 2024)

Process-controlled gas hydrate formation in coffee solutions for the application of cold concentration - R.M. Sutter; V. Meunier; S. Ruiz; J. Doebelin; C. Milo; C. Rauh; C. Hartmann (Innovative Food Science & Emerging Technologies, 2024)

Nitrogen fertilizer and plant density affect maize residue quantity and quality more than previous crop and genotype - Alejo Ruiz; Jode W. Edwards; Michael J. Castellano; Brenda L. Gambin; Mark A. Licht; Kenneth J. Moore; Sotirios V. Archontoulis (European Journal of Agronomy, 2024)

Designing a safer circular economy of chemicals - Gerardo J. Ruiz-Mercado (Clean Technologies and Environmental Policy, 2024)

Biogeographic variation in environmental and biotic resistance modifies predicted risk of marine invasions by ships - Mariana Bonfim; Samuel L. Bunson; Andrew J. Sellers; Mark E. Torchin; Gregory M. Ruiz; Amy L. Freestone (Frontiers in Marine Science, 2024)
Introduction Global shipping has accelerated the spread of non-native species. Factors such as environmental filtering and interactions with local biota can affect invasion likelihood, yet their relative contribution to predicting invasion risk remains unresolved. To test how abiotic filters and an experimentally-derived measure of biotic resistance interact with propagule pressure, we developed an integrated model to evaluate their relative effects on invasion risk of marine biofouling organisms to different focal port regions. We predicted that environmental filtering impacts invasion risk when fewer but stronger connections are part of the network. Further, predation is a mechanism of biotic resistance, which can reduce invasion risk, with most pronounced effects predicted in the tropics that decline at higher latitudes. Methods We examined shipping traffic and predation impact at three coastal bioregions spanning 47-degrees of latitude al range in the Northeast Pacific (Alaska, California, and Panama). We used vessel traffic databases to characterize propagule pressure and construct a worldwide port network of marine shipping routes and ports. Environmental resistance was estimated using temperature and salinity data from donor and recipient regions. We further used standardized predator exposure experiments to quantify predation impact on fouling community biomass as an estimate of potential for biotic resistance. We then expanded on existing models of relative invasion risk to incorporate the probability that propagules will survive predation by local predators and overcome environmental filtering to generate a predicted invasion risk for each port. Results Environmental filtering in all regions and predation pressure in the tropics worked to reduce the invasion risk, resulting in markedly different cumulative risk profiles over time among regions. Discussion In an increasingly connected world with more vessel traffic, our results highlight that while the number and distribution of shipping routes are important to understand risk, abiotic and biotic filters can modify model predictions.

Corrigendum to: The influence of environmental particulate matter exposure during late gestation and early life on the risk of neurodevelopmental disorders: A systematic review of experimental evidences [Environ Res. 2023 Nov 1;236(Pt 1):116792] - R. Rodulfo-Cárdenas; D. Ruiz-Sobremazas; J. Biosca-Brull; M. Cabré; J. Blanco; C. López-Granero; F. Sánchez-Santed; M.T. Colomina (Environmental Research, 2024)

Empowering intermediate cities: cost-effective heritage preservation through satellite remote sensing and deep learning - I. Rodríguez-Antuñano; Joaquim J. Sousa; M. Bakoň; A. M. Ruiz-Armenteros; J. Martínez-Sánchez; B. Riveiro (International Journal of Remote Sensing, 2024)

Environmental evaluation of the Reloncaví estuary in southern Chile based on lipophilic shellfish toxins as related to harmful algal blooms - Gonzalo Fuenzalida; Kyoko Yarimizu; Luis Norambuena; So Fujiyoshi; Ishara Uhanie Perera; Joaquin-Ignacio Rilling; Marco Campos; Tay Ruiz-Gil; Jonnathan Vilugrón; Alondra Sandoval-Sanhueza; Mario Ortiz; Oscar Espinoza-González; et al. (Science of The Total Environment, 2024)

Upper Cretaceous Crustacea from Central Cuba - Francisco J. Vega; Torrey Nyborg; Alessandro Garassino; Giovanni Pasini; Javier Aguilar-Pérez; Carlos R. Borges-Sellén; Alberto F. Arano-Ruiz; Servilio J. Quintero-Vázquez; Roberto Manuel Gutiérrez-Domech (Journal of South American Earth Sciences, 2024)

Structure and morphology of chars and activated carbons obtained from thermal treatment of coal and biomass origin materials, including their wastes: Results from the ICCP Microscopy of Carbon Materials Working Group - G. Predeanu; M. Wojtaszek-Kalaitzidi; I. Suárez Ruiz; M.N Bălănescu; A. Gómez Borrego; M.D. Ghiran; P.C. Hackley; S. Kalaitzidis; J. Kus; M. Mastalerz; M. Misz-Kennan; S. Pusz; et al. (International Journal of Coal Geology, 2024)

Sustainable cultivation of melon landraces: Effects of grafting on the accumulation of flavor-related compounds - A. Flores-León; R. Martí; M. Valcarcel; S. Roselló; J. Beltrán; S. García-Martínez; J.J. Ruiz; C. Gisbert; J. Cebolla-Cornejo; B. Picó (Food Chemistry, 2024)

Improvements in fermentation and nutritive quality of elephant grass [Cenchrus purpureus (Schumach.) Morrone] silages: a review - N. A. Sánchez-Guerra; M. Gonzalez-Ronquillo; R. C. Anderson; M. E. Hume; M. Ruiz-Albarrán; Y. Bautista-Martínez; A. Zúñiga-Serrano; O. G. Nájera-Pedraza; J. Salinas-Chavira (Tropical Animal Health and Production, 2024)

An impact evaluation of conservation investments targeting long‐distance migratory species - C. Josh Donlan; Diana Eusse‐González; Gloria M. Luque; Matthew E. Reiter; Viviana Ruiz‐Gutierrez; Michael C. Allen; Richard Johnston‐González; Orin J. Robinson; Guillermo Fernández; Eduardo Palacios; Jorge Valenzuela (Conservation Biology, 2024)
We evaluated the impact of a philanthropic program investing in the conservation of sites along the Pacific Americas Flyway, which spans >16,000 km of coastline and is used by millions of shorebirds. Using a quasi‐experimental, mixed methods approach, we estimated what would have happened to shorebird populations at 17 wintering sites without the sustained and additional investment they received. We modeled shorebird populations across the entire flyway and at sites with and without investment. Combining shorebird abundance estimates with a land‐cover classification model, we used the synthetic control method to create counterfactuals for shorebird trends at the treatment sites. We found no evidence of an overall effect across three outcome variables. Species‐ and site‐level treatment effects were heterogeneous, with a few cases showing evidence of a positive effect, including a site with a high level of overall investment. Results suggest six shorebirds declined across the entire flyway, including at many Latin American sites. However, the percentage of flyway populations present at the sites remained stable, and the percentage at the treatment sites was higher (i.e., investment sites) than at control sites. Multiple mechanisms behind our results are possible, including that investments have yet to mitigate impacts and negative impacts at other sites are driving declines at the treatment sites. A limitation of our evaluation is the sole focus on shorebird abundance and the lack of data that prohibits the inclusion of other outcome variables. Monitoring infrastructure is now in place to design a more robust and a priori shorebird evaluation framework across the entire flyway. With this framework, it will prove easier to prioritize limited dollars to result in the most positive conservation outcomes.

Dietary calcifediol reduces mesenteric adiposity to the benefit of carcass growth independently of circulating vitamin D hormone in juvenile Atlantic salmon - S. Rider; E. Yamashita; E. Chenal; P. Cabo-Valcarce; F. Kuschel; P. Orellana; J. Ruiz; A. Hernández; P. Dantagnan (Aquaculture, 2024)

Trade-offs between sociality and gastrointestinal parasite infection in the context of a natural disaster - Melissa A. Pavez-Fox; Carla M. Escabi-Ruiz; Jordan D.A. Hart; Josue E. Negron-Del Valle; Daniel Phillips; Angelina Ruiz-Lambides; Samuel E. Bauman; Melween I. Martinez; Michael J. Montague; Michael L. Platt; James P. Higham; Noah Snyder-Mackler; et al. (Animal Behaviour, 2024)

Expected effects of climate change on the soil organic matter content related to contrasting agricultural management practices based on a crop model ensemble for locations in Czechia - E. Pohanková; P. Hlavinka; K.C. Kersebaum; C. Nendel; A. Rodríguez; J. Balek; M. Dubrovský; A. Gobin; G. Hoogenboom; M. Moriondo; E.J. Olesen; R. Rötter; et al. (European Journal of Agronomy, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Enso influence on water vapor transport and thermodynamics over Northwestern South America - Melissa Ruiz-Vásquez; Paola A. Arias; J. Alejandro Martínez (Theoretical and Applied Climatology, 2024)
The interannual variability of hydroclimatic conditions in Northwestern South America, especially precipitation, is mainly influenced by the El Niño–Southern Oscillation (ENSO). We explore potential mechanisms that affect precipitation occurrence in Northwestern South America during El Niño and La Niña events over the period 1980–2019, using data from the ERA5 reanalysis. We look at the atmospheric moisture contribution from different sources using the Dynamic Recycling Model to track water vapor trajectories. Interestingly, conditions with reduced precipitation during El Niño events can take place along with increased precipitable water. To understand this, we analyze thermodynamic conditions in the atmosphere that are necessary for precipitation to occur over the region, such as convective available potential energy, convective inhibition, lifting condensation level, and low-level relative humidity. With this approach, we find more favorable thermodynamic conditions for the occurrence of precipitation during La Niña events, even if the content of water vapor is equal or even less than during El Niño events. We also look at the structure of the regional Hadley and Walker circulation in both types of events and find that a weaker ascending motion during El Niño events also inhibits convection. This study provides an integral picture of how precipitation anomalies over Northwestern South America during ENSO events are related to dynamic and thermodynamic conditions and sources of atmospheric moisture.

Multivariate analysis of pharmaceutical pollutants adsorption in aqueous media with tailored waste-based carbonaceous adsorbent materials and commercial activated carbons - J. Lladó; F. López; J.M. Rossell; C. Lao-Luque; R.R. Gil; E. Fuente; B. Ruiz (Sustainable Chemistry and Pharmacy, 2024)

Porcine circovirus 3 (PCV-3) experimental inoculation in pregnant gilts - A. Cobos; M. Sibila; E. Huerta; A. Llorens; A. Ruiz; M. Pérez; A. Barceló; R. Lohse; M. Balasch; J. Segalés (Journal of Comparative Pathology, 2024)

Assessment of nitrification process in a sequencing batch reactor: Modelling and genomic approach - M.C. Gutiérrez; A. Cáceres; A.M. Herruzo-Ruiz; J.A. Siles; F. Vázquez; J. Alhama; C. Michán; M.A. Martín (Environmental Research, 2024)

Diadenosine pentaphosphate regulates dendrite growth and number in cultured hippocampal neurons - M. Diez-Zaera; A. Ruiz-Calvo; J. I. Diaz-Hernandez; A. Sebastián-Serrano; P. Aivar; B. Alvarez-Castelao; J. Pintor; M. Diaz-Hernandez; M. T. Miras-Portugal (Purinergic Signalling, 2024)
During the establishment of neuronal circuits, axons and dendrites grow and branch to establish specific synaptic connections. This complex process is highly regulated by positive and negative extracellular cues guiding the axons and dendrites. Our group was pioneer in describing that one of these signals are the extracellular purines. We found that extracellular ATP, through its selective ionotropic P2X7 receptor (P2X7R), negatively regulates axonal growth and branching. Here, we evaluate if other purinergic compounds, such as the diadenosine pentaphosphate (Ap 5 A), may module the dynamics of dendritic or axonal growth and branching in cultured hippocampal neurons. Our results show that Ap 5 A negatively modulates the dendrite’s growth and number by inducing transient intracellular calcium increases in the dendrites’ growth cone. Interestingly, phenol red, commonly used as a pH indicator in culture media, also blocks the P2X1 receptors, avoided the negative modulation of Ap 5 A on dendrites. Subsequent pharmacological studies using a battery of selective P2X1R antagonists confirmed the involvement of this subunit. In agreement with pharmacological studies, P2X1R overexpression caused a similar reduction in dendritic length and number as that induced by Ap 5 A. This effect was reverted when neurons were co-transfected with the vector expressing the interference RNA for P2X1R. Despite small hairpin RNAs reverting the reduction in the number of dendrites caused by Ap 5 A, it did not avoid the dendritic length decrease induced by the polyphosphate, suggesting, therefore, the involvement of a heteromeric P2X receptor. Our results are indicating that Ap 5 A exerts a negative influence on dendritic growth.

Exploring alternative crop rotations to continuous winter wheat for agricultural intensification in the US central Great Plains - Ignacio Massigoge; Rudra Baral; Sofía Cominelli; Ethan Denson; Paula García Helguera; Cesar Guareschi; Luana M. Simão; Joaquín Peraza Rud; Carlos B. Pires; J. Anita Dille; Romulo P. Lollato; Doohong Min; et al. (Agricultural Systems, 2024)

High response diversity and conspecific density‐dependence, not species interactions, drive dynamics of coral reef fish communities - Alfonso Ruiz‐Moreno; Michael J. Emslie; Sean R. Connolly (Ecology Letters, 2024)
Species‐to‐species and species‐to‐environment interactions are key drivers of community dynamics. Disentangling these drivers in species‐rich assemblages is challenging due to the high number of potentially interacting species (the ‘curse of dimensionality’). We develop a process‐based model that quantifies how intraspecific and interspecific interactions, and species’ covarying responses to environmental fluctuations, jointly drive community dynamics. We fit the model to reef fish abundance time series from 41 reefs of Australia's Great Barrier Reef. We found that fluctuating relative abundances are driven by species’ heterogenous responses to environmental fluctuations, whereas interspecific interactions are negligible. Species differences in long‐term average abundances are driven by interspecific variation in the magnitudes of both conspecific density‐dependence and density‐independent growth rates. This study introduces a novel approach to overcoming the curse of dimensionality, which reveals highly individualistic dynamics in coral reef fish communities that imply a high level of niche structure.

Comparative MRI analysis of the forebrain of three sauropsida models - S Jiménez; I Santos-Álvarez; E Fernández-Valle; D Castejón; P Villa-Valverde; C Rojo-Salvador; P Pérez-Llorens; M. J. Ruiz-Fernández; S. Ariza-Pastrana; R. Martín-Orti; Juncal González-Soriano; Nerea Moreno (Brain Structure and Function, 2024)
The study of the brain by magnetic resonance imaging (MRI) allows to obtain detailed anatomical images, useful to describe specific encephalic structures and to analyze possible variabilities. It is widely used in clinical practice and is becoming increasingly used in veterinary medicine, even in exotic animals; however, despite its potential, its use in comparative neuroanatomy studies is still incipient. It is a technology that in recent years has significantly improved anatomical resolution, together with the fact that it is non-invasive and allows for systematic comparative analysis. All this makes it particularly interesting and useful in evolutionary neuroscience studies, since it allows for the analysis and comparison of brains of rare or otherwise inaccessible species. In the present study, we have analyzed the prosencephalon of three representative sauropsid species, the turtle Trachemys scripta (order Testudine), the lizard Pogona vitticeps (order Squamata) and the snake Python regius (order Squamata) by MRI. In addition, we used MRI sections to analyze the total brain volume and ventricular system of these species, employing volumetric and chemometric analyses together. The raw MRI data of the sauropsida models analyzed in the present study are available for viewing and downloading and have allowed us to produce an atlas of the forebrain of each of the species analyzed, with the main brain regions. In addition, our volumetric data showed that the three groups presented clear differences in terms of total and ventricular brain volumes, particularly the turtles, which in all cases presented distinctive characteristics compared to the lizards and snakes.

Evaluation of maritime spatial planning for offshore wind energy in the Canary Islands: A comparative analysis - M. Martín-Betancor; J. Osorio; A. Ruiz-García; I. Nuez (Marine Policy, 2024)

Effects of 700 and 3500 MHz 5G radiofrequency exposure on developing zebrafish embryos - Monica Torres-Ruiz; Oscar J. Suárez; Victoria López; Pablo Marina; Aránzazu Sanchis; Isabel Liste; Mercedes de Alba; Victoria Ramos (Science of The Total Environment, 2024)

Overprinting orogenic events, ductile extrusion and strain partitioning during Caledonian transpression, NW Mainland Shetland - Timothy B. Armitage; Robert E. Holdsworth; Robin A. Strachan; Edward D. Dempsey; Richard J. Walker; Diana T. Alvarez-Ruiz; Geoffrey E. Lloyd (Journal of Structural Geology, 2024)

Observation of the Southern Polar cap during MY34-36 with ExoMars-TGO NOMAD LNO - L. Ruiz Lozano; F. Oliva; Ö. Karatekin; G. Bellucci; V. Dehant; E. D'Aversa; F.G. Carrozzo; F. Schmidt; G. Cruz Mermy; I.R. Thomas; A.C. Vandaele; F. Daerden; et al. (Icarus, 2024)

Impact of Chondrites on trace metal distribution in the sapropel S7 (ODP Site 966): Implications for paleoenvironmental and paleoceanographic reconstructions - Ricardo D. Monedero-Contreras; Francisco J. Rodríguez-Tovar; Francisca Martínez-Ruiz (Global and Planetary Change, 2024)

Mapping the cellular landscape of Atlantic salmon head kidney by single cell and single nucleus transcriptomics - Adriana M.S. Andresen; Richard S. Taylor; Unni Grimholt; Rose Ruiz Daniels; Jianxuan Sun; Ross Dobie; Neil C. Henderson; Samuel A.M. Martin; Daniel J. Macqueen; Johanna H. Fosse (Fish & Shellfish Immunology, 2024)

Source tracing of Anthonomus grandis captured in areas of the USA where the species had previously been eradicated - Tyler J. Raszick; Lindsey C. Perkin; Xanthe A. Shirley; Raul Ruiz-Arce; Zoey A. Kramer; Charles P.-C. Suh; Gregory A. Sword (Journal of Pest Science, 2024)
Anthonomus grandis Boheman (Coleoptera: Curculionidae) is comprised of two subspecies: the boll weevil ( A. g. grandis ) and the thurberia weevil ( A. g. thurberiae ). The thurberia weevil is generally regarded as a non-pest variant of the species, whereas the boll weevil is an important economic pest of commercial cotton. In the USA, a nationwide eradication program has been largely successful against the boll weevil, but reintroductions of eradicated zones remain a threat. In 2015, A. grandis was trapped in the functionally eradicated Winter Garden growing region in Texas, where it had not been found since 2012. Weevils established in the area and triggered a multi-year, multi-million-dollar mitigation effort. In 2017, the species was trapped in Hidalgo County, New Mexico, another area where it had been previously eradicated. In this study, we obtained specimens from both trapping events and used double digest restriction site-associated DNA sequencing to obtain genetic data in homology with previously published A. grandis population genetic data. We conducted source tracing to match the captured weevils to previously described populations to determine a likely source population. We also compared the accuracy of the approach to other diagnostic methods currently used by the United States Department of Agriculture. The results suggested that a small founder population of weevils dispersed from the Lower Rio Grande Valley population in southern Texas and northern Tamaulipas and established in the Winter Garden. In Hidalgo Co., NM, the weevils were found to be genetically indistinct from non-pest populations of thurberia weevil associated with Arizona wild cotton ( Gossypium thurberi ). Thurberia weevils in Arizona remain unlikely to threaten commercial growers. Improved rapid diagnostic tools may be desirable to enable better assessment of trap captures and allow for a reduction in the application of mitigation efforts when the non-pest variant is identified.

Influence of the time of day in the effect of caffeine on maximal fat oxidation during exercise in women: a randomized, crossover, double-blind, and placebo-controlled study - Alejandro Muñoz; Millán Aguilar-Navarro; Carlos Ruiz-Moreno; David Varillas-Delgado; Francisco J. Amaro-Gahete; Jorge Gutiérrez-Hellín; Juan Del Coso; Álvaro López-Samanes (European Journal of Applied Physiology, 2024)

Meta-analysis of Behavioural Research in Lizards Reveals that Viviparity Contributes Better to Animal Personality than Secretory Glands - M. R. Ruiz-Monachesi; J. J. Martínez (Evolutionary Biology, 2024)

Air Pollution PM10 Forecasting Maps in the Maritime Area of the Bay of Algeciras (Spain) - María Inmaculada Rodríguez-García; María Gema Carrasco-García; Maria da Conceição Rodrigues Ribeiro; Javier González-Enrique; Juan Jesús Ruiz-Aguilar; Ignacio J. Turias (Journal of Marine Science and Engineering, 2024)
Predicting the levels of a pollutant in a given area is an open problem, mainly because historical data are typically available at certain locations, where monitoring stations are located, but not at all locations in the area. This work presents an approach based on developing predictions at each of the points where an immission station is available; in this case, based on shallow Artificial Neural Networks, ANNs, and then using a simple geostatistical interpolation algorithm (Inverse Distance Weighted, IDW), a pollutant map is constructed over the entire study area, thus providing predictions at each point in the plane. The ANN models are designed to make 1 h ahead and 4 h ahead predictions, using an autoregressive scheme as inputs (in the case of 4 h ahead as a jumping strategy). The results are then compared using the Friedman and Bonferroni tests to select the best model at each location, and predictions are made with all the best models. In general, to the 1 h ahead prediction models, the optimal models typically have fewer neurons and require minimal historical data. For instance, the best model in Algeciras has an R of almost 0.89 and consists of 1 hidden neuron and 3 to 5 lags, similar to Colegio Los Barrios. In the case of 4h ahead prediction, Colegio Carteya station shows the best model, with an R of almost 0.89 and a MSE of less than 240, including 5 hidden neurons and different lags from the past. The results are sufficiently adequate, especially in the case of predictions 4 h into the future. The aim is to integrate the models into a tool for citizens and administrations to make decisions.

Relationships between the specific growth rate and the thermal-unit growth coefficient applied to cultured juvenile fish - Lorenzo Márquez; Eduardo Almansa; Nancy E. Ruiz Díaz; Manuel Díaz; Francisco J. Moyano (Frontiers in Marine Science, 2024)
The growth of cultured juvenile fish is usually quantified by two indexes, the specific growth rate or SGR, and the thermal-unit growth coefficient or TGC. The SGR is a relative growth index based on logarithms of body weights, and it decreases with body weight. The classical TGC is based on one-third powers of body weights and the summation of temperature over time. It can also depend on body weight, but it is possible to release this dependency by empirically adjusting the power function in its mathematical definition. These two indexes are usually presented in the same article to compare the growth attained by different groups of fish subjected to different experimental treatments. However, no formal framework linking both indexes is available for researchers up to the moment, the meanings of SGR and TGC remaining unrelated. The present work shows that the TGC of a group of fish growing at a given temperature can be expressed as a function of the SGR. In addition, the relationship between SGR and TGC here reported provides the basis to re-defined the TGC as a size-independent index with application to fish culture.

A solar evaporator fabricated from corncob waste for the desalination of seawater and removal of oil/herbicides from contaminated water - E. Valadez-Renteria; J. Oliva; A.I. Oliva; M.A. Ruiz-Gomez; A. Encinas; V. Rodriguez-Gonzalez (Chemosphere, 2024)

Heavy metal concentrations in sharks, rays and chimaeras from the western Mediterranean Sea - Pol Carrasco-Puig; Ana I. Colmenero; David Ruiz-García; Alejandro J. Molera-Arribas; Ana M. Hernández-Martínez; Juan A. Raga; Claudio Barría (Marine Pollution Bulletin, 2024)

Effects of Aurantiochytrium acetophilum as a source of docosahexaenoic acid for juvenile Atlantic salmon (Salmo salar) on growth, nutrient apparent digestibility, tissue fatty acid composition and expression of lipid metabolism-related genes - Joceline Ruiz; Adrián J. Hernández; Geneviève Corraze; Paola Orellana; Ricardo Oyarzún-Salazar; Luis Vargas-Chacoff; Patricio Dantagnan (Aquaculture, 2024)

Supplementation of gilthead seabream (Sparus aurata) diets with spices as a functional strategy to control excess adiposity through lipid, cholesterol and bile acid metabolism, and to induce an immunomodulatory intestinal regulation - Alberto Ruiz; Ignasi Sanahuja; Karl B. Andree; Dolors Furones; Paul G. Holhorea; Josep A. Calduch-Giner; Jose J. Pastor; Marc Viñas; Jaume Pérez-Sánchez; Sofia Morais; Enric Gisbert (Aquaculture, 2024)

Effects of sediment transport on flood hazards: Lessons learned and remaining challenges - D. Vázquez-Tarrío; V. Ruiz-Villanueva; J. Garrote; G. Benito; M. Calle; A. Lucía; A. Díez-Herrero (Geomorphology, 2024)

Integrated cyclostratigraphy of the Cau core (SE Spain) - A timescale for climate change during the early Aptian Anoxic Event (OAE 1a) and the late Aptian - Rafael Martínez-Rodríguez; Sietske J. Batenburg; José M. Castro; Ginés A. de Gea; Luis M. Nieto; Pedro A. Ruiz-Ortiz; Stuart Robinson (Global and Planetary Change, 2024)

Cell atlas of the Atlantic salmon spleen reveals immune cell heterogeneity and cell-specific responses to bacterial infection - Jianxuan Sun; Rose Ruiz Daniels; Adam Balic; Adriana M.S. Andresen; Håvard Bjørgen; Ross Dobie; Neil C. Henderson; Erling Olaf Koppang; Samuel A.M. Martin; Johanna Hol Fosse; Richard S. Taylor; Daniel J. Macqueen (Fish & Shellfish Immunology, 2024)

Bioinspired phenol-based coatings for medical fabrics against antimicrobial resistance - Jose Bolaños-Cardet; Daniel Ruiz-Molina; Victor J. Yuste; Salvio Suárez-García (Chemical Engineering Journal, 2024)

Spontaneous Behavioural Recovery Following Stroke Relates to the Integrity of Parietal and Temporal Regions - Joseph Y. Nashed; Kaden T. Shearer; Justin Z. Wang; Yining Chen; Elise E. Cook; Allen A. Champagne; Nicole S. Coverdale; Juan Fernandez-Ruiz; Shirley I. Striver; J. Randal Flanagan; Jason P. Gallivan; Douglas J. Cook (Translational Stroke Research, 2024)

Human plasmacytoid dendritic cells express the functional purinergic halo (CD39/CD73) - S. A. Sosa-Luis; W. J. Ríos-Ríos; A. Almaraz-Arreortua; M. A. Romero-Tlalolini; S. R. Aguilar-Ruiz; R. Valle-Ríos; C. Sánchez-Torres; H. Torres-Aguilar (Purinergic Signalling, 2024)

The enzymatic properties of Arabidopsis thaliana DNA polymerase λ suggest a role in base excision repair - T. Morales-Ruiz; C. Beltrán-Melero; D. Ortega-Paredes; J. A. Luna-Morillo; M. I. Martínez-Macías; T. Roldán-Arjona; R. R. Ariza; D. Córdoba-Cañero (Plant Molecular Biology, 2024)
Base excision repair (BER) generates gapped DNA intermediates containing a 5′-terminal 2-deoxyribose-5-phosphate (5′-dRP) group. In mammalian cells, gap filling and dRP removal are catalyzed by Pol β, which belongs to the X family of DNA polymerases. In higher plants, the only member of the X family of DNA polymerases is Pol λ. Although it is generally believed that plant Pol λ participates in BER, there is limited experimental evidence for this hypothesis. Here we have characterized the biochemical properties of Arabidopsis thaliana Pol λ (AtPol λ) in a BER context, using a variety of DNA repair intermediates. We have found that AtPol λ performs gap filling inserting the correct nucleotide, and that the rate of nucleotide incorporation is higher in substrates containing a C in the template strand. Gap filling catalyzed by AtPol λ is most efficient with a phosphate at the 5′-end of the gap and is not inhibited by the presence of a 5′-dRP mimic. We also show that AtPol λ possesses an intrinsic dRP lyase activity that is reduced by mutations at two lysine residues in its 8-kDa domain, one of which is present in Pol λ exclusively and not in any Pol β homolog. Importantly, we also found that the dRP lyase activity of AtPol λ allows efficient completion of uracil repair in a reconstituted short-patch BER reaction. These results suggest that AtPol λ plays an important role in plant BER.

Marine debris facilitates the long-distance dispersal of fish species - Clara Benadon; Chela J. Zabin; Linsey Haram; James T. Carlton; Nikolai Maximenko; Peter Nelson; Mary Crowley; Gregory M. Ruiz (Marine Biology, 2024)

Predictive models for grape downy mildew (Plasmopara viticola) as a decision support system in Mediterranean conditions - M. Puelles; J. Arbizu-Milagro; F.J. Castillo-Ruiz; J.M. Peña (Crop Protection, 2024)

Effects of climate change on Platanus flowering in Western Mediterranean cities: Current trends and future projections - Antonio Picornell; José M. Maya-Manzano; Marta Fernández-Ramos; Juan J. Hidalgo-Barquero; Raúl Pecero-Casimiro; Rocío Ruiz-Mata; Enrique de Gálvez-Montañez; María del Mar Trigo; Marta Recio; Santiago Fernández-Rodríguez (Science of The Total Environment, 2024)

Redox geochemical signatures in Mediterranean sapropels: Implications to constrain deoxygenation dynamics in deep-marine settings - Ricardo D. Monedero-Contreras; Francisca Martínez-Ruiz; Francisco J. Rodríguez-Tovar; Gert de Lange (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Facilitation of macrofaunal assemblages in marinas by the habitat-forming invader Amathia verticillata (Bryozoa: Gymnolaemata) across a spatiotemporal scale - J.M. Guerra-García; S. Ruiz-Velasco; C. Navarro-Barranco; J. Moreira; G. Angulo; R. García-Domínguez; J. Amengual; P. Saenz-Arias; C.M. López-Fé; I. Martínez-Pita; F.J. García-García; M. Ros (Marine Environmental Research, 2024)

An advanced control system for nitrogen removal and energy consumption optimization in full-scale wastewater treatment plants - M.V. Ruano; J. Ribes; A. Ruiz-Martinez; A. Seco; A. Robles (Journal of Water Process Engineering, 2024)

Exploring domestic cat behavior using the Fe-BARQ - David J. Menor-Campos; Carlos Ruiz-Soriano; James Serpell (Journal of Veterinary Behavior, 2024)

Biocidal and synergistic effect of three types of biologically synthesised silver/silver chloride nanoparticles - Antonio J. Muñoz; Francisco Espínola; Encarnación Ruiz; Manuel Moya; Eulogio Castro (World Journal of Microbiology and Biotechnology, 2024)

Two-trace two-dimensional correlation spectra (2T2D-COS) analysis using FTIR spectra to monitor the immune response by COVID-19 - Sivakumaran Karthikeyan; Gustavo J. Vazquez-Zapien; Adriana Martinez-Cuazitl; Raul J. Delgado-Macuil; Daniel E. Rivera-Alatorre; Francisco Garibay-Gonzalez; Josemaria Delgado-Gonzalez; Daniel Valencia-Trujillo; Melissa Guerrero-Ruiz; Consuelo Atriano-Colorado; Alberto Lopez-Reyes; Dante J. Lopez-Mezquita; et al. (Journal of Molecular Medicine, 2024)

Numerical modeling of the influence of reservoir management on the algal blooms of San Roque - J. Muchiut; M. I. Rodríguez; A. L. Ruibal Conti; M. Ruiz; A. Rodríguez (International Journal of Environmental Science and Technology, 2024)

Relationships between rhizosphere microbiota and forest health conditions in Pinus pinaster stands at the Iberian Peninsula - Carmen Morales-Rodríguez; Jorge Martín-García; Francisco J. Ruiz-Gómez; Jorge Poveda; Julio J. Diez (Applied Soil Ecology, 2024)

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

Precipitation homogenization and trends in the Usumacinta River Basin ( Mexico‐Guatemala ) over the period 1959–2018 - Johanna L. J. Jupin; Alan A. Garcia‐López; Francisco J. Briceño‐Zuluaga; Abdelfettah Sifeddine; Ana Carolina Ruiz‐Fernández; Joan‐Albert Sanchez‐Cabeza; José Gilberto Cardoso‐Mohedano (International Journal of Climatology, 2024)
The precipitation variability and trends were investigated in the Usumacinta River Basin (URB) for the period 1959–2018, based on imputed and homogenized data records from 60 meteorological stations in Mexico and Guatemala. The homogenization process played a crucial role in enhancing the quality of the original precipitation series, reducing regional inconsistencies and improving temporal and spatial coherence. The dataset reliably captured large‐scale climate variations, revealing three regions with similar precipitation variability and trends in the URB. Notably, maximum precipitation occurred at 636 m a.s.l., while minimum precipitation was at 1531 m a.s.l., indicating an orographic effect in the region. Extreme precipitation events were linked to El Niño–Southern Oscillation. Although the Mann–Kendall test showed statistically significant negative trends in only 18% of the stations, integration of Sen's slope analysis and 30‐year normals and dry year occurrences highlighted a progressive shift towards dryer conditions throughout the study period in the URB. These drier conditions could notably affect regions with higher precipitation, requiring special attention due to possible socioeconomic impacts associated with drought events. By identifying these vulnerable regions, policymakers and stakeholders can proactively plan and execute adaptive measures to mitigate the potential impacts of droughts on communities, ecosystems, and economic activities within the basin.

Does non‐native diversity mirror Earth's biodiversity? - Elizabeta Briski; Syrmalenia G. Kotronaki; Ross N. Cuthbert; Alejandro Bortolus; Marnie L. Campbell; Jaimie T. A. Dick; Paul Fofonoff; Bella S. Galil; Chad L. Hewitt; Julie L. Lockwood; Hugh J. MacIsaac; Anthony Ricciardi; et al. (Global Ecology and Biogeography, 2024)
Aim Human activities have introduced numerous non‐native species (NNS) worldwide. Understanding and predicting large‐scale NNS establishment patterns remain fundamental scientific challenges. Here, we evaluate if NNS composition represents a proportional subset of the total species pool available to invade (i.e. total global biodiversity), or, conversely, certain taxa are disproportionately pre‐disposed to establish in non‐native areas. Location Global. Time period Present day. Major taxa studied Global diversity. Methods We compiled one of the most comprehensive global databases of NNS (36,822 established species) to determine if NNS diversity is a representative proportional subset of global biodiversity. Results Our study revealed that, while NNS diversity mirrors global biodiversity to a certain extent, due to significant deviance from the null model it is not always a representative proportional subset of global biodiversity. The strength of global biodiversity as a predictor depended on the taxonomic scale, with successive lower taxonomic levels less predictive than the one above it. Consequently, on average, 58%, 42% and 28% of variability in NNS numbers were explained by global biodiversity for phylum, class and family respectively. Moreover, global biodiversity was a similarly strong explanatory variable for NNS diversity among regions, but not habitats (i.e. terrestrial, freshwater and marine), where it better predicted NNS diversity for terrestrial than for freshwater and marine habitats. Freshwater and marine habitats were also greatly understudied relative to invasions in the terrestrial habitats. Over‐represented NNS relative to global biodiversity tended to be those intentionally introduced and/or ‘hitchhikers’ associated with deliberate introductions. Finally, randomness is likely an important factor in the establishment success of NNS. Main conclusions Besides global biodiversity, other important explanatory variables for large‐scale patterns of NNS diversity likely include propagule and colonization pressures, environmental similarity between native and non‐native regions, biased selection of intentionally introduced species and disparate research efforts of habitats and taxa.

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

Lactic acid bacteria viability in different refrigerated food matrices: a systematic review and Meta‑analysis - Lorena P. Soto; Noelí E. Sirini; Laureano S. Frizzo; María V. Zbrun; Jorge A. Zimmermann; María J. Ruiz; Marcelo R. Rosmini; Gabriel J. Sequeira; Camila Miotti; Marcelo L. Signorini (Critical Reviews in Food Science and Nutrition, 2023)

Wine yeast selection in the Iberian Peninsula: Saccharomyces and non- Saccharomyces as drivers of innovation in Spanish and Portuguese wine industries - A. Morata; T. Arroyo; M. A. Bañuelos; P. Blanco; A. Briones; J. M. Cantoral; D. Castrillo; G. Cordero-Bueso; J. M. del Fresno; C. Escott; R. Escribano-Viana; M. Fernández-González; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Molluscan assemblages in shelf and slope sedimentary habitats of the Northern Alboran Sea and their linkage to environmental variables - Elena Moya-Urbano; Javier Urra; Serge Gofas; Marina Gallardo-Núñez; Ángel Mateo-Ramírez; Carlos Farias; Xisco Ordinas; J. Antonio Caballero-Herrera; Patricia Bárcenas; Cristina García-Ruiz; José Luis Rueda (Regional Studies in Marine Science, 2023)

Tailoring CaCO3 microstructure to improve trace phosphate removal from water - Anai Acevedo-Macias; J. Rene Rangel-Mendez; Luis F. Chazaro-Ruiz; Miguel Ávalos-Borja; Ma. Catalina Alfaro-De la Torre; Cesar Nieto-Delgado (Journal of Water Process Engineering, 2023)

Lithospheric contraction concentric to Tharsis: 3D structural modeling of large thrust faults between Thaumasia highlands and Aonia Terra, Mars - A. Herrero-Gil; I. Egea‐González; A. Jiménez‐Díaz; S. Rivas Dorado; L.M. Parro; C. Fernández; J. Ruiz; I. Romeo (Journal of Structural Geology, 2023)

Photoreforming of glycerol to produce hydrogen from natural water in a compound parabolic collector solar photoreactor - J.G. Villachica-Llamosas; Jakub Sowik; A. Ruiz-Aguirre; G. Colón; J. Peral; S. Malato (Journal of Environmental Chemical Engineering, 2023)

Incorporation of bioactive compounds from avocado by-products to ethyl cellulose-reinforced paper for food packaging applications - Maria A. Acquavia; José J. Benítez; Giuliana Bianco; Maria A. Crescenzi; Jesús Hierrezuelo; Montserrat Grifé-Ruiz; Diego Romero; Susana Guzmán-Puyol; José A. Heredia-Guerrero (Food Chemistry, 2023)

Ecology, evolution and conservation of tidepool fishes of the Americas - Ryan Andrades; Saúl González-Murcia; Thaddaeus J. Buser; Raphael M. Macieira; Juliana M. Andrade; Hudson T. Pinheiro; Ciro C. Vilar; Caio R. Pimentel; João L. Gasparini; Thaís L. Quintão; Fabíola S. Machado; Gustavo Castellanos-Galindo; et al. (Reviews in Fish Biology and Fisheries, 2023)

Predictors for Prolonged Hospital Stay Solely to Complete Intravenous Antifungal Treatment in Patients with Candidemia: Results from the ECMM Candida III Multinational European Observational Cohort Study - Matthias Egger; Jon Salmanton-García; Aleksandra Barac; Jean-Pierre Gangneux; Hélène Guegan; Valentina Arsic-Arsenijevic; Tadeja Matos; Rok Tomazin; Nikolai Klimko; Matteo Bassetti; Helena Hammarström; Eelco F. J. Meijer; et al. (Mycopathologia, 2023)
Background To date, azoles represent the only viable option for oral treatment of invasive Candida infections, while rates of azole resistance among non-albicans Candida spp. continue to increase. The objective of this sub-analysis of the European multicenter observational cohort study Candida III was to describe demographical and clinical characteristics of the cohort requiring prolonged hospitalization solely to complete intravenous (iv) antifungal treatment (AF Tx). Methods Each participating hospital (number of eligible hospitals per country determined by population size) included the first ~ 10 blood culture proven adult candidemia cases occurring consecutively after July 1st, 2018, and treating physicians answered the question on whether hospital stay was prolonged only for completion of intravenous antifungal therapy. Descriptive analyses as well as binary logistic regression was used to assess for predictors of prolonged hospitalization solely to complete iv AF Tx. Findings Hospital stay was prolonged solely for the completion of iv AF Tx in 16% (100/621) of candidemia cases by a median of 16 days (IQR 8 – 28). In the multivariable model, initial echinocandin treatment was a positive predictor for prolonged hospitalization to complete iv AF Tx (aOR 2.87, 95% CI 1.55 – 5.32, p < 0.001), while (i) neutropenia, (ii) intensive care unit admission, (iii) catheter related candidemia, (iv) total parenteral nutrition, and (v) C. parapsilosis as causative pathogen were found to be negative predictors (aOR 0.22 – 0.45; p < 0.03). Interpretation Hospital stays were prolonged due to need of iv AF Tx in 16% of patients with candidemia. Those patients were more likely to receive echinocandins as initial treatment and were less severely ill and less likely infected with C. parapsilosis .

Environmental economy and greenhouse gas generation in a sanitary landfill in Mexico - M. E. Tavera-Cortés; X. Mena-Espino; G. Rosano-Ortega; F. J. Sánchez-Ruiz (International Journal of Environmental Science and Technology, 2023)

Associations between sociodemographic factors and breast, cervical, and colorectal cancer screening in the United States - Lía I. Mondragón Márquez; Daniela L. Domínguez Bueso; Liza M. González Ruiz; Jason J. Liu (Cancer Causes & Control, 2023)

Utilization of Renewable Feedstocks for the Production of Sophorolipids by Native Yeasts from Brazilian Cerrado Biome - T. M. Rocha; P. R. F. Marcelino; S. S. Muñoz; E. D. Díaz Ruiz; T. R. Balbino; E. J. C. Moraes; R. P. Murbach; J. C. Santos; S. S. da Silva (BioEnergy Research, 2023)

Airborne bacterial communities associated with particulate matter in Temuco (Chile), one of the most air-polluted cities in South America - Tay Ruiz-Gil; Joaquín I. Rilling; Marco Campos; Elizabeth Carrazana; So Fujiyoshi; Fumito Maruyama; Daisuke Tanaka; Akihiro Sakatoku; Jun Noda; Jacquelinne J. Acuña; Milko A. Jorquera (Aerobiologia, 2023)

Understanding socioecological interaction networks in Marine Protected Areas to inform management - Silvia de Juan; Andres Ospina-Alvarez; Antonio J. Castro; Emilio Fernández; Gonzalo Méndez-Martínez; Jone Molina; Pablo Pita; Ana Ruiz-Frau; Gabriela de Abreu; Sebastian Villasante (Ocean & Coastal Management, 2023)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Mammalian diversity and age of the Salicas Formation (Late Miocene–Early Pleistocene), Northwestern Argentina: State of knowledge and new contributions - Damián Ruiz-Ramoni; Cristo O. Romano; Sergio D. Tarquini; Analía M. Forasiepi; Juan L. García Massini; David L. Barbeau; Laura E. Cruz; Daniel Barasoain; Esperanza Cerdeño; M. Carolina Madozzo Jaén; Ana M. Combina; Estefanía Asurmendi; et al. (Journal of South American Earth Sciences, 2023)

Ensemble Forecast Sensitivity to Observations Impact (EFSOI) applied to a regional data assimilation system over south-eastern South America - Gimena Casaretto; Maria Eugenia Dillon; Yanina García Skabar; Juan J. Ruiz; Maximiliano Sacco (Atmospheric Research, 2023)

Forecasting air pollutants using classification models: a case study in the Bay of Algeciras (Spain) - M. I. Rodríguez-García; M. C. Ribeiro Rodrigues; J. González-Enrique; J. J. Ruiz-Aguilar; I. J. Turias (Stochastic Environmental Research and Risk Assessment, 2023)
The main goal of this work is to obtain reliable predictions of pollutant concentrations related to maritime traffic (SO 2 , PM 10 , NO 2 , NO X , and NO) in the Bay of Algeciras, located in Andalusia, the south of Spain. Furthermore, the objective is to predict future air quality levels of the principal maritime traffic-related pollutants in the Bay of Algeciras as a function of the rest of the pollutants, the meteorological variables, and vessel data. In this sense, three scenarios were analysed for comparison, namely Alcornocales Park and the cities of La Línea and Algeciras. A database of hourly records of air pollution immissions, meteorological measurements in the Bay of Algeciras region and a database of maritime traffic in the port of Algeciras during the years 2017 to 2019 were used. A resampling procedure using a five-fold cross-validation procedure to assure the generalisation capabilities of the tested models was designed to compute the pollutant predictions with different classification models and also with artificial neural networks using different numbers of hidden layers and units. This procedure enabled appropriate and reliable multiple comparisons among the tested models and facilitated the selection of a set of top-performing prediction models. The models have been compared using several quality classification indexes such as sensitivity, specificity, accuracy, and precision. The distance ( d 1 ) to the perfect classifier (1, 1, 1, 1) was also used as a discriminant feature, which allowed for the selection of the best models. Concerning the number of variables, an analysis was conducted to identify the most relevant ones for each pollutant. This approach aimed to obtain models with fewer inputs, facilitating the design of an optimised monitoring network. These more compact models have proven to be the optimal choice in many cases. The obtained sensitivities in the best models were 0.98 for SO 2 , 0.97 for PM 10 , 0.82 for NO 2 and NO X , and 0.83 for NO. These results demonstrate the potential of the models to forecast air pollution in a port city or a complex scenario and to be used by citizens and authorities to prevent exposure to pollutants and to make decisions concerning air quality.

Antifibrogenic and apoptotic effects of Ocoxin in cultured rat hepatic stellate cells - Marina Ruiz de Galarreta; Elena Arriazu; María P. Pérez de Obanos; Eduardo Ansorena; María J. Iraburu (Journal of Physiology and Biochemistry, 2023)
Ocoxin is a nutritional supplement that has been shown to exert antioxidant and immunomodulatory responses in patients with chronic hepatitis C. The present work aimed to determine the effects of Ocoxin on activated hepatic stellate cells (HSC), the cell type mainly responsible for collagen deposition in the fibrotic liver. Ocoxin was found to reduce the survival of a cell line of immortalized non-tumoral rat HSC in a dose–response fashion and to diminish collagen type I levels. This latter effect was observed even at doses not affecting cell survival, pointing to an antifibrogenic action for the supplement. The decrease in viability exerted by Ocoxin on HSC correlated with an increase in histone-associated fragments in the cytoplasm and with increased activity of caspase-3, indicating the induction of apoptosis. To determine the molecular mechanisms mediating Ocoxin-induced apoptosis, the activation of members of the MAPK family was analyzed. Incubation of HSC with Ocoxin caused a transient and dramatic enhancement on ERK, JNK, and p38 MAPK phosphorylation levels. Using specific inhibitors for these enzymes, p38 MAPK was identified as a key mediator of the apoptotic effect of Ocoxin on HSC.

Immune cell composition varies by age, sex and exposure to social adversity in free-ranging Rhesus Macaques - Mitchell R. Sanchez Rosado; Nicole Marzan-Rivera; Marina M. Watowich; Andrea D. Negron-Del Valle; Petraleigh Pantoja; Melissa A. Pavez-Fox; Erin R. Siracusa; Eve B. Cooper; Josue E. Negron-Del Valle; Daniel Phillips; Angelina Ruiz-Lambides; Melween I. Martinez; et al. (GeroScience, 2023)

Assessment of photo electro-Fenton and solar photo electro-Fenton processes for the efficient degradation of asulam herbicide - Héctor H. Vigil-Castillo; Edgar J. Ruiz-Ruiz; Khirbet López-Velázquez; Laura Hinojosa-Reyes; Octavio Gaspar-Ramírez; Jorge L. Guzmán-Mar (Chemosphere, 2023)

Do physical activity and trip characteristics differ when commuting to and from school?: The PACO study - P. Campos-Garzón; T.T. Amholt; D. Molina-Soberanes; X. Palma-Leal; A. Queralt; A.J. Lara-Sánchez; T. Stewart; J. Schipperijn; Y. Barranco-Ruiz; P. Chillón (Travel Behaviour and Society, 2023)

Multi-scale techno-economic assessment of nitrogen recovery systems for livestock operations - Edgar Martín-Hernández; Clara Montero-Rueda; Gerardo J. Ruiz-Mercado; Céline Vaneeckhaute; Mariano Martín (Sustainable Production and Consumption, 2023)

Impact of outdoor air pollution on severity and mortality in COVID-19 pneumonia - O. Bronte; F. García-García; D.-J. Lee; I. Urrutia; A. Uranga; M. Nieves; J. Martínez-Minaya; J.M. Quintana; I. Arostegui; R. Zalacain; L.A. Ruiz-Iturriaga; L. Serrano; et al. (Science of The Total Environment, 2023)

Towards integrative plant pathology - Tatiana Ruiz-Bedoya; Kathryn J. McTavish; Tamar V. Av-Shalom; Darrell Desveaux; David S. Guttman (Current Opinion in Plant Biology, 2023)

Evidence of postdepositional remobilization of redox-sensitive metals across sapropel boundaries: New insights from LA-ICP-MS and EDX mapping analyses - Ricardo D. Monedero-Contreras; Francisca Martínez-Ruiz; Francisco J. Rodríguez-Tovar (Chemical Geology, 2023)

Cloud condensation nuclei activation properties of Mediterranean pollen types considering organic chemical composition and surface tension effects - A. Casans; F. Rejano; J. Maldonado-Valderrama; J.A. Casquero-Vera; S. Ruiz-Peñuela; B.L. van Drooge; H. Lyamani; A. Cazorla; E. Andrews; Jack J. Lin; F. Mirza-Montoro; D. Pérez-Ramírez; et al. (Atmospheric Environment, 2023)

Correction to: Downstream processing of Scenedesmus sp. to obtain biostimulants - E. Navarro-López; A. Ruiz-Nieto; J. J. Gallardo-Rodríguez; M. C. Cerón-García; C. V. González-López; F. G. Acién-Fernández (Journal of Applied Phycology, 2023)

Downstream processing of Scenedesmus sp. to obtain biostimulants - E. Navarro-López; A. Ruiz-Nieto; J. J. Gallardo-Rodríguez; M. C. Cerón-García; C. V. González-López; F. G. Acién-Fernández (Journal of Applied Phycology, 2023)

Mercury in Neotropical birds: a synthesis and prospectus on 13 years of exposure data - Christopher J. Sayers; David C. Evers; Viviana Ruiz-Gutierrez; Evan Adams; Claudia M. Vega; Jessica N. Pisconte; Vania Tejeda; Kevin Regan; Oksana P. Lane; Abidas A. Ash; Reynold Cal; Stevan Reneau; et al. (Ecotoxicology, 2023)
Environmental mercury (Hg) contamination of the global tropics outpaces our understanding of its consequences for biodiversity. Knowledge gaps of pollution exposure could obscure conservation threats in the Neotropics: a region that supports over half of the world’s species, but faces ongoing land-use change and Hg emission via artisanal and small-scale gold mining (ASGM). Due to their global distribution and sensitivity to pollution, birds provide a valuable opportunity as bioindicators to assess how accelerating Hg emissions impact an ecosystem’s ability to support biodiversity, and ultimately, global health. We present the largest database on Neotropical bird Hg concentrations ( n = 2316) and establish exposure baselines for 322 bird species spanning nine countries across Central America, South America, and the West Indies. Patterns of avian Hg exposure in the Neotropics broadly align with those in temperate regions: consistent bioaccumulation across functional groups and high spatiotemporal variation. Bird species occupying higher trophic positions and aquatic habitats exhibited elevated Hg concentrations that have been previously associated with reductions in reproductive success. Notably, bird Hg concentrations were over four times higher at sites impacted by ASGM activities and differed by season for certain trophic niches. We developed this synthesis via a collaborative research network, the Tropical Research for Avian Conservation and Ecotoxicology (TRACE) Initiative, which exemplifies inclusive, equitable, and international data-sharing. While our findings signal an urgent need to assess sampling biases, mechanisms, and consequences of Hg exposure to tropical avian communities, the TRACE Initiative provides a meaningful framework to achieve such goals. Ultimately, our collective efforts support and inform local, scientific, and government entities, including Parties of the United Nations Minamata Convention on Mercury, as we continue working together to understand how Hg pollution impacts biodiversity conservation, ecosystem function, and public health in the tropics.

Prediction of ground-borne vibration induced by impact pile driving: numerical approach and experimental validation - A. Colaço; P. Alves Costa; C. Ferreira; C. Parente; J. Fernandez-Ruiz (Earthquake Engineering and Engineering Vibration, 2023)

P21-14: Neurodevelopmental toxicity of T-2 mycotoxin in human-based primary and induced pluripotent stem cell-derived neural progenitor cells in 3D and 2D - M. Taroncher Ruiz; J. Kapr; K. Bartmann; J. Tigges; Y. Rodriguez-Carrasco; M.J. Ruiz; E. Fritsche (Toxicology Letters, 2023)

P16-25: In vitro assessment of triazole and newly developed tetrazole antifungals for potential interferences with corticosteroid biosynthesis and peripheral metabolism - M.-C. Jäger; V. González-Ruiz; J. Boccard; F.L. Joos; D.V. Winter; G.R. Thompson III; S. Rudaz; A. Odermatt (Toxicology Letters, 2023)

P15-02: Exploring the impact of citrinin mycotoxin on SH-SY5Y cells: Apoptosis, cell cycle, oxidative stress, and mitochondrial function - F.J. Martí-Quijal; F.J. Barba; M.-J. Ruiz (Toxicology Letters, 2023)

Seismic activity at the eastern Pyrenean termination - M. Ruiz; J. Díaz; A. Canari; M. Ortuño; J. Vergés (Tectonophysics, 2023)

Tracking end-of-life stage of chemicals: A scalable data-centric and chemical-centric approach - Jose D. Hernandez-Betancur; Gerardo J. Ruiz-Mercado; Mariano Martin (Resources, Conservation and Recycling, 2023)

A techno-economic assessment of sCO2 Brayton cycles for low-grade geothermal reservoirs - Eduardo Ruiz-Casanova; Carlos Rubio-Maya; J. Jesús Pacheco-Ibarra; Víctor M. Ambriz-Díaz; C.J. Torres Pacheco; Edgar Pastor-Martínez (Geothermics, 2023)

Harvest index has increased over the last 50 years of maize breeding - Alejo Ruiz; Slobodan Trifunovic; Douglas M. Eudy; Cintia S. Sciarresi; Mitchell Baum; Gerasimos J.N. Danalatos; Elvis F. Elli; Georgios Kalogeropoulos; Kyle King; Caio dos Santos; August Thies; Lia Olmedo Pico; et al. (Field Crops Research, 2023)

Interactions of coral reef cleaner species in the Mexican Caribbean - Crista I. Ramírez-Ruiz; Juan J. Schmitter-Soto; Alicia C. Díaz-Osorio (Environmental Biology of Fishes, 2023)

Linear and Non-linear Analyses of EEG in a Group of ASD Children During Resting State Condition - Brenda Y. Angulo-Ruiz; Francisco J. Ruiz-Martínez; Elena I. Rodríguez-Martínez; Anca Ionescu; David Saldaña; Carlos M. Gómez (Brain Topography, 2023)
This study analyses the spontaneous electroencephalogram (EEG) brain activity of 14 children diagnosed with Autism Spectrum Disorder (ASD) compared to 18 children with normal development, aged 5–11 years. (i) Power Spectral Density (PSD), (ii) variability across trials (coefficient of variation: CV), and (iii) complexity (multiscale entropy: MSE) of the brain signal analysis were computed on the resting state EEG. PSD (0.5–45 Hz) and CV were averaged over different frequency bands (low-delta, delta, theta, alpha, low-beta, high-beta and gamma). MSE were calculated with a coarse-grained procedure on 67 time scales and divided into fine, medium and coarse scales. In addition, significant neurophysiological variables were correlated with behavioral performance data ( Kaufman Brief Intelligence Test (KBIT) and Autism Spectrum Quotient (AQ)). Results show increased PSD fast frequency bands (high-beta and gamma), higher variability (CV) and lower complexity (MSE) in children with ASD when compared to typically developed children. These results suggest a more variable, less complex and, probably, less adaptive neural networks with less capacity to generate optimal responses in ASD children.

Single cell genomics as a transformative approach for aquaculture research and innovation - Rose Ruiz Daniels; Richard S. Taylor; Diego Robledo; Daniel J. Macqueen (Reviews in Aquaculture, 2023)
Single cell genomics encompasses a suite of rapidly maturing technologies that measure the molecular profiles of individual cells within target samples. These approaches provide a large up‐step in biological information compared to long‐established ‘bulk’ methods that profile the average molecular profiles of all cells in a sample, and have led to transformative advances in understanding of cellular biology, particularly in humans and model organisms. The application of single cell genomics is fast expanding to non‐model taxa, including aquaculture species, where numerous research applications are underway with many more envisaged. In this review, we highlight the potential transformative applications of single cell genomics in aquaculture research, considering barriers and potential solutions to the broad uptake of these technologies. Focusing on single cell transcriptomics, we outline considerations for experimental design, including the essential requirement to obtain high quality cells/nuclei for sequencing in ectothermic aquatic species. We further outline data analysis and bioinformatics considerations, tailored to studies with the under‐characterized genomes of aquaculture species, where our knowledge of cellular heterogeneity and cell marker genes is immature. Overall, this review offers a useful source of knowledge for researchers aiming to apply single cell genomics to address biological challenges faced by the global aquaculture sector though an improved understanding of cell biology.

Mediterranean lifestyle index and 24-h systolic blood pressure and heart rate in community-dwelling older adults - Irene Talavera-Rodríguez; José R. Banegas; Juan J. de la Cruz; David Martínez-Gómez; Miguel Ruiz-Canela; Rosario Ortolá; Maria S. Hershey; Fernando Rodríguez Artalejo; Mercedes Sotos-Prieto (GeroScience, 2023)
Specific foods, nutrients, dietary patterns, and physical activity are associated with lower blood pressure (BP) and heart rate (HR), but little is known about the joint effect of lifestyle factors captured in a multidimensional score. We assessed the association of a validated Mediterranean-lifestyle (MEDLIFE) index with 24-h-ambulatory BP and HR in everyday life among community-living older adults. Data were taken from 2,184 individuals (51% females, mean age: 71.4 years) from the Seniors-ENRICA-2 cohort. The MEDLIFE index consisted of 29 items arranged in three blocks: 1) Food consumption; 2) Dietary habits; and 3) Physical activity, rest, and conviviality. A higher MEDLIFE score (0–29 points) represented a better Mediterranean lifestyle adherence. 24-h-ambulatory BP and HR were obtained with validated oscillometric devices. Analyses were performed with linear regression adjusted for the main confounders. The MEDLIFE-highest quintile (vs Q1) was associated with lower nighttime systolic BP (SBP) (-3.17 mmHg [95% CI: -5.25, -1.08]; p-trend = 0.011), greater nocturnal-SBP fall (1.67% [0.51, 2.83]; p-trend = 0.052), and lower HR (-2.04 bpm [daytime], -2.33 bpm [nighttime], and -1.93 bpm [24-h]; all p -trend < 0.001). Results were similar for each of the three blocks of MEDLIFE and by hypertension status (yes/no). Among older adults, higher adherence to MEDLIFE was associated with lower nighttime SBP, greater nocturnal-SBP fall, and lower HR in their everyday life. These results suggest a synergistic BP-related protection from the components of the Mediterranean lifestyle. Future studies should determine whether these results replicate in older adults from other Mediterranean and non-Mediterranean countries.

Short-term effects of tropospheric ozone and other environmental factors on emergency admissions due to pregnancy complications: A time-series analysis in the Madrid Region - A. Calle-Martínez; R. Ruiz-Páez; L. Gómez-González; A. Egea-Ferrer; J.A. López-Bueno; J. Díaz; C. Asensio; M.A. Navas; C. Linares (Environmental Research, 2023)

Understanding the demography of a reinforced population: Long-term survival of captive-bred and wild-born houbara bustards in Morocco - Stephanie M. Harris; Orin J. Robinson; Yves Hingrat; Eric Le Nuz; Viviana Ruiz-Gutierrez (Biological Conservation, 2023)

Addition of β-glucans in diets for tropical gar (Atractosteus tropicus) larvae: effects on growth, digestive enzymes and gene expression of intestinal epithelial integrity and immune system - L. A. Cigarroa-Ruiz; F. J. Toledo-Solís; S. A. Frías-Gómez; R. Guerrero-Zárate; S. Camarillo-Coop; C. S. Alvarez-Villagómez; E. S. Peña-Marín; M. A. Galaviz; R. Martínez-García; C. A. Álvarez-González (Fish Physiology and Biochemistry, 2023)

Common carp as an ecological indicator of environmental pollution in reservoirs of southern Spain: inferring the environmental risks of anthropogenic activities - Nestor Javier Mancera-Rodríguez; Daniel Ruiz Galiano; Antonio Jesús López-Montoya; Eulogio J. Llorent-Martínez; Lucía Molina-García; Concepción Azorit (Environmental Science and Pollution Research, 2023)

Role of climate variability on deep-water dynamics and deoxygenation during sapropel deposition: New insights from a palaeoceanographic empirical approach - Ricardo D. Monedero-Contreras; Francisca Martínez-Ruiz; Francisco J. Rodríguez-Tovar (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

How heat waves, ozone and sunlight hours affect endocrine and metabolic diseases emergency admissions? A case study in the region of Madrid (Spain) - A. Egea; C. Linares; J. Díaz; L. Gómez; A. Calle; M.A. Navas; R. Ruiz-Páez; C. Asensio; A. Padrón-Monedero; J.A. López-Bueno (Environmental Research, 2023)

Combined artificial intelligence, sustainable land management, and stakeholder engagement for integrated landscape management in Mediterranean watersheds - Itxaso Ruiz; João Pompeu; Antonio Ruano; Paloma Franco; Stefano Balbi; María J. Sanz (Environmental Science & Policy, 2023)

Air pollution relevance analysis in the bay of Algeciras (Spain) - M. I. Rodríguez-García; J. González-Enrique; J. A. Moscoso-López; J. J. Ruiz-Aguilar; I. J. Turias (International Journal of Environmental Science and Technology, 2023)
The aim of this work is to accomplish an in-depth analysis of the air pollution in the two main cities of the Bay of Algeciras (Spain). A large database of air pollutant concentrations and weather measurements were collected using a monitoring network installed throughout the region from the period of 2010–2015. The concentration parameters contain nitrogen dioxide (NO 2 ), sulphur dioxide (SO 2 ) and particulate matter (PM 10 ). The analysis was developed in two monitoring stations (Algeciras and La Línea). The higher average concentration values were obtained in Algeciras for NO 2 (28.850 µg/m 3 ) and SO 2 (11.966 µg/m 3 ), and in La Línea for PM 10 (30.745 µg/m 3 ). The analysis shows patterns that coincide with human activity. One of the goals of this work is to develop a useful virtual sensor capable of achieving a more robust monitoring network, which can be used, for instance, in the case of missing data. By means of trends analysis, groups of equivalent stations were determined, implying that the values of one station could be substituted for those in the equivalent station in case of failure (e.g., SO 2 weekly trends in Algeciras and Los Barrios show equivalence). On the other hand, a calculation of relative risks was developed showing that relative humidity, wind speed and wind direction produce an increase in the risk of higher pollutant concentrations. Besides, obtained results showed that wind speed and wind direction are the most important variables in the distribution of particles. The results obtained may allow administrations or citizens to support decisions.

Effects of bisphenol F, bisphenol S, and bisphenol AF on cultured human osteoblasts - E. García-Recio; V. J. Costela-Ruiz; L. Melguizo-Rodríguez; J. Ramos-Torrecillas; R. Illescas-Montes; E. De Luna-Bertos; C. Ruiz (Archives of Toxicology, 2023)
Bisphenol A (BPA) analogs, like BPA, could have adverse effects on human health including bone health. The aim was to determine the effect of BPF, BPS and BPAF on the growth and differentiation of cultured human osteoblasts. Osteoblasts primary culture from bone chips harvested during routine dental work and treated with BPF, BPS, or BPAF for 24 h at doses of 10 –5 , 10 –6 , and 10 –7 M. Next, cell proliferation was studied, apoptosis induction, and alkaline phosphatase (ALP) activity. In addition, mineralization was evaluated at 7, 14, and 21 days of cell culture in an osteogenic medium supplemented with BP analog at the studied doses. BPS treatment inhibited proliferation in a dose-dependent manner at all three doses by inducing apoptosis; BPF exerted a significant inhibitory effect on cell proliferation at the highest dose alone by an increase of apoptosis; while BPAF had no effect on proliferation or cell viability. Cell differentiation was adversely affected by treatment with BPA analogs in a dose-dependent, observing a reduction in calcium nodule formation at 21 days. According to the results obtained, these BPA analogs could potentially pose a threat to bone health, depending on their concentration in the organism.

Non-indigenous aquatic fauna in transitional waters from the Spanish Mediterranean coast: A comprehensive assessment - José M. Zamora-Marín; Antonio A. Herrero-Reyes; Ana Ruiz-Navarro; Francisco J. Oliva-Paterna (Marine Pollution Bulletin, 2023)

Brief emotional eating scale: A multinational study of factor structure, validity, and invariance - Montse C. Ruiz; Tracey J. Devonport; Chao-Hwa (Josephine) Chen-Wilson; Wendy Nicholls; Jonathan Y. Cagas; Javier Fernandez-Montalvo; Youngjun Choi; Yiqun Gan; Claudio Robazza (Appetite, 2023)

Corrigendum to ‘A horizon scan exercise for aquatic invasive alien species in Iberian inland waters’ Sci. Total Environ.869 (2023) 161798 - Francisco J. Oficialdegui; José M. Zamora-Marín; Simone Guareschi; Pedro M. Anastácio; Pablo García-Murillo; Filipe Ribeiro; Rafael Miranda; Fernando Cobo; Belinda Gallardo; Emili García-Berthou; Dani Boix; Andrés Arias; et al. (Science of The Total Environment, 2023)

Applicability of the probiotic Lactiplantibacillus plantarum BFL as an adjunct culture in a dry fermented sausage - Noelí Sirini; María Stegmayer; María J. Ruiz; Facundo Cuffia; Eugenia Rossler; José Otero; Lorena Soto; José M. Lorenzo; José Ángel Pérez-Álvarez; Marcelo Rosmini; Laureano Frizzo (Meat Science, 2023)

Life cycle costing of AnMBR technology for urban wastewater treatment: A case study based on a demo-scale AnMBR system - A. Jiménez-Benítez; A. Ruiz-Martínez; J. Ferrer; J. Ribes; F. Rogalla; A. Robles (Journal of Environmental Chemical Engineering, 2023)

An intensive culinary intervention programme to empower type 2 diabetic patients in cooking skills: The SUKALMENA pilot study - L. Gayoso; L. Goni; V. de la O; J. Domper; C. Razquin; M. Ruiz-Canela; U. Etxeberria (International Journal of Gastronomy and Food Science, 2023)

Dietary intake of polychlorinated dibenzo-p-dioxins and furans, adiposity and obesity status. - Nadine Khoury; María Ángeles Martínez; Indira Paz-Graniel; Miguel Ángel Martínez-González; Dolores Corella; Olga Castañer; J. Alfredo Martínez; Ángel M. Alonso-Gómez; Julia Wärnberg; Jesús Vioque; Dora Romaguera; José López-Miranda; et al. (Environmental Research, 2023)

Composites of Co-Al hydrotalcites and carbon nanomaterials for photocatalytic H2 production - Dolores G. Gil-Gavilán; Daniel Cosano; Miguel Castillo-Rodríguez; Gustavo de Miguel; Dolores Esquivel; César Jiménez-Sanchidrián; José R. Ruiz; Francisco J. Romero-Salguero (Applied Clay Science, 2023)

Correction to: Sharing food with hyenas: a latrine of Pachycrocuta brevirostris in the Early Pleistocene assemblage of Fuente Nueva‑3 (Orce, Baza Basin, SE Spain) - M. P. Espigares; P. Palmqvist; M. D. Rodríguez‑Ruiz; S. Ros‑Montoya; A. Pérez‑Ramos; G. Rodríguez‑Gómez; A. Guerra‑Merchán; J. M. García‑Aguilar; A. Granados; I. Campaña; B. Martínez‑Navarro (Archaeological and Anthropological Sciences, 2023)

Sharing food with hyenas: a latrine of Pachycrocuta brevirostris in the Early Pleistocene assemblage of Fuente Nueva-3 (Orce, Baza Basin, SE Spain) - M. P. Espigares; P. Palmqvist; M. D. Rodríguez-Ruiz; S. Ros-Montoya; A. Pérez-Ramos; G. Rodríguez-Gómez; A. Guerra-Merchán; J. M. García-Aguilar; A. Granados; I. Campaña; B. Martínez-Navarro (Archaeological and Anthropological Sciences, 2023)
The Early Pleistocene archeological site of Fuente Nueva-3 (FN3) preserves some of the oldest evidence of hominin presence in Western Europe, including a huge assemblage of Oldowan tools and evidence of butchering and marrow processing of large mammal bones. Moreover, there is also evidence of the regular presence of carnivores at the site, including a small proportion of bones that show tooth marks, the majority of which can be attributed to the giant, short-faced hyena Pachycrocuta brevirostris , and there are 220 coprolites, most of them from the Upper Archeological Level. In order to identify the defecating agent, we analyze here the coprolites and compare them with other specimens from the literature and with scats from zoo spotted hyenas ( Crocuta crocuta ). The morphology, color, size, and chemical composition of the FN3 coprolites allow us to attribute them to the hyena P. brevirostris , which is also represented at the site by fossil specimens. In addition, we evaluate the origin of the accumulation of coprolites and discuss on the role played by the scavenging hyenas in the accumulation and modification of the bone remains unearthed at the site, which allows evaluating the contribution of the giant hyena to this Early Pleistocene site. Finally, based on the lithology of layer 5 of the Upper Archeological Level, fine sands and clays deposited in a salt-lake environment, we hypothesize that this layer may have acted as a quicksand where large-sized animals like elephants were trapped and their carcasses lured scavenging carnivores.

Editorial: Coastal environment in a changing world - J. Benavente; A. Ruiz de Alegría-Arzaburu; T. A. Plomaritis; M. Sedrati; E. H. Ariffin (Frontiers in Marine Science, 2023)

Short-term impact of noise, other air pollutants and meteorological factors on emergency hospital mental health admissions in the Madrid region - L. Gómez González; C. Linares; J. Díaz; A. Egea; A. Calle-Martínez; M.Y. Luna; M.A. Navas; M.S. Ascaso-Sánchez; R. Ruiz-Páez; C. Asensio; A. Padrón-Monedero; J.A. López-Bueno (Environmental Research, 2023)

The holobiome of marine harmful algal blooms (HABs): A novel ecosystem-based approach for implementing predictive capabilities and managing decisions - Gonzalo Gajardo; Jesús Morón-López; Karen Vergara; Shoko Ueki; Leonardo Guzmán; Oscar Espinoza-González; Alondra Sandoval; Gonzalo Fuenzalida; Alejandro A. Murillo; Carlos Riquelme; Henry Camerón; Satoshi Nagai; et al. (Environmental Science & Policy, 2023)

Why phylogenetic signal of traits is important in ecosystems: uniformity of a plant trait increases soil fauna, but only in a phylogenetically uniform vegetation - F. Molleman; N. Rossignol; J. F. Ponge; G. Peres; D. Cluzeau; N. Ruiz-Camacho; J. Cortet; C. Pernin; C. Villenave; A. Prinzing (Oecologia, 2023)
Phylogenetically closely related plant species often share similar trait states (phylogenetic signal), but local assembly may favor dissimilar relatives and thereby decouple the diversity of a trait from the diversity of phylogenetic lineages. Associated fauna might either benefit from plant trait diversity, because it provides them complementary resources, or suffer from it due to dilution of preferred resources. We hence hypothesize that decoupling of trait and phylogenetic diversity weakens the relationship between the plant-trait diversity and the abundance and diversity of associated fauna. Studying permanent meadows, we tested for combined effects of plant phylogenetic diversity and diversity of two functional traits (specific leaf area, leaf dry matter content) on major groups of soil fauna (earthworms, mites, springtails, nematodes). We found that only in phylogenetically uniform plant communities, was uniformity in the functional traits associated with (i) high abundance in springtails, and (ii) high abundance of the sub-group that feeds more directly on plant material (in springtails and mites) or those that are more prone to disturbance (in nematodes), and (iii) high diversity in all three groups tested (springtails, earthworms, nematodes). Our results suggest that soil fauna profits from the resource concentration in local plant communities that are uniform in both functional traits and phylogenetic lineages. Soil fauna would hence benefit from co-occurrence of closely related plants that have conserved the same trait values, rather than of distantly related plants that have converged in traits. This might result in faster decomposition and a positive feedback between trait conservatism and ecosystem functioning.

Genetic composition and diversity of Arabica coffee in the crop’s centre of origin and its impact on four major fungal diseases - Beyene Zewdie; Yves Bawin; Ayco J. M. Tack; Sileshi Nemomissa; Kassahun Tesfaye; Steven B. Janssens; Sabine Van Glabeke; Isabel Roldán‐Ruiz; Tom Ruttink; Olivier Honnay; Kristoffer Hylander (Molecular Ecology, 2023)
Conventional wisdom states that genetic variation reduces disease levels in plant populations. Nevertheless, crop species have been subject to a gradual loss of genetic variation through selection for specific traits during breeding, thereby increasing their vulnerability to biotic stresses such as pathogens. We explored how genetic variation in Arabica coffee sites in southwestern Ethiopia was related to the incidence of four major fungal diseases. Sixty sites were selected along a gradient of management intensity, ranging from nearly wild to intensively managed coffee stands. We used genotyping‐by‐sequencing of pooled leaf samples (pool‐GBS) derived from 16 individual coffee shrubs in each of the 60 sites to assess the variation in genetic composition (multivariate: reference allele frequency) and genetic diversity (univariate: mean expected heterozygosity) between sites. We found that genetic composition had a clear spatial pattern and that genetic diversity was higher in less managed sites. The incidence of the four fungal diseases was related to the genetic composition of the coffee stands, but in a specific way for each disease. In contrast, genetic diversity was only related to the within‐site variation of coffee berry disease, but not to the mean incidence of any of the four diseases across sites. Given that fungal diseases are major challenges of Arabica coffee in its native range, our findings that genetic composition of coffee sites impacted the major fungal diseases may serve as baseline information to study the molecular basis of disease resistance in coffee. Overall, our study illustrates the need to consider both host genetic composition and genetic diversity when investigating the genetic basis for variation in disease levels.

Integrating stakeholders' inputs to co-design climate resilience adaptation measures in Mediterranean areas with conflicts between wetland conservation and intensive agriculture - David Pulido-Velazquez; Leticia Baena-Ruiz; Beatriz Mayor; Pedro Zorrilla-Miras; Elena López-Gunn; Juan de Dios Gómez-Gómez; África de la Hera-Portillo; Antonio-Juan Collados-Lara; Miguel Mejías Moreno; José Luis García Aróstegui; Francisco J. Alcalá (Science of The Total Environment, 2023)

A horizon scan exercise for aquatic invasive alien species in Iberian inland waters - Francisco J. Oficialdegui; José M. Zamora-Marín; Simone Guareschi; Pedro M. Anastácio; Pablo García-Murillo; Filipe Ribeiro; Rafael Miranda; Fernando Cobo; Belinda Gallardo; Emili García-Berthou; Dani Boix; Andrés Arias; et al. (Science of The Total Environment, 2023)

A semi-industrial AnMBR plant for urban wastewater treatment at ambient temperature: Analysis of the filtration process, energy balance and quantification of GHG emissions - A. Jiménez-Benítez; A. Ruiz-Martínez; Á. Robles; J. Serralta; J. Ribes; F. Rogalla; A. Seco; J. Ferrer (Journal of Environmental Chemical Engineering, 2023)

Estimation of body weight using body measurements in female water buffaloes reared in southeastern Mexico - Jorge Ruiz-Ramos; Oswaldo M. Torres-Chable; Jorge A. Peralta-Torres; Nadia F. Ojeda-Robertos; Carlos Luna-Palomera; Rodrigo Portillo-Salgado; Thobela Louis Tyasi; Antonio Leandro Chaves Gurgel; Luís Carlos Vinhas Ítavo; Alfonso J. Chay-Canul (Tropical Animal Health and Production, 2023)

Assessing the drought effect on tree rings' width and xylem traits plasticity in Symplocos coccinea and S. speciosa: two rare and endemic Neotropical montane oak forest trees from eastern Mexico - E. C. Rodríguez-Ramírez; D. Ruiz-Santiago; E. J. Requena-Rojas; T. Longhi-Santos; A. Suárez-Islas; I. Luna-Vega (Trees, 2023)

Carbon-to-nitrogen ratios on laccase and mushroom production of Lentinus crinitus - I. M. Colla; O. B. Q. de O. Filho; M. B. D. Bertéli; J. D. S. de Freitas; K. V. Avelino; S. P. Ruiz; J. S. do Valle; G. A. Linde; N. B. Colauto (International Journal of Environmental Science and Technology, 2023)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Bile salt dietary supplementation promotes growth and reduces body adiposity in gilthead seabream (Sparus aurata) - Alberto Ruiz; Karl B. Andree; Ignasi Sanahuja; Paul G. Holhorea; Josep À. Calduch-Giner; Sofia Morais; Jose J. Pastor; Jaume Pérez-Sánchez; Enric Gisbert (Aquaculture, 2023)

New constraints on the closure of the Betic Seaway and the western Mediterranean palaeoclimate during the Messinian Salinity Crisis from the Campo Coy Basin (SE Spain) - Victoriano Pineda; David Artiaga; Francisco J. Ruiz-Sánchez; Plini Montoya; Jesús M. Soria; Hugo Corbí; Luis Gibert (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Impact of food preservatives based on immobilized phenolic compounds on an in vitro model of human gut microbiota - María Ruiz-Rico; Simone Renwick; Sarah J. Vancuren; Avery V. Robinson; Connor Gianetto-Hill; Emma Allen-Vercoe; José M. Barat (Food Chemistry, 2023)

The nonpathogenic strain of Fusarium oxysporum FO12 induces Fe deficiency responses in cucumber (Cucumis sativus L.) plants - Miguel A. Aparicio; Carlos Lucena; María J. García; Francisco J. Ruiz-Castilla; Pablo Jiménez-Adrián; Manuel S. López-Berges; Pilar Prieto; Esteban Alcántara; Rafael Pérez-Vicente; José Ramos; Francisco J. Romera (Planta, 2023)
Main conclusion FO12 strain enhances Fe deficiency responses in cucumber plants, probably through the production of ethylene and NO in the subapical regions of the roots. Abstract Rhizosphere microorganisms can elicit induced systemic resistance (ISR) in plants. This type of resistance involves complex mechanisms that confer protection to the plant against pathogen attack. Additionally, it has been reported by several studies that ISR and Fe deficiency responses are modulated by common pathways, involving some phytohormones and signaling molecules, like ethylene and nitric oxide (NO). The aim of this study was to determine whether the nonpathogenic strain of Fusarium oxysporum FO12 can induce Fe deficiency responses in cucumber ( Cucumis sativus L.) plants. Our results demonstrate that the root inoculation of cucumber plants with the FO12 strain promotes plant growth after several days of cultivation, as well as rhizosphere acidification and enhancement of ferric reductase activity. Moreover, Fe-related genes, such as FRO1, IRT1 and HA1 , are upregulated at certain times after FO12 inoculation either upon Fe-deficiency or Fe-sufficient conditions. Furthermore, it has been found that this fungus colonizes root cortical tissues, promoting the upregulation of ethylene synthesis genes and NO production in the root subapical regions. To better understand the effects of the FO12 strain on field conditions, cucumber plants were inoculated and cultivated in a calcareous soil under greenhouse conditions. The results obtained show a modification of some physiological parameters in the inoculated plants, such as flowering and reduction of tissue necrosis. Overall, the results suggest that the FO12 strain could have a great potential as a Fe biofertilizer and biostimulant.

Recent trace element contamination in a rural crater lake, NW Mexico - A. C. Ruiz-Fernández; J. A. Sanchez-Cabeza; L. H. Pérez-Bernal; M. Blaauw; J. G. Cardoso-Mohedano; M. A. Aquino-López; S. Giralt (Journal of Paleolimnology, 2023)

Regulation of CO2 by the sea in areas around Latin America in a context of climate change - V. Lutz; M. Chidiak; R. Frouin; R. Negri; A. I. Dogliotti; E. Santamaria-del-Angel; C. F. Berghoff; J. Rojas; C. Filipello; Y. Astor; V. Segura; A. Gonzalez-Silvera; et al. (Environmental Monitoring and Assessment, 2023)

Applying genetic technologies to combat infectious diseases in aquaculture - Nicholas A. Robinson; Diego Robledo; Lene Sveen; Rose Ruiz Daniels; Aleksei Krasnov; Andrew Coates; Ye Hwa Jin; Luke T. Barrett; Marie Lillehammer; Anne H. Kettunen; Ben L. Phillips; Tim Dempster; et al. (Reviews in Aquaculture, 2023)
Disease and parasitism cause major welfare, environmental and economic concerns for global aquaculture. In this review, we examine the status and potential of technologies that exploit genetic variation in host resistance to tackle this problem. We argue that there is an urgent need to improve understanding of the genetic mechanisms involved, leading to the development of tools that can be applied to boost host resistance and reduce the disease burden. We draw on two pressing global disease problems as case studies—sea lice infestations in salmonids and white spot syndrome in shrimp. We review how the latest genetic technologies can be capitalised upon to determine the mechanisms underlying inter‐ and intra‐species variation in pathogen/parasite resistance, and how the derived knowledge could be applied to boost disease resistance using selective breeding, gene editing and/or with targeted feed treatments and vaccines. Gene editing brings novel opportunities, but also implementation and dissemination challenges, and necessitates new protocols to integrate the technology into aquaculture breeding programmes. There is also an ongoing need to minimise risks of disease agents evolving to overcome genetic improvements to host resistance, and insights from epidemiological and evolutionary models of pathogen infestation in wild and cultured host populations are explored. Ethical issues around the different approaches for achieving genetic resistance are discussed. Application of genetic technologies and approaches has potential to improve fundamental knowledge of mechanisms affecting genetic resistance and provide effective pathways for implementation that could lead to more resistant aquaculture stocks, transforming global aquaculture.

Effect of marine climate and baitfish availability on the tuna baitboat fishery CPUE OFF northwestern Mexico - Emigdio Marín-Enríquez; J. Saúl Ramírez-Pérez; Marcelino Ruiz-Domínguez; Vanessa Izquierdo-Peña; Rebeca Sánchez-Cárdenas; Víctor H. Cruz-Escalona; Concepción Enciso-Enciso (Ocean & Coastal Management, 2023)

Lizards' response to the sound of fire is modified by fire history - Lola Álvarez-Ruiz; Juli G. Pausas; Daniel T. Blumstein; Breanna J. Putman (Animal Behaviour, 2023)

Pyrolysis of mixed plastic waste: Predicting the product yields - Homer C. Genuino; M. Pilar Ruiz; Hero J. Heeres; Sascha R.A. Kersten (Waste Management, 2023)

Phytoliths as indicators of plant water availability: The case of millets cultivation in the Indus Valley civilization - F. D'Agostini; J. Ruiz-Pérez; M. Madella; V. Vadez; J. Kholova; C. Lancelotti (Review of Palaeobotany and Palynology, 2023)

MgO-containing porous carbon spheres derived from magnesium lignosulfonate as sustainable basic catalysts - M. García-Rollán; F.J. García-Mateos; R. Ruiz-Rosas; J.M. Rosas; J. Rodríguez-Mirasol; T. Cordero (Journal of Environmental Chemical Engineering, 2023)

Short–term effects of air pollution and noise on emergency hospital admissions in Madrid and economic assessment - R. Ruiz-Páez; J. Díaz; J.A. López-Bueno; C. Asensio; M.S. Ascaso; M. Saez; M.Y. Luna; M.A. Barceló; M.A. Navas; C. Linares (Environmental Research, 2023)

Advances in process design, techno-economic assessment and environmental aspects for hydrothermal pretreatment in the fractionation of biomass under biorefinery concept - Héctor A. Ruiz; William Gustavo Sganzerla; Valeria Larnaudie; Romy J. Veersma; Gijs van Erven; Shiva; Leopoldo J. Ríos-González; Rosa M. Rodríguez-Jasso; Gilver Rosero-Chasoy; Mario Daniel Ferrari; Mirjam A. Kabel; Tânia Forster-Carneiro; et al. (Bioresource Technology, 2023)

Mapping of solar insolation using air temperature in tropical and mountainous environments - L. S. Hoyos; B. J. Ruiz (Meteorology and Atmospheric Physics, 2023)

Correction to: Mobilization of potentially toxic elements from harbor contaminated sediments capped with mixtures of hematite and active carbon - O. A. Rubio-Hernández; C. R. Green-Ruiz; J. R. Rivera-Hernández; M. Soto-Jimenez (International Journal of Environmental Science and Technology, 2023)

Mobilization of potentially toxic elements from harbor contaminated sediments capped with mixtures of hematite and active carbon - O. A. Rubio-Hernández; C. R. Green-Ruiz; J. R. Rivera-Hernández (International Journal of Environmental Science and Technology, 2023)

Wild plants canopies may adsorb dust particles eroded from mine tailings, decreasing potentially toxic elements dispersion - M. C. A. González-Chávez; M. E. Santiago-Martínez; J. E. Corona-Sánchez; A. Ruiz-Olivares; R. Carrillo-González (International Journal of Environmental Science and Technology, 2023)

Understanding the impact of wild boar on the European wild rabbit and red-legged partridge populations using a diet metabarcoding approach - Antonio J. Carpio; João Queirós; Eduardo Laguna; Saúl Jiménez-Ruiz; Joaquín Vicente; Paulo C. Alves; Pelayo Acevedo (European Journal of Wildlife Research, 2023)
European wild rabbit ( Oryctolagus cuniculus ) and red-legged partridge ( Alectoris rufa ) are main small game species of conservation concern in Mediterranean ecosystems. To date, their presence in wild boar’s ( Sus scrofa ) diet and factors driving their consumption have been little investigated. A genetic metabarcoding approach was used on 80 wild boar faeces collected from four hunting estates devoted to small game hunting during two different seasons. Abundances of wild boar, rabbits and partridges were first estimated. Results showed DNA of seventeen chordate species. The highest frequency of occurrence (FO) corresponded to mammals and birds, with 77.6 and 22.3%, respectively. DNA of game species was detected in 39/71 (FO = 55.0%) samples, highlighting the presence of European wild rabbit in 27 (FO = 38.0%) and red-legged partridge in eight (FO = 11.3%). Dietary composition varied between seasons and estates, being rabbit the main responsible (explaining 35.26% and 39.45% of differences, respectively). Rabbit FO in the diet was positively related to the abundance of wild boar and rabbit density on the estate. It was greater in autumn and in estates where rabbits were hunted. Regarding red-legged partridge, a significant and positive relationship between its population density and its diet FO was observed, without significant differences between seasons or estates. Overall, our results suggest wild boar as an opportunistic species whose diet is largely determined by the relative availability of different food resources. Its ecological role concerning small game species in Mediterranean agroecosystems seems to be more related to consumption of carrion during the hunting season than to direct predation.

Deciphering interactions between the marine dinoflagellate Prorocentrum lima and the fungus Aspergillus pseudoglaucus - Olivier Berry; Enora Briand; Alizé Bagot; Maud Chaigné; Laurence Meslet‐Cladière; Julien Wang; Olivier Grovel; Jeroen J. Jansen; Nicolas Ruiz; Thibaut Robiou du Pont; Yves François Pouchus; Philipp Hess; et al. (Environmental Microbiology, 2023)
The comprehension of microbial interactions is one of the key challenges in marine microbial ecology. This study focused on exploring chemical interactions between the toxic dinoflagellate Prorocentrum lima and a filamentous fungal species, Aspergillus pseudoglaucus , which has been isolated from the microalgal culture. Such interspecies interactions are expected to occur even though they were rarely studied. Here, a co‐culture system was designed in a dedicated microscale marine‐like condition. This system allowed to explore microalgal–fungal physical and metabolic interactions in presence and absence of the bacterial consortium. Microscopic observation showed an unusual physical contact between the fungal mycelium and dinoflagellate cells. To delineate specialized metabolome alterations during microalgal–fungal co‐culture metabolomes were monitored by high‐performance liquid chromatography coupled to high‐resolution mass spectrometry. In‐depth multivariate statistical analysis using dedicated approaches highlighted (1) the metabolic alterations associated with microalgal–fungal co‐culture, and (2) the impact of associated bacteria in microalgal metabolome response to fungal interaction. Unfortunately, only a very low number of highlighted features were fully characterized. However, an up‐regulation of the dinoflagellate toxins okadaic acid and dinophysistoxin 1 was observed during co‐culture in supernatants. Such results highlight the importance to consider microalgal–fungal interactions in the study of parameters regulating toxin production.

Occurrence of Z-drugs, benzodiazepines, and ketamine in wastewater in the United States and Mexico during the Covid-19 pandemic - Sangeet Adhikari; Rahul Kumar; Erin M. Driver; Devin A. Bowes; Keng Tiong Ng; Juan Eduardo Sosa-Hernandez; Mariel Araceli Oyervides-Muñoz; Elda M. Melchor-Martínez; Manuel Martínez-Ruiz; Karina G. Coronado-Apodaca; Ted Smith; Aruni Bhatnagar; et al. (Science of The Total Environment, 2023)

Mistaking plastic for zooplankton: Risk assessment of plastic ingestion in the Mediterranean sea - S. Fabri-Ruiz; A. Baudena; F. Moullec; F. Lombard; J.-O. Irisson; M.L. Pedrotti (Science of The Total Environment, 2023)

Does the meteorological origin of heat waves influence their impact on health? A 6-year morbidity and mortality study in Madrid (Spain) - R. Ruiz-Páez; J. Díaz; J.A. López-Bueno; M.A. Navas; I.J. Mirón; G.S. Martínez; M.Y. Luna; C. Linares (Science of The Total Environment, 2023)

A generic scenario analysis of end-of-life plastic management: Chemical additives - John D. Chea; Kirti M. Yenkie; Joseph F. Stanzione; Gerardo J. Ruiz-Mercado (Journal of Hazardous Materials, 2023)

Prediction of enteric methane emissions by sheep using an intercontinental database - Alejandro Belanche; Alexander N. Hristov; Henk J. van Lingen; Stuart E. Denman; Ermias Kebreab; Angela Schwarm; Michael Kreuzer; Mutian Niu; Maguy Eugène; Vincent Niderkorn; Cécile Martin; Harry Archimède; et al. (Journal of Cleaner Production, 2023)

Nested spatial data structures for optimal indexing of LiDAR data - Carlos J. Ogayar-Anguita; Alfonso López-Ruiz; Antonio J. Rueda-Ruiz; Rafael J. Segura-Sánchez (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Enhanced photocatalytic oxidation of a phenoxyacetic acid herbicide using TiO2–FeOOH/Fe2O3 assisted with sulfate radicals - B. Mendoza-Reyes; S. Mendiola-Alvarez; J. L. Guzmán-Mar; M. Villanueva-Rodríguez; E. J. Ruiz-Ruiz; L. Hinojosa-Reyes (International Journal of Environmental Science and Technology, 2023)

Temperature dependence on hydrogen production from hydrolysis reaction of recycled aluminum - M. A. Escalante Soberanis; Caridad Vales-Pinzón; Emanuel Hernández-Núñez; Manuel Flota-Bañuelos; J. Medina; R. Quintal-Palomo; Liliana San-Pedro; Miguel Ruiz-Gómez (Clean Technologies and Environmental Policy, 2023)

Natural products and their mechanisms in potential photoprotection of the skin - J C Pizano-Andrade; B Vargas-Guerrero; C M Gurrola-Díaz; J J Vargas-Radillo; M A Ruiz-López (Journal of Biosciences, 2022)

Differences in fouling community composition and space occupation across broad spatial and temporal scales - Elizabeth B. Jewett; Katherine N. Lawson; Kristen J. Larson; Brianna M. Tracy; Safra Altman; Andrew L. Chang; Scott Cowan; Jeffrey A. Crooks; Tamar Huber; Elizabeth H. Wells; Gregory M. Ruiz (Frontiers in Marine Science, 2022)
Sessile marine invertebrate (biofouling) communities have served as an important model in ecology for evaluating fundamental patterns and processes, including invasion dynamics, which vary at broad spatial and temporal scales. Here, we tested for differences in biofouling community development among three biogeographically distinct bays in North America (Chesapeake Bay, Tampa Bay, and San Francisco Bay), exploring possible explanations for differential non-native species success. In particular, we aimed to examine if San Francisco Bay (a global hotspot for non-native species richness) differed in composition and space occupation, especially since open space can facilitate colonization. Additionally, we explored how biogeography, assembly and succession dynamics over the short and long term, and space availability affect marine communities across broad spatial scales. Patterns of community assembly differed among bays, with more bare space and less secondary cover (species settling on species) in San Francisco Bay. San Francisco Bay was also distinguished by a higher percent cover of Tunicata (almost all of which are non-native and historically absent) over multiple time scales. Cirripedia recruited on bare panels in all three Bays but cover increased only in Tampa Bay, as soak time increased. Tube-dwelling Polychaeta distinguished Chesapeake Bay from Tampa Bay and San Francisco Bay. Low-salinity events temporarily restructured the communities in all three bays. Whether differences among bays reflect coastal versus bay-specific patterns remains to be tested.

Modelling floating riverine litter in the south-eastern Bay of Biscay: a regional distribution from a seasonal perspective - Irene Ruiz; Anna Rubio; Ana J. Abascal; Oihane C. Basurko (Ocean Science, 2022)
Although rivers contribute to the flux of litter to the marine environment, estimates of riverine litter amounts and detailed studies on floating riverine litter behaviour once it has reached the sea are still scarce. This paper provides an analysis of the seasonal behaviour of floating marine litter released by rivers within the south-eastern Bay of Biscay based on riverine litter characterizations, drifters, and high-frequency radar observations and Lagrangian simulations. Virtual particles were released in the coastal area as a proxy of the floating fraction of riverine litter entering from rivers and reaching the open waters. Particles were parameterized with a wind drag coefficient (Cd) to represent their trajectories and fate according to the buoyancy of the litter items. They were forced with numerical winds and measured currents provided by high-frequency radars covering selected seasonal week-long periods between 2009 and 2021. To gain a better insight into the type and buoyancy of the items, samples collected from a barrier placed at the Deba River (Spain) were characterized at the laboratory. Items were grouped into two categories: low-buoyancy items (objects not exposed to wind forcing, e.g. plastic bags) and highly buoyant items (objects highly exposed to wind forcing, e.g. bottles). Overall, low-buoyancy items encompassed almost 90 % by number and 68 % by weight. Weakly buoyant items were parameterized with Cd = 0 % and highly buoyant items with Cd = 4 %; this latter value is the result of the joint analysis of modelled and observed trajectories of four satellite drifting buoys released at the Adour (France), Deba (Spain), and Oria (Spain) river mouths. Particles parameterized with Cd = 4 % drifted faster towards the coast through the wind, notably during the first 24 h. In summer, over 97 % of particles beached after 1 week of simulation. In autumn this value fell to 54 %. In contrast, low-buoyancy items took longer to arrive at the shoreline, particularly during spring with fewer than 25 % of particles beached by the end of the simulations. The highest concentrations (>200 particles km−1) were recorded during summer for Cd = 4 % in the French region of Pyrénées-Atlantiques. Results showed that the regions in the study area were highly affected by rivers within or nearby the region itself. These results couple observations and a river-by-river modelling approach and can assist decision-makers on setting emergency responses to high fluxes of floating riverine litter and on defining future monitoring strategies for heavily polluted regions within the south-eastern Bay of Biscay.

Historical reconstruction of sediment accumulation rates as an indicator of global change impacts in a tropical crater lake - A. C. Ruiz-Fernández; J. A. Sanchez-Cabeza; M. Blaauw; L. H. Pérez-Bernal; J. G. Cardoso-Mohedano; M. A. Aquino-López; E. Keaveney; S. Giralt (Journal of Paleolimnology, 2022)

The Interplay of the Tree and Stand-Level Processes Mediate Drought-Induced Forest Dieback: Evidence from Complementary Remote Sensing and Tree-Ring Approaches - Daniel Moreno-Fernández; J. Julio Camarero; Mariano García; Emily R. Lines; Jesús Sánchez-Dávila; Julián Tijerín; Cristina Valeriano; Alba Viana-Soto; Miguel Á. Zavala; Paloma Ruiz-Benito (Ecosystems, 2022)
Drought-induced forest dieback can lead to a tipping point in community dominance, but the coupled response at the tree and stand-level response has not been properly addressed. New spatially and temporally integrated monitoring approaches that target different biological organization levels are needed. Here, we compared the temporal responses of dendrochronological and spectral indices from 1984 to 2020 at both tree and stand levels, respectively, of a drought-prone Mediterranean Pinus pinea forest currently suffering strong dieback. We test the influence of climate on temporal patterns of tree radial growth, greenness and wetness spectral indices; and we address the influence of major drought episodes on resilience metrics. Tree-ring data and spectral indices followed different spatio-temporal patterns over the study period (1984–2020). Combined information from tree growth and spectral trajectories suggests that a reduction in tree density during the mid-1990s could have promoted tree growth and reduced dieback risk. Additionally, over the last decade, extreme and recurrent droughts have resulted in crown defoliation greater than 40% in most plots since 2019. We found that tree growth and the greenness spectral index were positively related to annual precipitation, while the wetness index was positively related to mean annual temperature. The response to drought, however, was stronger for tree growth than for spectral indices. Our study demonstrates the value of long-term retrospective multiscale analyses including tree and stand-level scales to disentangle mechanisms triggering and driving forest dieback.

Estimating the impact of COVID-19 pandemic on alternative semi-intensive shrimp (Penaeus vannamei) production schedules in Mexico: a stochastic bioeconomic approach - Javier M. J. Ruiz-Velazco; Margarita Estrada-Perez; Nallely Estrada-Perez; Alfredo Hernández-Llamas (Aquaculture International, 2022)

Preliminary study on the fresh and mechanical properties of UHPC made with recycled UHPC aggregates - Marta Roig-Flores; Ruben Paul Borg; Cecilia Ruiz-Muñoz; Eduardo J. Mezquida-Alcaraz; Ester Giménez-Carbó; Albany Milena Lozano Násner; Pedro Serna (European Journal of Environmental and Civil Engineering, 2022)

Killer whales of the Strait of Gibraltar, an endangered subpopulation showing a disruptive behavior - Ruth Esteban; Alfredo López; Álvaro Garcia de los Rios; Marisa Ferreira; Francisco Martinho; Paula Méndez‐Fernandeza; Ezequiel Andréu; José C. García‐Gómez; Liliana Olaya‐Ponzone; Rocío Espada‐Ruiz; Francisco J. Gil‐Vera; Cristina Martín Bernal; et al. (Marine Mammal Science, 2022)

Effect of low‐dose Piscirickettsia salmonis infection on haematological‐biochemical blood parameters in Atlantic salmon ( Salmo salar ) - Adolfo Isla; Patricio Sánchez; Pamela Ruiz; Romina Albornoz; Juan P. Pontigo; María Cecilia Rauch; Christopher Hawes; Luis Vargas‐Chacoff; Alejandro J. Yáñez (Journal of Fish Biology, 2022)
Piscirickettsia salmonis is the etiological agent of Piscirickettsiosis, a severe disease that affects Atlantic salmon ( Salmo salar ) farmed in Chile and many other areas (Norway, Scotland, Ireland, Canada and the USA). This study investigated the effects of low‐dose P. salmonis infection (1 × 10 2 CFU/ml) on Atlantic salmon. In this study, we challenged fish with an isolated representative of the EM‐90 genogroup via intraperitoneal injection for 42 days. Infected fish displayed decreased haematocrit and haemoglobin levels at day 13 post‐infection, indicating erythropenia, haemolysis and haemodilution. Conversely, their white blood cell counts increased on days 13 and 21 post‐infection. Additionally, their iron levels decreased from day 2 post‐infection, indicating iron deficiency and an inability to retrieve stored iron before infection. Their magnesium levels also decreased at day 28 post‐infection, possibly due to osmoregulatory problems. Also, we observed an increase in lactate dehydrogenase activity on days 5, 21, and 28 post‐infection, suggesting early symptoms of hepatotoxicity. Later analyses determined a decrease in plasma glucose levels from day 2 post‐infection. This may be attributed to the hypoxic conditions caused by P. salmonis , leading to an excess utilization of stored carbohydrates. Our results suggest that the blood parameters we studied are useful for monitoring the physiological status of Atlantic salmon infected with P. salmonis .

The role of spray-drying atmosphere on fridericia chica (bonpl.) L.G. Lohmann standardized extract production for wound healing activity - Ilza Maria de Oliveira Sousa; Gerardo Alvarez Rivera; Diana Pinto; Nubia de Cássia Almeida Queiroz; Veronica Isabel Correia Bastos; Lucia Elaine O. Braga; Josman Dantas Palmeira; Helena Amaral; Helena Maria Neto Ferreira; Helena Cristina Correia Oliveira; Fernando J. Mendes Gonçalves; Ana Lucia T.G Ruiz; et al. (Natural Product Research, 2022)

Rainwater treatment: an approach for drinking water provision to indigenous people in Ecuadorian Amazon - E. Pineda; D. Guaya; G. Rivera; M. J. García-Ruiz; F. Osorio (International Journal of Environmental Science and Technology, 2022)
This study is about the use of naturally occurring filtering materials for rainwater treatment for drinking water proposal. Crushed gravel, ceramic spheres from natural clays, silica sand and natural zeolite were used as filtering materials. The mineralogical composition of filtering materials was determined, being the illite and mordenite the major components of ceramic spheres and natural zeolite, respectively. Naturally occurring materials were simultaneous evaluated on two configuration of pilot plant systems (biofilters) for rainwater treatment. Three columns were arranged in series with unstratified flooded beds. The first stage was packed using crushed gravel. The second stage was packed using ceramic spheres. The third stage was packed with silica sand for the first plant and a natural zeolite was used for the second pilot plant system. Finally, a last stage of ultraviolet disinfection was incorporated. The trial period was 90 days, and it was evaluated the removal of Fe +2 and Mn +2 , total coliforms, faecal coliforms and Escherichia col ( E. coli ). The rainwater treatment system using natural zeolite provided better results than the one using silica sand at third stage. The concentration of Fe +2 and Mn +2 was below the maximum permissible limits within 45 days. The efficiency of the treatment systems was optimal within 45 days, after the efficiency decreased progressively. Then, it is an attractive proposal for rural areas in developing countries for single-family water treatment systems.

Mendelian nightmares: the germline-restricted chromosome of songbirds - Pavel Borodin; Augustin Chen; Wolfgang Forstmeier; Simone Fouché; Lyubov Malinovskaya; Yifan Pei; Radka Reifová; Francisco J. Ruiz-Ruano; Stephen A. Schlebusch; Manuelita Sotelo-Muñoz; Anna Torgasheva; Niki Vontzou; et al. (Chromosome Research, 2022)
Germline-restricted chromosomes (GRCs) are accessory chromosomes that occur only in germ cells. They are eliminated from somatic cells through programmed DNA elimination during embryo development. GRCs have been observed in several unrelated animal taxa and show peculiar modes of non-Mendelian inheritance and within-individual elimination. Recent cytogenetic and phylogenomic evidence suggests that a GRC is present across the species-rich songbirds, but absent in non-passerine birds, implying that over half of all 10,500 bird species have extensive germline/soma genome differences. Here, we review recent insights gained from genomic, transcriptomic, and cytogenetic approaches with regard to the genetic content, phylogenetic distribution, and inheritance of the songbird GRC. While many questions remain unsolved in terms of GRC inheritance, elimination, and function, we discuss plausible scenarios and future directions for understanding this widespread form of programmed DNA elimination.

Soil macroinvertebrate communities: A world‐wide assessment - Patrick Lavelle; Jérôme Mathieu; Alister Spain; George Brown; Carlos Fragoso; Emmanuel Lapied; Adriana De Aquino; Isabelle Barois; Edmundo Barrios; Maria Eleusa Barros; Jose Camilo Bedano; Eric Blanchart; et al. (Global Ecology and Biogeography, 2022)
Aim Macroinvertebrates comprise a highly diverse set of taxa with great potential as indicators of soil quality. Communities were sampled at 3,694 sites distributed world‐wide. We aimed to analyse the patterns of abundance, composition and network characteristics and their relationships to latitude, mean annual temperature and rainfall, land cover, soil texture and agricultural practices. Location Sites are distributed in 41 countries, ranging from 55° S to 57° N latitude, from 0 to 4,000 m in elevation, with annual rainfall ranging from 500 to >3,000 mm and mean temperatures of 5–32°C. Time period 1980–2018. Major taxa studied All soil macroinvertebrates: Haplotaxida; Coleoptera; Formicidae; Arachnida; Chilopoda; Diplopoda; Diptera; Isoptera; Isopoda; Homoptera; Hemiptera; Gastropoda; Blattaria; Orthoptera; Lepidoptera; Dermaptera; and “others”. Methods Standard ISO 23611‐5 sampling protocol was applied at all sites. Data treatment used a set of multivariate analyses, principal components analysis (PCA) on macrofauna data transformed by Hellinger’s method, multiple correspondence analysis for environmental data (latitude, elevation, temperature and average annual rainfall, type of vegetation cover) transformed into discrete classes, coinertia analysis to compare these two data sets, and bias‐corrected and accelerated bootstrap tests to evaluate the part of the variance of the macrofauna data attributable to each of the environmental factors. Network analysis was performed. Each pairwise association of taxonomic units was tested against a null model considering local and regional scales, in order to avoid spurious correlations. Results Communities were separated into five clusters reflecting their densities and taxonomic richness. They were significantly influenced by climatic conditions, soil texture and vegetation cover. Abundance and diversity, highest in tropical forests (1,895 ± 234 individuals/m 2 ) and savannahs (1,796 ± 72 individuals/m 2 ), progressively decreased in tropical cropping systems (tree‐associated crops, 1,358 ± 120 individuals/m 2 ; pastures, 1,178 ± 154 individuals/m 2 ; and annual crops, 867 ± 62 individuals/m 2 ), temperate grasslands (529 ± 60 individuals/m 2 ), forests (232 ± 20 individuals/m 2 ) and annual crops (231 ± 24 individuals/m 2 ) and temperate dry forests and shrubs (195 ± 11 individuals/m 2 ). Agricultural management decreased overall abundance by ≤54% in tropical areas and 64% in temperate areas. Connectivity varied with taxa, with dominant positive connections in litter transformers and negative connections with ecosystem engineers and Arachnida. Connectivity and modularity were higher in communities with low abundance and taxonomic richness. Main conclusions Soil macroinvertebrate communities respond to climatic, soil and land‐cover conditions. All taxa, except termites, are found everywhere, and communities from the five clusters cover a wide range of geographical and environmental conditions. Agricultural practices significantly decrease abundance, although the presence of tree components alleviates this effect.

Kinetic Modeling of Cd(II) and Pb(II) Biosorption from Aqueous Solution by Inactive Biomass of Nannochloropsis oculata Microalgae - Omar Nateras-Ramírez; Jaime López-Cervantes; Dalia I. Sánchez-Machado; Rocio J. Aguilar-Ruiz; María R. Martínez-Macias (Water, Air, & Soil Pollution, 2022)

Epigenetic clock and methylation studies in marsupials: opossums, Tasmanian devils, kangaroos, and wallabies - Steve Horvath; Amin Haghani; Joseph A. Zoller; Ken Raj; Ishani Sinha; Todd R. Robeck; Pete Black; Aidan Couzens; Clive Lau; Meghety Manoyan; Yadiamaris Aviles Ruiz; Annais Talbott; et al. (GeroScience, 2022)
The opossum ( Monodelphis domestica ), with its sequenced genome, ease of laboratory care and experimental manipulation, and unique biology, is the most used laboratory marsupial. Using the mammalian methylation array, we generated DNA methylation data from n = 100 opossum samples from the ear, liver, and tail. We contrasted postnatal development and later aging effects in the opossum methylome with those in mouse ( Mus musculus , C57BL/6 J strain) and other marsupial species such as Tasmanian devil, kangaroos, and wallabies. While the opossum methylome is similar to that of mouse during postnatal development, it is distinct from that shared by other mammals when it comes to the age-related gain of methylation at target sites of polycomb repressive complex 2. Our immunohistochemical staining results provide additional support for the hypothesis that PRC2 activity increases with later aging in mouse tissues but remains constant in opossum tissues. We present several epigenetic clocks for opossums that are distinguished by their compatibility with tissue type (pan-tissue and blood clock) and species (opossum and human). Two dual-species human-opossum pan-tissue clocks accurately measure chronological age and relative age, respectively. The human-opossum epigenetic clocks are expected to provide a significant boost to the attractiveness of opossum as a biological model. Additional epigenetic clocks for Tasmanian devil, red kangaroos and other species of the genus Macropus may aid species conservation efforts.

Regional climate modeling of the diurnal cycle of precipitation and associated atmospheric circulation patterns over an Andean glacier region (Antisana, Ecuador) - C. Junquas; M. B. Heredia; T. Condom; J. C. Ruiz-Hernández; L. Campozano; J. Dudhia; J. C. Espinoza; M. Menegoz; A. Rabatel; J. E. Sicart (Climate Dynamics, 2022)

Quality of Pellet Made from Agricultural and Forestry Waste in Mexico - A. Carrillo-Parra; J. G. Rutiaga-Quiñones; J. C. Ríos-Saucedo; V. M. Ruiz-García; M. Ngangyo-Heya; C. A. Nava-Berumen; V. D. Núñez-Retana (BioEnergy Research, 2022)

The understanding of phytopathogens as a tool in the conservation of heroic viticulture areas - J. Antonio Cortiñas; María Fernández-González; Rosa A. Vázquez-Ruiz; M. Jesús Aira; F. Javier Rodríguez-Rajo (Aerobiologia, 2022)

Rockfalls: analysis of the block fragmentation through field experiments - J. A. Gili; R. Ruiz-Carulla; G. Matas; J. Moya; A. Prades; J. Corominas; N. Lantada; M. A. Núñez-Andrés; F. Buill; C. Puig; J. Martínez-Bofill; Ll. Saló; et al. (Landslides, 2022)
Fragmentation is a common feature of rockfall that exerts a strong control on the trajectories of the generated blocks, the impact energies, and the runout. In this paper, we present a set of four real-scale rockfall tests aimed at studying the fragmentation of the rocky blocks, from the global design of the field procedure to the data analysis and the main results. A total of 124 limestone, dacite, or granite blocks ranging between 0.2 and 5 m 3 were dropped from different heights (8.5 to 23.6 m) onto four slopes with different shapes (single or double bench) and slope angles (42º to 71º). The characteristics of the blocks, in particular the size, surface texture and joint condition, were measured before the drops. The trajectories of the blocks and both the initial and the impact velocities were tracked and recorded by means of three high-speed video cameras. A total of 200 block-to-ground impacts have been studied. On average, 40% of the blocks broke upon impact on the slope or on the ground, making it necessary to measure the fragments. The initial and final sizes of the blocks/fragments were measured by hand with tape, though photogrammetric techniques (UAV and terrestrial) were also used for comparison purposes. The information gathered during the field tests provides a deep insight into the fragmentation processes. On the one hand, the high-resolution slow-motion videos help to describe when and how the block breakage takes place and the spatial distribution of the pieces. On the other hand, it is possible to compute the block trajectories, the velocities, and the energy losses using videogrammetry. The results include, for instance, a block average fragmentation of 54% and 14% for the limestone and granitoids, respectively; the systematic inventory of the size fragments, which may be used for fitting the power law distributions; and after each breakage, the total angle of aperture occupied by the fragments has been measured, with values in the range 25º–145º. To figure out the different behavior of the blocks in terms of breakage/no breakage, each block-to-ground impact has been characterized with a set of parameters describing the energy level, the robustness of the substrate, and the configuration of the block contact at the impact point, among others. All these terms are combined in a function F , which is used to adjust the field data. The adjustment has been carried out, first, for the whole 200 events and later for a subset of them. The procedure and the results are described in the paper. Although the discrimination capability of F is moderately satisfactory, it is very sensitive to the test site and setup. It must be highlighted that these field tests are a unique source of data to adjust the parameters of the numerical simulation models in use for rockfall studies and risk mitigation, especially when fragmentation during the propagation is considered.

Monitoring metallothionein-like protein concentrations and cholinesterase activity in tropical cup oysters as biomarkers of exposure to metals and pesticides in the southern Caribbean, Colombia - Angela M. Moncaleano-Niño; Maria Camila Gómez-Cubillos; Andrea Luna-Acosta; Luisa Villamil; Samuel Casseres-Ruiz; Michael J. Ahrens (Environmental Science and Pollution Research, 2022)

The effect of polychaetes infestation on calcification rates and morphological changes in reef-building coral Porites lobata - J. J. Adolfo Tortolero-Langarica; Patricia Salazar-Silva; Estefanía Morales-Ruiz; Yuridia Curiel-Vizcarra; Juan P. Carricart-Ganivet (Symbiosis, 2022)

First international workshop of the ATM and cancer risk group (4-5 December 2019) - Fabienne Lesueur; Douglas F. Easton; Anne-Laure Renault; Sean V. Tavtigian; Jonine L. Bernstein; Zsofia Kote-Jarai; Rosalind A. Eeles; Dijana Plaseska-Karanfia; Lidia Feliubadaló; Alejandro Moles-Fernández; Marta Santamariña-Pena; Alysson T. Sánchez; et al. (Familial Cancer, 2022)

Recreational boats routinely transfer organisms and promote marine bioinvasions - Gail V. Ashton; Chela J. Zabin; Ian C. Davidson; Gregory M. Ruiz (Biological Invasions, 2022)

Parasite resistance and immunity across female castes in a social insect - Mario X. Ruiz-González; Michael Kelly; Yannick Moret; Mark J. F. Brown (Behavioral Ecology and Sociobiology, 2022)
Living in a social group increases the risks of parasitism, especially in highly-related groups. In homogenous groups, with no reproductive division of labour, the impact of parasitism is unlikely to vary with host identity. Many social systems, however, do exhibit division of reproductive labour, most famously in social insects with their reproductive queens and generally infertile workers. In such systems, the impact of parasitism will differ for each group. Consequently, we predict that susceptibility to parasites will vary to reflect such differential impact. We tested this prediction using a trypanosome-bumble bee system, where Crithidia bombi infects both gynes and workers of Bombus terrestris . We studied both susceptibility to the parasite and relevant measures of the immune function. As predicted, gynes were significantly less susceptible to the parasite than workers, but while gynes and workers expressed different immune profiles, how these link to differential susceptibility remains unclear. In conclusion, our results suggest that differential selection pressures exerted by parasites may produce multiple phenotypes from a single genotype in order to maximise fitness in a social group context. Significance statement Social insect colonies dominate terrestrial ecology, and as such are targets for parasites. How they defend themselves against such threats is a key question. Here, we show that bumble bee gynes — the reproductive individuals that overwinter and found colonies in this annual social system — are more resistant to a parasite that disproportionately affects reproductive fitness than their sister workers. Differential patterns of susceptibility may help to explain the success of these social insects.

No evidence that grooming is exchanged for coalitionary support in the short- or long-term via direct or generalized reciprocity in unrelated rhesus macaques - William J. O’Hearn; Angelina Ruiz-Lambides; Michael L. Platt; Lauren J. N. Brent (Behavioral Ecology and Sociobiology, 2022)
Reciprocity is a prominent explanation for cooperation between non-kin. Studies designed to demonstrate reciprocity often focus on direct reciprocity in the timescale of minutes to hours, whereas alternative mechanisms like generalized reciprocity and the possibility of reciprocation over longer timescales of months and years are less often explored. Using a playback experiment, we tested for evidence of direct and generalized reciprocity across short and longer timescales. We examined the exchange of grooming for coalitionary support between unrelated female rhesus macaques in a population with a complete genetic pedigree. Females that received grooming were not more responsive to calls for coalitionary support from unrelated female group mates compared to control females that received agonism or no interaction — even when the call belonged to a females’ most recent grooming partner. Similarly, females were not more responsive to calls for support from their most frequent unrelated grooming partner of the last two years, nor if they received large amounts of grooming from all other females in their group. We interpret these results as an absence of evidence for direct or generalized reciprocity on any timescale in the exchange of grooming for coalitionary support in rhesus macaques. If grooming is exchanged for support in this population, it is with an intensity below our ability to detect it or over a longer timescale than we examined. We propose by-product explanations may also be at play and highlight the importance of investigating multiple mechanisms when testing apparently cooperative behaviors. Significance statement The receipt of help can make some animals more likely to provide help in return, whether it be a singular act, or many acts accumulated over months. Similarly, the receipt of help, be it one act of aid, or a group’s worth of help over time, can make some animals more likely to pay help forward to others. Studies on Old World monkeys suggest females may give grooming and in return receive aid in future physical conflicts. Using a playback experiment, we found female rhesus macaques were not more responsive to calls for intervention in a simulated conflict after being groomed by unrelated females, even if the calling combatant was her most recent, or a long-time grooming partner. Our results suggest females in our study population may be receiving benefits other than support in conflicts for the grooming they provide.

Translational Modeling Identifies Synergy between Nanoparticle-Delivered miRNA-22 and Standard-of-Care Drugs in Triple-Negative Breast Cancer - Prashant Dogra; Javier Ruiz Ramírez; Joseph D. Butner; Maria J. Peláez; Caroline Chung; Anupama Hooda-Nehra; Renata Pasqualini; Wadih Arap; Vittorio Cristini; George A. Calin; Bulent Ozpolat; Zhihui Wang (Pharmaceutical Research, 2022)
Purpose Downregulation of miRNA-22 in triple-negative breast cancer (TNBC) is associated with upregulation of eukaryotic elongation 2 factor kinase (eEF2K) protein, which regulates tumor growth, chemoresistance, and tumor immunosurveillance. Moreover, exogenous administration of miRNA-22, loaded in nanoparticles to prevent degradation and improve tumor delivery (termed miRNA-22 nanotherapy), to suppress eEF2K production has shown potential as an investigational therapeutic agent in vivo. Methods To evaluate the translational potential of miRNA-22 nanotherapy, we developed a multiscale mechanistic model, calibrated to published in vivo data and extrapolated to the human scale, to describe and quantify the pharmacokinetics and pharmacodynamics of miRNA-22 in virtual patient populations. Results Our analysis revealed the dose-response relationship, suggested optimal treatment frequency for miRNA-22 nanotherapy, and highlighted key determinants of therapy response, from which combination with immune checkpoint inhibitors was identified as a candidate strategy for improving treatment outcomes. More importantly, drug synergy was identified between miRNA-22 and standard-of-care drugs against TNBC, providing a basis for rational therapeutic combinations for improved response Conclusions The present study highlights the translational potential of miRNA-22 nanotherapy for TNBC in combination with standard-of-care drugs.

Fish morphology and passage through velocity barriers. Experience with northern straight-mouth nase (Pseudochondrostoma duriense Coelho, 1985) in an open channel flume - J. R. Sánchez-González; F. Morcillo; J. Ruiz-Legazpi; F. J. Sanz-Ronda (Hydrobiologia, 2022)
Knowing the relationship between size, morphological traits and swimming performance of fish is essential to understand the swimming capacity to successfully surpass these obstacles and the selective pressure that barriers in rivers and streams could exert on fish. Northern straight-mouth nase, an endemic potamodromous cyprinid fish species from the Northwest of the Iberian Peninsula, was selected to carry out volitionally swimming performance experiments in an open channel against three different flow velocities, using telemetry and video cameras. The use of thin-plate spline, on 10 landmarks, evidenced unknown patterns linked to velocity barriers. At lower flow velocity, size is the main factor explaining the swimming performance; thus, large individuals swim up more efficiently. In contrast, at high flow velocities, shape becomes the essential explanatory variable; thereby, streamlined body shapes with a higher relative position of the tail and a narrower caudal peduncle are more efficient. The obtained results show the existence of a relationship between fish morphology and swimming performance, with potential consequences due to selection pressures associated with velocity barriers and their implications on behavioural and dispersal processes. To sum up, velocity barriers could exert a selection pressure on nase populations, so the fishway design and removal should be (re)considered.

Predictive Factors of Chemical and Visual Sensory Organ Size: The Roles of Sex, Environment, and Evolution - M. R. Ruiz-Monachesi; C. S. Abdala; J. A. Schulte; F. B. Cruz (Evolutionary Biology, 2022)

Severe introduced predator impacts despite attempted functional eradication - Brian S. Cheng; Jeffrey Blumenthal; Andrew L. Chang; Jordanna Barley; Matthew C. Ferner; Karina J. Nielsen; Gregory M. Ruiz; Chela J. Zabin (Biological Invasions, 2022)

Response to “Practice what you preach: Ensuring scientific spheres integrate Indigenous Peoples’ and Local Communities’ rights and agency too” by Lopez-Maldonado - Victoria Reyes-García; Álvaro Fernández-Llamazares; Yildiz Aumeeruddy-Thomas; Petra Benyei; Rainer W. Bussmann; David García-del-Amo; Natalia Hanazaki; Ana C. Luz; Pamela McElwee; Vicky J. Meretsky; Zsolt Molnár; Isabel Ruiz-Mallén; et al. (Ambio, 2022)

Airborne bacterial community associated with fine particulate matter (PM2.5) under different air quality indices in Temuco city, southern Chile - Jacquelinne J. Acuña; Tay Ruiz-Gil; Luis Marileo; Elizabeth Carrazana; Joaquin Rilling; Marco Campos; Francisco Correa-Araneda; So Fujiyoshi; Milko A. Jorquera (Archives of Microbiology, 2022)

Next‐generation phylogeography resolves post‐glacial colonization patterns in a widespread carnivore, the red fox ( Vulpes vulpes ), in Europe - Allan D. McDevitt; Ilaria Coscia; Samuel S. Browett; Aritz Ruiz‐González; Mark J. Statham; Iwona Ruczyńska; Liam Roberts; Joanna Stojak; Alain C. Frantz; Karin Norén; Erik O. Ågren; Jane Learmount; et al. (Molecular Ecology, 2022)
Carnivores tend to exhibit a lack of (or less pronounced) genetic structure at continental scales in both a geographic and temporal sense and this can confound the identification of post‐glacial colonization patterns in this group. In this study we used genome‐wide data (using genotyping by sequencing [GBS]) to reconstruct the phylogeographic history of a widespread carnivore, the red fox ( Vulpes vulpes ), by investigating broad‐scale patterns of genomic variation, differentiation and admixture amongst contemporary populations in Europe. Using 15,003 single nucleotide polymorphisms (SNPs) from 524 individuals allowed us to identify the importance of refugial regions for the red fox in terms of endemism (e.g., Iberia). In addition, we tested multiple post‐glacial recolonization scenarios of previously glaciated regions during the Last Glacial Maximum using an Approximate Bayesian Computation (ABC) approach that were unresolved from previous studies. This allowed us to identify the role of admixture from multiple source population post‐Younger Dryas in the case of Scandinavia and ancient land‐bridges in the colonization of the British Isles. A natural colonization of Ireland was deemed more likely than an ancient human‐mediated introduction as has previously been proposed and potentially points to a larger mammalian community on the island in the early post‐glacial period. Using genome‐wide data has allowed us to tease apart broad‐scale patterns of structure and diversity in a widespread carnivore in Europe that was not evident from using more limited marker sets and provides a foundation for next‐generation phylogeographic studies in other non‐model species.

Global genotype by environment trends in growth traits for Eucalyptus dunnii - Michael G. Bird; Craig M. Hardner; Mark Dieters; Mónica Heberling; Cristian Montouto; Roger J. Arnold; Federico Ruiz; Juan Schapovaloff; Peter L. Gore (New Forests, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Effect of Activated Carbon in Thin Sand Caps Challenged with Ongoing PCB Inputs from Sediment Deposition: PCB Uptake in Clams (Mercenaria mercenaria) and Passive Samplers - Philip T. Gidley; Guilherme R. Lotufo; Alan J. Kennedy; Nicolas L. Melby; Allyson H. Wooley; Charles H. Laber; Robert M. Burgess; Carlos E. Ruiz; Todd S. Bridges (Archives of Environmental Contamination and Toxicology, 2022)

Recognizing Indigenous peoples’ and local communities’ rights and agency in the post-2020 Biodiversity Agenda - Victoria Reyes-García; Álvaro Fernández-Llamazares; Yildiz Aumeeruddy-Thomas; Petra Benyei; Rainer W. Bussmann; Sara K. Diamond; David García-del-Amo; Sara Guadilla-Sáez; Natalia Hanazaki; Nicolas Kosoy; Margarita Lavides; Ana C. Luz; et al. (Ambio, 2022)
The Convention on Biological Diversity is defining the goals that will frame future global biodiversity policy in a context of rapid biodiversity decline and under pressure to make transformative change. Drawing on the work of Indigenous and non-Indigenous scholars, we argue that transformative change requires the foregrounding of Indigenous peoples’ and local communities’ rights and agency in biodiversity policy. We support this argument with four key points. First, Indigenous peoples and local communities hold knowledge essential for setting realistic and effective biodiversity targets that simultaneously improve local livelihoods. Second, Indigenous peoples’ conceptualizations of nature sustain and manifest CBD’s 2050 vision of “Living in harmony with nature.” Third, Indigenous peoples’ and local communities’ participation in biodiversity policy contributes to the recognition of human and Indigenous peoples’ rights. And fourth, engagement in biodiversity policy is essential for Indigenous peoples and local communities to be able to exercise their recognized rights to territories and resources.

Development, nutrition, and rearing practices of relevant catfish species (Siluriformes) at early stages - Enric Gisbert; Ronald Kennedy Luz; Ignacio Fernández; Pravata K. Pradhan; Maria Salhi; Mansour T. Mozanzadeh; Aditya Kumar; Yannis Kotzamanis; Diana Castro‐Ruiz; Martin Bessonart; Maria J. Darias (Reviews in Aquaculture, 2022)
Catfish (Siluriformes) are important species for aquaculture worldwide, with an annual production in 2018 of ca . 6 million t. This review focuses on reassessing larval development, first feeding, and early rearing practices of the most important farmed catfish species, along with some candidate species for aquaculture diversification: Pangasianodon hypophthalmus (Pangasiidae), Clarias gariepinus (Clariidae), Ictalurus punctatus (Ictaluridae), Pseudoplatystoma spp. (Pimelodidae), Heteropneustes fossilis (Heteropneustidae), Rhamdia quelen (Heptapteridae), Ompok bimaculatus (Siluridae), and Lophiosilurus alexandri (Pseudopimelodidade). These species are initially reared indoors from one day to two weeks and are then transferred to fertilised outdoor ponds where they either feed on natural zooplankton or compound feeds. With the exception of C. gariepinus , I. punctatus , R. quelen and P. hypophthalmus , consistent and reliable fry production is a bottleneck that limits the expansion of farming of other species, such as Pseudoplatystoma spp., H. fossilis , O. bimaculatus , and L. alexandri . Rearing systems (extensive, semi‐extensive, intensive) and feeding protocols vary with species and geographical regions. Cannibalism and size heterogeneity are common, and these features create problems for larval and fry rearing of catfish species. Information about their nutritional requirements is required for the formulation of compound feeds that can guarantee high survival and good growth of catfish fries. However, such knowledge for most species is scarce, although some data are available for I. punctatus . Further genomic resources might allow fine‐tuning rearing success. This review describes some successes in this field, and also highlights gaps in knowledge to guide future research that can promote the development of catfish aquaculture.

Intra-Annual Variation in Mesophotic Benthic Assemblages on the Insular Slope of Southwest Puerto Rico as a Function of Depth and Geomorphology - Richard S. Appeldoorn; David L. Ballantine; Milton Carlo; Juan J. Cruz Motta; Michael Nemeth; Hector J. Ruiz; Nikolaos V. Schizas; Clark E. Sherman; Ernesto Weil; Paul M. Yoshioka (Frontiers in Marine Science, 2021)
There is limited information on the intra-annual variability of mesophotic coral ecosystems (MCEs), worldwide. The benthic communities, measured as % cover, of two geomorphologically different mesophotic sites (El Hoyo and Hole-in-the-Wall) were examined during 2009–2010 in southwest Puerto Rico. Depths sampled were 50 and 70 m. At each site/depth combination, two permanent transects, measuring 10-m long by 40-cm wide, were surveyed by successive photoquadrants, 0.24 m 2 in area. Scleractinian corals, octocorals, macroalgae, crustose coralline algae (CCA), sponges and unconsolidated sediment were the main components along the transects. Significant community differences were observed both among sites and among depths. Differences among sites were greater at 50 m than at 70 m. The El Hoyo site at 50 m was the most divergent, and this was due to a lower coral and sponge cover and a higher algal cover ( Amphiroa spp., Peyssonnelia iridescens , turf) relative to the other site/depth combinations. As a consequence, the differences in community structure with depth were larger at El Hoyo than at Hole-in-the-Wall. The communities at 70 m were distinguished from those at 50 m by the greater proportion of the corals Agaricia undata, Madracis pharensis and CCA, and a reduced cover of the cyanobacterium Schizothrix . Temporal variation in the benthic assemblages was documented throughout the year. For both mesophotic sites, the magnitude of change at 50 m was significantly greater than at 70 m. For both depths, the magnitude of change at El Hoyo was significantly greater than at Hole-in-the-Wall. All assemblages experienced almost the same temporal patterns, despite the differences in species composition across sites and depths. Changes in temporal patterns are driven by an increase in the percent cover of the macroalgae Dictyota spp., and a decrease in the percent cover of non-colonized substrata (sand, pavement or rubble). Relatively rapid, intra-annual changes are dictated by the negative correlation between cyclic Dictyota spp. cover and open substrata cover. Other observed mechanisms for rapid community changes in the photoquadrants were diseases and collapses of substrata along with their associated fauna indicating that small-scale disturbance processes may play an important role within MCEs.

Stimulation of brown adipose tissue by polyphenols in extra virgin olive oil - L. Melguizo Rodríguez; R. Illescas-Montes; V. J. Costela-Ruiz; O. García-Martínez (Critical Reviews in Food Science and Nutrition, 2021)

A comparison of ranking filter methods applied to the estimation of NO2 concentrations in the Bay of Algeciras (Spain) - Javier González-Enrique; Juan Jesús Ruiz-Aguilar; José Antonio Moscoso-López; Daniel Urda; Ignacio J. Turias (Stochastic Environmental Research and Risk Assessment, 2021)

ASL expression in ALDH1A1+ neurons in the substantia nigra metabolically contributes to neurodegenerative phenotype - Shaul Lerner; Raya Eilam; Lital Adler; Julien Baruteau; Topaz Kreiser; Michael Tsoory; Alexander Brandis; Tevie Mehlman; Mina Ryten; Juan A. Botia; Sonia Garcia Ruiz; Alejandro Cisterna Garcia; et al. (Human Genetics, 2021)
Argininosuccinate lyase (ASL) is essential for the NO-dependent regulation of tyrosine hydroxylase (TH) and thus for catecholamine production. Using a conditional mouse model with loss of ASL in catecholamine neurons, we demonstrate that ASL is expressed in dopaminergic neurons in the substantia nigra pars compacta, including the ALDH1A1 + subpopulation that is pivotal for the pathogenesis of Parkinson disease (PD). Neuronal loss of ASL results in catecholamine deficiency, in accumulation and formation of tyrosine aggregates, in elevation of α-synuclein, and phenotypically in motor and cognitive deficits. NO supplementation rescues the formation of aggregates as well as the motor deficiencies. Our data point to a potential metabolic link between accumulations of tyrosine and seeding of pathological aggregates in neurons as initiators for the pathological processes involved in neurodegeneration. Hence, interventions in tyrosine metabolism via regulation of NO levels may be therapeutic beneficial for the treatment of catecholamine-related neurodegenerative disorders.

Global evidence of constraints and limits to human adaptation - Adelle Thomas; Emily Theokritoff; Alexandra Lesnikowski; Diana Reckien; Kripa Jagannathan; Roger Cremades; Donovan Campbell; Elphin Tom Joe; Asha Sitati; Chandni Singh; Alcade C. Segnon; Brian Pentz; et al. (Regional Environmental Change, 2021)
Constraints and limits to adaptation are critical to understanding the extent to which human and natural systems can successfully adapt to climate change. We conduct a systematic review of 1,682 academic studies on human adaptation responses to identify patterns in constraints and limits to adaptation for different regions, sectors, hazards, adaptation response types, and actors. Using definitions of constraints and limits provided by the Intergovernmental Panel on Climate Change (IPCC), we find that most literature identifies constraints to adaptation but that there is limited literature focused on limits to adaptation. Central and South America and Small Islands generally report greater constraints and both hard and soft limits to adaptation. Technological, infrastructural, and ecosystem-based adaptation suggest more evidence of constraints and hard limits than other types of responses. Individuals and households face economic and socio-cultural constraints which also inhibit behavioral adaptation responses and may lead to limits. Finance, governance, institutional, and policy constraints are most prevalent globally. These findings provide early signposts for boundaries of human adaptation and are of high relevance for guiding proactive adaptation financing and governance from local to global scales.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Diagnosing hospital bacteraemia in the framework of predictive, preventive and personalised medicine using electronic health records and machine learning classifiers - Oscar Garnica; Diego Gómez; Víctor Ramos; J. Ignacio Hidalgo; José M. Ruiz-Giardín (EPMA Journal, 2021)
Background The bacteraemia prediction is relevant because sepsis is one of the most important causes of morbidity and mortality. Bacteraemia prognosis primarily depends on a rapid diagnosis. The bacteraemia prediction would shorten up to 6 days the diagnosis, and, in conjunction with individual patient variables, should be considered to start the early administration of personalised antibiotic treatment and medical services, the election of specific diagnostic techniques and the determination of additional treatments, such as surgery, that would prevent subsequent complications. Machine learning techniques could help physicians make these informed decisions by predicting bacteraemia using the data already available in electronic hospital records. Objective This study presents the application of machine learning techniques to these records to predict the blood culture’s outcome, which would reduce the lag in starting a personalised antibiotic treatment and the medical costs associated with erroneous treatments due to conservative assumptions about blood culture outcomes. Methods Six supervised classifiers were created using three machine learning techniques, Support Vector Machine, Random Forest and K-Nearest Neighbours, on the electronic health records of hospital patients. The best approach to handle missing data was chosen and, for each machine learning technique, two classification models were created: the first uses the features known at the time of blood extraction, whereas the second uses four extra features revealed during the blood culture. Results The six classifiers were trained and tested using a dataset of 4357 patients with 117 features per patient. The models obtain predictions that, for the best case, are up to a state-of-the-art accuracy of 85.9%, a sensitivity of 87.4% and an AUC of 0.93. Conclusions Our results provide cutting-edge metrics of interest in predictive medical models with values that exceed the medical practice threshold and previous results in the literature using classical modelling techniques in specific types of bacteraemia. Additionally, the consistency of results is reasserted because the three classifiers’ importance ranking shows similar features that coincide with those that physicians use in their manual heuristics. Therefore, the efficacy of these machine learning techniques confirms their viability to assist in the aims of predictive and personalised medicine once the disease presents bacteraemia-compatible symptoms and to assist in improving the healthcare economy.

In vitro screening and in vivo colonization pilot model of Lactobacillus plantarum LP5 and Campylobacter coli DSPV 458 in mice - M. J. Ruiz; M. V. Zbrun; M. L. Signorini; J. A. Zimmermann; L. P. Soto; M. R. Rosmini; L. S. Frizzo (Archives of Microbiology, 2021)

Invasion history shapes host transcriptomic response to a body‐snatching parasite - Zachary J. C. Tobias; Amy E. Fowler; April M. H. Blakeslee; John A. Darling; Mark E. Torchin; A. Whitman Miller; Gregory M. Ruiz; Carolyn K. Tepolt (Molecular Ecology, 2021)
By shuffling biogeographical distributions, biological invasions can both disrupt long‐standing associations between hosts and parasites and establish new ones. This creates natural experiments with which to study the ecology and evolution of host–parasite interactions. In estuaries of the Gulf of Mexico, the white‐fingered mud crab ( Rhithropanopeus harrisii ) is infected by a native parasitic barnacle, Loxothylacus panopaei (Rhizocephala), which manipulates host physiology and behaviour. In the 1960s, L . panopaei was introduced to the Chesapeake Bay and has since expanded along the southeastern Atlantic coast, while host populations in the northeast have so far been spared. We use this system to test the host's transcriptomic response to parasitic infection and investigate how this response varies with the parasite's invasion history, comparing populations representing (i) long‐term sympatry between host and parasite, (ii) new associations where the parasite has invaded during the last 60 years and (iii) naïve hosts without prior exposure. A comparison of parasitized and control crabs revealed a core response, with widespread downregulation of transcripts involved in immunity and moulting. The transcriptional response differed between hosts from the parasite's native range and where it is absent, consistent with previous observations of increased susceptibility in populations lacking exposure to the parasite. Crabs from the parasite's introduced range, where prevalence is highest, displayed the most dissimilar response, possibly reflecting immune priming. These results provide molecular evidence for parasitic manipulation of host phenotype and the role of gene regulation in mediating host–parasite interactions.

The effects of three types of exercise training on steroid hormones in physically inactive middle-aged adults: a randomized controlled trial - Manuel Dote-Montero; Alejandro De-la-O; Lucas Jurado-Fasoli; Jonatan R. Ruiz; Manuel J. Castillo; Francisco J. Amaro-Gahete (European Journal of Applied Physiology, 2021)

First evidence of fish nocardiosis in Mexico caused by Nocardia seriolae in farmed red drum ( Sciaenops ocellatus , Linnaeus) - Rodolfo Enrique del Rio‐Rodriguez; Jose Gustavo Ramirez‐Paredes; Sonia Araceli Soto‐Rodriguez; Yechiam Shapira; Mariana del Jesus Huchin‐Cortes; Judith Ruiz‐Hernandez; Monica Isela Gomez‐Solano; David J. Haydon (Journal of Fish Diseases, 2021)
Between August and December 2013, the offshore cages of a commercial marine farm culturing red drum Sciaenops ocellatus in Campeche Bay Mexico were affected by an outbreak of an ulcerative granulomatous disease with up to 70% cumulative mortality. Thirty‐one adults displaying open ulcers on the skin were submitted for diagnosis. At necropsy, multiple white‐yellowish nodules (0.1–0.5 cm in diameter) were present in all internal organs, where the kidney and the spleen were the most severely affected. Histopathology evinced typical systemic granulomatous formations. Gram and Ziehl–Neelsen stains on tissue imprints, bacterial swabs and tissue sections revealed Gram‐positive, acid‐fast, branching beaded long rod filamentous bacteria. Tissue samples resulted positive for nocardiosis with a Nocardia genus‐specific nested PCR. Definite identification at the species level and taxonomic positioning of the fastidious pathogen were achieved through a specific Nocardia seriolae PCR and by sequencing the gyrB gene of pure isolates. After administration of antibiotics during fry production, a posterior follow‐up monitoring (from 2014 to 2017) detected mild but recurrent outbreaks of the bacteria with no seasonality pattern. To the extent of our knowledge, this is the first report of piscine nocardiosis in Mexico and the first time this disease is detected in red drum.

Stronger predation intensity and impact on prey communities in the tropics - Amy L. Freestone; Mark E. Torchin; Laura J. Jurgens; Mariana Bonfim; Diana P. López; Michele F. Repetto; Carmen Schlöder; Brent J. Sewall; Gregory M. Ruiz (Ecology, 2021)
The hypothesis that biotic interactions strengthen toward lower latitudes provides a framework for linking community‐scale processes with the macroecological scales that define our biosphere. Despite the importance of this hypothesis for understanding community assembly and ecosystem functioning, the extent to which interaction strength varies across latitude and the effects of this variation on natural communities remain unresolved. Predation in particular is central to ecological and evolutionary dynamics across the globe, yet very few studies explore both community‐scale causes and outcomes of predation across latitude. Here we expand beyond prior studies to examine two important components of predation strength: intensity of predation (including multiple dimensions of the predator guild) and impact on prey community biomass and structure, providing one of the most comprehensive examinations of predator–prey interactions across latitude. Using standardized experiments, we tested the hypothesis that predation intensity and impact on prey communities were stronger at lower latitudes. We further assessed prey recruitment to evaluate the potential for this process to mediate predation effects. We used sessile marine invertebrate communities and their fish predators in nearshore environments as a model system, with experiments conducted at 12 sites in four regions spanning the tropics to the subarctic. Our results show clear support for an increase in both predation intensity and impact at lower relative to higher latitudes. The predator guild was more diverse at low latitudes, with higher predation rates, longer interaction durations, and larger predator body sizes, suggesting stronger predation intensity in the tropics. Predation also reduced prey biomass and altered prey composition at low latitudes, with no effects at high latitudes. Although recruitment rates were up to three orders of magnitude higher in the tropics than the subarctic, prey replacement through this process was insufficient to dampen completely the strong impacts of predators in the tropics. Our study provides a novel perspective on the biotic interaction hypothesis, suggesting that multiple components of the predator community likely contribute to predation intensity at low latitudes, with important consequences for the structure of prey communities.

Occurrence but not intensity of mortality rises towards the climatic trailing edge of tree species ranges in European forests - Alexandre Changenet; Paloma Ruiz‐Benito; Sophia Ratcliffe; Thibaut Fréjaville; Juliette Archambeau; Annabel J. Porte; Miguel A. Zavala; Jonas Dahlgren; Aleksi Lehtonen; Marta Benito Garzón (Global Ecology and Biogeography, 2021)
Aim Tree mortality is increasing world‐wide, leading to changes in forest composition and altering global biodiversity. Nonetheless, owing to the multifaceted stochastic nature of tree mortality, large‐scale spatial patterns of mortality across species ranges and their underlying drivers remain difficult to understand. Our main goal was to describe the geographical patterns and drivers of the occurrence of mortality (presence of a mortality event) and the intensity of tree mortality (amount of mortality related to that mortality event) in Europe. We hypothesized that the occurrence of mortality represents background mortality and is higher in the margin than in core populations, whereas the intensity of mortality could have a more even distribution according to the spatial and temporal stochasticity of die‐off events. Location Europe (Spain, France, Germany, Belgium, Sweden and Finland). Major taxa studied More than 1.5 million trees belonging to 20 major forest tree species. Methods We developed binomial and truncated negative binomial models to tease apart the occurrence and intensity of tree mortality in National Forest Inventory plots at the range‐wide scale. The occurrence of mortality indicated that at least one tree had died in the plot, whereas the intensity of mortality referred to the number of dead trees per plot. Results The highest occurrence of mortality was found in peripheral regions and the climatic trailing edge linked with drought, whereas the intensity of mortality was driven by competition, drought and high temperatures and was scattered uniformly across species ranges. Main conclusions We show that tree background mortality, but not die‐off, is generally higher in the trailing‐edge populations. It remains to be explored whether other demographic traits, such as growth, reproduction and regeneration, also decrease at the trailing edge of European tree populations.

Neochloris oleoabundans oil production in an outdoor tubular photobioreactor at pilot scale - Niels-Henrik Norsker; Maria Cuaresma; Jeroen de Vree; Mari Carmen Ruiz-Domínguez; Maria Carmen Márquez García; Pauliina Uronen; Maria J. Barbosa; René Wijffels (Journal of Applied Phycology, 2021)
Oil production was tested with Neochloris oleoabundans in a 6 m 3 , horizontal soft sleeve tubular reactor from 22 October to 7 November in Matalascañas, southern Spain. Biomass productivity during the nitrogen replete phase was 7.4 g dw m −2 day −1 . Maximum lipid content in the biomass was 39% and average lipid productivity during the nitrogen depletion phase was 2.0 g m −2 day −1 . Nitrogen depletion of the cultures was carried out in order to enhance fatty acid formation, using the inverse nitrogen quota in the biomass to predict the fatty acid content. TFA concentration at harvest was 14% DW, compared to a value of 17%, predicted by the inverse nitrogen quota. The overall feasibility of the horizontal tubular technology for microalgal oil production, including mixing energy expenditure, was evaluated.

Mandibular muscle troponin of the Florida carpenter ant Camponotus floridanus: extending our insights into invertebrate Ca2+ regulation - Yun Shi; Julia P. Bethea; Hannah L. Hetzel-Ebben; Maicon Landim-Vieira; Ross J. Mayper; Regan L. Williams; Lauren E. Kessler; Amanda M. Ruiz; Kathryn Gargiulo; Jennifer S. M. Rose; Grayson Platt; Jose R. Pinto; et al. (Journal of Muscle Research and Cell Motility, 2021)

Red blood cell distribution width as mortality biomarker in patients with traumatic brain injury - Leonardo Lorente; María M. Martín; Candelaria Ruiz; Pedro Abreu-González; Antonia Pérez-Cejas; Agustín F. González-Rivero; Luis Ramos-Gómez; Mónica Argueso; Jordi Solé-Violán; Juan J. Cáceres; Alejandro Jiménez; Victor García-Marín (Acta Neurologica Belgica, 2021)

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Temporal changes in extreme precipitation and exposure of tourism in Eastern and South-Eastern Spain - Oliver Meseguer-Ruiz; Joan A. Lopez-Bustins; Laia Arbiol-Roca; Javier Martin-Vide; Javier Miró; María J. Estrela (Theoretical and Applied Climatology, 2021)

Spatial ecology of the stone marten in an Alpine area: combining camera-trapping and genetic surveys - A. Balestrieri; A. Mosini; F. Fonda; M. Piana; P. Tirozzi; A. Ruiz-González; E. Capelli; M. Vergara; L. J. Chueca; G. Chiatante; C. Movalli (Mammal Research, 2021)
A species’ potential distribution can be modelled adequately only if no factor other than habitat availability affects its occurrences. Space use by stone marten Martes foina is likely to be affected by interspecific competition with the strictly related pine marten Martes martes , the latter being able to outcompete the first species in forested habitats. Hence, to point out the environmental factors which determine the distribution and density of the stone marten, a relatively understudied mesocarnivore, we applied two non-invasive survey methods, camera-trapping and faecal-DNA based genetic analysis, in an Alpine area where the pine marten was deemed to be absent (Val Grande National Park N Italy). Camera trapping was conducted from October 2014 to November 2015, using up to 27 cameras. Marten scats were searched for between July and November 2015 and, to assess density, in spring 2017. Species identification was accomplished by a PCR-RFLP method, while 17 autosomal microsatellites were used for individual identification. The stone marten occurred in all available habitats (83% of trapping sites and 73.2% of scats); nonetheless, habitat suitability, as assessed using MaxEnt, depended on four major land cover variables—rocky grasslands, rocks and debris, beech forests and chestnut forests—, martens selecting forests and avoiding open rocky areas. Sixteen individuals were identified, of which 14 related to each other, possibly forming six different groups. Using capwire estimators, density was assessed as 0.95 (0.7–1.3) ind/km 2 . In the study area, the widespread stone marten selected forested areas, attaining density values like those reported for the pine marten in northern Europe and suggesting that patterns of habitat selection may depend on the relative abundance of the two competing martens.

The influence of vector‐borne disease on human history: socio‐ecological mechanisms - Tejas S. Athni; Marta S. Shocket; Lisa I. Couper; Nicole Nova; Iain R. Caldwell; Jamie M. Caldwell; Jasmine N. Childress; Marissa L. Childs; Giulio A. De Leo; Devin G. Kirk; Andrew J. MacDonald; Kathryn Olivarius; et al. (Ecology Letters, 2021)
Vector‐borne diseases (VBDs) are embedded within complex socio‐ecological systems. While research has traditionally focused on the direct effects of VBDs on human morbidity and mortality, it is increasingly clear that their impacts are much more pervasive. VBDs are dynamically linked to feedbacks between environmental conditions, vector ecology, disease burden, and societal responses that drive transmission. As a result, VBDs have had profound influence on human history. Mechanisms include: (1) killing or debilitating large numbers of people, with demographic and population‐level impacts; (2) differentially affecting populations based on prior history of disease exposure, immunity, and resistance; (3) being weaponised to promote or justify hierarchies of power, colonialism, racism, classism and sexism; (4) catalysing changes in ideas, institutions, infrastructure, technologies and social practices in efforts to control disease outbreaks; and (5) changing human relationships with the land and environment. We use historical and archaeological evidence interpreted through an ecological lens to illustrate how VBDs have shaped society and culture, focusing on case studies from four pertinent VBDs: plague, malaria, yellow fever and trypanosomiasis. By comparing across diseases, time periods and geographies, we highlight the enormous scope and variety of mechanisms by which VBDs have influenced human history.

How much leaf area do insects eat? A data set of insect herbivory sampled globally with a standardized protocol - Gisele M. Mendes; Fernando A. O. Silveira; Carolina Oliveira; Wesley Dáttilo; Roger Guevara; Betsabé Ruiz‐Guerra; Maria Gabriela Boaventura; Sershen; Syd Ramdhani; Shyam S. Phartyal; Sérvio P. Ribeiro; Victor Diniz Pinto; et al. (Ecology, 2021)
Herbivory is ubiquitous. Despite being a potential driver of plant distribution and performance, herbivory remains largely undocumented. Some early attempts have been made to review, globally, how much leaf area is removed through insect feeding. Kozlov et al., in one of the most comprehensive reviews regarding global patterns of herbivory, have compiled published studies regarding foliar removal and sampled data on global herbivory levels using a standardized protocol. However, in the review by Kozlov et al., only 15 sampling sites, comprising 33 plant species, were evaluated in tropical areas around the globe. In Brazil, which ranks first in terms of plant biodiversity, with a total of 46,097 species, almost half (43%) being endemic, a single data point was sampled, covering only two plant species. In an attempt to increase knowledge regarding herbivory in tropical plant species and to provide the raw data needed to test general hypotheses related to plant–herbivore interactions across large spatial scales, we proposed a joint, collaborative network to evaluate tropical herbivory. This network allowed us to update and expand the data on insect herbivory in tropical and temperate plant species. Our data set, collected with a standardized protocol, covers 45 sampling sites from nine countries and includes leaf herbivory measurements of 57,239 leaves from 209 species of vascular plants belonging to 65 families from tropical and temperate regions. They expand previous data sets by including a total of 32 sampling sites from tropical areas around the globe, comprising 152 species, 146 of them being sampled in Brazil. For temperate areas, it includes 13 sampling sites, comprising 59 species. Thus, when compared to the most recent comprehensive review of insect herbivory (Kozlov et al.), our data set has increased the base of available data for the tropical plants more than 460% (from 33 to 152 species) and the Brazilian sampling was increased 7,300% (from 2 to 146 species). Data on precise levels of herbivory are presented for more than 57,000 leaves worldwide. There are no copyright restrictions. Please cite this paper when using the current data in publications; the authors request to be informed how the data is used in the publications.

Molecular sexing of Xenarthra: a tool for genetic and ecological studies - Carmen Elena Barragán-Ruiz; Eliana Paviotti-Fischer; Karen Giselle Rodríguez-Castro; Arnaud L. J. Desbiez; Pedro Manoel Galetti (Conservation Genetics Resources, 2021)

Uncovering patterns of freshwater positive interactions using meta‐analysis: Identifying the roles of common participants, invasive species and environmental context - Lindsey K. Albertson; Michael J. MacDonald; Benjamin B. Tumolo; Michelle A. Briggs; Zachary Maguire; Sierra Quinn; Jose A. Sanchez‐Ruiz; Jaris Veneros; Laura A. Burkle (Ecology Letters, 2021)
Positive interactions are sensitive to human activities, necessitating synthetic approaches to elucidate broad patterns and predict future changes if these interactions are altered or lost. General understanding of freshwater positive interactions has been far outpaced by knowledge of these important relationships in terrestrial and marine ecosystems. We conducted a global meta‐analysis to evaluate the magnitude of positive interactions across freshwater habitats. In 340 studies, we found substantial positive effects, with facilitators increasing beneficiaries by, on average, 81% across all taxa and response variables. Mollusks in particular were commonly studied as both facilitators and beneficiaries. Amphibians were one group benefiting the most from positive interactions, yet few studies investigated amphibians. Invasive facilitators had stronger positive effects on beneficiaries than non‐invasive facilitators. We compared positive effects between high‐ and low‐stress conditions and found no difference in the magnitude of benefit in the subset of studies that manipulated stressors. Future areas of research include understudied facilitators and beneficiaries, the stress gradient hypothesis, patterns across space or time and the influence of declining taxa whose elimination would jeopardise fragile positive interaction networks. Freshwater positive interactions occur among a wide range of taxa, influence populations, communities and ecosystem processes and deserve further exploration.

Activity Patterns, Diet and Home Range of Night Monkeys (Aotus griseimembra and Aotus lemurinus) in Tropical Lowland and Mountain Forests of Central Colombia - Sebastián O. Montilla; Alex Mauricio Mopán-Chilito; Laura Natalia Sierra Murcia; Jonathan David Mahecha Triana; Otto Mauricio Caro Ruiz; Juanita Montoya-Cepeda; Daniela Alejandra Gutierrez-Barreto; Julie Alejandra Holguín-Vivas; Carlos J. Agámez; Luis Javier Pérez-Grisales; Mariana Cruz-Moncada; Nicole Juliana Corredor-Durango; et al. (International Journal of Primatology, 2021)

Compromised resting cerebral metabolism after sport-related concussion: A calibrated MRI study - Allen A. Champagne; Nicole S. Coverdale; Juan Fernandez-Ruiz; Clarisse I. Mark; Douglas J. Cook (Brain Imaging and Behavior, 2021)

Molecular histology of spermatogenesis in the Japanese macaque monkey (Macaca fuscata) - Sawako Okada; Kota Kuroki; Cody A. Ruiz; Anthony J. Tosi; Masanori Imamura (Primates, 2021)

The role of food transfers in wild golden lion tamarins (Leontopithecus rosalia): Support for the informational and nutritional hypothesis - Camille A. Troisi; William J. E. Hoppitt; Carlos R. Ruiz-Miranda; Kevin N. Laland (Primates, 2021)
Callitrichidae is a unique primate family not only in terms of the large number of food transfers to infants but also for the prevalence of transfers that are initiated by the adults. It has been hypothesized that, as well as provisioning infants, callitrichid food transfers might function to teach the receiver what food types to eat. If food provisioning has a teaching function, we would expect successful food transfers to be more likely with food types that are novel to the juveniles. We would also expect juveniles to learn about foods from those transfers. We introduced different types of food (some familiar, some novel) to wild groups of golden lion tamarins ( Leontopithecus rosalia ). While novel foods were not more successfully transferred than familiar food in the experiment, transfers were more successful (i.e., the receiver obtained food) when the donor had previous experience with that food. Moreover, we found evidence suggesting that food transfers influenced the future foraging choices of juveniles. Our findings are consistent with the first and third criteria of the functional definition of teaching, which requires that tutors (the adults) modify their behavior in the presence of a naïve individual (a juvenile), and that the naïve individual learns from the modified behavior of the demonstrator. Our findings are also consistent with the provisioning function of food transfer. Social learning seems to play an important role in the development of young tamarins’ foraging preferences.

The current situation and future perspectives of Quercus ilex and Pinus halepensis afforestation on agricultural land in Spain under climate change scenarios - L. Quinto; Rafael M. Navarro-Cerrillo; Guillermo Palacios-Rodriguez; F. Ruiz-Gómez; J. Duque-Lazo (New Forests, 2021)

Elimination of total coliforms and Escherichia coli from water by means of filtration with natural clays and silica sand in developing countries - Edgar Pineda; María J. García-Ruiz; Diana Guaya; John Manrique; Francisco Osorio (Environmental Geochemistry and Health, 2021)

Report of the fifth meeting of the European Consortium 'Care for CMMRD' (C4CMMRD), Leiden, The Netherlands, July 6th 2019 - M. Suerink; K. Wimmer; L. Brugieres; C. Colas; R. Gallon; T. Ripperger; P. R. Benusiglio; E. M. A. Bleiker; Z. Ghorbanoghli; Y. Goldberg; J. C. H. Hardwick; M. Kloor; et al. (Familial Cancer, 2021)

Ground validation of TRMM 3B43 V7 precipitation estimates over Colombia. Part I: Monthly and seasonal timescales - Sara M. Vallejo‐Bernal; Viviana Urrea; Juan M. Bedoya‐Soto; Daniela Posada; Alejandro Olarte; Yadira Cárdenas‐Posso; Franklyn Ruiz‐Murcia; María T. Martínez; Walter A. Petersen; George J. Huffman; Germán Poveda (International Journal of Climatology, 2021)
In this study, we validate precipitation estimates remotely sensed by the Tropical Rainfall Measuring Mission (TRMM) at monthly and seasonal timescales, during the period 1998–2015, by calculating and analyzing diverse error metrics between the 3B43 V7 product and in situ measurements from 1,180 rain gauges over Colombia, of which at least 987 are fully independent of TRMM. We explore the existence of spatiotemporal patterns to assess the performance of 3B43 V7 over the five major natural regions of Colombia: Caribbean, Pacific, Andes, Orinoco and Amazon. The results show that 3B43 V7 product is able to capture the phase of the annual cycle of monthly mean precipitation, but the performance is not good for the amplitude, in particular over the Andes and Pacific regions owing to complex climatic and topographic conditions. In general, 3B43 V7 exhibits good performance in the low‐lying and plain Amazon, Orinoco and Caribbean regions. Over the Andes region, characterized by complex topography, overestimation errors are identified [root mean squared error (RMSE) ≥83.59 mm·month −1 and relative bias (BIAS) ≥4.69%], whereas the extremely wet rainfall regime of the Pacific region is largely underestimated (RMSE ≥253.52 mm ·month −1 and BIAS ≤−11.75%). These errors are greater during the wet seasons when the metrics reach worse scores than those reported in similar studies worldwide. Occurrence analyses showed that 3B43 V7 misses very frequent light rainfall events and less frequent but very heavy storms, which contribute to the overall underestimation (overestimation) observed over the Pacific (Andes) region. The error characteristics identified and quantified in this study confirm the well‐documented limitations of remote precipitation sensing and constitute a warning about major challenges that complex climatic and physiographic features can impose on satellite rainfall missions.

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Beach Leveling Using a Remotely Piloted Aircraft System (RPAS): Problems and Solutions - Francisco Contreras-de-Villar; Francisco J. García; Juan J. Muñoz-Perez; Antonio Contreras-de-Villar; Veronica Ruiz-Ortiz; Patricia Lopez; Santiago Garcia-López; Bismarck Jigena (Journal of Marine Science and Engineering, 2020)
The size and great dynamism of coastal systems require faster and more automated mapping methods like the use of a remotely piloted aircraft system (RPAS) or unmanned aerial vehicle (UAV). This method allows for shorter intervals between surveys. The main problem for surveying using low-altitude digital photogrammetry in beach areas is their visual homogeneity. Obviously, the fewer the homologous points defined by the program, the lower the accuracy. Moreover, some factors influence the error performed in photogrammetric techniques, such as flight height, flight time, percentage of frame overlap (side and forward), and the number of ground control points (GCPs). A total of 72 different cases were conducted varying these factors, and the results were analyzed. Among the conclusions, it should be highlighted that the error for noon flights is almost double that for the early morning flights. Secondly, there is no appreciable difference regarding the side overlap. But, on the other side, RMSE increased to three times (from 0.05 to 0.15 m) when forward overlap decreased from 85% to 70%. Moreover, relative accuracy is 0.05% of the flying height which means a significant increase in error (66%) between flights performed at 60 and 100 m height). Furthermore, the median of the error for noon flights (0.12 m) is almost double that for the early morning flights (0.07 m) because of the higher percentage of grids with data for early flights. Therefore, beach levelings must never be performed at noon when carried out by RPAS. Eventually, a new parameter has been considered: the relationship between the number of GCPs and the surface to be monitored. A minimum value of 7 GCP/Ha should be taken into account when designing a beach leveling campaign using RPAS.

Studies on the bioactive flavonoids isolated from Azadirachta indica - Francisco Cen-Pacheco; Araceli Ortiz-Celiseo; Alvaro Peniche-Cardeña; Omar Bravo-Ruiz; Fernando C. López-Fentanes; Gerardo Valerio-Alfaro; José J. Fernández (Natural Product Research, 2020)

Phenolic profile and antioxidant activity of Euonymus japonicus Thunb. - Alba Ruiz-Riaguas; M. L. Fernández-de Córdova; Eulogio J. Llorent-Martínez (Natural Product Research, 2020)

Distribution and length composition of lemon sharks (Negaprion brevirostris) in a nursery ground in southern Cuba - Alexei Ruiz-Abierno; J. Fernando Márquez-Farías; Robert E. Hueter; Lázaro Macías-Romero; J. Manuel Barros-García; Lisandra García-Córdova; Andrés Hurtado; Valerie Miller (Environmental Biology of Fishes, 2020)
Characterization of essential habitat for sharks is a key requirement for effective conservation of shark populations. In Cuba, shark essential habitat is largely undocumented. Here we present the first study of a shark nursery area in Cuban waters, for the lemon shark. Nursery areas for lemon sharks are typically surrounded by mangroves and contain sandy substrate where the young can feed, grow, move, and eventually disperse from the area. We conducted our study in Cuba’s La Salina Wildlife Refuge during 2015–2019, to understand the role this refuge might play as a lemon shark nursery area, by documenting the distribution and length structure of juveniles. Our results indicate that juvenile lemon sharks are present throughout much of the refuge with no clear pattern of aggregation by size. The size range of all juveniles captured was 39.8–108.0 cm precaudal length (PCL) with a mode in length-class 70.0–75.0 cm PCL. The mean size and weight of all individuals during the study period was 75.8 cm PCL and 5.5 kg, respectively. We infrequently observed neonates in May, June, and September with size range 39.8–55.5 cm PCL. Enforcement of management regulations, difficult access to the refuge for fishers and other user groups, and isolation from human settlements are factors that help maintain nearly pristine conditions in La Salina Wildlife Refuge. The size/age structure of lemon sharks likely represents a population unaltered by human influence. We recommend our study be expanded to contribute to shark conservation and management as outlined in Cuba’s National Plan of Action for sharks.

Co-localized impaired regional cerebrovascular reactivity in chronic concussion is associated with BOLD activation differences during a working memory task - Nicole S. Coverdale; Juan Fernandez-Ruiz; Allen A. Champagne; Clarisse I. Mark; Douglas J. Cook (Brain Imaging and Behavior, 2020)

Influence of nutrient enrichment on the growth, recruitment and trophic ecology of a highly invasive freshwater fish - Ana Ruiz-Navarro; Michelle C. Jackson; David Almeida; J. Robert Britton (Aquatic Ecology, 2020)
The establishment probability of introduced alien fish can be context dependent, varying according to factors including propagule pressure and biotic resistance. The influence of nutrient enrichment on establishment outcomes of alien fishes is uncertain, yet this is a common anthropogenic stressor of many freshwaters. Here, the small-bodied alien topmouth gudgeon Pseudorasbora parva was used in mesocosms to experimentally test how a gradient of nutrient enrichment affected their growth rates, recruitment and trophic ecology. A ‘Control’ represented ambient, mesotrophic conditions, while treatments covered three levels of nutrient enrichment: low (eutrophic), medium (hypertrophic) and high (very hypertrophic). Each mesocosm was seeded with 6 mature P. parva (equal sex ratio) at the start of their reproductive season. After 100 days, length increments of the adult fish were significantly elevated in the low treatment, and these fish had also produced significantly higher numbers of 0+ fish compared to all other treatments. The trophic niche width of the mature fish was substantially higher in the control than the treatments, but this did not appear to confer any advantages to them in somatic growth rate or reproductive output. These results suggest that the nutrient status of receiving waters can have substantial impacts on the outcomes of fish introductions, where eutrophic conditions can assist the rapid population establishment of some alien species.

Slackwater Sediments Record the Increase in Sub-daily Rain Flood due to Climate Change in a European Mediterranean Catchment - J. D. Moral-Erencia; P. Bohorquez; P. J. Jimenez-Ruiz; F. J. Pérez-Latorre (Water Resources Management, 2020)

Urinary metabolic signatures reflect cardiovascular risk in the young, middle-aged, and elderly populations - Paula J. Martinez; Marta Agudiez; Dolores Molero; Marta Martin-Lorenzo; Montserrat Baldan-Martin; Aranzazu Santiago-Hernandez; Juan Manuel García-Segura; Felipe Madruga; Martha Cabrera; Eva Calvo; Gema Ruiz-Hurtado; Maria G Barderas; et al. (Journal of Molecular Medicine, 2020)
The predictive value of traditional cardiovascular risk estimators is limited, and young and elderly populations are particularly underrepresented. We aimed to investigate the urine metabolome and its association with cardiovascular risk to identify novel markers that might complement current estimators based on age. Urine samples were collected from 234 subjects categorized into three age-grouped cohorts: 30–50 years (cohort I, young), 50–70 years (cohort II, middle-aged), and > 70 years (cohort III, elderly). Each cohort was further classified into three groups: (a) control, (b) individuals with cardiovascular risk factors, and (c) those who had a previous cardiovascular event. Novel urinary metabolites linked to cardiovascular risk were identified by nuclear magnetic resonance in cohort I and then evaluated by target mass spectrometry quantification in all cohorts. A previously identified metabolic fingerprint associated with atherosclerosis was also analyzed and its potential risk estimation investigated in the three aged cohorts. Three different metabolic signatures were identified according to age: 2-hydroxybutyrate, gamma-aminobutyric acid, hypoxanthine, guanidoacetate, oxaloacetate, and serine in young adults; citrate, cyclohexanol, glutamine, lysine, pantothenate, pipecolate, threonine, and tyramine shared by middle-aged and elderly adults; and trimethylamine N-oxide and glucuronate associated with cardiovascular risk in all three cohorts. The urinary metabolome contains a metabolic signature of cardiovascular risk that differs across age groups. These signatures might serve to complement existing algorithms and improve the accuracy of cardiovascular risk prediction for personalized prevention. Key messages • Cardiovascular risk in the young and elderly is underestimated. • The urinary metabolome reflects cardiovascular risk across all age groups. • Six metabolites constitute a metabolic signature of cardiovascular risk in young adults. • Middle-aged and elderly adults share a cardiovascular risk metabolic signature. • TMAO and glucuronate levels reflect cardiovascular risk across all age groups.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Evaluation of dose-tapering strategies for intravenous tocilizumab in rheumatoid arthritis patients using model-based pharmacokinetic/pharmacodynamic simulations - Carla Bastida; Alwin D.R. Huitema; Merel J. l’Ami; Virginia Ruiz-Esquide; Gerrit Jan Wolbink; Raimon Sanmartí; Dolors Soy (European Journal of Clinical Pharmacology, 2020)

Genotyping-by-sequencing reveals the effects of riverscape, climate and interspecific introgression on the genetic diversity and local adaptation of the endangered Mexican golden trout (Oncorhynchus chrysogaster) - Marco A. Escalante; Charles Perrier; Francisco J. García-De León; Arturo Ruiz-Luna; Enrique Ortega-Abboud; Stéphanie Manel (Conservation Genetics, 2020)

Frequency spectra characterization of noncoding human genomic sequences - O. Paredes; Rebeca Romo-Vázquez; Israel Román-Godínez; Hugo Vélez-Pérez; Ricardo A. Salido-Ruiz; J. Alejandro Morales (Genes & Genomics, 2020)

Third time’s the charm: COVID-19 testing issues - Syed Nazeer Mahmood; Mishaal Talish; Daniel J. Wallach; Fred King; Sheena K. Ramdeen; Christian J. Woods; Maria Elena Ruiz (Infectious Diseases, 2020)

Comparative landscape genetics reveals differential effects of environment on host and pathogen genetic structure in Tasmanian devils ( Sarcophilus harrisii ) and their transmissible tumour - Christopher P. Kozakiewicz; Lauren Ricci; Austin H. Patton; Amanda R. Stahlke; Sarah A. Hendricks; Mark J. Margres; Manuel Ruiz‐Aravena; David G. Hamilton; Rodrigo Hamede; Hamish McCallum; Menna E. Jones; Paul A. Hohenlohe; et al. (Molecular Ecology, 2020)
Genetic structure in host species is often used to predict disease spread. However, host and pathogen genetic variation may be incongruent. Understanding landscape factors that have either concordant or divergent influence on host and pathogen genetic structure is crucial for wildlife disease management. Devil facial tumour disease (DFTD) was first observed in 1996 and has spread throughout almost the entire Tasmanian devil geographic range, causing dramatic population declines. Whereas DFTD is predominantly spread via biting among adults, devils typically disperse as juveniles, which experience low DFTD prevalence. Thus, we predicted little association between devil and tumour population structure and that environmental factors influencing gene flow differ between devils and tumours. We employed a comparative landscape genetics framework to test the influence of environmental factors on patterns of isolation by resistance (IBR) and isolation by environment (IBE) in devils and DFTD. Although we found evidence for broad‐scale costructuring between devils and tumours, we found no relationship between host and tumour individual genetic distances. Further, the factors driving the spatial distribution of genetic variation differed for each. Devils exhibited a strong IBR pattern driven by major roads, with no evidence of IBE. By contrast, tumours showed little evidence for IBR and a weak IBE pattern with respect to elevation in one of two tumour clusters we identify herein. Our results warrant caution when inferring pathogen spread using host population genetic structure and suggest that reliance on environmental barriers to host connectivity may be ineffective for managing the spread of wildlife diseases. Our findings demonstrate the utility of comparative landscape genetics for identifying differential factors driving host dispersal and pathogen transmission.

Drivers of future alien species impacts: An expert‐based assessment - Franz Essl; Bernd Lenzner; Sven Bacher; Sarah Bailey; Cesar Capinha; Curtis Daehler; Stefan Dullinger; Piero Genovesi; Cang Hui; Philip E. Hulme; Jonathan M. Jeschke; Stelios Katsanevakis; et al. (Global Change Biology, 2020)
Understanding the likely future impacts of biological invasions is crucial yet highly challenging given the multiple relevant environmental, socio‐economic and societal contexts and drivers. In the absence of quantitative models, methods based on expert knowledge are the best option for assessing future invasion trajectories. Here, we present an expert assessment of the drivers of potential alien species impacts under contrasting scenarios and socioecological contexts through the mid‐21st century. Based on responses from 36 experts in biological invasions, moderate (20%–30%) increases in invasions, compared to the current conditions, are expected to cause major impacts on biodiversity in most socioecological contexts. Three main drivers of biological invasions—transport, climate change and socio‐economic change—were predicted to significantly affect future impacts of alien species on biodiversity even under a best‐case scenario. Other drivers (e.g. human demography and migration in tropical and subtropical regions) were also of high importance in specific global contexts (e.g. for individual taxonomic groups or biomes). We show that some best‐case scenarios can substantially reduce potential future impacts of biological invasions. However, rapid and comprehensive actions are necessary to use this potential and achieve the goals of the Post‐2020 Framework of the Convention on Biological Diversity.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Effect of the mother tree age and acorn weight in the regenerative characteristics of Quercus faginea - I. M. Alonso-Crespo; F. Silla; P. Jiménez del Nogal; M. J. Fernández; C. Martínez-Ruiz; B. Fernández-Santos (European Journal of Forest Research, 2020)

Mesquite (Prosopis spp.) tree as a feed resource for animal growth - J. E. Ruiz-Nieto; J. Hernández-Ruiz; J. Hernández-Marín; J. Mendoza-Carrillo; M. Abraham-Juárez; P. M. Isiordia-Lachica; A. I. Mireles-Arriaga (Agroforestry Systems, 2020)

Identifying key transcription factors for pharmacogenetic studies of antipsychotics induced extrapyramidal symptoms - Daniel Boloc; Natalia Rodríguez; Teresa Torres; Susana García-Cerro; Mara Parellada; Jeronimo Saiz-Ruiz; Manuel J. Cuesta; Miquel Bernardo; Patricia Gassó; Amalia Lafuente; Sergi Mas; Joan Albert Arnaiz (Psychopharmacology, 2020)

Coastal Scenic Evaluation of Continental Ecuador and Galapagos Islands: Human Impacts and Management Issues - Carlos Mestanza-Ramón; Giorgio Anfuso; J. Adolfo Chica-Ruiz; Alexis Mooser; Camilo M. Botero; Enzo Pranzini (Journal of Marine Science and Engineering, 2020)
The scenery, safety, facilities, water quality and litter quantities in coastal areas are relevant and determining elements in the choice of a tourist destination. This paper focused on the evaluation of coastal scenic value in 55 and 12 sites respectively located in continental Ecuador and the Galapagos Islands. The information obtained gives public administrators and coastal managers the relevant data to avoid further environmental degradation and suggests measures to improve the present scenic value of tourist destinations. The methodology used was based on the analysis of 26 physical/human factors and applied fuzzy logic analysis and weighting matrices that allowed the sites to be classified into five classes, from Class I (natural areas with superior scenic characteristics) to Class V (poor scenic areas with relevant impact of human interventions). The most attractive beaches were in the Galapagos Islands due to the magnificent physical and environmental characteristics, while the Esmeraldas province presented sites of lower scenic beauty due to the low natural scenic value and the increase of human impacts. In total, 22% (15 out of 67) of the beaches investigated belonged to Class I, 12% (8) to Class II and 15% (10) to Class III. The last two classes included 51% of the beaches (i.e., 34 out of 67), of which 31% (21) was in Class IV and 20% (13) in Class V. Such results provide local managers and planners a solid inventory on coastal scenic characteristics and baseline information for any envisaged subsequent management plan.

In-Water Cleaning and Capture to Remove Ship Biofouling: An Initial Evaluation of Efficacy and Environmental Safety - Mario N. Tamburri; Ian C. Davidson; Matthew R. First; Christopher Scianni; Katherine Newcomer; Graeme J. Inglis; Eugene T. Georgiades; Janet M. Barnes; Gregory M. Ruiz (Frontiers in Marine Science, 2020)

Sensitive fluorometric determination of quinclorac residues in rice - J. Jiménez-López; E. J. Llorent-Martínez; A. Ruiz-Medina (Food Additives & Contaminants: Part A, 2020)

Epidemiology of Non-Tuberculous Mycobacteria isolated from clinical specimens in Madrid, Spain, from 2013 to 2017 - P López-Roa; E Aznar; J Cacho; R Cogollos-Agruña; D Domingo; MI García-Arata; R Millán; M Páez; E Perez-Cecilia; MJ Ruiz-Serrano; M Simón; M Tato; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Technological challenges in the preclinical development of an HIV nanovaccine candidate - Tamara G. Dacoba; Luisa Ruiz-Gatón; Ana Benito; Marlène Klein; Damien Dupin; Ma Luo; Mathieu Menta; Desirée Teijeiro-Osorio; Iraida Loinaz; María J. Alonso; José Crecente-Campo (Drug Delivery and Translational Research, 2020)

Melatonin in flowering, fruit set and fruit ripening - M. B. Arnao; J. Hernández-Ruiz (Plant Reproduction, 2020)

Proteins from femoral gland secretions of male rock lizards Iberolacerta cyreni allow self—but not individual—recognition of unfamiliar males - Marco Mangiacotti; José Martín; Pilar López; Claudio V. Reyes-Olivares; Gonzalo Rodríguez-Ruiz; Alan J. Coladonato; Stefano Scali; Marco A. L. Zuffi; Roberto Sacchi (Behavioral Ecology and Sociobiology, 2020)

Productive behavior in growing kid goats and methane production with the inclusion of chokecherry leaf (Prunus salicifolia) - Lizbeth E. Robles Jimenez; Jose A. Ruiz Perez; Di Lorenzo Nicolas; Alfonso J. Chay Canul; Julio Cesar Ramirez-Rivera; Daniela Villegas-Estrada; Einar Vargas-Bello-Pérez; Manuel Gonzalez-Ronquillo (Tropical Animal Health and Production, 2020)

Genotoxicity in fishes environmentally exposed to As, Se, Hg, Pb, Cr and toxaphene in the lower Colorado River basin, at Mexicali valley, Baja California, México - M. A. Flores-Galván; L. W. Daesslé; E. Arellano-García; O. Torres-Bugarín; J. V. Macías-Zamora; G. Ruiz-Campos (Ecotoxicology, 2020)

Effects of Amazon basin deforestation on regional atmospheric circulation and water vapor transport towards tropical South America - Melissa Ruiz-Vásquez; Paola A. Arias; J. Alejandro Martínez; Jhan Carlo Espinoza (Climate Dynamics, 2020)

Regulation of hepatic P-gp expression and activity by genistein in rats - M. Semeniuk; L. I. Ceré; N. Ciriaci; M. Bucci-Muñoz; S. S. M. Villanueva; A. D. Mottino; V. A. Catania; J. P. Rigalli; María Laura Ruiz (Archives of Toxicology, 2020)

A Design Parameter for Reef Beach Profiles—A Methodology Applied to Cadiz, Spain - Antonio Contreras; Juan J. Muñoz-Perez; Francisco Contreras; Gregorio Gomez-Pina; Veronica Ruiz-Ortiz; Gabriel Chamorro; Pablo Cabrera (Journal of Marine Science and Engineering, 2020)
The southwestern coast of Spain is in a tidal zone (mesotidal) which causes the equilibrium profile to be developed in two different sections: the breakage section and the swash section. These two sections give rise to the typical bi-parabolic profile existing in tidal seas. The existence of areas with reefs/rocks which interrupt the normal development of the typical bi-parabolic profile causes different types of beach profiles. The objective of this article is designing an easy methodology for determining new formulations for the design parameters of the equilibrium profile of beaches with reefs in tidal seas. These formulations are applied on 16 profiles to quantify the error between the real profile data and the modelling results. A comparative analysis is extended to the formulations proposed by other authors, from which it is found that better results are obtained with the new formulations.

Neocosmospora keratoplastica, a relevant human fusarial pathogen is found to be associated with wilt and root rot of Muskmelon and Watermelon crops in Spain: epidemiological and molecular evidences - V. González; S. García-Martínez; A. Flores-León; J. J. Ruiz; B. Picó; A. Garcés-Claver (European Journal of Plant Pathology, 2020)

Contrasting patterns of tree species mixture effects on wood δ13C along an environmental gradient - G. de Streel; C. Collet; I. Barbeito; K. Bielak; A. Bravo-Oviedo; G. Brazaitis; L. Coll; L. Drössler; D. Forrester; M. Heym; M. Löf; M. Pach; et al. (European Journal of Forest Research, 2020)

Analysis of Rockfalls by Means of a Fractal Fragmentation Model - R. Ruiz-Carulla; J. Corominas (Rock Mechanics and Rock Engineering, 2020)

The complete mitochondrial genome of Talpa aquitania (Talpidae; Insectivora), a mole species endemic to northern Spain and southern France - Gaël Aleix-Mata; Juana Gutiérrez; Francisco J. Ruiz-Ruano; Pedro Lorite; Juan A. Marchal; Antonio Sánchez (Molecular Biology Reports, 2020)

Presence of Seropositive Patients to Trypanosoma cruzi in a Municipality of the Mixtec Sierra of the State of Puebla: A Preliminary Study - L. Zumaquero-Ríos; J. Sarracent-Pérez; C. Sandoval-Ruiz; R. M. Aldana-Arnas; A. López-Monteon; J. Torres-Montero; D. Guzmán-Gómez; A. Ramos-Ligonio (Acta Parasitologica, 2020)

An initial comparative genomic autopsy of wasting disease in sea stars - Dannise V. Ruiz‐Ramos; Lauren M. Schiebelhut; Katharina J. Hoff; John P. Wares; Michael N Dawson (Molecular Ecology, 2020)
Beginning in 2013, sea stars throughout the Eastern North Pacific were decimated by wasting disease, also known as “asteroid idiopathic wasting syndrome” (AIWS) due to its elusive aetiology. The geographic extent and taxonomic scale of AIWS meant events leading up to the outbreak were heterogeneous, multifaceted, and oftentimes unobserved; progression from morbidity to death was rapid, leaving few tell‐tale symptoms. Here, we take a forensic genomic approach to discover candidate genes that may help explain sea star wasting syndrome. We report the first genome and annotation for Pisaster ochraceus , along with differential gene expression (DGE) analyses in four size classes, three tissue types, and in symptomatic and asymptomatic individuals. We integrate nucleotide polymorphisms associated with survivors of the wasting disease outbreak, DGE associated with temperature treatments in P. ochraceus , and DGE associated with wasting in another asteroid Pycnopodia helianthoides . In P. ochraceus , we found DGE across all tissues, among size classes, and between asymptomatic and symptomatic individuals; the strongest wasting‐associated DGE signal was in pyloric caecum. We also found previously identified outlier loci co‐occur with differentially expressed genes. In cross‐species comparisons of symptomatic and asymptomatic individuals, consistent responses distinguish genes associated with invertebrate innate immunity and chemical defence, consistent with context‐dependent stress responses, defensive apoptosis, and tissue degradation. Our analyses thus highlight genomic constituents that may link suspected environmental drivers (elevated temperature) with intrinsic differences among individuals (age/size, alleles associated with susceptibility) that elicit organismal responses (e.g., coelomocyte proliferation) and manifest as sea star wasting mass mortality.

Protein and lipid requirements of three-spot cichlid Cichlasoma trimaculatum larvae - F. J. Toledo-Solís; R. Martínez-García; M. A. Galaviz; A. G. Hilerio-Ruiz; C. A. Álvarez-González; M. Saenz de Rodrigáñez (Fish Physiology and Biochemistry, 2020)

Niche separation within aerobic methanotrophic bacteria across lakes and its link to methane oxidation rates - Paula C. J. Reis; Shoji D. Thottathil; Clara Ruiz‐González; Yves T. Prairie (Environmental Microbiology, 2020)
Summary Lake methane (CH 4 ) emissions are largely controlled by aerobic methane‐oxidizing bacteria (MOB) which mostly belong to the classes Alpha‐ and Gammaproteobacteria (Alpha‐ and Gamma‐MOB). Despite the known metabolic and ecological differences between the two MOB groups, their main environmental drivers and their relative contribution to CH 4 oxidation rates across lakes remain unknown. Here, we quantified the two MOB groups through CARD‐FISH along the water column of six temperate lakes and during incubations in which we measured ambient CH 4 oxidation rates. We found a clear niche separation of Alpha‐ and Gamma‐MOB across lake water columns, which is mostly driven by oxygen concentration. Gamma‐MOB appears to dominate methanotrophy throughout the water column, but Alpha‐MOB may also be an important player particularly in well‐oxygenated bottom waters. The inclusion of Gamma‐MOB cell abundance improved environmental models of CH 4 oxidation rate, explaining part of the variation that could not be explained by environmental factors alone. Altogether, our results show that MOB composition is linked to CH 4 oxidation rates in lakes and that information on the MOB community can help predict CH 4 oxidation rates and thus emissions from lakes.

Climate drives community‐wide divergence within species over a limited spatial scale: evidence from an oceanic island - Antonia Salces‐Castellano; Jairo Patiño; Nadir Alvarez; Carmelo Andújar; Paula Arribas; Juan José Braojos‐Ruiz; Marcelino del Arco‐Aguilar; Víctor García‐Olivares; Dirk N. Karger; Heriberto López; Ioanna Manolopoulou; Pedro Oromí; et al. (Ecology Letters, 2020)
Geographic isolation substantially contributes to species endemism on oceanic islands when speciation involves the colonisation of a new island. However, less is understood about the drivers of speciation within islands. What is lacking is a general understanding of the geographic scale of gene flow limitation within islands, and thus the spatial scale and drivers of geographical speciation within insular contexts. Using a community of beetle species, we show that when dispersal ability and climate tolerance are restricted, microclimatic variation over distances of only a few kilometres can maintain strong geographic isolation extending back several millions of years. Further to this, we demonstrate congruent diversification with gene flow across species, mediated by Quaternary climate oscillations that have facilitated a dynamic of isolation and secondary contact. The unprecedented scale of parallel species responses to a common environmental driver for evolutionary change has profound consequences for understanding past and future species responses to climate variation.

Assessing Knowledge Gaps and Management Needs to Cope With Barriers for Environmental, Economic, and Social Sustainability of Marine Recreational Fisheries: The Case of Spain - Pablo Pita; Josep Alós; Manel Antelo; Iñaki Artetxe; Sebastián Biton-Porsmoguer; Arnau Carreño; Amalia Cuadros; Toni Font; José Beiro; Jose A. García-Charton; Ana Gordoa; Kieran Hyder; et al. (Frontiers in Marine Science, 2020)

Holocene vegetation and fire dynamics in the supra-Mediterranean belt of the Gredos Range (central Iberian Peninsula) - S. Robles-López; S. Pérez-Díaz; M. Ruiz-Alonso; O. Blarquez; R. Luelmo-Lautenschlaeger; J. A. López-Sáez (Plant Biosystems, 2020)

Effect of calving age on genetic evaluation of milk yield in Holstein cattle - G. J. Martínez-Marín; A. García-Ruiz; C. G. Vásquez-Peláez; S. I. Román-Ponce; F. J. Ruiz-López (Tropical Animal Health and Production, 2020)

Satellite DNA content of B chromosomes in the characid fish Characidium gomesi supports their origin from sex chromosomes - Érica A. Serrano-Freitas; Duílio M. Z. A. Silva; Francisco J. Ruiz-Ruano; Ricardo Utsunomia; Cristian Araya-Jaime; Claudio Oliveira; Juan Pedro M. Camacho; Fausto Foresti (Molecular Genetics and Genomics, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Liver damage in bleomycin-induced pulmonary fibrosis in mice - V. R. Vásquez-Garzón; A. Ramírez-Cosmes; E. Reyes-Jiménez; G. Carrasco-Torres; S. Hernández-García; S. R. Aguilar-Ruiz; H. Torres-Aguilar; J. Alpuche; L. Pérez-Campos Mayoral; S. Pina-Canseco; J. Arellanes-Robledo; S. Villa-Treviño; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Trace elements and lead isotopic composition of copper deposits from the eastern part of the Internal Zone of the Betic Cordillera (SE Iberia): application to provenance of archaeological materials - M. Murillo-Barroso; I. Montero-Ruiz; J. M. Nieto; M. D. Camalich Massieu; D. Martín Socas; M. Martinón-Torres (Journal of Iberian Geology, 2019)

The citrus flavanone naringenin attenuates zymosan-induced mouse joint inflammation: induction of Nrf2 expression in recruited CD45+ hematopoietic cells - Allan J. C. Bussmann; Sergio M. Borghi; Tiago H. Zaninelli; Telma S. dos Santos; Carla F. S. Guazelli; Victor Fattori; Talita P. Domiciano; Felipe A. Pinho-Ribeiro; Kenji W. Ruiz-Miyazawa; Antonio M. B. Casella; Josiane A. Vignoli; Doumit Camilios-Neto; et al. (Inflammopharmacology, 2019)

An artificial neural network ensemble approach to generate air pollution maps - S. Van Roode; J. J. Ruiz-Aguilar; J. González-Enrique; I. J. Turias (Environmental Monitoring and Assessment, 2019)

Maternal versus artificial rearing shapes the rumen microbiome having minor long‐term physiological implications - Alejandro Belanche; David R. Yáñez‐Ruiz; Andrew P. Detheridge; Gareth W. Griffith; Alison H. Kingston‐Smith; Charles J. Newbold (Environmental Microbiology, 2019)
Summary Increasing productivity is a key target in ruminant science which requires better understanding of the rumen microbiota. This study investigated how maternal versus artificial rearing shapes the rumen microbiota using 24 sets of triplet lambs. Lambs within each sibling set were randomly assigned to natural rearing on the ewe (NN); ewe colostrum for 24 h followed by artificial milk feeding (NA); and colostrum alternative and artificial milk feeding (AA). Maternal colostrum feeding enhanced VFA production at weaning but not thereafter. At weaning, lambs reared on milk replacer had no rumen protozoa and lower microbial diversity, whereas natural rearing accelerated the rumen microbial development and facilitated the transition to solid diet. Differences in the rumen prokaryotic communities disappear later in life when all lambs were grouped on the same pasture up to 23 weeks of age. However, NN animals retained higher fungal diversity and abundances of Piromyces , Feramyces and Diplodiniinae protozoa as well as higher feed digestibility (+4%) and animal growth (+6.5%) during the grazing period. Nevertheless, no correlations were found between rumen microbiota and productive outcomes. These findings suggest that the early life nutritional intervention determine the initial rumen microbial community, but the persistence of these effects later in life is weak.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Sand-swimming behaviour reduces ectoparasitism in an iguanian lizard - Ken S. Toyama; José C. Florián; Emily J. Ruiz; Wilfredo L. Gonzáles; Ernesto Gianoli (The Science of Nature, 2019)

Prediction of air pollutants PM10 by ARBX(1) processes - J. Álvarez-Liébana; M. D. Ruiz-Medina (Stochastic Environmental Research and Risk Assessment, 2019)

Mice expressing the variant rs1143679 allele of ITGAM (CD11b) show impaired DC-mediated T cell proliferation - Justin T. Avery; Rachel V. Jimenez; Joseph L. Blake; Tyler T. Wright; Beatriz Leόn-Ruiz; Trenton R. Schoeb; Alexander J. Szalai; Daniel C. Bullard (Mammalian Genome, 2019)
Genome-wide association studies (GWAS) and functional genomic analyses have implicated several ITGAM (CD11b) single-nucleotide polymorphisms (SNPs) in the development of SLE and other disorders. ITGAM encodes the α M chain of the β 2 integrin Mac-1, a receptor that plays important roles in myeloid cell functions. The ITGAM SNP rs1143679, which results in an arginine to histidine change at amino acid position 77 of the CD11b protein, has been shown to reduce binding to several ligands and to alter Mac-1-mediated cellular response in vitro. Importantly, however, the potential contribution of this SNP variant to the initiation and/or progression of immune and inflammatory processes in vivo remains unexplored. Herein, we describe for the first time the generation and characterization of a mouse line expressing the 77His variant of CD11b. Surprisingly, we found that 77His did not significantly affect Mac-1-mediated leukocyte migration and activation as assessed using thioglycollate-induced peritonitis and LPS/TNF-α-induced dermal inflammation models. In contrast, expression of this variant did alter T cell immunity, as evidenced by significantly reduced proliferation of ovalbumin (OVA)-specific transgenic T cells in 77His mice immunized with OVA. Reduced antigen-specific T cell proliferation was also observed when either 77His splenic dendritic cells (DCs) or bone marrow-derived DCs were used as antigen-presenting cells (APCs). Although more work is necessary to determine how this alteration might influence the development of SLE or other diseases, these in vivo findings suggest that the 77His variant of CD11b can compromise the ability of DCs to induce antigen-driven T cell proliferation.

Likely annual calving in the vaquita, Phocoena sinus : A new hope? - Barbara L. Taylor; Randall S. Wells; Paula A. Olson; Robert L. Brownell; Frances M. D. Gulland; Andrew J. Read; Francisco J. Valverde‐Esparza; Oscar H. Ortiz‐García; Diego Ruiz‐Sabio; Armando M. Jaramillo‐Legorreta; Edwyna Nieto‐Garcia; Gustavo Cardenas‐Hinojosa; et al. (Marine Mammal Science, 2019)

In a Model of Neuroinflammation Designed to Mimic Delirium, Quetiapine Reduces Cortisol Secretion and Preserves Reversal Learning in the Attentional Set Shifting Task - Zyad J. Carr; Lauren Miller; Victor Ruiz-Velasco; Allen R. Kunselman; Kunal Karamchandani (Journal of Neuroimmune Pharmacology, 2019)

Metvan, bis(4,7-Dimethyl-1,10-phenanthroline)sulfatooxidovanadium(IV): DFT and Spectroscopic Study—Antitumor Action on Human Bone and Colorectal Cancer Cell Lines - Ignacio E. León; María C. Ruiz; Carlos A. Franca; Beatriz S. Parajón-Costa; Enrique J. Baran (Biological Trace Element Research, 2019)

Responses of a native and a recent invader snail to warming and dry conditions: the case of the lower Ebro River - M. V. López-van Oosterom; J. P. Casas-Ruiz; D. Gampe; M. A. López-Robles; R. Ludwig; A. Núñez-Marcé; I. Muñoz (Aquatic Ecology, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Trk1, the sole potassium-specific transporter in Candida glabrata, contributes to the proper functioning of various cell processes - Gabriel Caro; Jan Bieber; Francisco J. Ruiz-Castilla; Carmen Michán; Hana Sychrova; José Ramos (World Journal of Microbiology and Biotechnology, 2019)

Comments on “Use of Rh (III)-Heteropolymolybdate as Potential Catalysts for the Removal of Nitrates in Human Drinking Water: Synthesis, Characterisation and Catalytic Performance” by María A. Jaworski et al. (Water Air Soil Pollut (2018) 229: 309) - Francisco Ruiz-Bevia; Maria J. Fernandez-Torres (Water, Air, & Soil Pollution, 2019)

Correction to: Similarities and differences in tissue distribution of DLK1 and DLK2 during E16.5 mouse embryogenesis - P. Garcia-Gallastegi; A. Ruiz-García; G. Ibarretxe; S. Rivero-Hinojosa; A. D. González-Siccha; J. Laborda; O. Crende; F. Unda; J. J. García-Ramírez (Histochemistry and Cell Biology, 2019)

Similarities and differences in tissue distribution of DLK1 and DLK2 during E16.5 mouse embryogenesis - P. Garcia-Gallastegi; A. Ruiz-García; G. Ibarretxe; S. Rivero-Hinojosa; A. D. González-Siccha; J. Laborda; O. Crende; F. Unda; J. J. García-Ramírez (Histochemistry and Cell Biology, 2019)

Pleistocene climate changes, and not agricultural spread, accounts for range expansion and admixture in the dominant grassland species Lolium perenne L. - José Luis Blanco‐Pastor; Stéphanie Manel; Philippe Barre; Anna M. Roschanski; Evelin Willner; Klaus J. Dehmer; Mathew Hegarty; Hilde Muylle; Tom Ruttink; Isabel Roldán‐Ruiz; Thomas Ledauphin; Abraham Escobar‐Gutiérrez; et al. (Journal of Biogeography, 2019)
Aim Grasslands have been pivotal in the development of herbivore breeding since the Neolithic and still represent the most widespread agricultural land use across Europe. However, it remains unclear whether the current large‐scale genetic variation of plant species found in natural grasslands of Europe is the result of human activities or natural processes. Location Europe. Taxon Lolium perenne L. (perennial ryegrass). Methods We reconstructed the phylogeographic history of L. perenne , a dominant grassland species, using 481 natural populations, including 11 populations of closely related taxa. We combined Genotyping‐by‐Sequencing (GBS) and pool‐Sequencing (pool‐Seq) to obtain high‐quality allele frequency calls of ~500 k SNP loci. We performed genetic structure analyses and demographic reconstructions based on the site frequency spectrum (SFS). We additionally used the same genotyping protocol to assess the genomic diversity of a set of 32 cultivars representative of the L. perenne cultivars widely used for forage purposes. Results Expansion across Europe took place during the Würm glaciation (12–110 kya), a cooling period that decreased the dominance of trees in favour of grasses. Splits and admixtures in L. perenne fit historical climate changes in the Mediterranean basin. The development of agriculture in Europe (7–3.5 kya), that caused an increase in the abundance of grasslands, did not have an effect on the demographic patterns of L. perenne . We found that most modern cultivars are closely related to natural diversity from north‐western Europe. Thus, modern cultivars do not represent the wide genetic variation found in natural populations. Main conclusions Demographic events in L. perenne can be explained by the changing climatic conditions during the Pleistocene. Natural populations maintain a wide genomic variability at continental scale that has been minimally exploited by recent breeding activities. This variability constitutes valuable standing genetic variation for future adaptation of grasslands to climate change, safeguarding the agricultural services they provide.

Spatio-temporal mangrove canopy variation (2001–2016) assessed using the MODIS enhanced vegetation index (EVI) - Marta Rocío Nepita-Villanueva; César Alejandro Berlanga-Robles; Arturo Ruiz-Luna; J. Héctor Morales Barcenas (Journal of Coastal Conservation, 2019)

Biomonitoring Organochlorine Pesticides in Didelphis virginiana from Yucatan, Mexico by GC-ECD - Jesús Alfredo Araujo-León; Gonzalo J. Mena-Rejón; Elsy B. Canché-Pool; Hugo A. Ruiz-Piña (Bulletin of Environmental Contamination and Toxicology, 2019)

Echeveria sonianevadensis (Crassulaceae), una nueva especie del Volcán Nevado de Colima del occidente de México y una clave para la serie Gibbiflorae - H. David Jimeno-Sevilla; J. Antonio Vázquez-García; Miguel Ángel Muñiz-Castro; Ignacio García-Ruiz; Gerardo Hernández-Vera; y José Villa Castillo (Brittonia, 2019)

Salicylic Acid-Cryotherapy Treatment for Elimination of Potato Virus S from Solanum Tuberosum - Diana R. Ruiz-Sáenz; Diana D. Ayala-Hernández; Takao Niino; Esmeralda J. Cruz-Gutiérrez; Jesús G. Aquino-Martínez; Humberto A. López-Delgado (American Journal of Potato Research, 2019)

Production and viability of Fraxinus pollen and its relationship with aerobiological data in the northwestern Iberian Peninsula - P. Castiñeiras; R. A. Vázquez-Ruiz; M. Fernández-González; F. J. Rodríguez-Rajo; M. J. Aira (Aerobiologia, 2019)

Selective Knockdown of TASK3 Potassium Channel in Monoamine Neurons: a New Therapeutic Approach for Depression - M. Neus Fullana; Albert Ferrés-Coy; Jorge E. Ortega; Esther Ruiz-Bronchal; Verónica Paz; J. Javier Meana; Francesc Artigas; Analia Bortolozzi (Molecular Neurobiology, 2019)

Impaired Mitophagy and Protein Acetylation Levels in Fibroblasts from Parkinson’s Disease Patients - Sokhna M. S. Yakhine-Diop; Mireia Niso-Santano; Mario Rodríguez-Arribas; Rubén Gómez-Sánchez; Guadalupe Martínez-Chacón; Elisabet Uribe-Carretero; José A. Navarro-García; Gema Ruiz-Hurtado; Ana Aiastui; J. Mark Cooper; Adolfo López de Munaín; José M. Bravo-San Pedro; et al. (Molecular Neurobiology, 2019)

Draft genome sequence of Lactobacillus plantarum C4 (CECT 9567), a potential probiotic strain isolated from kefir - Soumi De Montijo-Prieto; David J. Castro; Jose C. Reina; Maria Jimenez-Valera; Alfonso Ruiz-Bravo (Archives of Microbiology, 2019)

Spatial and meteorological relevance in NO2 estimations: a case study in the Bay of Algeciras (Spain) - Javier González-Enrique; Ignacio J. Turias; Juan Jesús Ruiz-Aguilar; José Antonio Moscoso-López; Leonardo Franco (Stochastic Environmental Research and Risk Assessment, 2019)

Early Miocene mammal assemblages from the Campisano ravine in the Ribesalbes-Alcora Basin (E Spain) - Vicente D. Crespo; Oier Suárez-Hernando; Xabier Murelaga; Francisco J. Ruiz-Sánchez; Plini Montoya (Journal of Iberian Geology, 2019)

Holocene palaeoenvironmental evolution of Saltés Island (Tinto and Odiel estuary, SW Spain) during the Roman period (1st century BC–5th century AD) - María L. González-Regalado; Paula Gómez; Francisco Ruiz; Luis M. Cáceres; María J. Clemente; Joaquín Rodríguez-Vidal; Antonio Toscano; Guadalupe Monge; Manuel Abad; Tatiana Izquierdo; Antonio M. Monge Soares; Juan M. Campos; et al. (Journal of Iberian Geology, 2019)

6-Methoxyquinoline complexes as lung carcinoma agents: induction of oxidative damage on A549 monolayer and multicellular spheroid model - J. F. Cadavid-Vargas; C. Villa-Pérez; M. C. Ruiz; I. E. León; G. C. Valencia-Uribe; D. B. Soria; S. B. Etcheverry; A. L. Di Virgilio (JBIC Journal of Biological Inorganic Chemistry, 2019)

Hotspots in the genomic architecture of field drought responses in wheat as breeding targets - Sergio Gálvez; Rosa Mérida-García; Carlos Camino; Philippa Borrill; Michael Abrouk; Ricardo H. Ramírez-González; Sezgi Biyiklioglu; Francisco Amil-Ruiz; Gabriel Dorado; Hikmet Budak; Victoria Gonzalez-Dugo; Pablo J. Zarco-Tejada; et al. (Functional & Integrative Genomics, 2019)

Measurement of the basic friction angle of planar rock discontinuities with three rock cores - C. C. Li; N. Zhang; J. Ruiz (Bulletin of Engineering Geology and the Environment, 2019)

Decontamination of Diesel particles from air by using the Counterfog® system - J. L. Pérez-Díaz; F. J. Llerena-Aguilar; T. Martín-Pérez; J. Sánchez-García-Casarrubios; E. Ruiz-Navas (Air Quality, Atmosphere & Health, 2019)

Combining multiple visual surveys to model the habitat of deep‐diving cetaceans at the basin scale - Auriane Virgili; Matthieu Authier; Oliver Boisseau; Ana Cañadas; Diane Claridge; Tim Cole; Peter Corkeron; Ghislain Dorémus; Léa David; Nathalie Di‐Méglio; Charlotte Dunn; Tim E. Dunn; et al. (Global Ecology and Biogeography, 2019)
Aim Deep‐diving cetaceans are oceanic species exposed to multiple anthropogenic pressures including high intensity underwater noise, and knowledge of their distribution is crucial to manage their conservation. Due to intrinsic low densities, wide distribution ranges and limited presence at the sea surface, these species are rarely sighted. Pooling data from multiple visual surveys sharing a common line‐transect methodology can increase sightings but requires accounting for heterogeneity in protocols and platforms. Location North Atlantic Ocean and Mediterranean Sea. Time period 1998 to 2015. Major taxa Ziphiidae; Physeteriidae; Kogiidae. Methods About 1,240,000 km of pooled effort provided 630 sightings of ziphiids, 836 of physeteriids and 106 of kogiids. For each taxon, we built a hierarchical model to estimate the effective strip width depending on observation conditions and survey types. We then modelled relative densities in a generalized additive modelling framework. Geographical predictions were limited to interpolations identified with a gap analysis of environmental space coverage. Results Deeper areas of the North Atlantic gyre were mostly environmental extrapolation in the predictions, thereby highlighting gaps in sampling across the different surveys. For the three species groups, the highest relative densities were predicted along continental slopes, particularly in the western North Atlantic Ocean where the Gulf Stream creates dynamic frontal zones and eddies. Main conclusions Pooling a large number of surveys provided the first basin‐wide models of distribution for deep‐diving cetaceans, including several data‐deficient taxa, across the North Atlantic Ocean and the Mediterranean Sea. These models can help the conservation of elusive and poorly known marine megafauna.

Anti-leukemia activity of 4-amino-2-aryl-6,9-dichlorobenzo[g]pteridines - Antonio J. Ruiz-Alcaraz; Violeta Carmona-Martínez; Antonio Guirado; Jesús Gálvez; María Martínez-Esparza; Pilar García-Peñarrubia (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Transcriptional response of immune-related genes in Litopenaeus vannamei post-larvae cultured in recirculating aquaculture systems with and without biofloc - Jorge Soto-Alcalá; Píndaro Álvarez-Ruiz; J. M. Audelo-Naranjo; H. M. Esparza-Leal; I. E. Luis-Villaseñor; J. A. Estrada-Godínez; A. Luna-González; C. Gámez-Jiménez; G. Diarte-Plata (Aquaculture International, 2019)

Risk factors associated with reproductive performance in small-scale dairy farms in Mexico - Luis Javier Montiel-Olguín; Eliab Estrada-Cortés; Mario Alfredo Espinosa-Martínez; Miguel Mellado; Josafath Omar Hernández-Vélez; Guillermina Martínez-Trejo; Felipe J. Ruiz-López; Hector Raymundo Vera-Avila (Tropical Animal Health and Production, 2019)

On the Discoloration of Methylene Blue by Visible Light - A. Sáenz-Trevizo; P. Pizá-Ruiz; D. Chávez-Flores; J. Ogaz-Parada; P. Amézaga-Madrid; A. Vega-Ríos; M. Miki-Yoshida (Journal of Fluorescence, 2019)

Definition of a temporal distribution index for high temporal resolution precipitation data over Peninsular Spain and the Balearic Islands: the fractal dimension; and its synoptic implications - Oliver Meseguer-Ruiz; Timothy J. Osborn; Pablo Sarricolea; Philip D. Jones; Jorge Olcina Cantos; Roberto Serrano-Notivoli; Javier Martin-Vide (Climate Dynamics, 2019)

Full plastome sequence of the fern Vandenboschia speciosa (Hymenophyllales): structural singularities and evolutionary insights - F. J. Ruiz-Ruano; B. Navarro-Domínguez; J. P. M. Camacho; Manuel A. Garrido-Ramos (Journal of Plant Research, 2019)

Food-Offering Calls in Wild Golden Lion Tamarins (Leontopithecus rosalia): Evidence for Teaching Behavior? - Camille A. Troisi; Will J. E. Hoppitt; Carlos R. Ruiz-Miranda; Kevin N. Laland (International Journal of Primatology, 2018)

Development of a serosurveillance assay for detection of Necoclí virus exposure - Carolina Montoya-Ruiz; Francisco J. Díaz; McBride Jere W; Zhang Xiaofeng; Silvana Levis; Juan Carlos Zapata; Carlos E. Muskus; Cristian M. Álvarez; Juan David Rodas (Archives of Virology, 2018)

Seeds in motion: Genetic assignment and hydrodynamic models demonstrate concordant patterns of seagrass dispersal - Elizabeth A. Sinclair; Leonardo Ruiz‐Montoya; Siegfried L. Krauss; Janet M. Anthony; Renae K. Hovey; Ryan J. Lowe; Gary A. Kendrick (Molecular Ecology, 2018)
Movement is fundamental to the ecology and evolutionary dynamics within species. Understanding movement through seed dispersal in the marine environment can be difficult due to the high spatial and temporal variability of ocean currents. We employed a mutually enriching approach of population genetic assignment procedures and dispersal predictions from a hydrodynamic model to overcome this difficulty and quantify the movement of dispersing floating fruit of the temperate seagrass Posidonia australis Hook.f. across coastal waters in south‐western Australia. Dispersing fruit cohorts were collected from the water surface over two consecutive years, and seeds were genotyped using microsatellite DNA markers. Likelihood‐based genetic assignment tests were used to infer the meadow of origin for seed cohorts and individuals. A three‐dimensional hydrodynamic model was coupled with a particle transport model to simulate the movement of fruit at the water surface. Floating fruit cohorts were mainly assigned genetically to the nearest meadow, but significant genetic differentiation between cohort and most likely meadow of origin suggested a mixed origin. This was confirmed by genetic assignment of individual seeds from the same cohort to multiple meadows. The hydrodynamic model predicted 60% of fruit dispersed within 20 km, but that fruit was physically capable of dispersing beyond the study region. Concordance between these two independent measures of dispersal provides insight into the role of physical transport for long distance dispersal of fruit and the consequences for spatial genetic structuring of seagrass meadows.

A simplistic approach to detect health anomalies at a regional level using shrimp production data - Ana Muniesa; Julio Cabanillas‐Ramos; Imanol Ruiz‐Zarzuela; Francisco J. Magallón‐Barajas; Ignacio de Blas (Reviews in Aquaculture, 2018)
The global production and yield of shrimp ponds depend on multiple factors, and an unexpected variation in production parameters could be an indicator of pathological events such as white spot disease (WSD) outbreaks in a syndromic surveillance system. Using the production data from 7139 production cycles at farm level collected at two Mexican states (Sonora and Sinaloa) from 2004 to 2011, an ecological survey (also called correlational study) has been carried out summarizing data for year and oceanic basin. The production results had been analysed looking for significant association ( P

Risk Perception of Coastal Communities and Authorities on Harmful Algal Blooms in Ecuador - Mercy J. Borbor-Córdova; Mireya Pozo-Cajas; Alexandra Cedeno-Montesdeoca; Gabriel Mantilla Saltos; Chippie Kislik; Maria E. Espinoza-Celi; Rene Lira; Omar Ruiz-Barzola; Gladys Torres (Frontiers in Marine Science, 2018)

Effects of Botanical Insecticides on Hymenopteran Parasitoids: a Meta-analysis Approach - R J Monsreal-Ceballos; E Ruiz-Sánchez; H S Ballina-Gómez; A Reyes-Ramírez; A González-Moreno (Neotropical Entomology, 2018)

Cell-free expression, purification and immunoreactivity assessment of recombinant Fasciola hepatica saposin-like protein-2 - Marcos J. Ramos-Benítez; Luis M. Lopez-Cruz; Vasti Aguayo; Caleb Ruiz-Jimenez; Ana M. Espino (Molecular Biology Reports, 2018)

Landslide-dam paleolakes in the Central Pyrenees, Upper Gállego River Valley, NE Spain: timing and relationship with deglaciation - J. Guerrero; F. Gutiérrez; J. M. García-Ruiz; D. Carbonel; P. Lucha; L. J. Arnold (Landslides, 2018)

Effects of lead and lead–melatonin exposure on protein and gene expression of metal transporters, proteins and the copper/zinc ratio in rats - Karla J. Soto-Arredondo; Juvencio Robles; Erik Díaz-Cervantes; Carolina Ruiz-Ramírez; Marco A. García-Revilla; Katarzyna Wrobel; Kazimierz Wrobel; Mauricio Díaz-Muñoz; Isabel Méndez; Alberto Flores; Francisco Javier Acevedo-Aguilar; Minerva Martínez-Alfaro (BioMetals, 2018)

Methodological issues related to maximal fat oxidation rate during exercise - Francisco J. Amaro-Gahete; Jonatan R. Ruiz (European Journal of Applied Physiology, 2018)

Transformation towards sustainable bioenergy systems - Gerardo J. Ruiz-Mercado; Juan Gabriel Segovia-Hernández; Agustín J. Castro-Montoya (Clean Technologies and Environmental Policy, 2018)

Optimization of multi-pathway production chains and multi-criteria decision-making through sustainability evaluation: a biojet fuel production case study - Eduardo Vyhmeister; Gerardo J. Ruiz-Mercado; Ana I. Torres; John A. Posada (Clean Technologies and Environmental Policy, 2018)

A process systems framework for rapid generation of life cycle inventories for pollution control and sustainability evaluation - Shuyun Li; Yacine Feliachi; Selorme Agbleze; Gerardo J. Ruiz-Mercado; Raymond L. Smith; David E. Meyer; Michael A. Gonzalez; Fernando V. Lima (Clean Technologies and Environmental Policy, 2018)

New records and range extension of three fish species in the Gulf of California - A. F. González-Acosta; M. I. Miranda-Marín; J. De la Cruz-Torres; G. Ruiz-Campos (Marine Biodiversity, 2018)

Pla2g6 Deficiency in Zebrafish Leads to Dopaminergic Cell Death, Axonal Degeneration, Increased β-Synuclein Expression, and Defects in Brain Functions and Pathways - Elena Sánchez; Luis J. Azcona; Coro Paisán-Ruiz (Molecular Neurobiology, 2018)

The Servilia tomb: an architecturally and pictorially important Roman building - S. E. Jorge-Villar; I. Rodríguez Temiño; H. G. M. Edwards; A. Jiménez Hernández; J. I. Ruiz Cecilia; I. Miralles (Archaeological and Anthropological Sciences, 2018)

Prediction of enteric methane production, yield, and intensity in dairy cattle using an intercontinental database - Mutian Niu; Ermias Kebreab; Alexander N. Hristov; Joonpyo Oh; Claudia Arndt; André Bannink; Ali R. Bayat; André F. Brito; Tommy Boland; David Casper; Les A. Crompton; Jan Dijkstra; et al. (Global Change Biology, 2018)
Enteric methane ( CH 4 ) production from cattle contributes to global greenhouse gas emissions. Measurement of enteric CH 4 is complex, expensive, and impractical at large scales; therefore, models are commonly used to predict CH 4 production. However, building robust prediction models requires extensive data from animals under different management systems worldwide. The objectives of this study were to (1) collate a global database of enteric CH 4 production from individual lactating dairy cattle; (2) determine the availability of key variables for predicting enteric CH 4 production (g/day per cow), yield [g/kg dry matter intake ( DMI )], and intensity (g/kg energy corrected milk) and their respective relationships; (3) develop intercontinental and regional models and cross‐validate their performance; and (4) assess the trade‐off between availability of on‐farm inputs and CH 4 prediction accuracy. The intercontinental database covered Europe ( EU ), the United States ( US ), and Australia ( AU ). A sequential approach was taken by incrementally adding key variables to develop models with increasing complexity. Methane emissions were predicted by fitting linear mixed models. Within model categories, an intercontinental model with the most available independent variables performed best with root mean square prediction error ( RMSPE ) as a percentage of mean observed value of 16.6%, 14.7%, and 19.8% for intercontinental, EU , and United States regions, respectively. Less complex models requiring only DMI had predictive ability comparable to complex models. Enteric CH 4 production, yield, and intensity prediction models developed on an intercontinental basis had similar performance across regions, however, intercepts and slopes were different with implications for prediction. Revised CH 4 emission conversion factors for specific regions are required to improve CH 4 production estimates in national inventories. In conclusion, information on DMI is required for good prediction, and other factors such as dietary neutral detergent fiber ( NDF ) concentration, improve the prediction. For enteric CH 4 yield and intensity prediction, information on milk yield and composition is required for better estimation.

The interplay of riverscape features and exotic introgression on the genetic structure of the Mexican golden trout ( Oncorhynchus chrysogaster ), a simulation approach - Marco Alejandro Escalante; Francisco J. García‐De León; Arturo Ruiz‐Luna; Erin Landguth; Stéphanie Manel (Journal of Biogeography, 2018)
Aim We explored the factors between riverscape features and exotic introgression of cultured rainbow trout ( Oncorhynchus mykiss ) that drive the current genetic structure in the endemic Mexican golden trout ( Oncorhynchus chrysogaster ) using a riverscape genetics simulator. Location Sierra Madre Occidental, Northwest Mexico, North America. Methods We created a system model for Mexican golden trout to test various scenarios for the effect of riverscape resistance and rainbow trout introgression on the native genetic structure of the Mexican golden trout. Individual genotypes were used to initialize the model and were based upon empirical allele frequencies from three genetically and spatially distinct groups in the study area. The geographical location of the simulated populations was defined using a species distribution model. We included hypotheses for movement of riverine distance and riverscape resistance. We evaluated model performance by conducting population and landscape genetics analyses on the simulation outputs. Results The most plausible scenario included riverscape resistance without introgression, which presented a spatial genetic structure matching the observed riverscape genetic structure and fitting expected general life‐history patterns for high elevation trout streams. In addition, temperature, precipitation, hydrology and topography were the most important variables influencing species occurrence and dispersal. Main conclusion This work presents one of the first empirically derived simulation studies of introgression. It highlights the importance of considering riverscape resistance (i.e. hydroclimatic and topographical gradient effects) in models of spatial genetic structure and introgression. Moreover, our modelling suggests that what we characterize as riverscape resistance is acting as a boundary against exotic introgression. The results of this study could help to develop management strategies that preserve native gene pools.

Variability of the Mixed-Layer Height Over Mexico City - J. L. García-Franco; W. Stremme; A. Bezanilla; A. Ruiz-Angulo; M. Grutter (Boundary-Layer Meteorology, 2018)

Effects of short-term grazing exclusion on vegetation and soil in early succession of a Subhumid Mediterranean reclaimed coal mine - F. Sigcha; Y. Pallavicini; M. J. Camino; C. Martínez-Ruiz (Plant and Soil, 2018)

Diabetes modifies the role of prostanoids and potassium channels which regulate the hypereactivity of the rabbit renal artery to BNP - José M. Centeno; Luis Miranda-Gómez; Mikahela A. López-Morales; Teresa Jover-Mengual; María C. Burguete; Vannina G. Marrachelli; María Castelló-Ruiz; Alicia Aliena-Valero; Enrique Alborch; Francisco J. Miranda (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Correction to: Deleterious Effects of VEGFR2 and RET Inhibition in a Preclinical Model of Parkinson’s Disease - C. Requejo; J. A. Ruiz-Ortega; H. Bengoetxea; S. Bulnes; L. Ugedo; J. V. Lafuente (Molecular Neurobiology, 2018)

Geographical ecology of dry forest tree communities in the West Indies - Janet Franklin; Riley Andrade; Mark L. Daniels; Patrick Fairbairn; Maria C. Fandino; Thomas W. Gillespie; Grizelle González; Otto Gonzalez; Daniel Imbert; Valerie Kapos; Daniel L. Kelly; Humfredo Marcano‐Vega; et al. (Journal of Biogeography, 2018)
Aim Seasonally dry tropical forest ( SDTF ) of the Caribbean Islands (primarily West Indies) is floristically distinct from Neotropical SDTF in Central and South America. We evaluate whether tree species composition was associated with climatic gradients or geographical distance. Turnover (dissimilarity) in species composition of different islands or among more distant sites would suggest communities structured by speciation and dispersal limitations. A nested pattern would be consistent with a steep resource gradient. Correlation of species composition with climatic variation would suggest communities structured by broad‐scale environmental filtering. Location The West Indies (The Bahamas, Cuba, Hispaniola, Jamaica, Puerto Rico, US Virgin Islands, Guadeloupe, Martinique, St. Lucia), Providencia (Colombia), south Florida ( USA ) and Florida Keys ( USA ). Taxon Seed plants—woody taxa (primarily trees). Methods We compiled 572 plots from 23 surveys conducted between 1969 and 2016. Hierarchical clustering of species in plots, and indicator species analysis for the resulting groups of sites, identified geographical patterns of turnover in species composition. Nonparametric analysis of variance, applied to principal components of bioclimatic variables, determined the degree of covariation in climate with location. Nestedness versus turnover in species composition was evaluated using beta diversity partitioning. Generalized dissimilarity modelling partitioned the effect of climate versus geographical distance on species composition. Results Despite a set of commonly occurring species, SDTF tree community composition was distinct among islands and was characterized by spatial turnover on climatic gradients that covaried with geographical gradients. Greater Antillean islands were characterized by endemic indicator species. Northern subtropical areas supported distinct, rather than nested, SDTF communities in spite of low levels of endemism. Main conclusions The SDTF species composition was correlated with climatic variation. SDTF on large Greater Antillean islands (Hispaniola, Jamaica and Cuba) was characterized by endemic species, consistent with their geological history and the biogeography of plant lineages. These results suggest that both environmental filtering and speciation shape Caribbean SDTF tree communities.

Sediment Geochemistry, Accumulation Rates and Forest Structure in a Large Tropical Mangrove Ecosystem - A. C. Ruiz-Fernández; C. M. Agraz-Hernández; J. A. Sanchez-Cabeza; M. Díaz-Asencio; L. H. Pérez-Bernal; C. A. Chan Keb; P. G. López-Mendoza; J. M. Blanco y Correa; J. F. Ontiveros-Cuadras; J. Osti Saenz; J. E. Reyes Castellanos (Wetlands, 2018)

Implications on 1 + 1 D Tsunami Runup Modeling due to Time Features of the Earthquake Source - M. Fuentes; S. Riquelme; J. Ruiz; J. Campos (Pure and Applied Geophysics, 2018)

A Clinical and Molecular Genetic Study of 50 Families with Autosomal Recessive Parkinsonism Revealed Known and Novel Gene Mutations - Shaghayegh Taghavi; Rita Chaouni; Abbas Tafakhori; Luis J. Azcona; Saghar Ghasemi Firouzabadi; Mir Davood Omrani; Javad Jamshidi; Babak Emamalizadeh; Gholam Ali Shahidi; Mona Ahmadi; Seyed Amir Hassan Habibi; Azadeh Ahmadifard; et al. (Molecular Neurobiology, 2018)

Gene expression of thyrotropin- and corticotrophin-releasing hormones is regulated by environmental salinity in the euryhaline teleost Sparus aurata - Ignacio Ruiz-Jarabo; J. A. Martos-Sitcha; C. Barragán-Méndez; G. Martínez-Rodríguez; J. M. Mancera; F. J. Arjona (Fish Physiology and Biochemistry, 2018)

Appraising timing response of paleoenvironmental proxies to the Bond cycle in the western Mediterranean over the last 20 kyr - Marta Rodrigo-Gámiz; Francisca Martínez-Ruiz; Francisco J. Rodríguez-Tovar; Eulogio Pardo-Igúzquiza; Miguel Ortega-Huertas (Climate Dynamics, 2018)

Functional biogeography and host specificity of bacterial communities associated with the Marine Green Alga Ulva spp. - Alexandra J. Roth‐Schulze; José Pintado; Enrique Zozaya‐Valdés; Javier Cremades; Patricia Ruiz; Staffan Kjelleberg; Torsten Thomas (Molecular Ecology, 2018)
Bacterial communities play an essential role for the function of marine macroalgae. Recent work has shown that bacterial communities associated with individual macroalgae possess on a local scale a functional core that is likely derived from diverse members of functional guilds. It is not known whether such functional cores also exist across large spatial scales or between closely related host species. To address this, we studied here the bacterial communities on three species of the green macroalgal genus Ulva from different geographic locations. While the taxonomic composition was too variable to describe a community core, we identified genes that were enriched across all Ulva samples as compared to the communities of the surrounding seawater. Of these core functions, 70% were consistently found and independent of the Ulva species and biogeography, while the remaining functions (~30%) are possibly involved in local or host‐specific adaptations. For each host individual, the core functions are provided by bacteria with distinct phylogenetic origin and these bacteria could constitute a global guild of Ulva ‐associated bacteria. Together, our results demonstrate the presence of a stable core set of functional genes in the bacterial communities associated with closely related host species and across large biogeographies.

Spatio‐temporal variability of daily precipitation concentration in Spain based on a high‐resolution gridded data set - R. Serrano‐Notivoli; J. Martín‐Vide; M. A. Saz; L. A. Longares; S. Beguería; P. Sarricolea; O. Meseguer‐Ruiz; M. de Luis (International Journal of Climatology, 2018)
An analysis of the spatial and temporal variability of daily precipitation concentration (CI) in Spain was made based on a high‐resolution (5 × 5 km) daily gridded precipitation data set for the 1950–2012 period. For each grid point in the Iberian Peninsula (IP) and Balearic and Canary Islands, the average annual CI was computed, as well as its coefficient of variation and the 5th and 95th percentiles. Annual values were also computed, and the time series of the index were used to assess temporal trends over the whole period. The spatial distribution of the CI showed a strong relationship with the orographic barriers near the coastlines. The Canary Islands showed the highest values of CI, along with the eastern Mediterranean facade of the IP. The highest inter‐annual variations of the CI occurred in the southern IP and in the southern Canary Islands. The trends of CI were, overall, positive and significant, which indicates an increase of daily precipitation concentration over the study period and an increasing environmental risks scenario where erosivity, torrentiality, and floods may become more frequent.

Overexpression of the Arginine Decarboxylase Gene Improves Tolerance to Salt Stress in Lotus tenuis Plants - Fabiana D. Espasandin; Pablo I. Calzadilla; Santiago J. Maiale; Oscar A. Ruiz; Pedro A. Sansberro (Journal of Plant Growth Regulation, 2018)

A comparative analysis of tellurite detoxification by members of the genus Shewanella - M. A. Valdivia-González; W. A. Díaz-Vásquez; D. Ruiz-León; A. A. Becerra; D. R. Aguayo; J. M. Pérez-Donoso; C. C. Vásquez (Archives of Microbiology, 2018)

Physiological evidence that Piscirickettsia salmonis produces siderophores and uses iron from different sources - P Calquín; P Ruiz; C Oliver; P Sánchez; R Haro; H Oliva; L Vargas‐Chacoff; R Avendaño‐Herrera; A. J. Yáñez (Journal of Fish Diseases, 2018)

Non-native species colonization of highly diverse, wave swept outer coast habitats in Central California - Chela J. Zabin; Michelle Marraffini; Steve I. Lonhart; Linda McCann; Lina Ceballos; Chad King; James Watanabe; John S. Pearse; Gregory M. Ruiz (Marine Biology, 2018)

Fishway with two entrance branches: Understanding its performance for potamodromous Mediterranean barbels - F. J. Bravo‐Córdoba; F. J. Sanz‐Ronda; J. Ruiz‐Legazpi; L. Fernandes Celestino; S. Makrakis (Fisheries Management and Ecology, 2018)
Many fish passes have been built across the world in recent years. This study analyses the performance of a modified type of pool and weir fishway with two access branches, using passive integrated transponder telemetry. A circum‐Mediterranean barbel, Luciobarbus bocagei (Steindachner, 1864), was chosen as the target species. Both hydraulic values (flow and volumetric energy dissipation) and biological parameters (attraction, entrance and passage success) were measured in the fishway, these being related to the environmental variables affecting upstream fish movement. Flow discharge, water temperature and atmospheric pressure were important for fish entering the fishway. There was no preference between path routes, even though the main discharge was concentrated in the turbine channel. This type of fishway design could be an alternative for the conservation of fish populations where multiple fish approach options are possible.

Insights into petrogenesis of the Jálama pluton (Central Iberian Zone, western Spain) - A. Pesquera; P. P. Gil-Crespo; J. Torres-Ruiz; E. Roda-Robles (International Geology Review, 2018)

Adolescent cannabinoid exposure effects on natural reward seeking and learning in rats - H. Schoch; M. Y. Huerta; C. M. Ruiz; M. R. Farrell; K. M. Jung; J. J. Huang; R. R. Campbell; D. Piomelli; S. V. Mahler (Psychopharmacology, 2018)

Analysis of somaclonal variation in transgenic and regenerated plants of Arabidopsis thaliana using methylation related metAFLP and TMD markers - Carlos J. Coronel; Ana I. González; María L. Ruiz; Carlos Polanco (Plant Cell Reports, 2018)

Nanodelivery of Cerebrolysin and Rearing in Enriched Environment Induce Neuroprotective Effects in a Preclinical Rat Model of Parkinson’s Disease - C. Requejo; J. A. Ruiz-Ortega; H. Cepeda; A. Sharma; H. S. Sharma; A. Ozkizilcik; R. Tian; H. Moessler; L. Ugedo; J. V. Lafuente (Molecular Neurobiology, 2018)

Deleterious Effects of VEGFR2 and RET Inhibition in a Preclinical Model of Parkinson’s Disease - C. Requejo; J. A. Ruiz-Ortega; H. Bengoetxea; S. Bulnes; L. Ugedo; J. V. Lafuente (Molecular Neurobiology, 2018)

Distribution of fishes in the Río Guayalejo-Río Tamesí system and relationships with environmental factors in northeastern Mexico - Francisco J. García-De León; Andrés I. Hernández Sandoval; Fernando Contreras-Catala; Laura Sánchez-Velasco; Gorgonio Ruiz-Campos (Environmental Biology of Fishes, 2018)

Breeding southern house wrens exhibit a threat-sensitive response when exposed to different predator models - Natalia M. Duré Ruiz; Mariana Fasanella; Gustavo J. Fernández (Journal of Ethology, 2018)

An integrated analysis (microfacies and ichnology) of a shallow carbonate-platform succession: upper Aptian, Lower Cretaceous, Betic Cordillera - L. M. Nieto; M. Reolid; F. J. Rodríguez-Tovar; J. M. Castro; J. M. Molina; P. A. Ruiz-Ortiz (Facies, 2018)

Effect of feed restriction on intake of Moringa oleifera and Leucaena leucocephala and growth performance of rabbits - R. Santos-Ricalde; E. Gutiérrez-Ruiz; W. Novelo-Ucan; P. Martinez-Romero; J. Segura-Correa (Tropical Animal Health and Production, 2017)

Cloud-based monitoring system for lysimetric and agroclimatic data - C. Jiménez-Carvajal; A. J. García-Bañón; J. A. Vera-Repullo; M. Jiménez-Buendía; L. Ruiz-Peñalver; J. M. Molina-Martínez (Precision Agriculture, 2017)

Morphological Changes in a Severe Model of Parkinson’s Disease and Its Suitability to Test the Therapeutic Effects of Microencapsulated Neurotrophic Factors - C. Requejo; J. A. Ruiz-Ortega; H. Bengoetxea; A. García-Blanco; E. Herrán; A. Aristieta; M. Igartua; J. L. Pedraz; L. Ugedo; R. M. Hernández; J. V. Lafuente (Molecular Neurobiology, 2017)

Co-culture of chondrons and mesenchymal stromal cells reduces the loss of collagen VI and improves extracellular matrix production - H. A. Owida; T. De Las Heras Ruiz; A. Dhillon; Y. Yang; N. J. Kuiper (Histochemistry and Cell Biology, 2017)

Global change and the distributional dynamics of migratory bird populations wintering in Central America - Frank A. La Sorte; Daniel Fink; Peter J. Blancher; Amanda D. Rodewald; Viviana Ruiz‐Gutierrez; Kenneth V. Rosenberg; Wesley M. Hochachka; Peter H. Verburg; Steve Kelling (Global Change Biology, 2017)
Understanding the susceptibility of highly mobile taxa such as migratory birds to global change requires information on geographic patterns of occurrence across the annual cycle. Neotropical migrants that breed in North America and winter in Central America occur in high concentrations on their non‐breeding grounds where they spend the majority of the year and where habitat loss has been associated with population declines. Here, we use eBird data to model weekly patterns of abundance and occurrence for 21 forest passerine species that winter in Central America. We estimate species’ distributional dynamics across the annual cycle, which we use to determine how species are currently associated with public protected areas and projected changes in climate and land‐use. The effects of global change on the non‐breeding grounds is characterized by decreasing precipitation, especially during the summer, and the conversion of forest to cropland, grassland, or peri‐urban. The effects of global change on the breeding grounds are characterized by increasing winter precipitation, higher temperatures, and the conversion of forest to peri‐urban. During spring and autumn migration, species are projected to encounter higher temperatures, forests that have been converted to peri‐urban, and increased precipitation during spring migration. Based on current distributional dynamics, susceptibility to global change is characterized by the loss of forested habitats on the non‐breeding grounds, warming temperatures during migration and on the breeding grounds, and declining summer rainfall on the non‐breeding grounds. Public protected areas with low and medium protection status are more prevalent on the non‐breeding grounds, suggesting that management opportunities currently exist to mitigate near‐term non‐breeding habitat losses. These efforts would affect more individuals of more species during a longer period of the annual cycle, which may create additional opportunities for species to respond to changes in habitat or phenology that are likely to develop under climate change.

Marine antifouling performance of polymer coatings incorporating zwitterions - Claudia Ventura; Andrew J. Guerin; Osama El-Zubir; Antonio J. Ruiz-Sanchez; Luke I. Dixon; Kevin J. Reynolds; Marie L. Dale; James Ferguson; Andrew Houlton; Benjamin R. Horrocks; Anthony S. Clare; David A. Fulton (Biofouling, 2017)

RockGIS: a GIS-based model for the analysis of fragmentation in rockfalls - G. Matas; N. Lantada; J. Corominas; J. A. Gili; R. Ruiz-Carulla; A. Prades (Landslides, 2017)

Pathogen-related factors affecting outcome of catheter-related bacteremia due to methicillin-susceptible Staphylococcus aureus in a Spanish multicenter study - R. San-Juan; D. Pérez-Montarelo; E. Viedma; A. Lalueza; J. Fortún; E. Loza; M. Pujol; C. Ardanuy; I. Morales; M. de Cueto; E. Resino-Foz; M. A. Morales-Cartagena; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Use of 3D printing for biofuel production: efficient catalyst for sustainable biodiesel production from wastes - M. E. Borges; L. Hernández; J. C. Ruiz-Morales; P. F. Martín-Zarza; J. L. G. Fierro; P. Esparza (Clean Technologies and Environmental Policy, 2017)

The cyclin dependent kinase subunit Cks1 is required for infection‐associated development of the rice blast fungus Magnaporthe oryzae - Xiaofeng Yue; Yawei Que; Shuzhen Deng; Lin Xu; Miriam Oses‐Ruiz; Nicholas J. Talbot; Youliang Peng; Zhengyi Wang (Environmental Microbiology, 2017)
Summary Cell cycle regulation is pivotal for proper cell division and cellular differentiation in eukaryotic cells. The central regulators that govern eukaryotic cell cycle progression are cyclin‐dependent kinases (CDKs) and their partners. Here, we report that Magnaporthe oryzae CKS1 encodes a cyclin‐dependent kinase subunit, which plays a significant role in regulation of plant infection. We demonstrate that CKS1 is a functional homolog of CKS1 / SUC1 and can physically interact with the CDK protein Cdc28, and Som1, a downstream regulator of the cyclic AMP‐dependent Protein Kinase A pathway. CKS1 deletion mutants are severely impaired in hyphal growth, sexual reproduction, melanin pigmentation and conidiogenesis. Cks1 mutants are able to form appressoria from hyphal tips, but these are unable to re‐polarize, and rice infection is impaired. CKS1 also affects chitin and glucan synthase activity during cell wall differentiation and fungal hydrophobin function. CKS1 , therefore, encodes a conserved CDK‐binding partner, essential for appressorium‐mediated plant infection by the rice blast fungus.

Assessing ecological impairments in Neotropical rivers of Mexico: calibration and validation of the Biomonitoring Working Party Index - R. A. Ruiz-Picos; B. Kohlmann; J. E. Sedeño-Díaz; E. López-López (International Journal of Environmental Science and Technology, 2017)

Ventilator-associated pneumonia by methicillin-susceptible Staphylococcus aureus: do minimum inhibitory concentrations to vancomycin and daptomycin matter? - J. Ruiz-Ramos; P. Vidal-Cortés; A. Díaz-Lamas; R. Reig-Valero; F. Roche-Campo; M. Del Valle-Ortiz; X. Nuvials-Casals; M. Ortiz-Piquer; D. Andaluz-Ojeda; L. Tamayo-Lomas; M. A. Blasco-Navalpotro; M. Rodriguez-Aguirregabiria; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Cis ‐regulatory evolution in a wild primate: Infection‐associated genetic variation drives differential expression of MHC ‐ DQA 1 in vitro - Noah D. Simons; Geeta N. Eick; Maria J. Ruiz‐Lopez; Patrick A. Omeja; Colin A. Chapman; Tony L. Goldberg; Nelson Ting; Kirstin N. Sterner (Molecular Ecology, 2017)
Few studies have combined genetic association analyses with functional characterization of infection‐associated SNP s in natural populations of nonhuman primates. Here, we investigate the relationship between host genetic variation, parasitism and natural selection in a population of red colobus ( Procolobus rufomitratus tephrosceles ) in Kibale National Park, Uganda. We collected parasitological, cellular and genomic data to test the following hypotheses: (i) MHC ‐ DQA 1 regulatory genetic variation is associated with control of whipworm ( Trichuris ) infection in a natural population of red colobus; (ii) infection‐associated SNP s are functional in driving differential gene expression in vitro; and (iii) balancing selection has shaped patterns of variation in the MHC ‐ DQA 1 promoter. We identified two SNP s in the MHC ‐ DQA 1 promoter, both in transcription factor binding sites, and both of which are associated with decreased control of Trichuris infection. We characterized the function of both SNP s by testing differences in gene expression between the two alleles of each SNP in two mammalian cell lines. Alleles of one of the SNP s drove differential gene expression in both cell lines, while the other SNP drove differences in expression in one of the cell lines. Additionally, we found evidence of balancing selection acting on the MHC ‐ DQA 1 promoter, including extensive trans‐species polymorphisms between red colobus and other primates, and an excess of intermediate‐frequency alleles relative to genome‐wide, coding and noncoding RAD seq data. Our data suggest that balancing selection provides adaptive regulatory flexibility that outweighs the consequences of increased parasite infection intensity in heterozygotes.

Heteroreceptor Complexes Formed by Dopamine D1, Histamine H3, and N-Methyl-D-Aspartate Glutamate Receptors as Targets to Prevent Neuronal Death in Alzheimer’s Disease - Mar Rodríguez-Ruiz; Estefanía Moreno; David Moreno-Delgado; Gemma Navarro; Josefa Mallol; Antonio Cortés; Carme Lluís; Enric I. Canela; Vicent Casadó; Peter J. McCormick; Rafael Franco (Molecular Neurobiology, 2017)

Silver-embedded screens in the intensive care unit. A new tool to control multi-drug resistant bacterial cross-transmission - J. Ruiz; P. Ramirez; E. Villarreal; M. Gordon; S. Cuesta; M. Piñol; J. Frasquet; Á. Castellanos (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Potential distribution of endangered Mexican golden trout (Oncorhynchus chrysogaster) in the Rio Sinaloa and Rio Culiacan basins (Sierra Madre Occidental) based on landscape characterization and species distribution models - Arturo Ruiz-Luna; Rafael Hernández-Guzmán; Francisco J. García-De León; Alejandro L. Ramírez-Huerta (Environmental Biology of Fishes, 2017)

Alcoholism and sexual dimorphism in the middle longitudinal fascicle: a pilot study - Johanna Seitz; Kayle S. Sawyer; George Papadimitriou; Marlene Oscar-Berman; Isaac Ng; Antoni Kubicki; Palig Mouradian; Susan M. Ruiz; Marek Kubicki; Gordon J. Harris; Nikos Makris (Brain Imaging and Behavior, 2017)

Changes of flood risk on the northern foothills of the Tatra Mountains - Z. W. Kundzewicz; M. Stoffel; B. Wyżga; V. Ruiz-Villanueva; T. Niedźwiedź; R. Kaczka; J. A. Ballesteros-Cánovas; I. Pińskwar; E. Łupikasza; J. Zawiejska; P. Mikuś; A. Choryński; et al. (Acta Geophysica, 2017)

Impact of changes in mean and extreme temperatures caused by climate change on olive flowering in southern Spain - Clara Gabaldón‐Leal; Margarita Ruiz‐Ramos; Raúl de la Rosa; Lorenzo León; Angjelina Belaj; Alfredo Rodríguez; Cristina Santos; Ignacio J. Lorite (International Journal of Climatology, 2017)
Due to the severe increase projected in future temperatures and the great economic and social importance of olive growing for vast agricultural areas in the Mediterranean Basin, accurate climate change impact assessment on olive orchards is required. The aim of this study is to assess the flowering date and the impact of mean and extreme temperature events on olive flowering in southern Spain under baseline and future climate conditions. To that end, experimental data were obtained from ten olive genotypes: six well‐known olive cultivars in the region, one cultivar, ‘Chiquitita’, obtained via conventional breeding, and three wild olives from the Canary Islands. A site‐specific model calibration was conducted resulting in satisfactory performance with an average error of 2 days for flowering date estimation under baseline and future climate conditions, and a RMSE equal to 5.5 days in the validation process. The outputs from 12 regional climate models from the ENSEMBLES European project with a bias correction in temperature and precipitation were used. Results showed an advance in the olive flowering dates of about 17 days at the end of the 21st century compared with the baseline period (1981–2010), and an increase in the frequency of extreme events around the flowering period. A spatial analysis of results identified the areas in southern Spain that are most vulnerable to climate change impact caused by the lack of chilling hours accumulation (areas located on the Atlantic coast and the south‐eastern coast) and by the occurrence of high temperatures during the flowering period (areas located in the north and north‐eastern areas of the Andalusian region).

Could superimposed electromyostimulation be an effective training to improve aerobic and anaerobic capacity? Methodological considerations for its development - Francisco J. Amaro-Gahete; Alejandro de la O; Lucas Jurado-Fasoli; Jonatan R. Ruiz; Ángel Gutiérrez (European Journal of Applied Physiology, 2017)

Genetic Relationships and Spatial Genetic Structure Among Populations of Rhodnius prolixus (Hemiptera: Reduviidae) in Colombia and Venezuela Based on Mitochondrial Cytochrome-b Sequences - K P Luna-Marín; V M Angulo-Silva; J Hernández-Torres; M Ruiz-García (Neotropical Entomology, 2017)

Inactivation of RAD52 and HDF1 DNA repair genes leads to premature chronological aging and cellular instability - Silvia Mercado-Sáenz; Beatriz López-Díaz; Francisco Sendra-Portero; Manuel Martínez-Morillo; Miguel J Ruiz-Gómez (Journal of Biosciences, 2017)

Growth activity, rooting capacity, and tropism: three auxinic precepts fulfilled by melatonin - M. B. Arnao; J. Hernández-Ruiz (Acta Physiologiae Plantarum, 2017)

Air–Water CO2 Fluxes and Net Ecosystem Production Changes in a Baja California Coastal Lagoon During the Anomalous North Pacific Warm Condition - Ma Carmen Ávila-López; J. Martín Hernández-Ayón; Víctor F. Camacho-Ibar; Armando Félix Bermúdez; Adan Mejía-Trejo; Isaí Pacheco-Ruiz; Jose M. Sandoval-Gil (Estuaries and Coasts, 2017)

Numerical Study of Blood Clots Influence on the Flow Pattern and Platelet Activation on a Stented Bifurcation Model - P. García Carrascal; J. García García; J. Sierra Pallares; F. Castro Ruiz; F. J. Manuel Martín (Annals of Biomedical Engineering, 2017)

Intrinsic and extrinsic drivers of yard vegetation in urban residential areas: implications for conservation planning - Khrisia A. Torres-Camacho; Elvia J. Meléndez-Ackerman; Elizabeth Díaz; Nicolás Correa; Cristina Vila-Ruiz; Sofía Olivero-Lora; Angélica Erazo; José Fontánez; Luis Santiago; José Seguinot (Urban Ecosystems, 2017)

Prediction of the effects of climate change on Sechium edule (Jacq.) Swartz varietal groups in Mexico - Rosalinda González-Santos; Jorge Cadena-Íñiguez; Francisco J. Morales-Flores; Víctor M. Ruiz-Vera; José Pimentel-López (Genetic Resources and Crop Evolution, 2017)

Intraspecific avian brood parasites avoid host nests infested by ectoparasites - Gustavo Tomás; David Martín-Gálvez; Magdalena Ruiz-Rodríguez; Juan J. Soler (Journal of Ornithology, 2017)

A synthesis of radial growth patterns preceding tree mortality - Maxime Cailleret; Steven Jansen; Elisabeth M. R. Robert; Lucía Desoto; Tuomas Aakala; Joseph A. Antos; Barbara Beikircher; Christof Bigler; Harald Bugmann; Marco Caccianiga; Vojtěch Čada; Jesus J. Camarero; et al. (Global Change Biology, 2017)
Tree mortality is a key factor influencing forest functions and dynamics, but our understanding of the mechanisms leading to mortality and the associated changes in tree growth rates are still limited. We compiled a new pan‐continental tree‐ring width database from sites where both dead and living trees were sampled (2970 dead and 4224 living trees from 190 sites, including 36 species), and compared early and recent growth rates between trees that died and those that survived a given mortality event. We observed a decrease in radial growth before death in ca. 84% of the mortality events. The extent and duration of these reductions were highly variable (1–100 years in 96% of events) due to the complex interactions among study species and the source(s) of mortality. Strong and long‐lasting declines were found for gymnosperms, shade‐ and drought‐tolerant species, and trees that died from competition. Angiosperms and trees that died due to biotic attacks (especially bark‐beetles) typically showed relatively small and short‐term growth reductions. Our analysis did not highlight any universal trade‐off between early growth and tree longevity within a species, although this result may also reflect high variability in sampling design among sites. The intersite and interspecific variability in growth patterns before mortality provides valuable information on the nature of the mortality process, which is consistent with our understanding of the physiological mechanisms leading to mortality. Abrupt changes in growth immediately before death can be associated with generalized hydraulic failure and/or bark‐beetle attack, while long‐term decrease in growth may be associated with a gradual decline in hydraulic performance coupled with depletion in carbon reserves. Our results imply that growth‐based mortality algorithms may be a powerful tool for predicting gymnosperm mortality induced by chronic stress, but not necessarily so for angiosperms and in case of intense drought or bark‐beetle outbreaks.

Tree mortality across biomes is promoted by drought intensity, lower wood density and higher specific leaf area - Sarah Greenwood; Paloma Ruiz‐Benito; Jordi Martínez‐Vilalta; Francisco Lloret; Thomas Kitzberger; Craig D. Allen; Rod Fensham; Daniel C. Laughlin; Jens Kattge; Gerhard Bönisch; Nathan J. B. Kraft; Alistair S. Jump (Ecology Letters, 2017)
Drought events are increasing globally, and reports of consequent forest mortality are widespread. However, due to a lack of a quantitative global synthesis, it is still not clear whether drought‐induced mortality rates differ among global biomes and whether functional traits influence the risk of drought‐induced mortality. To address these uncertainties, we performed a global meta‐analysis of 58 studies of drought‐induced forest mortality. Mortality rates were modelled as a function of drought, temperature, biomes, phylogenetic and functional groups and functional traits. We identified a consistent global‐scale response, where mortality increased with drought severity [log mortality (trees trees −1 year −1 ) increased 0.46 (95% CI = 0.2–0.7) with one SPEI unit drought intensity]. We found no significant differences in the magnitude of the response depending on forest biomes or between angiosperms and gymnosperms or evergreen and deciduous tree species. Functional traits explained some of the variation in drought responses between species (i.e. increased from 30 to 37% when wood density and specific leaf area were included). Tree species with denser wood and lower specific leaf area showed lower mortality responses. Our results illustrate the value of functional traits for understanding patterns of drought‐induced tree mortality and suggest that mortality could become increasingly widespread in the future.

A combined approach of methods for determining the regional assessment of the disjunct plant Primula pedemontana in Spain - E. Alfaro-Saiz; R. Alonso-Redondo; A. Rodríguez; J. A. Ruiz de Gopegui; L. García; M. García-González (Plant Biosystems, 2017)

Mutations in chromatin regulators functionally link Cornelia de Lange syndrome and clinically overlapping phenotypes - Ilaria Parenti; María E. Teresa-Rodrigo; Jelena Pozojevic; Sara Ruiz Gil; Ingrid Bader; Diana Braunholz; Nuria C. Bramswig; Cristina Gervasini; Lidia Larizza; Lutz Pfeiffer; Ferda Ozkinay; Feliciano Ramos; et al. (Human Genetics, 2017)

Characterization of the primary metabolome during the long-term response to NaHCO3-derived alkalinity in Lotus japonicus ecotypes Gifu B-129 and Miyakojima MG-20 - Cesar D. Bordenave; Rubén Rocco; María Florencia Babuin; María Paula Campestre; Francisco J. Escaray; Andrés Gárriz; Cristian Antonelli; Pedro Carrasco; Oscar A. Ruiz; Ana B. Menéndez (Acta Physiologiae Plantarum, 2017)

A cost-effective canopy temperature measurement system for precision agriculture: a case study on sugar beet - J. Martínez; G. Egea; J. Agüera; M. Pérez-Ruiz (Precision Agriculture, 2017)

Autoimmune reaction after anti-tetanus vaccination—description of four cases and review of the literature - N. Ruhrman-Shahar; J. Torres-Ruiz; P. Rotman-Pikielny; Y. Levy (Immunologic Research, 2017)

Frequency shift in topography of spontaneous brain rhythms from childhood to adulthood - E. I. Rodríguez-Martínez; F. J. Ruiz-Martínez; C. I. Barriga Paulino; Carlos M. Gómez (Cognitive Neurodynamics, 2017)

Immunological evidence for the presence of peroxiredoxin in pea leaf peroxisomes and response to oxidative stress conditions - Francisco J. Corpas; José R. Pedrajas; José M. Palma; Raquel Valderrama; Marta Rodríguez-Ruiz; Mounira Chaki; Luis A. del Río; Juan B. Barroso (Acta Physiologiae Plantarum, 2017)

Feeding regime, adult age and sexual size dimorphism as determinants of pre-copulatory sexual cannibalism in virgin wolf spiders - M. P. Gavín-Centol; S. Kralj-Fišer; E. De Mas; D. Ruiz-Lupión; J. Moya-Laraño (Behavioral Ecology and Sociobiology, 2017)

An Olive Tree Pruning Biorefinery for Co-Producing High Value-Added Bioproducts and Biofuels: Economic and Energy Efficiency Analysis - J. M. Romero-García; A. Sanchez; G. Rendón-Acosta; J. C. Martínez-Patiño; E. Ruiz; G. Magaña; E. Castro (BioEnergy Research, 2016)

Significance of the isolation of Staphylococcus aureus from a central venous catheter tip in the absence of concomitant bacteremia: a clinical approach - F. López-Medrano; J. Lora-Tamayo; M. Fernández-Ruiz; I. Losada; P. Hernández; M. Cepeda; R. San Juan; F. Chaves; J. M. Aguado (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Defenses against keratinolytic bacteria in birds living in radioactively contaminated areas - Magdalena Ruiz-Rodríguez; Anders Pape Møller; Timothy A. Mousseau; Juan J. Soler (The Science of Nature, 2016)

Neuroprotective Effect of the Novel Compound ITH33/IQM9.21 Against Oxidative Stress and Na+ and Ca2+ Overload in Motor Neuron-like NSC-34 Cells - Ana J. Moreno-Ortega; Lamiaa Mouhid Al-achbili; Elba Alonso; Cristóbal de los Ríos; Antonio G. García; Ana Ruiz-Nuño; María F. Cano-Abad (Neurotoxicity Research, 2016)

Infections shared with wildlife: an updated perspective - C. Gortázar; J. F. Ruiz-Fons; U. Höfle (European Journal of Wildlife Research, 2016)

When Cotton Rats Grasp Like Pandas - Juan Abella; Francisco J. Ruiz-Sánchez; Alberto Valenciano; Daniel Hontecillas; Alejandro Pérez-Ramos; Douglas Vera; Jonathan A. Santana-Cabrera; María H. Cornejo; Plinio Montoya; Jorge Morales (Journal of Mammalian Evolution, 2016)

Exploratory karyological and genome size studies in Chilean Sophora species - J Espejo; CM Baeza; J Loureiro; C Santos; D Boshier; E Ruiz (New Zealand Journal of Botany, 2016)
The genome of Sophora toromiro (Phil.) Skottsb. ( Papilionaceae ) is characterised by means of chromosome counts of accessions called Viña del Mar Botanical Garden (JBV), Göteborg (Got) and Titze. Karyotypes were obtained and genome size quantified using flow cytometry and compared to the closely related species Sophora macrocarpa J.E.Sm. and Sophora cassioides (Phil.) Sparre. No differences were detected in chromosome number of Sophora at intra‐specific or inter‐specific levels with 2 n = 2 x = 18. Analyses on the symmetry coefficients CV cl and M ca shows affinity between the analysed material of the Titze line. The graph clearly indicates differences between S. toromiro lines if compared with S. cassioides and S. macrocarpa . Genome size range from 788 Mbp for S. cassioides, 795 Mbp for S. macrocarpa and a range of 796–808 Mbp in S. toromiro . This is the first report of chromosome number and genome size for S. toromiro, S. macrocarpa and S. cassioides . This is of particular importance in S. toromiro , as it is has been considered extinct in its natural habitat for the past 50 years.

Shifts in the climate space of temperate cyprinid fishes due to climate change are coupled with altered body sizes and growth rates - Ana Ruiz‐Navarro; Phillipa K. Gillingham; J. Robert Britton (Global Change Biology, 2016)
Predictions of species responses to climate change often focus on distribution shifts, although responses can also include shifts in body sizes and population demographics. Here, shifts in the distributional ranges (‘climate space’), body sizes (as maximum theoretical body sizes, L ∞) and growth rates (as rate at which L ∞ is reached, K ) were predicted for five fishes of the Cyprinidae family in a temperate region over eight climate change projections. Great Britain was the model area, and the model species were Rutilus rutilus , Leuciscus leuciscus , Squalius cephalus , Gobio gobio and Abramis brama . Ensemble models predicted that the species' climate spaces would shift in all modelled projections, with the most drastic changes occurring under high emissions; all range centroids shifted in a north‐westerly direction. Predicted climate space expanded for R. rutilus and A. brama , contracted for S. cephalus , and for L. leuciscus and G. gobio , expanded under low‐emission scenarios but contracted under high emissions, suggesting the presence of some climate‐distribution thresholds. For R. rutilus , A. brama , S. cephalus and G. gobio , shifts in their climate space were coupled with predicted shifts to significantly smaller maximum body sizes and/or faster growth rates, aligning strongly to aspects of temperature‐body size theory. These predicted shifts in L ∞ and K had considerable consequences for size‐at‐age per species, suggesting substantial alterations in population age structures and abundances. Thus, when predicting climate change outcomes for species, outputs that couple shifts in climate space with altered body sizes and growth rates provide considerable insights into the population and community consequences, especially for species that cannot easily track their thermal niches.

Heterogeneous responses to ozone and nitrogen alter the species composition of Mediterranean annual pastures - H. Calvete-Sogo; I. González-Fernández; J. Sanz; S. Elvira; R. Alonso; H. García-Gómez; M. A. Ibáñez-Ruiz; V. Bermejo-Bermejo (Oecologia, 2016)

Evaluation of Dicyphus hesperus for biological control of sweet potato whitefly and potato psyllid on greenhouse tomato - F. J. Calvo; A. Torres-Ruiz; J. C. Velázquez-González; E. Rodríguez-Leyva; J. R. Lomeli-Flores (BioControl, 2016)

Metabolic responses to salinity changes in the subantarctic notothenioid teleost Eleginops maclovinus - L. Vargas-Chacoff; F. Moneva; R. Oyarzún; D. Martínez; E. Saavedra; I. Ruiz-Jarabo; J. L. P. Muñoz; C. Bertrán; J. M. Mancera (Polar Biology, 2016)

Reconstruction of Recent Sedimentary Processes in a Carbonate Platform (Gulf of Batabano, Cuba) Using Environmental Radiotracers - M. Díaz-Asencio; J. A. Corcho-Alvarado; J. A. Sánchez-Cabeza; A. C. Ruiz-Fernández; M. Eriksson (Estuaries and Coasts, 2016)

Origin of B chromosomes in the genus Astyanax (Characiformes, Characidae) and the limits of chromosome painting - Duílio M. Z. de A. Silva; Sandro Natal Daniel; Juan Pedro M. Camacho; Ricardo Utsunomia; Francisco J. Ruiz-Ruano; Manolo Penitente; José Carlos Pansonato-Alves; Diogo Teruo Hashimoto; Claudio Oliveira; Fábio Porto-Foresti; Fausto Foresti (Molecular Genetics and Genomics, 2016)

Reduced salivary gland size and increased presence of epithelial progenitor cells in DLK1-deficient mice - P. García-Gallastegui; J. Luzuriaga; M. Aurrekoetxea; V. Baladrón; M. J. Ruiz-Hidalgo; J. J. García-Ramírez; J. Laborda; F. Unda; G. Ibarretxe (Cell and Tissue Research, 2016)

Does larval food affect cuticular profiles and recognition in eusocial bees? a test on Scaptotrigona gynes (Hymenoptera: Meliponini) - E. Gutiérrez; D. Ruiz; T. Solís; W. de J. May-Itzá; H. Moo-Valle; J. J. G. Quezada-Euán (Behavioral Ecology and Sociobiology, 2016)

Disentangling the biogeography of ship biofouling: barnacles in the Northeast Pacific - G. V. Ashton; I. C. Davidson; J. Geller; G. M. Ruiz (Global Ecology and Biogeography, 2016)
Aim The movement of biofouling organisms by ships results in the transfer of marine species across biogeographical boundaries on a global scale. We used barnacles, a relatively well‐studied taxon, to investigate the extent to which modern commercial vessels disperse biofouling species beyond their current known ranges. Location Vessels predominantly operated in the North Pacific; sampling was conducted in Los Angeles (CA), Portland (OR), Ketchikan (AK) and Apra Harbor (GU). Methods Barnacles were collected from submerged surfaces of commercial vessel hulls and identified to the lowest taxonomic unit using a combination of taxonomic and molecular phylogenetic techniques. Their known native and non‐native geographical ranges were assessed and compared with the voyage history of the vessels. Results Forty distinct taxonomic groups of barnacles (22 assigned to species) were detected from 15 vessels. Six of these recognized species have a world‐wide distribution, due to natural and anthropogenic dispersal. Sixteen species were on vessels with voyage routes that extend beyond the barnacles' known distributions, including 12 species sampled outside of their known range. Main conclusions A diverse suite of barnacle species is in continuous motion globally on commercial vessel hulls, and the potential scale of this transfer is underscored by the documented species richness for ship biofouling and what is known about the global fleet of vessels. We estimate roughly 680,000 separate arrival events per year for barnacle species to US ports distributed on both Atlantic and Pacific coasts. Genetic methods revealed high richness compared with previous studies, and the real rate is likely to be much higher than this because (1) it is likely that not all species on a vessel were sampled and (2) only a subset of sampled barnacles were successfully sequenced. Our limited knowledge about the total species pool in flux on ship hulls around the globe constrains our ability to analyse and interpret processes affecting species distribution patterns in the Anthropocene.

Modulation of superoxide dismutase (SOD) isozymes by organ development and high long-term salinity in the halophyte Cakile maritima - Hayet Houmani; Marta Rodríguez-Ruiz; José M. Palma; Chedly Abdelly; Francisco J. Corpas (Protoplasma, 2016)

DADA: data assimilation for the detection and attribution of weather and climate-related events - A. Hannart; A. Carrassi; M. Bocquet; M. Ghil; P. Naveau; M. Pulido; J. Ruiz; P. Tandeo (Climatic Change, 2016)

Interindividual variation in gene expression responses and metabolite formation in acetaminophen-exposed primary human hepatocytes - Marlon J. A. Jetten; Ainhoa Ruiz-Aracama; Maarten L. J. Coonen; Sandra M. Claessen; Marcel H. M. van Herwijnen; Arjen Lommen; Joost H. M. van Delft; Ad A. C. M. Peijnenburg; Jos C. S. Kleinjans (Archives of Toxicology, 2016)

Identification and reproducibility of diagnostic DNA markers for tuber starch and yield optimization in a novel association mapping population of potato (Solanum tuberosum L.) - E. M. Schönhals; F. Ortega; L. Barandalla; A. Aragones; J. I. Ruiz de Galarreta; J.-C. Liao; R. Sanetomo; B. Walkemeier; E. Tacke; E. Ritter; C. Gebhardt (Theoretical and Applied Genetics, 2016)

Oscillations, Timing, Plasticity, and Learning in the Cerebellum - G. Cheron; J. Márquez-Ruiz; B. Dan (The Cerebellum, 2016)

Impact of acid mine drainages on surficial waters of an abandoned mining site - M L García-Lorenzo; J. Marimón; M C Navarro-Hervás; C. Pérez-Sirvent; M J Martínez-Sánchez; José Molina-Ruiz (Environmental Science and Pollution Research, 2016)

Implementation of an experimental nutrient film technique-type aquaponic system - D. Castillo-Castellanos; I. Zavala-Leal; J. M. J. Ruiz-Velazco; A. Radilla-García; J. T. Nieto-Navarro; C. A. Romero-Bañuelos; J. González-Hernández (Aquaculture International, 2016)

Small-Scale Assays for Studying Dissolution of Pharmaceutical Cocrystals for Oral Administration - Karl J. Box; John Comer; Robert Taylor; Shyam Karki; Rebeca Ruiz; Robert Price; Nikoletta Fotaki (AAPS PharmSciTech, 2016)

Arbuscular mycorrhizal symbiosis regulates physiology and performance of Digitaria eriantha plants subjected to abiotic stresses by modulating antioxidant and jasmonate levels - H. Pedranzani; M. Rodríguez-Rivera; M. Gutiérrez; R. Porcel; B. Hause; J. M. Ruiz-Lozano (Mycorrhiza, 2016)

New member of the R2R3-MYB transcription factors family in grapevine suppresses the anthocyanin accumulation in the flowers of transgenic tobacco - J. Ricardo Pérez-Díaz; Jorge Pérez-Díaz; José Madrid-Espinoza; Enrique González-Villanueva; Yerko Moreno; Simón Ruiz-Lara (Plant Molecular Biology, 2016)

Effects on the metabolism, growth, digestive capacity and osmoregulation of juvenile of Sub-Antarctic Notothenioid fish Eleginops maclovinus acclimated at different salinities - L. Vargas-Chacoff; E. Saavedra; R. Oyarzún; E. Martínez-Montaño; J. P. Pontigo; A. Yáñez; I. Ruiz-Jarabo; J. M. Mancera; E. Ortiz; C. Bertrán (Fish Physiology and Biochemistry, 2015)

Pollen calendars: a guide to common airborne pollen in Andalusia - M. Martínez-Bracero; P. Alcázar; C. Díaz de la Guardia; F. J. González-Minero; L. Ruiz; M. M. Trigo Pérez; C. Galán (Aerobiologia, 2015)

Numerical simulation of tsunami runup in northern Chile based on non-uniform k −2 slip distributions - J. A. Ruiz; M. Fuentes; S. Riquelme; J. Campos; A. Cisternas (Natural Hazards, 2015)

Functional and in silico assessment of MAX variants of unknown significance - Iñaki Comino-Méndez; Luis J Leandro-García; Guillermo Montoya; Lucía Inglada-Pérez; Aguirre A. de Cubas; María Currás-Freixes; Carolyn Tysoe; Louise Izatt; Rocío Letón; Álvaro Gómez-Graña; Veronika Mancikova; María Apellániz-Ruiz; et al. (Journal of Molecular Medicine, 2015)

The effect of electron acceptors on biogas production from tannery sludge of a Mexican wastewater plant - G. M. L. Ruiz-Aguilar; N. Lovanh; E. A. Camarena-Aguilar; B. E. Gomez-Luna; J. Molina-Ochoa; V. J. Alvarez-Villafaña; O. Sosa (International Journal of Environmental Science and Technology, 2015)

Synergistic effects of propagule pressure and trophic subsidies overcome biotic resistance to a non-native fish - J. Robert Britton; Thi Nhat Quyen Tran; Ana Ruiz-Navarro (Biological Invasions, 2015)

Canopy warming caused photosynthetic acclimation and reduced seed yield in maize grown at ambient and elevated [ CO 2 ] - Ursula M. Ruiz‐Vera; Matthew H. Siebers; David W. Drag; Donald R. Ort; Carl J. Bernacchi (Global Change Biology, 2015)
Rising atmospheric CO 2 concentration ([ CO 2 ]) and attendant increases in growing season temperature are expected to be the most important global change factors impacting production agriculture. Although maize is the most highly produced crop worldwide, few studies have evaluated the interactive effects of elevated [ CO 2 ] and temperature on its photosynthetic physiology, agronomic traits or biomass, and seed yield under open field conditions. This study investigates the effects of rising [ CO 2 ] and warmer temperature, independently and in combination, on maize grown in the field throughout a full growing season. Free‐air CO 2 enrichment ( FACE ) technology was used to target atmospheric [ CO 2 ] to 200 μ mol mol −1 above ambient [ CO 2 ] and infrared heaters to target a plant canopy increase of 3.5 °C, with actual season mean heating of ~2.7 °C, mimicking conditions predicted by the second half of this century. Photosynthetic gas‐exchange parameters, leaf nitrogen and carbon content, leaf water potential components, and developmental measurements were collected throughout the season, and biomass and yield were measured at the end of the growing season. As predicted for a C 4 plant, elevated [ CO 2 ] did not stimulate photosynthesis, biomass, or yield. Canopy warming caused a large shift in aboveground allocation by stimulating season‐long vegetative biomass and decreasing reproductive biomass accumulation at both CO 2 concentrations, resulting in decreased harvest index. Warming caused a reduction in photosynthesis due to down‐regulation of photosynthetic biochemical parameters and the decrease in the electron transport rate. The reduction in seed yield with warming was driven by reduced photosynthetic capacity and by a shift in aboveground carbon allocation away from reproduction. This field study portends that future warming will reduce yield in maize, and this will not be mitigated by higher atmospheric [ CO 2 ] unless appropriate adaptation traits can be introduced into future cultivars.

Topographical Distribution of Morphological Changes in a Partial Model of Parkinson’s Disease—Effects of Nanoencapsulated Neurotrophic Factors Administration - C. Requejo; J. A. Ruiz-Ortega; H. Bengoetxea; A. Garcia-Blanco; E. Herrán; A. Aristieta; M. Igartua; L. Ugedo; J. L. Pedraz; R. M. Hernández; J. V. Lafuente (Molecular Neurobiology, 2015)

Biodiversity in the by-catch communities of the pelagic ecosystem in the Western Indian Ocean - N. Lezama-Ochoa; H. Murua; G. Chust; J. Ruiz; P. Chavance; A. Delgado de Molina; A. Caballero; I. Sancristobal (Biodiversity and Conservation, 2015)

Isolation by distance, resistance and/or clusters? Lessons learned from a forest‐dwelling carnivore inhabiting a heterogeneous landscape - Aritz Ruiz‐Gonzalez; Samuel A. Cushman; María José Madeira; Ettore Randi; Benjamín J. Gómez‐Moliner (Molecular Ecology, 2015)
Landscape genetics provides a valuable framework to understand how landscape features influence gene flow and to disentangle the factors that lead to discrete and/or clinal population structure. Here, we attempt to differentiate between these processes in a forest‐dwelling small carnivore [European pine marten ( Martes martes )]. Specifically, we used complementary analytical approaches to quantify the spatially explicit genetic structure and diversity and analyse patterns of gene flow for 140 individuals genotyped at 15 microsatellite loci. We first used spatially explicit and nonspatial Bayesian clustering algorithms to partition the sample into discrete clusters and evaluate hypotheses of ‘isolation by barriers’ ( IBB ). We further characterized the relationships between genetic distance and geographical (‘isolation by distance’, IBD ) and ecological distances (‘isolation by resistance’, IBR ) obtained from optimized landscape models. Using a reciprocal causal modelling approach, we competed the IBD , IBR and IBB hypotheses with each other to unravel factors driving population genetic structure. Additionally, we further assessed spatially explicit indices of genetic diversity using sGD across potentially overlapping genetic neighbourhoods that matched the inferred population structure. Our results revealed a complex spatial genetic cline that appears to be driven jointly by IBD and partial barriers to gene flow ( IBB ) associated with poor habitat and interspecific competition. Habitat loss and fragmentation, in synergy with past overharvesting and possible interspecific competition with sympatric stone marten ( Martes foina ), are likely the main factors responsible for the spatial genetic structure we observed. These results emphasize the need for a more thorough evaluation of discrete and clinal hypotheses governing gene flow in landscape genetic studies, and the potential influence of different limiting factors affecting genetic structure at different spatial scales.

Relationships Between M w and Other Earthquake Size Parameters in the Spanish IGN Seismic Catalog - L. Cabañas; A. Rivas-Medina; J. M. Martínez-Solares; J. M. Gaspar-Escribano; B. Benito; R. Antón; S. Ruiz-Barajas (Pure and Applied Geophysics, 2015)

Microirradiation techniques in radiobiological research - Guido A Drexler; Miguel J Ruiz-Gómez (Journal of Biosciences, 2015)

Scenario-targeted toxicity assessment through multiple endpoint bioassays in a soil posing unacceptable environmental risk according to regulatory screening values - A. Rodriguez-Ruiz; J. Etxebarria; L. Boatti; I. Marigómez (Environmental Science and Pollution Research, 2015)

Effects of reaction time variability and age on brain activity during Stroop task performance - Angela Tam; Angela C. Luedke; Jeremy J. Walsh; Juan Fernandez-Ruiz; Angeles Garcia (Brain Imaging and Behavior, 2015)

Artificial M arine M icro‐ R eserves N etworks ( AMMRN s): an innovative approach to conserve marine littoral biodiversity and protect endangered species - José C. García‐Gómez; José M. Guerra‐García; Free Espinosa; Manuel J. Maestre; Georgina Rivera‐Ingraham; Darren Fa; Alexander R. González; Aurora Ruiz‐Tabares; Carlos M. López‐Fé (Marine Ecology, 2015)
Coastal engineering works, especially the outer breakwaters of ports where environmental conditions are usually good, often constitute new habitats for marine littoral species. Their potential indirect contribution to the regeneration and conservation of protected species opens up a new perspective in protection of marine biodiversity. This is particularly true when these works harbour, as we show here, important reproductive populations of species that are threatened or even in danger of extinction. We provide integrated data on protected marine species in Southern Iberia established on different substrata (quarried dolomitic rocks, concrete cubic blocks, concrete tetrapods and vertical concrete walls) that are used in the construction of artificial levees that could potentially be Artificial Marine Micro‐Reserves ( AMMR s). We also present the first evidence of the ‘reserve effect’ in potential AMMR s and we discuss the need for the creation of AMMR s including their effective networking ( AMMRN s), supporting data for which has been observed by studying coastal facilities subjected to strict access restrictions (for security reasons, not conservation). These facilities have acted as valuable proxies and, in reality, potentially act as AMMR s, as well as having a role in helping to detect and control invasive species. We discuss the ecological engineering aspects related to the design and type of materials used in coastal constructions with a view to aiding the integration of these into existing coastal ecosystems as well as promoting greater settlement of species and therefore increases in biodiversity. Finally, the environmental implications of AMMRN s within the future implementation strategy of the Water Framework Directive 2000/60 EC are also discussed.

Interpreting faecal nitrogen as a non-invasive indicator of diet quality and body condition in contexts of high ungulate density - Antonio J. Carpio; José Guerrero-Casado; Leire Ruiz-Aizpurua; Francisco S. Tortosa; Joaquin Vicente (European Journal of Wildlife Research, 2015)

A More Efficient Rainfall Intensity-Duration-Frequency Relationship by Using an “at-site” Regional Frequency Analysis: Application at Mediterranean Climate Locations - J. L. Ayuso-Muñoz; A. P. García-Marín; P. Ayuso-Ruiz; J. Estévez; R. Pizarro-Tapia; E. V. Taguas (Water Resources Management, 2015)

Roles of some nitrogenous compounds protectors in the resistance to zinc toxicity in Lactuca sativa cv. Phillipus and Brassica oleracea cv. Bronco - V. Paradisone; Y. Barrameda-Medina; D. Montesinos-Pereira; L. Romero; S. Esposito; J. M. Ruiz (Acta Physiologiae Plantarum, 2015)

Population Growth and Characterization of Plant Injuries of Steneotarsonemus spinki Smiley (Acari: Tarsonemidae) on Rice - I A Jaimez-Ruiz; G Otero-Colina; G Valdovinos-Ponce; J A Villanueva-Jiménez; J Vera-Graziano (Neotropical Entomology, 2015)

Intragenomic distribution of RTE retroelements suggests intrachromosomal movement - Eugenia E. Montiel; Francisco J. Ruiz-Ruano; Josefa Cabrero; Juan Alberto Marchal; Antonio Sánchez; Francisco Perfectti; María Dolores López-León; Juan Pedro M. Camacho (Chromosome Research, 2015)

Chronic and recreational use of cocaine is associated with a vulnerability to semantic interference - Manuel J. Ruiz; Daniela Paolieri; Lorenza S. Colzato; María Teresa Bajo (Psychopharmacology, 2015)

Mercury in the blue tilapia Oreochromis aureus from a dam located in a mining region of NW Mexico: seasonal variation and percentage weekly intake (PWI) - J. Ruelas-Inzunza; E. Rojas-Ruiz; M. Spanopoulos-Hernández; G. Barba-Quintero (Environmental Monitoring and Assessment, 2015)

The Addiction-Related Gene ANKK1 in Parkinsonian Patients with Impulse Control Disorder - Janet Hoenicka; Pedro J. García-Ruiz; Guillermo Ponce; Antonio Herranz; Dolores Martínez-Rubio; Estela Pérez-Santamarina; Francesc Palau (Neurotoxicity Research, 2015)

Topo-Iberia project: CGPS crustal velocity field in the Iberian Peninsula and Morocco - J. Garate; J. Martin-Davila; G. Khazaradze; A. Echeverria; E. Asensio; A. J. Gil; M. C. de Lacy; J. A. Armenteros; A. M. Ruiz; J. Gallastegui; F. Alvarez-Lobato; C. Ayala; et al. (GPS Solutions, 2015)

Re-assessing volcanic hazard zonation of Volcán de Colima, México - L. Capra; J. C. Gavilanes-Ruiz; R. Bonasia; R. Saucedo-Giron; R. Sulpizio (Natural Hazards, 2015)

Size-resolved characterisation of organic compounds in atmospheric aerosols collected at Welgegund, South Africa - Wanda Booyens; Pieter G. Van Zyl; Johan P. Beukes; Jose Ruiz-Jimenez; Matias Kopperi; Marja-Liisa Riekkola; Miroslav Josipovic; Andrew D. Venter; Kerneels Jaars; Lauri Laakso; Ville Vakkari; Markku Kulmala; et al. (Journal of Atmospheric Chemistry, 2015)

Genetic Differentiation in Response to Selection for Water-Soluble Carbohydrate Content in Perennial Ryegrass (Lolium perenne L.) - J. A. Gallagher; L. B. Turner; A. J. Cairns; M. Farrell; J. A. Lovatt; K. Skøt; I. P. Armstead; M. O. Humphreys; I. Roldan-Ruiz (BioEnergy Research, 2015)

Thermal Impact from a Thermoelectric Power Plant on a Tropical Coastal Lagoon - J. G. Cardoso-Mohedano; R. Bernardello; J. A. Sanchez-Cabeza; A. C. Ruiz-Fernández; R. Alonso-Rodriguez; A. Cruzado (Water, Air, & Soil Pollution, 2015)

Progressive migration and anagenesis in Drimys confertifolia of the Juan Fernández Archipelago, Chile - Patricio López-Sepúlveda; Koji Takayama; Josef Greimler; Daniel J. Crawford; Patricio Peñailillo; Marcelo Baeza; Eduardo Ruiz; Gudrun Kohl; Karin Tremetsberger; Alejandro Gatica; Luis Letelier; Patricio Novoa; et al. (Journal of Plant Research, 2015)

Daily otolith growth and ontogenetic geochemical signatures of age-0 anchovy (Engraulis encrasicolus) in the Gulf of Cádiz (SW Spain). - I. A. CATALÁN; S. PÉREZ-MAYOL; I. ÁLVAREZ; J. RUIZ; M. PALMER; F. BALDÓ; Á. PELIZ; B. MORALES-NIN (Mediterranean Marine Science, 2014)
The European anchovy fishery in the Gulf of Cádiz (ICES Division IXa South) is largely influenced by age-0 individuals. Knowledge of young of the year growth dynamics is crucial for management, yet data on daily growth are lacking in the area. Linking growth patterns to the environment requires information on habitat occupancy through ontogeny of the fish that reach the fishery, as anchovy use different areas of the Gulf and the Guadalquivir Estuary through development. We describe the growth dynamics of age-0 anchovy through otolith microstructure analysis, and couple these data with data on microchemical signals in the otoliths to shed light into habitat use and growth dynamics in the area. Age-0 anchovy captured in September, 2011 in the Gulf ranged from 3 to 6 months old for similar sizes, with average growth rates varying twofold. Individual non-linear growth curves showed that maximum otolith growth was positively correlated with the date of spawning, which in turn was negatively correlated with the time to reach maximum growth. There was no correlation between growth parameters and body length or condition (Fulton K) at capture. The strontium:calcium (Sr/Ca) and magnesium:calcium (Mg/Ca) ratios were significantly lower at the edge of the otolith (approximately the age of capture) than at ages corresponding to larval and early juveniles (

A high-resolution hydrodynamic-biogeochemical coupled model of the Gulf of Cadiz – Alboran Sea region. - D. M. MACIAS; C. T. GUERREIRO; L. PRIETO; A. PELIZ; J. RUIZ (Mediterranean Marine Science, 2014)
The southern Iberia regional seas comprise the Gulf of Cadiz and the Alboran Sea sub-basins connected by the narrow Strait of Gibraltar. Both basins are very different in their hydrological and biological characteristics but are, also, tightly connected to each other. Integrative studies of the whole regional oceanic system are scarce and difficult to perform due to the relative large area to cover and the different relevant time-scales of the main forcings in each sub-basin. Here we propose, for the first time, a fully coupled, 3D, hydrodynamic-biogeochemical model that covers, in a single domain (~2km resolution) both marine basins for a 20 years simulation (1989-2008). Model performance is assessed against available data in terms of spatial and temporal distributions of biological variables. In general, the proposed model is able to represent the climatological distributions of primary and secondary producers and also the main seasonality of primary production in the different sub-regions of the analyzed basins. Potential causes of the observed mismatches between model and data are identified and some solutions are proposed for future model development. We conclude that most of these mismatches could be attributed to the missing tidal forcing in the actual model configuration. This model is a first step to obtain a meaningful tool to study past and future oceanographic conditions in this important marine region constituting the unique connection of the Mediterranean Sea with the open world’s ocean.

Discoloration and Organic Matter Removal from Coffee Wastewater by Electrochemical Advanced Oxidation Processes - M. Villanueva-Rodríguez; R. Bello-Mendoza; D. G. Wareham; E. J. Ruiz-Ruiz; M. L. Maya-Treviño (Water, Air, & Soil Pollution, 2014)

Morphotectonic characterization of the quaternary intermontane basins of the Umbria-Marche Apennines (Italy) - D. Aringoli; P. Cavitolo; P. Farabollini; J. Galindo-Zaldivar; B. Gentili; S. I. Giano; A. C. Lòpez-Garrido; M. Materazzi; L. Nibbi; A. Pedrera; G. Pambianchi; P. Ruano; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2014)

Enhancing Effect of Glucose Microspheres in the Viability of Human Mesenchymal Stem Cell Suspensions for Clinical Administration - Patricia Gálvez; Maria J. Martín; Ana C. Calpena; Juan A. Tamayo; Maria A. Ruiz; Beatriz Clares (Pharmaceutical Research, 2014)

Spider mites adaptively learn recognizing mycorrhiza-induced changes in host plant volatiles - J. David Patiño-Ruiz; Peter Schausberger (Experimental and Applied Acarology, 2014)

Stand Structure and Recent Climate Change Constrain Stand Basal Area Change in European Forests: A Comparison Across Boreal, Temperate, and Mediterranean Biomes - P. Ruiz-Benito; J. Madrigal-González; S. Ratcliffe; D. A. Coomes; G. Kändler; A. Lehtonen; C. Wirth; M. A. Zavala (Ecosystems, 2014)

Late Jurassic terrane collision in the northwestern margin of Gondwana (Cajamarca Complex, eastern flank of the Central Cordillera, Colombia) - I. F. Blanco-Quintero; A. García-Casco; L. M. Toro; M. Moreno; E. C. Ruiz; C. J. Vinasco; A. Cardona; C. Lázaro; D. Morata (International Geology Review, 2014)

Large wood transport as significant influence on flood risk in a mountain village - V. Ruiz-Villanueva; J. M. Bodoque; A. Díez-Herrero; E. Bladé (Natural Hazards, 2014)

Multi-commutated fluorometric optosensor for the determination of citrinin in rice and red yeast rice supplements - J. Jiménez-López; E.J. Llorent-Martínez; P. Ortega-Barrales; A. Ruiz-Medina (Food Additives & Contaminants: Part A, 2014)

Comprehensive Study of Early Features in Spinocerebellar Ataxia 2: Delineating the Prodromal Stage of the Disease - Luis Velázquez-Pérez; Roberto Rodríguez-Labrada; Edilia M. Cruz-Rivas; Juan Fernández-Ruiz; Israel Vaca-Palomares; Jandy Lilia-Campins; Bulmaro Cisneros; Arnoy Peña-Acosta; Yaimeé Vázquez-Mojena; Rosalinda Diaz; Jonathan J. Magaña-Aguirre; Tania Cruz-Mariño; et al. (The Cerebellum, 2014)

Genetic introgression of cultured rainbow trout in the Mexican native trout complex - Marco A. Escalante; Francisco J. García-De-León; Casey B. Dillman; Anabelia de los Santos Camarillo; Anna George; Irene de los A. Barriga-Sosa; Arturo Ruiz-Luna; Richard L. Mayden; Stéphanie Manel (Conservation Genetics, 2014)

Distribution of peptidergic populations in the human dentate gyrus (Somatostatin [SOM-28, SOM-12] and Neuropeptide Y [NPY]) during postnatal development - S. Cebada-Sánchez; R. Insausti; J. González-Fuentes; M. M. Arroyo-Jiménez; E. Rivas-Infante; M. J. Lagartos; J. Martínez-Ruiz; G. Lozano; P. Marcos (Cell and Tissue Research, 2014)

Integration of conflict into integrative taxonomy: fitting hybridization in species delimitation of M esocarabus ( C oleoptera: C arabidae) - C. Andújar; P. Arribas; C. Ruiz; J. Serrano; J. Gómez‐Zurita (Molecular Ecology, 2014)
In species differentiation, characters may not diverge synchronously, and there are also processes that shuffle character states in lineages descendant from a common ancestor. Species are thus expected to show some degree of incongruence among characters; therefore, taxonomic delimitation can benefit from integrative approaches and objective strategies that account for character conflict. We illustrate the potential of exploiting conflict for species delimitation in a study case of ground beetles of the subgenus Carabus ( Mesocarabus ), where traditional taxonomy does not accurately delimit species. The molecular phylogenies of four mitochondrial and three nuclear genes, cladistic analysis of the aedeagus, ecological niche divergence and morphometry of pronotal shape in more than 500 specimens of Mesocarabus show that these characters are not fully congruent. For these data, a three‐step operational strategy is proposed for species delimitation by (i) delineating candidate species based on the integration of incongruence among conclusive lines of evidence, (ii) corroborating candidate species with inconclusive lines of evidence and (iii) refining a final species proposal based on an integrated characterization of candidate species based on the evolutionary analysis of incongruence. This procedure provided a general understanding of the reticulate process of hybridization and introgression acting on Mesocarabus and generated the hypothesis of seven Mesocarabus species, including two putative hybrid lineages. Our work emphasizes the importance of incorporating critical analyses of character and phylogenetic conflict to infer both the evolutionary history and species boundaries through an integrative taxonomic approach.

Seasonal dynamics of autotrophic and heterotrophic plankton metabolism and P CO2 in a subarctic Greenland fjord - Mikael K. Sejr; Dorte Krause-Jensen; Tage Dalsgaard; Sergio Ruiz-Halpern; Carlos M. Duarte; Mathias Middelboe; Ronne N. Glud; Jørgen Bendtsen; Thorsten J. S. Balsby; Søren Rysgaard (Limnology and Oceanography, 2014)
We measured net planktonic community production (NCP), community respiration (CR), and gross primary production (GPP) in September, February, and May in a subarctic Greenland fjord influenced by glacial meltwater and terrestrial runoff. Potential controls of pelagic carbon cycling, including the role of terrestrial carbon, were investigated by relating surface‐water partial pressure of CO 2 (P CO2 ), NCP, GPP, and CR to physicochemical conditions, chlorophyll a (Chl a) concentration, phytoplankton production, inventories of particulate (POC) and dissolved organic carbon (DOC) and vertical flux of POC. The planktonic community was net heterotrophic in the photic zone in September (NCP 5 ‒21 ± 45 mmol O 2 m ‒2 d ‒1 ) and February (NCP 5 ‒17 mmol O 2 m ‒2 d ‒1 ) but net autotrophic during a developing spring bloom in May (NCP 5 129 ± 102 mmol O 2 m ‒2 d ‒1 ). In September, higher temperatures, shorter day lengths, and lower Chl a concentrations compared with May caused increased rates of CR, lower GPP rates, and net heterotrophy in the photic zone. The GPP required to exceed CR and where NCP becomes positive was low (in May: 1.58 ± 0.48 µ mol O 2 L ‒1 d ‒1 and September: 3.06 ± 0.82 µ mol O 2 L ‒1 d ‒1 ) and in the range of open ocean values, indicating that allochtonous carbon did not stimulate CR. The P CO2 in the surface water was below atmospheric levels (September average 25.0 ± 0.71 Pa, February 35.4 ± 0.40 Pa, and May 19.8 ± 1.21 Pa), rendering the ecosystem a sink of atmospheric CO 2 . NCP was identified as an important driver of surface P CO2 , with high rates of autotrophy and vertical export of POC reducing surface P CO2 during summer. In winter, net heterotrophy added CO 2 to the water column, but this postive effect on P CO2 was balanced by simultaneous cooling of the water column, which decreased P CO2 because of increased solubility of CO 2 . High autochthonous production implies a relatively limited influence of allochthonous carbon on pelagic carbon balance and CO 2 dynamics in the fjord.

Dimorphism and hydrocarbon metabolism in Yarrowia lipolytica var. indica - A. S. Palande; S. V. Kulkarni; C. León-Ramirez; E. Campos-Góngora; J. Ruiz-Herrera; M. V. Deshpande (Archives of Microbiology, 2014)

The CarD / CarG regulatory complex is required for the action of several members of the large set of M yxococcus xanthus extracytoplasmic function σ factors - Javier Abellón‐Ruiz; Diego Bernal‐Bernal; María Abellán; Marta Fontes; S. Padmanabhan; Francisco J. Murillo; Montserrat Elías‐Arnanz (Environmental Microbiology, 2014)
Summary Extracytoplasmic function ( ECF ) σ factors are critical players in signal transduction networks involved in bacterial response to environmental changes. The M yxococcus xanthus genome reveals ∼45 putative ECF ‐σ factors, but for the overwhelming majority, the specific signals or mechanisms for selective activation and regulation remain unknown. One well‐studied ECF ‐σ, CarQ , binds to its anti‐σ, CarR , and is inactive in the dark but drives its own expression from promoter P QRS on illumination. This requires the CarD / CarG complex, the integration host factor ( IHF ) and a specific CarD ‐binding site upstream of P QRS . Here, we show that DdvS , a previously uncharacterized ECF ‐σ, activates its own expression in a CarD / CarG ‐dependent manner but is inhibited when specifically bound to the N ‐terminal zinc‐binding anti‐σ domain of its cognate anti‐σ, DdvA . Interestingly, we find that the autoregulatory action of 11 other ECF ‐σ factors studied here depends totally or partially on CarD / CarG but not IHF . In silico analysis revealed possible CarD ‐binding sites that may be involved in direct regulation by CarD / CarG of target promoter activity. CarD / CarG ‐linked ECF ‐σ regulation likely recurs in other myxobacteria with CarD / CarG orthologous pairs and could underlie, at least in part, the global regulatory effect of the complex on M . xanthus gene expression.

Distribution of heavy metals and pollution pathways in a shallow marine shelf: assessment for a future management - F. Ruiz; M. L. González-Regalado; J. M. Muñoz; M. Abad; A. Toscano; M. I. Prudencio; M. I. Dias (International Journal of Environmental Science and Technology, 2014)

Compositional Effects of Sea-Level Rise in a Patchy Landscape: The Dynamics of Tree Islands in the Southeastern Coastal Everglades - M. S. Ross; J. P. Sah; J. F. Meeder; P. L. Ruiz; G. Telesnicki (Wetlands, 2014)

The first incidence of an alien soft coral of the family Xeniidae in the Caribbean, an invasion in eastern Venezuelan coral communities - J. P. Ruiz Allais; M. E. Amaro; C. S. McFadden; A. Halász; Y. Benayahu (Coral Reefs, 2014)

Floods at the northern foothills of the Tatra Mountains — A Polish-Swiss research project - Zbigniew W. Kundzewicz; Markus Stoffel; Ryszard J. Kaczka; Bartłomiej Wyżga; Tadeusz Niedźwiedź; Iwona Pińskwar; Virginia Ruiz-Villanueva; Ewa Łupikasza; Barbara Czajka; Juan Antonio Ballesteros-Canovas; Łukasz Małarzewski; Adam Choryński; et al. (Acta Geophysica, 2014)

Direct ageing of Thunnus thynnus from the eastern Atlantic Ocean and western Mediterranean Sea using dorsal fin spines - P. L. Luque; E. Rodriguez‐Marin; J. Landa; M. Ruiz; P. Quelle; D. Macias; J. M. Ortiz De Urbina (Journal of Fish Biology, 2014)
This study deals with important methodology issues that affect age estimates of eastern Atlantic bluefin tuna Thunnus thynnus using dorsal fin spines. Nearly 3800 spine sections were used from fish caught in the north‐east Atlantic Ocean and western Mediterranean Sea over a 21 year period. Edge type and marginal increment analyses indicated a yearly periodicity of annulus formation with the translucent bands (50% of occurrence) appearing from October to May. Nucleus vascularization seriously affected specimens older than 6 years, with the disappearance of 40–50% of the presumed annuli by that age. An alternate sectioning location was a clear improvement and this finding is an important contribution to the methodology of using this structure for ageing the full‐length range of eastern T. thynnus . Finally, there were no significant differences between the coefficients of von Bertalanffy growth model estimated from mean length at age data ( L ∞ = 327·4; k = 0·097; t 0 = −0·838) and those estimated from the growth curves accepted for the eastern and western T. thynnus management units.

Modulation of the subthalamic nucleus activity by serotonergic agents and fluoxetine administration - A. Aristieta; T. Morera-Herreras; J. A. Ruiz-Ortega; C. Miguelez; I. Vidaurrazaga; A. Arrue; M. Zumarraga; L. Ugedo (Psychopharmacology, 2014)

A genome-wide association study on copy-number variation identifies a 11q11 loss as a candidate susceptibility variant for colorectal cancer - C. Fernandez-Rozadilla; J. B. Cazier; I. Tomlinson; A. Brea-Fernández; M. J. Lamas; M. Baiget; L. A. López-Fernández; J. Clofent; L. Bujanda; D. Gonzalez; L. de Castro; K. Hemminki; et al. (Human Genetics, 2014)

Assessment of Jatropha curcas L. biodiesel seed cake toxicity using the zebrafish (Danio rerio) embryo toxicity (ZFET) test - Arnold V. Hallare; Paulo Lorenzo S. Ruiz; J. C. Earl D. Cariño (Environmental Science and Pollution Research, 2014)

Evaluation of three simulation approaches for assessing yield of rainfed sunflower in a Mediterranean environment for climate change impact modelling - J. García-López; Ignacio J. Lorite; R. García-Ruiz; J. Domínguez (Climatic Change, 2014)

Improving Eye Safety in Citrus Harvest Crews Through the Acceptance of Personal Protective Equipment, Community-based Participatory Research, Social Marketing, and Community Health Workers - J. Antonio Tovar-Aguilar; Paul F. Monaghan; Carol A. Bryant; Andrew Esposito; Mark Wade; Omar Ruiz; Robert J. McDermott (Journal of Agromedicine, 2014)

Improving Eye Safety in Citrus Harvest Crews Through the Acceptance of Personal Protective Equipment, Community-Based Participatory Research, Social Marketing, and Community Health Workers - J. Antonio Tovar-Aguilar; Paul F. Monaghan; Carol A. Bryant; Andrew Esposito; Mark Wade; Omar Ruiz; Robert J. McDermott (Journal of Agromedicine, 2014)

Evaluation of resistance of Spanish olive cultivars to Verticillium dahliae in inoculations conducted in greenhouse - G. M. Garcia-Ruiz; C. Trapero; C. Del Rio; F. J. Lopez-Escudero (Phytoparasitica, 2014)

Genetic structure of a phytophagous mite species affected by crop practices: the case of Tetranychus urticae in clementine mandarins - S. Pascual-Ruiz; M. A. Gómez-Martinez; T. Ansaloni; J. G. Segarra-Moragues; B. Sabater-Muñoz; J. A. Jacas; M. A. Hurtado-Ruiz (Experimental and Applied Acarology, 2014)

A method for decision making using sustainability indicators - Raymond L. Smith; Gerardo J. Ruiz-Mercado (Clean Technologies and Environmental Policy, 2014)

Expanding GREENSCOPE beyond the gate: a green chemistry and life cycle perspective - Gerardo J. Ruiz-Mercado; Michael A. Gonzalez; Raymond L. Smith (Clean Technologies and Environmental Policy, 2014)

Distribution and conservation of the relict interaction between the butterfly Agriades zullichi and its larval foodplant (Androsace vitaliana nevadensis) - José Miguel Barea-Azcón; Blas M. Benito; Francisco J. Olivares; Helena Ruiz; Javier Martín; Antonio L. García; Rogelio López (Biodiversity and Conservation, 2014)

A phytosociological survey of some serpentine plant communities in the Dominican Republic - E. Cano; A. Cano-Ortiz; S. Del Río; A. Veloz Ramirez; F. J. Esteban Ruiz (Plant Biosystems, 2014)

Improving seismotectonics and seismic hazard assessment along the San Ramón Fault at the eastern border of Santiago city, Chile - A. Pérez; J. A. Ruiz; G. Vargas; R. Rauld; S. Rebolledo; J. Campos (Natural Hazards, 2014)

Quantitative Trait Loci (QTL) and Mendelian Trait Loci (MTL) Analysis in Prunus: a Breeding Perspective and Beyond - Juan Alfonso Salazar; David Ruiz; José Antonio Campoy; Raquel Sánchez-Pérez; Carlos H. Crisosto; Pedro J. Martínez-García; Anna Blenda; Sook Jung; Dorrie Main; Pedro Martínez-Gómez; Manuel Rubio (Plant Molecular Biology Reporter, 2014)

Do climatic conditions affect host and parasite phenotypes differentially? A case study of magpies and great spotted cuckoos - Juan J. Soler; Liesbeth De Neve; David Martín-Gálvez; Mercedes Molina-Morales; Tomás Pérez-Contreras; Magdalena Ruiz-Rodríguez (Oecologia, 2014)

Personality Traits in Rhesus Macaques (Macaca mulatta) Are Heritable but Do Not Predict Reproductive Output - Lauren J. N. Brent; Stuart Semple; Ann MacLarnon; Angelina Ruiz-Lambides; Janis Gonzalez-Martinez; Michael L. Platt (International Journal of Primatology, 2014)

Biofortification with potassium: antioxidant responses during postharvest of cherry tomato fruits in cold storage - C. Constán-Aguilar; R. Leyva; B. Blasco; E. Sánchez-Rodríguez; T. Soriano; J. M. Ruiz (Acta Physiologiae Plantarum, 2014)

Environmental impacts of Little Ice Age cooling in central Mexico recorded in the sediments of a tropical alpine lake - E. Cuna; E. Zawisza; M. Caballero; A. C. Ruiz-Fernández; S. Lozano-García; J. Alcocer (Journal of Paleolimnology, 2014)

Shoot hydraulic characteristics, plant water status and stomatal response in olive trees under different soil water conditions - J. M. Torres-Ruiz; A. Diaz-Espejo; A. Morales-Sillero; M. J. Martín-Palomo; S. Mayr; B. Beikircher; J. E. Fernández (Plant and Soil, 2013)

Isolation and characterization of 17 tetranucleotide microsatellite loci in the Mexican golden trout (Oncorhynchus chrysogaster, Needham & Gard 1964) derived from 454 pyrosequencing - Francisco J. García-De-León; O. Adrián Lozano-Garza; Richard L. Mayden; Rigoberto Delgado-Vega; Faustino Camarena-Rosales; Gorgonio Ruiz-Campos; Marco A. Escalante-Sánchez; Arturo Ruiz-Luna; Miguel Ángel Del Río-Portilla; Irene de los A. Barriga-Sosa; Guadalupe Fabiola Arcos-Ortega; Carmen Paniagua-Chávez (Conservation Genetics Resources, 2013)

Statistical and neural pattern recognition methods for dust aerosol detection - P. Rivas-Perea; J. G. Rosiles; J. Cota-Ruiz (International Journal of Remote Sensing, 2013)

Assessing the nursery role for marine fish species in a hypersaline coastal lagoon (Mar Menor, Mediterranean Sea) - David Verdiell-Cubedo; Francisco J. Oliva-Paterna; Ana Ruiz-Navarro; Mar Torralva (Marine Biology Research, 2013)

Vessel length and conductivity of Ulmus branches: ontogenetic changes and relation to resistance to Dutch elm disease - J. A. Martín; A. Solla; M. Ruiz-Villar; L. Gil (Trees, 2013)

The use of faecal markers for the delimitation of the European rabbit’s social territories (Oryctolagus cuniculus L.) - Leire Ruiz-Aizpurua; Aimara Planillo; Antonio J. Carpio; José Guerrero-Casado; Francisco S. Tortosa (acta ethologica, 2013)

First description of gastrointestinal nematodes of Barbary sheep (Ammotragus lervia): the case of Camelostrongylus mentulatus as a paradigm of phylogenic and specific relationship between the parasite and its ancient host - E. Mayo; J. Ortiz; C. Martínez-Carrasco; M. M. Garijo; G. Espeso; S. Hervías; M. R. Ruiz de Ybáñez (Veterinary Research Communications, 2013)

Does avian conspicuous colouration increase or reduce predation risk? - M. Ruiz-Rodríguez; J. M. Avilés; J. J. Cuervo; D. Parejo; F. Ruano; C. Zamora-Muñoz; F. Sergio; L. López-Jiménez; A. Tanferna; M. Martín-Vivaldi (Oecologia, 2013)

Freshwater ostracods as environmental tracers - F. Ruiz; M. Abad; A. M. Bodergat; P. Carbonel; J. Rodríguez-Lázaro; M. L. González-Regalado; A. Toscano; E. X. García; J. Prenda (International Journal of Environmental Science and Technology, 2013)

Genotypic variation influences reproductive success and thermal stress tolerance in the reef building coral, Acropora palmata - I. B. Baums; M. K. Devlin-Durante; N. R. Polato; D. Xu; S. Giri; N. S. Altman; D. Ruiz; J. E. Parkinson; J. N. Boulay (Coral Reefs, 2013)

Isolation and validation of microsatellite markers from a depleted South African sciaenid species, the dusky kob (Argyrosomus japonicus), by means of the FIASCO/454 approach - L. Mirimin; J. C. Ruiz Guajardo; J. Vervalle; Aletta Bester-Van der Merwe; S. Kerwath; B. Macey; P. Bloomer; R. Roodt-Wilding (Conservation Genetics Resources, 2013)

Local Understandings of Conservation in Southeastern Mexico and Their Implications for Community‐Based Conservation as an Alternative Paradigm - VICTORIA REYES‐GARCIA; ISABEL RUIZ‐MALLEN; LUCIANA PORTER‐BOLLAND; EDUARDO GARCIA‐FRAPOLLI; EDWARD A. ELLIS; MARIA‐ELENA MENDEZ; DIANA J. PRITCHARD; MARÍA‐CONSUELO SANCHEZ‐GONZALEZ (Conservation Biology, 2013)
Since the 1990s national and international programs have aimed to legitimize local conservation initiatives that might provide an alternative to the formal systems of state‐managed or otherwise externally driven protected areas. We used discourse analysis (130 semistructured interviews with key informants) and descriptive statistics (679 surveys) to compare local perceptions of and experiences with state‐driven versus community‐driven conservation initiatives. We conducted our research in 6 communities in southeastern Mexico. Formalization of local conservation initiatives did not seem to be based on local knowledge and practices. Although interviewees thought community‐based initiatives generated less conflict than state‐managed conservation initiatives, the community‐based initiatives conformed to the biodiversity conservation paradigm that emphasizes restricted use of and access to resources. This restrictive approach to community‐based conservation in Mexico, promoted through state and international conservation organizations, increased the area of protected land and had local support but was not built on locally relevant and multifunctional landscapes, a model that community‐based conservation is assumed to advance. Percepciones Locales de Conservación en el Sureste de México e Implicaciones para la Conservación Comunitaria como Paradigma Alternativo

Assessing water stress in a hedgerow olive orchard from sap flow and trunk diameter measurements - M. V. Cuevas; M. J. Martín-Palomo; A. Diaz-Espejo; J. M. Torres-Ruiz; C. M. Rodriguez-Dominguez; A. Perez-Martin; R. Pino-Mejías; J. E. Fernández (Irrigation Science, 2013)

The Use of Blood in Anas clypeata as an Efficient and Non-lethal Method for the Biomonitoring of Mercury - J. R. Raygoza-Viera; A. C. Ruiz-Fernández; J. Ruelas-Inzunza; F. Páez-Osuna (Bulletin of Environmental Contamination and Toxicology, 2013)

Triatoma dimidiata (Latreille) Abundance and Infection with Trypanosoma cruzi in a Rural Community of Yucatan, Mexico - E Reyes-Novelo; H Ruiz-Piña; J Escobedo-Ortegón; M Barrera-Pérez; P Manrique-Saide; R I Rodríguez-Vivas (Neotropical Entomology, 2013)

A Pilot Program in Collaboration with Community Centers to Increase Awareness and Participation in Skin Cancer Screening Among Latinos in Chicago - Claudia Hernandez; Hajwa Kim; Gerardo Mauleon; Adriana Ruiz; June K. Robinson; Robin J. Mermelstein (Journal of Cancer Education, 2013)

Non-invasive genetic sampling of sympatric marten species (Martes martes and Martes foina): assessing species and individual identification success rates on faecal DNA genotyping - Aritz Ruiz-González; María José Madeira; Ettore Randi; Fermin Urra; Benjamín J. Gómez-Moliner (European Journal of Wildlife Research, 2013)

Antiviral activity of casein and α s2 casein hydrolysates against the infectious haematopoietic necrosis virus, a rhabdovirus from salmonid fish - S Rodríguez Saint‐Jean; A De las Heras; W Carrillo; I Recio; J B Ortiz‐Delgado; M Ramos; J A Gomez‐Ruiz; C Sarasquete; S I Pérez‐Prieto (Journal of Fish Diseases, 2013)
Salmonid fish viruses, such as infectious haematopoietic necrosis virus ( IHNV ), are responsible for serious losses in the rainbow trout and salmon‐farming industries, and they have been the subject of intense research in the field of aquaculture. Thus, the aim of this work is to study the antiviral effect of milk‐derived proteins as bovine caseins or casein‐derived peptides at different stages during the course of IHNV infection. The results indicate that the 3‐h fraction of casein and α S2 ‐casein hydrolysates reduced the yield of infectious IHNV in a dose‐dependent manner and impaired the production of IHNV ‐specific antigens. Hydrolysates of total casein and α S2 ‐casein target the initial and later stages of viral infection, as demonstrated by the reduction in the infective titre observed throughout multiple stages and cycles. In vivo , more than 50% protection was observed in the casein‐treated fish, and the kidney sections exhibited none of the histopathological characteristics of IHNV infection. The active fractions from casein were identified, as well as one of the individual IHNV ‐inhibiting peptides. Further studies will be required to determine which other peptides possess this activity. These findings provide a basis for future investigations on the efficacy of these compounds in treating other viral diseases in farmed fish and to elucidate the underlying molecular mechanisms of action. However, the present results provide convincing evidence in support of a role for several milk casein fractions as suitable candidates to prevent and treat some fish viral infections.

Future carbon dioxide concentration decreases canopy evapotranspiration and soil water depletion by field‐grown maize - Mir Zaman Hussain; Andy VanLoocke; Matthew H. Siebers; Ursula M. Ruiz‐Vera; R. J. Cody Markelz; Andrew D. B. Leakey; Donald R. Ort; Carl J. Bernacchi (Global Change Biology, 2013)
Maize, in rotation with soybean, forms the largest continuous ecosystem in temperate N orth A merica, therefore changes to the biosphere‐atmosphere exchange of water vapor and energy of these crops are likely to have an impact on the M idwestern US climate and hydrological cycle. As a C 4 crop, maize photosynthesis is already CO 2 ‐saturated at current CO 2 concentrations ([ CO 2 ]) and the primary response of maize to elevated [ CO 2 ] is decreased stomatal conductance ( g s ). If maize photosynthesis is not stimulated in elevated [ CO 2 ], then reduced g s is not offset by greater canopy leaf area, which could potentially result in a greater ET reduction relative to that previously reported in soybean, a C 3 species. The objective of this study is to quantify the impact of elevated [ CO 2 ] on canopy energy and water fluxes of maize ( Z ea mays ). Maize was grown under ambient and elevated [ CO 2 ] (550 μmol mol −1 during 2004 and 2006 and 585 μmol mol −1 during 2010) using Free Air Concentration Enrichment ( FACE ) technology at the Soy FACE facility in U rbana, I llinois. Maize ET was determined using a residual energy balance approach based on measurements of sensible ( H ) and soil heat fluxes, and net radiation. Relative to control, elevated [ CO 2 ] decreased maize ET (7–11%; P H increased (25–30 W m −2 ; P ET in elevated [ CO 2 ] is approximately half that previously reported for soybean. A partitioning analysis showed that transpiration contributed less to total ET for maize compared to soybean, indicating a smaller role of stomata in dictating the ET response to elevated [ CO 2 ]. Nonetheless, both maize and soybean had significantly decreased ET and increased H , highlighting the critical role of elevated [ CO 2 ] in altering future hydrology and climate of the region that is extensively cropped with these species.

Morphological characterization of Pelibuey sheep in Colima, México - Victalina Arredondo-Ruiz; Rafael Macedo-Barragán; Jaime Molina-Cárdenas; Julio Magaña-Álvarez; Omar Prado-Rebolledo; Luis J. García-Márquez; Alejandra Herrera-Corredor; Héctor Lee-Rangel (Tropical Animal Health and Production, 2013)

Response of Bemisia tabaci Genn. (Hemiptera: Aleyrodidae) Biotype B to Genotypes of Pepper Capsicum annuum (Solanales: Solanaceae) - H Ballina-Gomez; E Ruiz-Sanchez; W Chan-Cupul; L Latournerie-Moreno; L Hernández-Alvarado; I Islas-Flores; J J Zuñiga-Aguilar (Neotropical Entomology, 2013)

Erratum to: Targeting the association of calgranulin B (S100A9) with insulin resistance and type 2 diabetes - Francisco J. Ortega; Josep M. Mercader; José M. Moreno-Navarrete; Mónica Sabater; Neus Pueyo; Sergio Valdés; Bartomeu Ruiz; Elodie Luche; Matteo Serino; Deborah Naon; Wifredo Ricart; Patricia Botas; et al. (Journal of Molecular Medicine, 2013)

Targeting the association of calgranulin B (S100A9) with insulin resistance and type 2 diabetes - Francisco J. Ortega; Josep M. Mercader; José M. Moreno-Navarrete; Mónica Sabater; Neus Pueyo; Sergio Valdés; Bartomeu Ruiz; Elodie Luche; Deborah Naon; Wifredo Ricart; Patricia Botas; Elias Delgado; et al. (Journal of Molecular Medicine, 2013)

Utilization of holdfast fragments for vegetative propagation of Macrocystis integrifolia in Atacama, Northern Chile - Renato Westermeier; Pedro Murúa; David J. Patiño; Liliana Muñoz; Ailin Ruiz; Carlos Atero; Dieter G. Müller (Journal of Applied Phycology, 2013)

Distributed lag associations between respiratory illnesses and mortality with suspended particle concentration in Tula, a highly polluted industrial region in Central Mexico - Eva M. Melgar-Paniagua; Elizabeth Vega-Rangel; Luz M. Del Razo; Carlos A. Lucho-Constantino; Stephen J. Rothenberg; Andrea De Vizcaya-Ruiz (International Archives of Occupational and Environmental Health, 2013)

Postglacial recolonization history of the E uropean crabapple ( Malus sylvestris M ill.), a wild contributor to the domesticated apple - A. Cornille; T. Giraud; C. Bellard; A. Tellier; B. Le Cam; M. J. M. Smulders; J. Kleinschmit; I. Roldan‐Ruiz; P. Gladieux (Molecular Ecology, 2013)
Understanding the way in which the climatic oscillations of the Quaternary Period have shaped the distribution and genetic structure of extant tree species provides insight into the processes driving species diversification, distribution and survival. Deciphering the genetic consequences of past climatic change is also critical for the conservation and sustainable management of forest and tree genetic resources, a timely endeavour as the Earth heads into a period of fast climate change. We used a combination of genetic data and ecological niche models to investigate the historical patterns of biogeographic range expansion of a wild fruit tree, the E uropean crabapple ( M alus sylvestris ), a wild contributor to the domesticated apple. Both climatic predictions for the last glacial maximum and analyses of microsatellite variation indicated that M . sylvestris experienced range contraction and fragmentation. Bayesian clustering analyses revealed a clear pattern of genetic structure, with one genetic cluster spanning a large area in Western E urope and two other genetic clusters with a more limited distribution range in Eastern E urope, one around the Carpathian Mountains and the other restricted to the Balkan P eninsula. Approximate Bayesian computation appeared to be a powerful technique for inferring the history of these clusters, supporting a scenario of simultaneous differentiation of three separate glacial refugia. Admixture between these three populations was found in their suture zones. A weak isolation by distance pattern was detected within each population, indicating a high extent of historical gene flow for the E uropean crabapple.

Antioxidant Defenses and Trace Metal Bioaccumulation Capacity of Cymbula nigra (Gastropoda: Patellidae) - G. A. Rivera-Ingraham; G. Malanga; S. Puntarulo; A. F. Pérez; A. Ruiz-Tabares; M. Maestre; R. González-Aranda; F. Espinosa; J. C. García-Gómez (Water, Air, & Soil Pollution, 2013)

Molecular phylogeny of the Helicodontidae and Trissexodontidae (Gastropoda) - Benjamín J. Gómez‐Moliner; Arantzazu M. Elejalde; Jose R. Arrébola; Ana I. Puente; Alberto Martínez‐Ortí; Antonio Ruiz; María J. Madeira (Zoologica Scripta, 2013)
Gómez‐Moliner, B.J., Elejalde, A.M., Arrébola, J.R., Puente, A.I., Martínez‐Ortí, A., Ruiz, A. & Madeira, MJ. (2012). Molecular phylogeny of the Helicodontidae and Trissexodontidae (Gastropoda). — Zoologica Scripta , 00 , 000–000. In this study, we present a molecular phylogeny of the Trissexodontidae and Helicodontidae obtained by means of Maximum Parsimony, Neighbor Joining, Maximum Likelihood and Bayesian analyses of DNA sequences. Nearly 3 KB of sequence data of two mitochondrial genes (COI, 16S rDNA) and the nuclear rRNA gene cluster including ITS‐1, the 3′end of the 5.8S gene, the complete ITS‐2 region and 5′ end of the large subunit 28S were used to reconstruct the phylogeny of these two families. Monophyly of Trissexodontidae and Helicodontidae at the family level is well supported. A new classification of the genera in the Trissexodontidae is proposed. It includes two subfamilies: Gittenbergeriinae (monotypic for Gittenbergeria turriplana ) and Trissexodontinae. The latter includes three strongly supported tribes: (i) Trissexodontini, including Mastigophallus , Trissexodon , Oestophorella and Suboestophora ; (ii) Oestophorini, with Oestophora ; and (iii) Caracollinini, with Caracollina , Gasulliella , Gasullia and Hatumia . The polytypic Oestophora and Suboestophora are recovered as two monophyletic genera. The anatomy of the auxiliary copulatory organs of the reproductive system is coherent with the new taxonomic interpretation of the Trissexodontidae. Further work, including some more taxa is needed to delimitate subfamilies within Helicodontidae. Finally, the addition of some sequences of other Helicoidea shows that the genus Ciliella is not closely related to Trissexodontidae, being grouped within the Hygromiidae, instead.

Structural and Functional Maturation of Active Zones in Large Synapses - Raquel Cano; Laura Torres-Benito; Rocío Tejero; Anca I. Biea; Rocío Ruiz; William J. Betz; Lucía Tabares (Molecular Neurobiology, 2013)

Comparison of image analysis and direct measurement of UPOV taxonomic characteristics for variety discrimination as determined over five growing seasons, using industrial chicory as a model crop - P. Lootens; B. Chaves; J. Baert; J. Pannecoucque; J. Van Waes; I. Roldán-Ruiz (Euphytica, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Studying the effects of multiple invasive mammals on Cory’s shearwater nest survival - S. Hervías; A. Henriques; N. Oliveira; T. Pipa; H. Cowen; J. A. Ramos; M. Nogales; P. Geraldes; C. Silva; R. Ruiz de Ybáñez; S. Oppel (Biological Invasions, 2013)

The Western Mediterranean summer variability and its feedbacks - M. J. OrtizBeviá; F. J. Alvarez-García; A. M. Ruiz de Elvira; G. Liguori; J. H. Carretero (Climate Dynamics, 2012)

Use of the probiotic Shewanella putrefaciens Pdp11 on the culture of Senegalese sole (Solea senegalensis, Kaup 1858) and gilthead seabream (Sparus aurata L.) - S. T. Tapia-Paniagua; P. Díaz-Rosales; J. M. León-Rubio; I. García de La Banda; C. Lobo; F. J. Alarcón; M. Chabrillón; P. Rosas-Ledesma; J. L. Varela; I. Ruiz-Jarabo; S. Arijo; M. A. Esteban; et al. (Aquaculture International, 2012)

Analysis of parcel-based image classification methods for monitoring the activities of the Land Bank of Galicia (Spain) - T. Hermosilla; J. M. Díaz-Manso; L. A. Ruiz; J. A. Recio; A. Fernández-Sarría; P. Ferradáns-Nogueira (Applied Geomatics, 2012)

The black petrel ( Procellaria parkinsoni ) in pelagic waters off northern Chile: a southern extension to the known distribution and interactions with the pelagic longline fishery - LA Cabezas; J Ruiz; O Yates; M Bernal (New Zealand Journal of Marine and Freshwater Research, 2012)
During seabird censuses performed as part of scientific research looking into seabird bycatch onboard industrial pelagic longline vessels targeting swordfish ( Xiphias gladius ) we made the first documented records of black petrel ( Procellaria parkinsoni ) in the pelagic waters of northern Chile, considerably extending the species’ range southward. These observations were made during hauling operations in the austral winters of 2008, 2009 and 2010 between 23°00'S and 32°49'S. Black petrels were observed in 9.6% of censuses and a total of 10 birds were recorded. Despite the fact that this species fed upon discards and wastes generated during fishing, no incidental mortality was observed. Our results are relevant to the conservation of the black petrel in the south‐eastern Pacific marine ecosystem, as they provide new information on species range and interactions with pelagic fisheries.

Morphological variation between non‐native lake‐ and stream‐dwelling pumpkinseed Lepomis gibbosus in the Iberian Peninsula - J. Naspleda; A. Vila‐Gispert; M. G. Fox; L. Zamora; A. Ruiz‐Navarro (Journal of Fish Biology, 2012)
The objective of this study was to test if morphological differences in pumpkinseed Lepomis gibbosus found in their native range (eastern North America) that are linked to feeding regime, competition with other species, hydrodynamic forces and habitat were also found among stream‐ and lake‐ or reservoir‐dwelling fish in Iberian systems. The species has been introduced into these systems, expanding its range, and is presumably well adapted to freshwater Iberian Peninsula ecosystems. The results show a consistent pattern for size of lateral fins, with L. gibbosus that inhabit streams in the Iberian Peninsula having longer lateral fins than those inhabiting reservoirs or lakes. Differences in fin placement, body depth and caudal peduncle dimensions do not differentiate populations of L. gibbosus from lentic and lotic water bodies and, therefore, are not consistent with functional expectations. Lepomis gibbosus from lotic and lentic habitats also do not show a consistent pattern of internal morphological differentiation, probably due to the lack of lotic–lentic differences in prey type. Overall, the univariate and multivariate analyses show that most of the external and internal morphological characters that vary among populations do not differentiate lotic from lentic Iberian populations. The lack of expected differences may be a consequence of the high seasonal flow variation in Mediterranean streams, and the resultant low‐ or no‐flow conditions during periods of summer drought.

Use of Cu isotopes to distinguish primary and secondary Cu mineralization in the Cañariaco Norte porphyry copper deposit, Northern Peru - Ryan Mathur; Joaquin Ruiz; Michael J. Casselman; Peter Megaw; Robert van Egmond (Mineralium Deposita, 2012)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Variations of chemical composition and energy content in natural and genetically defined cultivars of Macrocystis from Chile - Renato Westermeier; Pedro Murúa; David J. Patiño; Liliana Muñoz; Ailin Ruiz; Dieter G. Müller (Journal of Applied Phycology, 2012)

The effect of biomaterials and antifungals on biofilm formation by Candida species: a review - M. Cuéllar-Cruz; A. Vega-González; B. Mendoza-Novelo; E. López-Romero; E. Ruiz-Baca; M. A. Quintanar-Escorza; J. C. Villagómez-Castro (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Development of a Multiplex PCR Assay to Detect Gastroenteric Pathogens in the Feces of Mexican Children - R. Tolentino-Ruiz; D. Montoya-Varela; M. García-Espitia; M. Salas-Benito; A. Gutiérrez-Escolano; C. Gómez-García; P. Figueroa-Arredondo; J. Salas-Benito; M. De Nova-Ocampo (Current Microbiology, 2012)

Exploratory data analysis in the study of 7Be present in atmospheric aerosols - F. Piñero García; M. A. Ferro García; J. Drożdżak; C. Ruiz-Samblás (Environmental Science and Pollution Research, 2012)

The role of hydrodynamics on seed dispersal in seagrasses - L. Ruiz-Montoya; R. J. Lowe; K. P. Van Niel; G. A. Kendrick (Limnology and Oceanography, 2012)
Two widely distributed seagrasses in Western Australia with contrasting dispersal strategies were studied in terms of their physical characteristics and morphology to understand how physical processes (wind, waves, and currents) drive dispersal. Posidonia australis releases floating fruit that contain a single negatively buoyant seed that lacks dormancy. Halophila ovalis produces fruit and dormant seeds that sit on the sediment surface. The floating stage of P. australis was assessed in situ by tracking the movement of the fruit directly on the ocean surface, together with drifter devices to differentiate between the transport induced by surface currents and wind. The dehiscence time of P. australis fruit was evaluated in seawater tanks, and the associated viability of the seeds was assessed by growth after dehiscence. The settling velocities of P. australis seeds and H. ovalis fruit and seeds were quantified in settling tubes with image‐processing techniques to track the fall trajectories. The re‐suspension thresholds of the seeds were calculated based on the critical bed shear stresses required to transport the seeds in a unidirectional flow flume. P. australis can travel long distances at the air‐sea interface (∼ 55 km), due to wind alone, during its floating stage. The settling velocities of P. australis and H. ovalis seeds ( w s = 10.6 ± 0.4 cm s −1 and 4.7 ± 0.1 cm s −1 , respectively) and their re‐suspension thresholds ( τ = 107 ± 4 mPa and 66 ± 1 mPa, respectively) suggest that secondary movement is restricted, but likely to be produced by stronger wave‐induced shear stress events.

Response of Rhesus Macaques (Macaca mulatta) to the Body of a Group Member That Died from a Fatal Attack - Jacqueline S. Buhl; Bonn Aure; Angelina Ruiz-Lambides; Janis Gonzalez-Martinez; Michael L. Platt; Lauren J. N. Brent (International Journal of Primatology, 2012)

Safety analysis of high dose (>6 mg/kg/day) daptomycin in patients with concomitant statin therapy - J. Parra-Ruiz; C. Dueñas-Gutiérrez; C. Tomás-Jiménez; J. P. Linares-Palomino; J. Garrido-Gomez; J. Hernández-Quero (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Analysis of dry periods along a pluviometric gradient in Mediterranean southern Spain - J. D. Ruiz‐Sinoga; R. Garcia‐Marin; M. A. Gabarron‐Galeote; J. F. Martinez‐Murillo (International Journal of Climatology, 2012)
In southern Spain a longitudinal pluviometric gradient occurs under Mediterranean climatic conditions in an area that has at least two months of drought each year and very irregular rainfall. From the Strait of Gibraltar to the Cabo de Gata in Almería there is a reduction of more than 1,000 mm year −1 in the mean annual rainfall. Analysis of the frequency and intensity of drought periods is necessary in regions where water resources are scarce and the ecosystem is highly dependent on water availability. Drought periods in the region described above were analysed using the DDSLR (Dry Days Since Last Rain) index to i) characterize trends in number of dry days and the amount of rainfall along the pluviometric gradient, ii) assess how the DDSLR index changes along the gradient from semiarid to humid Mediterranean regions, and iii) contribute to studies addressing the importance of climatic gradients in relation to the dynamics of various ecosystems. The DDSLR method enables calculation of the probability of the occurrence of dry days (days without rain) at any time of the year, assessment of the risk of water deficits for vegetation during plant growth periods, and evaluation of the temporal variability of hydrological/geomorphological processes that depend on soil moisture throughout the year. The results showed that there is a critical period of rainfall scarcity during September and October, which has implications for the availability of soil water resources for vegetation. In short‐term, the major problems are predicted for the Spanish Southern Mediterranean due to the increasing irregularity in precipitations: the number of days with no rains and drought periods are increased, but also a significant increment in the probabilities of extreme rainfalls exceeding 30 mm day −1 . Copyright © 2011 Royal Meteorological Society

Muscular strength and markers of insulin resistance in European adolescents: the HELENA Study - D. Jiménez-Pavón; F. B. Ortega; J. Valtueña; J. Castro-Piñero; S. Gómez-Martínez; M. Zaccaria; F. Gottrand; D. Molnár; M. Sjöström; M. González-Gross; M. J. Castillo; L. A. Moreno; et al. (European Journal of Applied Physiology, 2012)

Isolation and characterization of polymorphic microsatellite markers in Tetranychus urticae and cross amplification in other Tetranychidae and Phytoseiidae species of economic importance - B. Sabater-Muñoz; S. Pascual-Ruiz; M. A. Gómez-Martínez; J. A. Jacas; M. A. Hurtado (Experimental and Applied Acarology, 2012)

Usefulness of consecutive biomarkers measurement in the management of community-acquired pneumonia - A. Lacoma; N. Rodríguez; C. Prat; J. Ruiz-Manzano; F. Andreo; A. Ramírez; A. Bas; M. Pérez; V. Ausina; J. Domínguez (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

In vitro interactions between ectomycorrhizal fungi and ericaceous plants - Luis Villarreal-Ruiz; Cecilia Neri-Luna; Ian C. Anderson; Ian J. Alexander (Symbiosis, 2012)

High-density fecal Enterococcus faecium colonization in hospitalized patients is associated with the presence of the polyclonal subcluster CC17 - P. Ruiz-Garbajosa; M. Regt; M. Bonten; F. Baquero; T. M. Coque; R. Cantón; H. J. Harmsen; R. J. L. Willems (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Prevalence and risk factors for quinolone resistance among Escherichia coli strains isolated from males with community febrile urinary tract infection - A. Smithson; C. Chico; J. Ramos; C. Netto; M. Sanchez; J. Ruiz; R. Porron; M. T. Bastida (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Wild vegetables of the Mediterranean area as valuable sources of bioactive compounds - M. C. Sánchez-Mata; R. D. Cabrera Loera; P. Morales; V. Fernández-Ruiz; M. Cámara; C. Díez Marqués; M. Pardo-de-Santayana; J. Tardío (Genetic Resources and Crop Evolution, 2012)

Mechanisms and traits associated with compensation for defoliation in Ruellia nudiflora - G. Rivera-Solís; L. Abdala-Roberts; J. C. Cervera; V. Parra-Tabla; J. Ruiz-Ruiz; D. Betancur-Ancona (Plant Ecology, 2012)

Hyaluronan receptors in the human ocular surface: a descriptive and comparative study of RHAMM and CD44 in tissues, cell lines and freshly collected samples - Laura García-Posadas; Laura Contreras-Ruiz; Antonio López-García; Sonia Villarón Álvarez; Miguel J. Maldonado; Yolanda Diebold (Histochemistry and Cell Biology, 2012)

Contrasting C and N isotope ratios from sperm whale skin and squid between the Gulf of Mexico and Gulf of California: effect of habitat - R. I. Ruiz-Cooley; D. T. Engelhaupt; J. G. Ortega-Ortiz (Marine Biology, 2012)

Morphological and molecular analysis of natural hybrids between the diploid Centaurea aspera L. and the tetraploid C. seridis L. (Compositae) - M. Ferriol; A. Garmendia; J. J. Ruiz; H. Merle; H. Boira (Plant Biosystems, 2012)

Influenza-like illness in pregnant women during summertime: clinical, epidemiological and microbiological features - J. R. Paño-Pardo; N. Martínez-Sánchez; A. Martín-Quirós; M. P. Romero-Gómez; M. Muñoz-Muñiz; M. Sánchez-Pastor; G. Ruiz; B. San-José; M. C. Prados; M. Mora-Rillo; A. Rico-Nieto; J.-R. Arribas (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Migration of bisphenol A from polycarbonate baby bottles purchased in the Spanish market by liquid chromatography and fluorescence detection - M.I. Santillana; E. Ruiz; M.T. Nieto; J. Bustos; J. Maia; R. Sendón; J.J. Sánchez (Food Additives & Contaminants: Part A, 2011)

The effect of landscape heterogeneity and host movement on a tick-borne pathogen - Edward O. Jones; Steven D. Webb; Francisco J. Ruiz-Fons; Steven Albon; Lucy Gilbert (Theoretical Ecology, 2011)

Assessing GNSS correction signals for assisted guidance systems in agricultural vehicles - M. Pérez-Ruiz; J. Carballido; J. Agüera; J. A. Gil (Precision Agriculture, 2011)

Montia fontana L. (Portulacaceae), an interesting wild vegetable traditionally consumed in the Iberian Peninsula - J. Tardío; M. Molina; L. Aceituno-Mata; M. Pardo-de-Santayana; R. Morales; V. Fernández-Ruiz; P. Morales; P. García; M. Cámara; M. C. Sánchez-Mata (Genetic Resources and Crop Evolution, 2011)

Handicapped females receive more feedings during incubation from their mates: support for the female nutrition hypothesis - Juan Moreno; Alberto J. Redondo; Alejandro Cantarero; Rafael Ruiz-de-Castañeda; Sonia González-Braojos (acta ethologica, 2011)

Seasonal progression of bud dormancy in apricot ( Prunus armeniaca L.) in a Mediterranean climate: A single-node cutting approach - J. A. Campoy; D. Ruiz; J. Egea (Plant Biosystems, 2011)

Variation in the use efficiency of N under moderate water deficit in tomato plants (Solanum lycopersicum) differing in their tolerance to drought - Eva Sánchez-Rodríguez; M. M. Rubio-Wilhelmi; B. Blasco; C. Constán-Aguilar; L. Romero; J. M. Ruiz (Acta Physiologiae Plantarum, 2011)

Optimization of agrochemical application in olive groves based on positioning sensor - M. Pérez-Ruiz; J. Agüera; J. A. Gil; D. C. Slaughter (Precision Agriculture, 2011)

The May 2005 eruption of Fernandina volcano, Galápagos: The first circumferential dike intrusion observed by GPS and InSAR - William W. Chadwick; Sigurjon Jónsson; Dennis J. Geist; Michael Poland; Daniel J. Johnson; Spencer Batt; Karen S. Harpp; Andres Ruiz (Bulletin of Volcanology, 2011)

Lipid profiles and oxidative stress parameters in male and female hemodialysis patients - A. Osorio; E. Ortega; T. de Haro; J. M. Torres; P. Sánchez; E. Ruiz-Requena (Molecular and Cellular Biochemistry, 2011)

Genetic mapping of rust resistance loci in biomass willow - Steven J. Hanley; Ming H. Pei; Stephen J. Powers; Carmen Ruiz; Mark D. Mallott; Jacqueline H. A. Barker; Angela Karp (Tree Genetics & Genomes, 2011)

The Why, What, and How of Global Biodiversity Indicators Beyond the 2010 Target - JULIA P. G. JONES; BEN COLLEN; GILES ATKINSON; PETER W. J. BAXTER; PHILIP BUBB; JANINE B. ILLIAN; TODD E. KATZNER; AIDAN KEANE; JONATHAN LOH; EVE MCDONALD‐MADDEN; EMILY NICHOLSON; HENRIQUE M. PEREIRA; et al. (Conservation Biology, 2011)
The 2010 biodiversity target agreed by signatories to the Convention on Biological Diversity directed the attention of conservation professionals toward the development of indicators with which to measure changes in biological diversity at the global scale. We considered why global biodiversity indicators are needed, what characteristics successful global indicators have, and how existing indicators perform. Because monitoring could absorb a large proportion of funds available for conservation, we believe indicators should be linked explicitly to monitoring objectives and decisions about which monitoring schemes deserve funding should be informed by predictions of the value of such schemes to decision making. We suggest that raising awareness among the public and policy makers, auditing management actions, and informing policy choices are the most important global monitoring objectives. Using four well‐developed indicators of biological diversity (extent of forests, coverage of protected areas, Living Planet Index, Red List Index) as examples, we analyzed the characteristics needed for indicators to meet these objectives. We recommend that conservation professionals improve on existing indicators by eliminating spatial biases in data availability, fill gaps in information about ecosystems other than forests, and improve understanding of the way indicators respond to policy changes. Monitoring is not an end in itself, and we believe it is vital that the ultimate objectives of global monitoring of biological diversity inform development of new indicators.

Entropy-based correlated shrinkage of spatial random processes - J. M. Angulo; A. E. Madrid; M. D. Ruiz-Medina (Stochastic Environmental Research and Risk Assessment, 2011)

Health Risk Associated to Dietary Intake of Mercury in Selected Coastal Areas of Mexico - J. Ruelas-Inzunza; F. Páez-Osuna; A. C. Ruiz-Fernández; N. Zamora-Arellano (Bulletin of Environmental Contamination and Toxicology, 2011)

Identification of High Frequency Pulses from Earthquake Asperities Along Chilean Subduction Zone Using Strong Motion - S. Ruiz; E. Kausel; J. Campos; G. R. Saragoni; R. Madariaga (Pure and Applied Geophysics, 2011)

Spices as Functional Foods - M. Viuda-Martos; Y. Ruiz-Navajas; J. Fernández-López; J. A. Pérez-Álvarez (Critical Reviews in Food Science and Nutrition, 2010)

Identification of a gene involved in the juvenile-to-adult transition (JAT) in cultivated olive trees - Ana Fernández-Ocaña; Mari Carmen García-López; Jaime Jiménez-Ruiz; Luisa Saniger; David Macías; Francisco Navarro; Ricardo Oya; Angjelina Belaj; Raul de la Rosa; Francisco J. Corpas; Juan Bautista Barroso; Francisco Luque (Tree Genetics & Genomes, 2010)

Photorespiration Process and Nitrogen Metabolism in Lettuce Plants (Lactuca sativa L.): Induced Changes in Response to Iodine Biofortification - Begoña Blasco; Juan J. Rios; Luis M. Cervilla; Eva Sánchez-Rodríguez; María M. Rubio-Wilhelmi; Miguel A. Rosales; Juan M. Ruiz; Luis Romero (Journal of Plant Growth Regulation, 2010)

Multi-Scaled Grassland-Woody Plant Dynamics in the Heterogeneous Marl Prairies of the Southern Everglades - Erin J. Hanan; Michael S. Ross; Pablo L. Ruiz; Jay P. Sah (Ecosystems, 2010)

Beyond nature: The management of a productive cultural landscape in Las Médulas area (El Bierzo, León, Spain) during pre-Roman and Roman times - L. López-Merino; L. Peña-Chocarro; M. Ruiz-Alonso; J. A. LópeZ-Sáez; F. J. Sánchez-Palencia (Plant Biosystems, 2010)

Landscape genetics of the key African acacia species Senegalia mellifera (Vahl)– the importance of the Kenyan Rift Valley - J. C. RUIZ GUAJARDO; A. SCHNABEL; R. ENNOS; S. PREUSS; A. OTERO‐ARNAIZ; G. STONE (Molecular Ecology, 2010)
Acacias across Africa have enormous ecological and economic importance, yet their population genetics are poorly studied. We used seven microsatellite loci to investigate spatial genetic structure and to identify potential ecological and geographic barriers to dispersal in the widespread acacia, Senegalia (Acacia) mellifera . We quantified variation among 791 individuals from 28 sampling locations, examining patterns at two spatial scales: (i) across Kenya including the Rift Valley, and (ii) for a local subset of 11 neighbouring locations on Mpala Ranch in the Laikipia plateau. Our analyses recognize that siblings can often be included in samples used to measure population genetic structure, violating fundamental assumptions made by these analyses. To address this potential problem, we maximized genetic independence of samples by creating a sibship‐controlled data set that included only one member of each sibship and compared the results obtained with the full data set. Patterns of genetic structure and barriers to gene flow were essentially similar when the two data sets were analysed. Five well‐defined geographic regions were identified across Kenya within which gene flow was localized, with the two strongest barriers to dispersal splitting the Laikipia Plateau of central Kenya from the Western and Eastern Rift Valley. At a smaller scale, in the absence of geographic features, regional habitat gradients appear to restrict gene flow significantly. We discuss the implications of our results for the management of this highly exploited species.

Functional traits and the growth–mortality trade‐off in tropical trees - S. Joseph Wright; Kaoru Kitajima; Nathan J. B. Kraft; Peter B. Reich; Ian J. Wright; Daniel E. Bunker; Richard Condit; James W. Dalling; Stuart J. Davies; Sandra Díaz; Bettina M. J. Engelbrecht; Kyle E. Harms; et al. (Ecology, 2010)
A trade‐off between growth and mortality rates characterizes tree species in closed canopy forests. This trade‐off is maintained by inherent differences among species and spatial variation in light availability caused by canopy‐opening disturbances. We evaluated conditions under which the trade‐off is expressed and relationships with four key functional traits for 103 tree species from Barro Colorado Island, Panama. The trade‐off is strongest for saplings for growth rates of the fastest growing individuals and mortality rates of the slowest growing individuals ( r 2 = 0.69), intermediate for saplings for average growth rates and overall mortality rates ( r 2 = 0.46), and much weaker for large trees ( r 2 ≤ 0.10). This parallels likely levels of spatial variation in light availability, which is greatest for fast‐ vs. slow‐growing saplings and least for large trees with foliage in the forest canopy. Inherent attributes of species contributing to the trade‐off include abilities to disperse, acquire resources, grow rapidly, and tolerate shade and other stresses. There is growing interest in the possibility that functional traits might provide insight into such ecological differences and a growing consensus that seed mass (SM), leaf mass per area (LMA), wood density (WD), and maximum height ( H max ) are key traits among forest trees. Seed mass, LMA, WD, and H max are predicted to be small for light‐demanding species with rapid growth and mortality and large for shade‐tolerant species with slow growth and mortality. Six of these trait–demographic rate predictions were realized for saplings; however, with the exception of WD, the relationships were weak ( r 2 r 2 80% of the explained variation and, after WD was included, LMA and H max made insignificant contributions. Virtually the full range of values of SM, LMA, and H max occurred at all positions on the growth–mortality trade‐off. Although WD provides a promising start, a successful trait‐based ecology of tropical forest trees will require consideration of additional traits.

Selection against Robertsonian fusions involving housekeeping genes in the house mouse: integrating data from gene expression arrays and chromosome evolution - Aurora Ruiz-Herrera; Marta Farré; Montserrat Ponsà; Terence J. Robinson (Chromosome Research, 2010)

Erratum to: Genotypic Characterization of Environmental Isolates of Cryptococcus gattii from Puerto Rico - Yaliz Loperena-Alvarez; Ping Ren; Xiaojiang Li; Dianna J. Schoonmaker-Bopp; Alejandro Ruiz; Vishnu Chaturvedi; Carlos Rios-Velazquez (Mycopathologia, 2010)

Genotypic Characterization of Environmental Isolates of Cryptococcus gattii from Puerto Rico - Yaliz Loperena-Alvarez; Ping Ren; Xiaojiang Li; D. J. Bopp; Alejandro Ruiz; Vishnu Chaturvedi; Carlos Rios-Velazquez (Mycopathologia, 2010)

Sleep patterns in Spanish adolescents: associations with TV watching and leisure-time physical activity - Francisco B. Ortega; Palma Chillón; Jonatan R. Ruiz; Manuel Delgado; Ulrike Albers; Jesús L. Álvarez-Granda; Ascensión Marcos; Luis A. Moreno; Manuel J. Castillo (European Journal of Applied Physiology, 2010)

Soil and Water Pollution in a Banana Production Region in Tropical Mexico - Violette Geissen; Franzisco Que Ramos; Pedro de J. Bastidas-Bastidas; Gilberto Díaz-González; Ricardo Bello-Mendoza; Esperanza Huerta-Lwanga; Luz E. Ruiz-Suárez (Bulletin of Environmental Contamination and Toxicology, 2010)

Identification of arid phases during the last 50 cal. ka BP from the Fuentillejo maar‐lacustrine record (Campo de Calatrava Volcanic Field, Spain) - Juana Vegas; Blanca Ruiz‐Zapata; José E. Ortiz; Luis Galán; Trinidad Torres; Ángel García‐Cortés; María J. Gil‐García; Alfredo Pérez‐González; José L. Gallardo‐Millán (Journal of Quaternary Science, 2010)
Geochemical (element analysis, molecular analysis of organic compounds), physical, palynological, mineralogical and sedimentary facies analysis were performed to characterise the sedimentary record in Fuentillejo maar‐lake in the Central Spanish Volcanic Field of Campo de Calatrava, in order to reconstruct the palaeoenvironmental and palaeoclimatic processes which controlled vegetation patterns and deposition of different sedimentary facies. The upper 20 m of core FUENT‐1 show variations in clastic input, water chemistry, vegetation and organic fraction sources in the lake throughout the Late Pleistocene and Holocene. The temporal framework provided by 14 C accelerator mass spectrometry dating allows assigning the sequence to the last 50 cal. ka BP. Arid phases identified in the FUENT‐1 sequence are correlated to Heinrich events (HE) and to stadials of the Dansgaard/Oeschger (D/O) cycles. Siliciclastic facies with high magnetic susceptibility values, high Juniperus pollen content, a low Paq index (aquatic macrophysics proxy index), a decrease in the relative percentage of the n ‐C 27 and an increase in the n ‐C 31 alkanes are indicative of arid and colder climatic events related to HE 2, HE 1 and the Younger Dryas (YD). Similar short cold and arid phases during the Holocene were identified at 9.2–8.6, 7.5–7 and 5.5–5 cal. ka BP. In dolomite–mud facies, the pollen data show an increase in the herbs component, mainly – Chenopodiaceae, Artemisia and Ephedra – steppe taxa; a low Paq index, a decrease in the relative percentage of the n ‐C 27 alkane and an increase in the n ‐C 31 alkane are also observed. This facies was probably the result of lower lake levels and more saline–alkaline conditions, which can be interpreted as linked to arid–warm periods. These warm and arid phases were more frequent during Marine Isotope Stage (MIS) 3 and the interstadials of MIS 2. HE 4, HE 2, HE 1 and the YD in core FUENT‐1 were immediately followed by increases of warm steppe pollen assemblages that document rapid warming similar to the D/O cycles but do not imply increasing humidity in the area. Fuentillejo hydrology is controlled by changes in the atmospheric and oceanic systems that operated on the North Atlantic region at millennial scale during the last 50 cal. ka BP. Copyright © 2009 John Wiley & Sons, Ltd.

SNP discovery and genetic mapping of T-DNA insertional mutants in Fragaria vesca L. - J. J. Ruiz-Rojas; D. J. Sargent; V. Shulaev; A. W. Dickerman; J. Pattison; S. H. Holt; A. Ciordia; Richard E. Veilleux (Theoretical and Applied Genetics, 2010)

Agrobacterium tumefaciens-mediated transformation of Lotus tenuis and regeneration of transgenic lines - F. D. Espasandin; M. M. Collavino; C. V. Luna; R. C. Paz; J. R. Tarragó; O. A. Ruiz; L. A. Mroginski; P. A. Sansberro (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Association of physical activity with muscular strength and fat-free mass in adolescents: the HELENA study - Diego Moliner-Urdiales; Francisco B. Ortega; Germán Vicente-Rodriguez; Juan P. Rey-Lopez; Luis Gracia-Marco; Kurt Widhalm; Michael Sjöström; Luis A. Moreno; Manuel J. Castillo; Jonatan R. Ruiz (European Journal of Applied Physiology, 2010)

Benomyl sensitivity assays and species-specific PCR reactions highlight association of two Colletotrichum gloeosporioides types and C. acutatum with rumple disease on Primofiori lemons - Manuel Valero; Santiago García-Martínez; Manuel J. Giner; Aranzazu Alonso; Juan J. Ruiz (European Journal of Plant Pathology, 2010)

Land-cover classification using radar and optical images: a case study in Central Mexico - J. Soria-Ruiz; Y. Fernandez-Ordoñez; I. H. Woodhouse (International Journal of Remote Sensing, 2010)

Acclimation of Solea senegalensis to different ambient temperatures: implications for thyroidal status and osmoregulation - Francisco J. Arjona; Ignacio Ruiz-Jarabo; Luis Vargas-Chacoff; María P. Martín del Río; Gert Flik; Juan M. Mancera; Peter H. M. Klaren (Marine Biology, 2010)

Nitrogen-Use Efficiency in Relation to Different Forms and Application Rates of Se in Lettuce Plants - Juan J. Ríos; Begoña Blasco; Luis M. Cervilla; Maria M. Rubio-Wilhelmi; Miguel A. Rosales; Eva Sanchez-Rodriguez; Luis Romero; Juan M. Ruiz (Journal of Plant Growth Regulation, 2010)

Mortality risk assessment through stationary space–time covariance functions - F. Martínez-Ruiz; J. Mateu; F. Montes; E. Porcu (Stochastic Environmental Research and Risk Assessment, 2010)

Validation of QTLs for Orobanche crenata resistance in faba bean (Vicia faba L.) across environments and generations - Ramón Díaz-Ruiz; A. M. Torres; Z. Satovic; M. V. Gutierrez; J. I. Cubero; Belén Román (Theoretical and Applied Genetics, 2010)

Evaluation of four digital classifiers for automated cartography of local soil classes based on reflectance and elevation in Mexico - G. Cruz-Cárdenas; C. A. Ortiz-Solorio; E. Ojeda-Trejo; J. F. Martínez-Montoya; E. D. Sotelo-Ruiz; A. L. Licona-Vargas (International Journal of Remote Sensing, 2010)

Nutrient Bioaccumulation in Phragmites australis: Management Tool for Reduction of Pollution in the Mar Menor - M. Ruiz; J. Velasco (Water, Air, & Soil Pollution, 2010)

Il6 gene promoter polymorphism (-174G/C) influences the association between fat mass and cardiovascular risk factors - A. Moleres; T. Rendo-Urteaga; C. Azcona; J. A. MartÍnez; S. Gómez-Martínez; J. R. Ruiz; L. A. Moreno; A. Marcos; A. Marti (AVENA group) (Journal of Physiology and Biochemistry, 2009)

Climbing time to exhaustion is a determinant of climbing performance in high-level sport climbers - Vanesa España-Romero; Francisco B. Ortega Porcel; Enrique G. Artero; David Jiménez-Pavón; Ángel Gutiérrez Sainz; Manuel J. Castillo Garzón; Jonatan R. Ruiz (European Journal of Applied Physiology, 2009)

Bleaching response of corals and their Symbiodinium communities in southern Africa - Carlos Ruiz Sebastián; Kerry J. Sink; Timothy R. McClanahan; Donald A. Cowan (Marine Biology, 2009)

Brain mitochondrial alterations after chronic alcohol consumption - I. Almansa; A. Fernández; C. García-Ruiz; M. Muriach; J. M. Barcia; M. Miranda; J. C. Fernández-Checa; F. J. Romero (Journal of Physiology and Biochemistry, 2009)

Neuroprotective effect of carvedilol and melatonin on 3-nitropropionic acid-induced neurotoxicity in neuroblastoma - I. Tasset; C. Espínola; F. J. Medina; M. Feijóo; C. Ruiz; E. Moreno; M. M. Gómez; J. A. Collado; C. Muñoz; J. Muntané; P. Montilla; I. Túnez (Journal of Physiology and Biochemistry, 2009)

Association of mitochondrial haplogroup J and mtDNA oxidative damage in two different North Spain elderly populations - Elena Domínguez-Garrido; Diana Martínez-Redondo; Carmen Martín-Ruiz; Aurora Gómez-Durán; Eduardo Ruiz-Pesini; Pilar Madero; Manuel Tamparillas; Julio Montoya; Thomas von Zglinicki; Carmen Díez-Sánchez; Manuel J. López-Pérez (Biogerontology, 2009)

The Risks of Assisted Colonization - Philip J. Seddon; Doug P. Armstrong; Pritpal Soorae; Frederic Launay; Sally Walker; Carlos R. Ruiz‐Miranda; Sanjay Molur; Heather Koldewey; Devra G. Kleiman (Conservation Biology, 2009)

Chilling damage in a changing climate in coastal landscapes of the subtropical zone: a case study from south Florida - MICHAEL S. ROSS; PABLO L. RUIZ; JAY P. SAH; ERIN J. HANAN (Global Change Biology, 2009)
Freeze events significantly influence landscape structure and community composition along subtropical coastlines. This is particularly true in south Florida, where such disturbances have historically contributed to patch diversity within the mangrove forest, and have played a part in limiting its inland transgression. With projected increases in mean global temperatures, such instances are likely to become much less frequent in the region, contributing to a reduction in heterogeneity within the mangrove forest itself. To understand the process more clearly, we explored the dynamics of a Dwarf mangrove forest following two chilling events that produced freeze‐like symptoms, i.e., leaf browning, desiccation, and mortality, and interpreted the resulting changes within the context of current winter temperatures and projected future scenarios. Structural effects from a 1996 chilling event were dramatic, with mortality and tissue damage concentrated among individuals comprising the Dwarf forest's low canopy. This disturbance promoted understory plant development and provided an opportunity for Laguncularia racemosa to share dominance with Rhizophora mangle . Mortality due to the less severe 2001 event was greatest in the understory, probably because recovery of the protective canopy following the earlier freeze was still incomplete. Stand dynamics were static over the same period in nearby unimpacted sites. The probability of reaching temperatures as low as those recorded at a nearby meteorological station (≤3 °C) under several warming scenarios was simulated by applying 1° incremental temperature increases to a model developed from a 42‐year temperature record. According to the model, the frequency of similar chilling events decreased from once every 1.9 years at present to once every 3.4 and 32.5 years with 1 and 4 °C warming, respectively. The large decrease in the frequency of these events would eliminate an important mechanism that maintains Dwarf forest structure, and promotes compositional diversity.

African ancestry is associated with risk of asthma and high total serum IgE in a population from the Caribbean Coast of Colombia - Candelaria Vergara; Luis Caraballo; Dilia Mercado; Silvia Jimenez; Winston Rojas; Nicholas Rafaels; Tracey Hand; Monica Campbell; Yuhjung J. Tsai; Li Gao; Constanza Duque; Sergio Lopez; et al. (Human Genetics, 2009)

Inhibition of Pichia stipitis fermentation of hydrolysates from olive tree cuttings - Manuel J. Díaz; Encarnación Ruiz; Inmaculada Romero; Cristóbal Cara; Manuel Moya; Eulogio Castro (World Journal of Microbiology and Biotechnology, 2009)

Trace Metals (Cd, Cu, Hg, and Pb) Accumulation Recorded in the Intertidal Mudflat Sediments of Three Coastal Lagoons in the Gulf of California, Mexico - A. C. Ruiz-Fernández; M. Frignani; C. Hillaire-Marcel; B. Ghaleb; M. D. Arvizu; J. R. Raygoza-Viera; F. Páez-Osuna (Estuaries and Coasts, 2009)

Evaluating different harvest intensities over understory plant diversity and pine seedlings, in a Pinus pinaster Ait. natural stand of Spain - J. González-Alday; C. Martínez-Ruiz; F. Bravo (Plant Ecology, 2009)

Gut ammonia production and its modulation - Manuel Romero-Gómez; María Jover; J. Jorge Galán; A. Ruiz (Metabolic Brain Disease, 2009)

Fungal colonization and/or infection in non-neutropenic critically ill patients: results of the EPCAN observational study - C. León; F. Álvarez-Lerma; S. Ruiz-Santana; M. Á. León; J. Nolla; R. Jordá; P. Saavedra; M. Palomar (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Persistence of Streptococcus pneumoniae urinary antigen excretion after pneumococcal pneumonia - F. Andreo; C. Prat; J. Ruiz-Manzano; L. Lores; S. Blanco; M. A. Cuesta; M. Giménez; J. Domínguez (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Filament lumachelle on top of Middle Jurassic oolite limestones: event deposits marking the drowning of a Tethysian carbonate platform (Subbetic, southern Spain) - V. Navarro; J. M. Molina; P. A. Ruiz-Ortiz (Facies, 2009)

Antibody seroprevalences against rabies in dogs vaccinated under field conditions in Bolivia - K. Suzuki; M. R. Pecoraro; A. Loza; M. Pérez; G. Ruiz; G. Ascarrunz; L. Rojas; A. I. Estevez; J. A. Guzman; J. A. C. Pereira; E. T. González (Tropical Animal Health and Production, 2008)

Weak genetic structuring indicates ongoing gene flow across White-ruffed Manakin (Corapipo altera) populations in a highly fragmented Costa Rica landscape - Jacob R. Barnett; Viviana Ruiz-Gutierrez; Aurélie Coulon; Irby J. Lovette (Conservation Genetics, 2008)

Defining the ancestral eutherian karyotype: A cladistic interpretation of chromosome painting and genome sequence assembly data - Terence J. Robinson; Aurora Ruiz-Herrera (Chromosome Research, 2008)

Clinical spectrum of fever of intermediate duration in the south of Spain - J. Parra Ruiz; A. Peña Monje; C. Tomás Jiménez; M. I. Parejo Sánchez; D. Vinuesa García; L. Muñoz Medina; M. A. Martínez Pérez; F. Garcia Garcia; J. Hernández Quero (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Population genetic structure and distribution of introduced American mink (Mustela vison) in Spain, based on microsatellite variation - Roberta Lecis; A. Ferrando; J. Ruiz-Olmo; S. Mañas; X. Domingo-Roura (Conservation Genetics, 2008)

One year of water vapour Raman Lidar measurements at the Andalusian Centre for Environmental Studies (CEAMA) - J. L. Guerrero‐Rascado; B. Ruiz; G. Chourdakis; G. Georgoussis; L. Alados‐Arboledas (International Journal of Remote Sensing, 2008)

Application of Sun/star photometry to derive the aerosol optical depth - D. Pérez‐Ramírez; B. Ruiz; J. Aceituno; F. J. Olmo; L. Alados‐Arboledas (International Journal of Remote Sensing, 2008)

Genetic characterization of Argentinean Artemia species with different fatty acid profiles - Olga Ruiz; Francisco Amat; Carlos Saavedra; Alba Papeschi; Rosa G. Cohen; Athanasios D. Baxevanis; Ilias Kappas; Theodore J. Abatzopoulos; Juan C. Navarro (Hydrobiologia, 2008)

Infraspecific variation of Sechium edule (Jacq.) Sw. in the state of Veracruz, Mexico - J. Cadena-Iñiguez; C. H. Avendaño-Arrazate; M. Soto-Hernández; L. M. Ruiz-Posadas; J. F. Aguirre-Medina; L. Arévalo-Galarza (Genetic Resources and Crop Evolution, 2008)

Slope breccias colonized by bivalves and serpulids during the Middle Jurassic (Subbetic, SE Spain) - Vicente Navarro; Matías Reolid; J. Miguel Molina; Pedro A. Ruiz-Ortiz (Facies, 2008)

Identification and mapping of a locus conferring plum pox virus resistance in two apricot-improved linkage maps - J. M. Soriano; E. M. Vera-Ruiz; S. Vilanova; J. Martínez-Calvo; G. Llácer; M. L. Badenes; C. Romero (Tree Genetics & Genomes, 2008)

Fluid inclusion and Re–Os isotopic evidence for hot, Cenozoic mineralization in the central Pennsylvanian Valley and Ridge Province - R. Mathur; L. Mutti; F. Barra; D. Gold; R. C. Smith; A. Doden; T. Detrie; J. Ruiz; A. McWilliams (Mineralogy and Petrology, 2008)

Geology, Geochemistry and Re–Os systematics of manganese deposits from the Santa Rosalía Basin and adjacent areas in Baja California Sur, México - R. Del Rio Salas; J. Ruiz; L. Ochoa-Landín; O. Noriega; F. Barra; D. Meza-Figueroa; F. Paz-Moreno (Mineralium Deposita, 2008)

Construction of a potato transcriptome map based on the cDNA–AFLP technique - E. Ritter; J. I. Ruiz de Galarreta; H. J. van Eck; I. Sánchez (Theoretical and Applied Genetics, 2008)

Phylogenetic and Structural Analysis of Translationally Controlled Tumor Proteins - Jesús Hinojosa-Moya; Beatriz Xoconostle-Cázares; Elías Piedra-Ibarra; Alfonso Méndez-Tenorio; William J. Lucas; Roberto Ruiz-Medrano (Journal of Molecular Evolution, 2008)

A non-invasive genetic method to identify the sympatric mustelids pine marten (Martes martes) and stone marten (Martes foina): preliminary distribution survey on the northern Iberian Peninsula - Aritz Ruiz-González; Jonathan Rubines; Oskar Berdión; Benjamín J. Gómez-Moliner (European Journal of Wildlife Research, 2008)

Multifractality in space–time statistical models - M. D. Ruiz-Medina; J. M. Angulo; V. V. Anh (Stochastic Environmental Research and Risk Assessment, 2008)

Spatiotemporal random fields associated with stochastic fractional Helmholtz and heat equations - J. M. Angulo; M. Ya. Kelbert; N. N. Leonenko; M. D. Ruiz-Medina (Stochastic Environmental Research and Risk Assessment, 2008)

Mitochondrial haplotype variation in wild trout populations (Teleostei: Salmonidae) from northwestern Mexico - Faustino Camarena-Rosales; Gorgonio Ruiz-Campos; Jorge De La Rosa-Vélez; Richard L. Mayden; Dean A. Hendrickson; Alejandro Varela-Romero; Francisco J. García de León (Reviews in Fish Biology and Fisheries, 2008)

Establishing the genetic relationships between the wild and cultivated olives using a nuclear intron from nitrate reductase (nia-i3) - A. M. Hamman-Khalifa; R. Navajas-Pérez; R. de la Herrán; M. Ruiz Rejón; M. A. Garrido-Ramos; C. Ruiz Rejón; J. L. Rosúa (Plant Systematics and Evolution, 2007)

Erratum to: Predictability of coral bleaching from synoptic satellite and in situ temperature observations - T. R. McClanahan; M. Ateweberhan; C. Ruiz Sebastián; N. A. J. Graham; S. K. Wilson; J. H. Bruggemann; M. M. M. Guillaume (Coral Reefs, 2007)

Predictability of coral bleaching from synoptic satellite and in situ temperature observations - T. R. McClanahan; M. Ateweberhan; C. Ruiz Sebastián; N. A. J. Graham; S. K. Wilson; J. H. Bruggemann; M. M. M. Guillaume (Coral Reefs, 2007)

Preferential accumulation of severe variants of Citrus tristeza virus in plants co-inoculated with mild and severe variants - A. Sambade; S. Ambrós; C. López; S. Ruiz-Ruiz; A. Hermoso de Mendoza; R. Flores; J. Guerri; P. Moreno (Archives of Virology, 2007)

An important new apricot disease in Spain is associated with Hop stunt viroid infection - K. Amari; D. Ruiz; G. Gómez; M. A. Sánchez-Pina; V. Pallás; J. Egea (European Journal of Plant Pathology, 2007)

Uncertainties in projected impacts of climate change on European agriculture and terrestrial ecosystems based on scenarios from regional climate models - J. E. Olesen; T. R. Carter; C. H. Díaz-Ambrona; S. Fronzek; T. Heidmann; T. Hickler; T. Holt; M. I. Minguez; P. Morales; J. P. Palutikof; M. Quemada; M. Ruiz-Ramos; et al. (Climatic Change, 2007)

Predictors of mortality in patients with methicillin-resistant Staphylococcus aureus (MRSA) bacteraemia: the role of empiric antibiotic therapy - J. Gómez; E. García-Vázquez; R. Baños; M. Canteras; J. Ruiz; V. Baños; J. A. Herrero; M. Valdés (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Relationships among four genera of mojarras (Teleostei: Perciformes: Gerreidae) from the western Atlantic and their tentative placement among percomorph fishes - W.‐J. Chen; R. Ruiz‐Carus; G. Ortí (Journal of Fish Biology, 2007)
A phylogenetic study of the percoid family Gerreidae at both lower and higher taxonomic levels is presented based on DNA sequence data of four genes: mitochondrial 12S and 16S, and nuclear genes rhodopsin and recombination activating gene 1 (RAG1). The taxonomic sampling includes four genera of Gerreidae from the western Atlantic, 39 additional percomorph representatives and two outgroups. Phylogenetic results confirm the monophyly of the Gerreidae and suggest that the family is divided into two sub‐groups ( Diapterus auratus plus Eugerres plumieri and Eucinostomus gula plus Gerres cinereus ), which correspond to two previously defined taxonomic assemblages characterized by the shape of the preoperculum. Gerreids are placed at an intermediate position in the percomorph tree between two basal clades (L and Q) and a terminal clade N (grouping tetraodontiforms, acanthuroids, lophiiforms, caproids and several percoids). In addition, topology tests indicate that two traditional assemblages, Labroidei (seven representatives sampled) and Percoidei (22 representatives sampled) are not natural groups. Labrids and scarids appear to be more closely related to gerreids and to the members of clade N than to any other basal percomorphs, including their labroid ‘allies’ sampled in this study, Embiotocidae, Pomacentridae and Cichlidae, which are all nested within clade Q that also includes atherinomorphs, mugiliforms and Chandidae. The percoid taxa included in this study are widely distributed among various percomorph lineages. The percomorph phylogeny obtained is highly congruent with results from recent molecular studies.

Spatial random field simulation by a numerical series representation - A. Oya; J. Navarro-Moreno; J. C. Ruiz-Molina (Stochastic Environmental Research and Risk Assessment, 2007)

Spatial and temporal variation in the elemental and stable isotopic content of the seagrasses Posidonia oceanica and Cymodocea nodosa from the Illes Balears, Spain - J. W. Fourqurean; N. Marbà; C. M. Duarte; E. Diaz-Almela; S. Ruiz-Halpern (Marine Biology, 2007)

Larval development rate predicts range expansion of an introduced crab - Catherine E. deRivera; Natasha Gray Hitchcock; Sarah J. Teck; Brian P. Steves; Anson H. Hines; Gregory M. Ruiz (Marine Biology, 2007)

Patterns of constitutive and IFN-γ inducible expression of HLA class II molecules in human melanoma cell lines - T. Rodríguez; R. Méndez; A. Del Campo; N. Aptsiauri; J. Martín; G. Orozco; G. Pawelec; D. Schadendorf; F. Ruiz-Cabello; F. Garrido (Immunogenetics, 2007)

Wavelet-vaguelette decomposition of spatiotemporal random fields - M. D. Ruiz-Medina; J. M. Angulo; R. Fernández-Pascual (Stochastic Environmental Research and Risk Assessment, 2007)

Chronic intracerebroventricular delivery of the secretory phospholipase A2 inhibitor, 12-epi-scalaradial, does not improve outcome after focal cerebral ischemia–reperfusion in rats - Germán Torregrosa; Fernando J. Pérez-Asensio; María C. Burguete; María Castelló-Ruiz; Juan B. Salom; Enrique Alborch (Experimental Brain Research, 2007)

Scattering of elastic waves in cracked media using a finite difference method - J. A. Pérez-Ruiz; F. Luzón; A. García-Jerez (Studia Geophysica et Geodaetica, 2007)

Linked vs. unlinked markers: multilocus microsatellite haplotype‐sharing as a tool to estimate gene flow and introgression - WIM J. M. KOOPMAN; YINGHUI LI; ELS COART; W. ERIC VAN DE WEG; BEN VOSMAN; ISABEL ROLDÁN‐RUIZ; MARINUS J. M. SMULDERS (Molecular Ecology, 2007)
We have explored the use of multilocus microsatellite haplotypes to study introgression from cultivated ( Malus domestica ) into wild apple ( Malus sylvestris ), and to study gene flow among remnant populations of M. sylvestris. A haplotype consisted of alleles at microsatellite loci along one chromosome. As destruction of haplotypes through recombination occurs much faster than loss of alleles due to genetic drift, the lifespan of a multilocus haplotype is much shorter than that of the underlying alleles. When different populations share the same haplotype, this may indicate recent gene flow between populations. Similarly, haplotypes shared between two species would be a strong signal for introgression. As the expected lifespan of a haplotype depends on the strength of the linkage, the length [in centiMorgans (cM)] of the haplotype shared contains information on the number of generations passed. This application of shared haplotypes is distinct from using haplotype‐sharing to detect association between markers and a certain trait. We inferred haplotypes for four to eight microsatellite loci on Linkage Group 10 of apple from genotype data using the program phase , and then identified those haplotypes shared between populations and species. Compared with a Bayesian analysis of unlinked microsatellite loci using the program structure , haplotype‐sharing detected a partially different set of putative hybrids. Cultivated haplotypes present in M. sylvestris were short ( F ST based on unlinked loci indicated small (0.032–0.058) but statistically significant differentiation between some populations only. However, various M. sylvestris haplotypes were shared in nearly all pairwise comparisons of populations, and their length indicated recent gene flow. Hence, all Dutch populations should be considered as one conservation unit. The added value of using sharing of multilocus microsatellite haplotypes as a source of population genetic information is discussed.

Global spatial patterns and temporal trends of burned area between 1981 and 2000 using NOAA‐NASA Pathfinder - D. RIAÑO; J. A. MORENO RUIZ; D. ISIDORO; S. L. USTIN (Global Change Biology, 2007)
An analysis of the spatial and temporal patterns of global burned area with the Daily Tile US National Oceanic and Atmospheric Administration‐Advanced Very High‐Resolution Radiometer Pathfinder 8 km Land dataset between 1981 and 2000 is presented. Nine distinct temporal and spatial fire patterns were identified at the global scale using principal components and cluster analysis. Three major fire seasons were identified from June to December and from February to June for different areas of the northern hemisphere and from October to March for the southern hemisphere. The area burned primarily followed the annual cycle and secondarily, an important 6‐month cycle. Temporal cycles were unimportant in some equatorial and tropical areas in the northern hemisphere. The total annual burned area has not increased in the last 20 years but a significant increase was found in the mid‐latitude and subtropical areas of the northern hemisphere which was offset by a slight decrease in burned area in tropical southeast Asia and Central America. Additionally, burned area has significantly increased during the summer in the mid‐latitudes of the northern hemisphere and in the boreal region, and the fire season starts earlier in the mid‐latitudes. Total burned area was explained by the extent of savanna (wooded grassland) cover. Latitude was not determinative as divergent fire patterns were encountered and did not have an impact on extent of burned area at our spatial level of analysis.

Sequencing EVC and EVC2 identifies mutations in two-thirds of Ellis–van Creveld syndrome patients - Stuart W. J. Tompson; Victor L. Ruiz-Perez; Helen J. Blair; Stephanie Barton; Victoria Navarro; Joanne L. Robson; Michael J. Wright; Judith A. Goodship (Human Genetics, 2006)

Elevated male European and female African contributions to the genomes of African American individuals - Joanne M. Lind; Holli B. Hutcheson-Dilks; Scott M. Williams; Jason H. Moore; Myron Essex; Eduardo Ruiz-Pesini; Douglas C. Wallace; Sarah A. Tishkoff; Stephen J. O’Brien; Michael W. Smith (Human Genetics, 2006)

Molecular Analysis of Local Potato Cultivars from Tenerife Island Using Microsatellite Markers - L. Barandalla; J. I. Ruiz de Galarreta; D. Rios; E. Ritter (Euphytica, 2006)

Multiple origins of cultivated grapevine ( Vitis vinifera L. ssp. sativa ) based on chloroplast DNA polymorphisms - R. ARROYO‐GARCÍA; L. RUIZ‐GARCÍA; L. BOLLING; R. OCETE; M. A. LÓPEZ; C. ARNOLD; A. ERGUL; G. SÖYLEMEZO˝LU; H. I. UZUN; F. CABELLO; J. IBÁÑEZ; M. K. ARADHYA; et al. (Molecular Ecology, 2006)
The domestication of the Eurasian grape ( Vitis vinifera ssp. sativa ) from its wild ancestor ( Vitis vinifera ssp. sylvestris ) has long been claimed to have occurred in Transcaucasia where its greatest genetic diversity is found and where very early archaeological evidence, including grape pips and artefacts of a ‘wine culture’, have been excavated. Whether from Transcaucasia or the nearby Taurus or Zagros Mountains, it is hypothesized that this wine culture spread southwards and eventually westwards around the Mediterranean basin, together with the transplantation of cultivated grape cuttings. However, the existence of morphological differentiation between cultivars from eastern and western ends of the modern distribution of the Eurasian grape suggests the existence of different genetic contribution from local sylvestris populations or multilocal selection and domestication of sylvestris genotypes. To tackle this issue, we analysed chlorotype variation and distribution in 1201 samples of sylvestris and sativa genotypes from the whole area of the species’ distribution and studied their genetic relationships. The results suggest the existence of at least two important origins for the cultivated germplasm, one in the Near East and another in the western Mediterranean region, the latter of which gave rise to many of the current Western European cultivars. Indeed, over 70% of the Iberian Peninsula cultivars display chlorotypes that are only compatible with their having derived from western sylvestris populations.

Heavy Metals in the Tissues of the Sea Turtle Lepidochelys olivacea from a Nesting Site of the Northwest Coast of Mexico - M. G. Frías-Espericueta; J. I. Osuna-López; A. Ruiz-Telles; J. M. Quintero-Alvarez; G. López-López; G. Izaguirre-Fierro; D. Voltolina (Bulletin of Environmental Contamination and Toxicology, 2006)

Males vs workers: testing the assumptions of the haploid susceptibility hypothesis in bumblebees - Mario X. Ruiz-González; Mark J. F. Brown (Behavioral Ecology and Sociobiology, 2006)

Contamination of the Coastal Waters of Gijón (North West Spain) by Butyltin Compounds - Pablo Rodríguez-González; Jorge Ruiz Encinar; J. Ignacio García Alonso; Alfredo Sanz-Medel (Water, Air, & Soil Pollution, 2006)

Level and Transmission of Genetic Heterozygosity in Apricot (Prunus armeniaca L.) Explored Using Simple Sequence Repeat Markers - R. Sánchez-Pérez; P. Martínez-Gómez; F. Dicenta; J. Egea; D. Ruiz (Genetic Resources and Crop Evolution, 2006)

Occurrence and distribution of resistance to QoI fungicides in populations of Podosphaera fusca in south central Spain - D. Fernández-Ortuño; A. Pérez-García; F. López-Ruiz; D. Romero; A. de Vicente; J. A. Torés (European Journal of Plant Pathology, 2006)

Nanotechnology for Cell–Substrate Interactions - Nathan J. Sniadecki; Ravi A. Desai; Sami Alom Ruiz; Christopher S. Chen (Annals of Biomedical Engineering, 2006)

Coat protein gene sequence of a Mexican isolate of Sugarcane mosaic virus and its infectivity in maize and sugarcane plants - F. Espejel; D. Jeffers; J. C. Noa-Carrazana; S. Ruiz-Castro; L. Silva-Rosales (Archives of Virology, 2006)

The complete nucleotide sequence of a severe stem pitting isolate of Citrus tristeza virus from Spain: comparison with isolates from different origins - S. Ruiz-Ruiz; P. Moreno; J. Guerri; S. Ambrós (Archives of Virology, 2006)

Heat-induced programmed cell death in Leishmania infantum is reverted by Bcl-XL expression - J. F. Alzate; A. Álvarez- Barrientos; V. M. González; A. Jiménez-Ruiz (Apoptosis, 2006)

The History of Potato (Solanum tuberosum L.) Research in Spain - J. I. Ruiz de Galarreta; J. Pascualena; F. J. Legorburu; L. Barandalla; E. Ritter (Potato Research, 2006)

Basis of selectivity of cyhalofop-butyl in Oryza sativa L. - J. P. Ruiz-Santaella; A. Heredia; R. De Prado (Planta, 2006)

Boron Increases Synthesis of Glutathione in Sunflower Plants Subjected to Aluminum Stress - J. M. Ruiz; R. M. Rivero; L. Romero (Plant and Soil, 2006)

Relationships Between Climatic Variables and Sap Flow, Stem Water Potential and Maximum Daily Trunk Shrinkage in Lemon Trees - M. F. Ortuño; Y. García-Orellana; W. Conejero; M. C. Ruiz-Sánchez; O. Mounzer; J. J. Alarcón; A. Torrecillas (Plant and Soil, 2006)

The effects of an antioxidant-supplemented beverage on exercise-induced oxidative stress: results from a placebo-controlled double-blind study in cyclists - J. Morillas-Ruiz; P. Zafrilla; M. Almar; M. J. Cuevas; F. J. López; P. Abellán; J. A. Villegas; J. González-Gallego (European Journal of Applied Physiology, 2005)

Mercury in surface sediments and benthic organisms from Guaymas Bay, east coast of the Gulf of California - C. Green-Ruiz; J. Ruelas-Inzunza; F. Páez-Osuna (Environmental Geochemistry and Health, 2005)

Isolation of Vagococcus salmoninarum in Rainbow Trout, Oncorhynchus mykiss (Walbaum), Broodstocks: Characterization of the Pathogen - I. Ruiz-Zarzuela; I. de Bias; O. Gironés; C. Ghittino; J. L. MúAzquiz (Veterinary Research Communications, 2005)

DNA methylation increases throughout Arabidopsis development - L. Ruiz-García; M. T. Cervera; J. M. Martínez-Zapater (Planta, 2005)

A PSP94-derived Peptide PCK3145 inhibits MMP-9 Secretion and Triggers CD44 Cell Surface Shedding: Implication in Tumor Metastasis - Borhane Annabi; Mounia Bouzeghrane; Jean-Christophe Currie; Robert Hawkins; Hélène Dulude; Luc Daigneault; Marcia Ruiz; Jan Wisniewski; Seema Garde; Shafaat A. Rabbani; Chandra Panchal; Jinzi J. Wu; et al. (Clinical & Experimental Metastasis, 2005)

Possibility of Reductive Deactivation of S-Triazines and Parent Compounds on Waters and Sediments - R. Marín GalvÍn; M. Ruiz Montoya; M. J. Higuera; R. Pérez; J. M. Rodríguez Mellado (Water, Air, & Soil Pollution, 2005)

Differential accumulation of dehydrin-like proteins by abiotic stresses in Deschampsia antarctica Desv. - Nélida Olave-Concha; León A. Bravo; Simón Ruiz-Lara; Luis J. Corcuera (Polar Biology, 2005)

Spatial root distribution of apricot trees in different soil tillage practices - M. C. Ruiz-Sánchez; V. Plana; M. F. Ortuño; L. M. Tapia; J. M. Abrisqueta (Plant and Soil, 2005)

Influence of the Th2 immune response established by Nippostrongylus brasiliensis infection on the protection offered by different vaccines against Chlamydophila abortus infection - M. R. Caro; A. J. Buenda; N. Ortega; M. C. Gallego; C. M. Martnez; F. Cuello; M. R. Ruiz-Ybaez; K. J. Erb; J. Salinas (Veterinary Research Communications, 2005)

U–Pb zircon and Re–Os molybdenite geochronology from La Caridad porphyry copper deposit: insights for the duration of magmatism and mineralization in the Nacozari District, Sonora, Mexico - V. A. Valencia; J. Ruiz; F. Barra; G. Geherls; M. Ducea; S. R. Titley; L. Ochoa-Landin (Mineralium Deposita, 2005)

Recruitment of Acropora, Millepora and Stylaster roseus on an experimental substratum - M. A. Ruiz-Zrate; J. E. Arias-Gonzlez (Coral Reefs, 2005)

Range wide versus local patterns of genetic diversity in hornbeam (Carpinus betulus L.) - Els Coart; Sabine Van Glabeke; Rémy J. Petit; Erik Van Bockstaele; Isabel Roldán-Ruiz (Conservation Genetics, 2005)

Enhanced anaerobic biodegradation of BTEX-ethanol mixtures in aquifer columns amended with sulfate, chelated ferric iron or nitrate - Marcio L. B. Da Silva; Graciela M. L. Ruiz-Aguilar; Pedro J. J. Alvarez (Biodegradation, 2005)

Joint estimation of spatial deformation and blurring in environmental data - A. Goita; M. D. Ruiz Medina; J. M. Angulo (Stochastic Environmental Research and Risk Assessment, 2005)

Short-term effects of data-loggers on Cory?s shearwater (Calonectris diomedea) - J. M. Igual; M. G. Forero; G. Tavecchia; J. Gonzlez-Solis; A. Martnez-Abran; K. A. Hobson; X. Ruiz; D. Oro (Marine Biology, 2005)

Protective effect of triflusal and its main metabolite HTB in an in vitro model of anoxia-reoxygenation in rat brain slices: comparison with acetylsalicylic and salicylic acids - J. A. González-Correa; M. M. Arrebola; I. M. Ureña; D. Ruiz-Villafranca; J. Muñoz-Marín; A. Guerrero; F. Sánchez de la Cuesta; J. P. De La Cruz (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

A novel ARH splice site mutation in a Mexican kindred with autosomal recessive hypercholesterolemia - Samuel Canizales-Quinteros; Carlos A. Aguilar-Salinas; Adriana Huertas-Vázquez; María L. Ordóñez-Sánchez; Maribel Rodríguez-Torres; José L. Venturas-Gallegos; Laura Riba; Salvador Ramírez-Jimenez; Rocío Salas-Montiel; Giovani Medina-Palacios; Ludivina Robles-Osorio; Angel Miliar-García; et al. (Human Genetics, 2005)

Identification of molecular markers linked with crown rust (Puccinia coronata f. sp. lolii) resistance in perennial ryegrass (Lolium perenne) using AFLP markers and a bulked segregant approach - H. Muylle; J. Baert; E. Van Bockstaele; B. Moerkerke; E. Goetghebeur; I. Roldán-Ruiz (Euphytica, 2005)

The American brine shrimp as an exotic invasive species in the western Mediterranean - Francisco Amat; Francisco Hontoria; Olga Ruiz; Andy J. Green; Marta I. Sánchez; Jordi Figuerola; Francisco Hortas (Biological Invasions, 2005)

Knowledge of post-exposure prophylaxis inadequate despite published guidelines - J. Parra-Ruiz; L. Muoz-Medina; J. Callejas-Rubio; M. Martnez; M. A. Martnez-Prez; J. Hernndez-Quero (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Improvement of Transfection Efficiency of Epithelioma Papulosum Cyprini Carp Cells by Modification of Cell Cycle and Use of an Optimal Promoter - A. Rocha; S. Ruiz; J. M. Coll (Marine Biotechnology, 2004)

Loss on ignition: a qualitative or quantitative method for organic matter and carbonate mineral content in sediments? - Juan I. Santisteban; Rosa Mediavilla; Enrique López-Pamo; Cristino J. Dabrio; M. Blanca Ruiz Zapata; M. José Gil García; Silvino Castaño; Pedro E. Martínez-Alfaro (Journal of Paleolimnology, 2004)

Effect of recombinant human GH and GHRH on plasma metabolite levels in rainbow trout (Oncorhynchus mykiss) - M. D. Hernández Llorente; M. J. Dato Gómez; J. de Costa Ruiz; P. Mendiola López; S. Zamora Navarro (Journal of Physiology and Biochemistry, 2004)

Tourmaline from the rare-element Pinilla pegmatite, (Central Iberian Zone, Zamora, Spain): chemical variation and implications for pegmatitic evolution - E. Roda-Robles; A. Pesquera; F. Fontan; P. P. Gil; J. Torres-Ruiz (Mineralogy and Petrology, 2004)

Tuberculous vertebral osteomyelitis in the new millennium: still a diagnostic and therapeutic challenge - J. D. Colmenero; M. E. Jimnez-Mejas; J. M. Reguera; J. Palomino-Nics; J. D. Ruiz-Mesa; J. Mrquez-Rivas; A. Lozano; J. Pachn (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Creation of BAC genomic resources for cocoa (Theobroma cacao L.) for physical mapping of RGA containing BAC clones - D. Clément; C. Lanaud; X. Sabau; O. Fouet; L. Le Cunff; E. Ruiz; A. M. Risterucci; J. C. Glaszmann; P. Piffanelli (Theoretical and Applied Genetics, 2004)

Application of Inducible and Targeted Gene Strategies to Produce Transgenic Fish: A Review - A. Rocha; S. Ruiz; A. Estepa; J. M. Coll (Marine Biotechnology, 2004)

Interaction and impacts of two introduced species on a soft-sediment marine assemblage in SE Tasmania - D. J. Ross; C. R. Johnson; C. L. Hewitt; G. M. Ruiz (Marine Biology, 2004)

QTL analysis of citrus tristeza virus-citradia interaction - M. J. Asins; G. P. Bernet; C. Ruiz; M. Cambra; J. Guerri; E. A. Carbonell (Theoretical and Applied Genetics, 2004)

Quantitation of Human Immunodeficiency Virus Type 1 RNA Loads in Cervicovaginal Secretions in Pregnant Women and Relationship Between Viral Loads in the Genital Tract and Blood - S. Garca-Bujalance; G. Ruiz; C. Ladrn de Guevara; J. M. Pea; I. Bates; J. J. Vzquez; A. Gutirrez (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

A Case of Multiorgan Failure Following Interruption of Antiretroviral Treatment - M. Crespo; J. C. Paradieiro; E. Ribera; I. Ruiz; V. Falc; J. Lopez-Quiones; I. Ocaa; A. Pahissa (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Southern bean Mosaic Virus the Causal Agent of a New Disease of Phaseolus vulgaris beans in Spain - J.Th.J. Verhoeven; J.W. Roenhorst; D.-E. Lesemann; E. Segundo; L. Velasco; L. Ruiz; D. Janssen; I.M. Cuadrado (European Journal of Plant Pathology, 2003)

NMR study of manganese(II) binding by a new versatile peroxidase from the white-rot fungus Pleurotus eryngii - Lucia Banci; Susana Camarero; Angel T. Martínez; María J. Martínez; Marta Pérez-Boada; Roberta Pierattelli; Francisco J. Ruiz-Dueñas (JBIC Journal of Biological Inorganic Chemistry, 2003)

Intestinal candidiasis. A clinical report and comments about this opportunistic pathology - D. Ruiz-Sánchez; L. Calderón-Romero; J. T. Sánchez-Vega; J. Tay (Mycopathologia, 2003)

Inheritance of resistance to two races of sunflower downy mildew (Plasmopara halstedii) in two Helianthus annuus L. lines - M. L. Molinero-Ruiz; J. M. Melero-Vara; J. Domínguez (Euphytica, 2003)

Genetic variation in the endangered wild apple ( Malus sylvestris (L.) Mill.) in Belgium as revealed by amplified fragment length polymorphism and microsatellite markers - Els Coart; Xavier Vekemans; Marinus J. M. Smulders; Iris Wagner; Johan Van Huylenbroeck; Erik Van Bockstaele; Isabel Roldán‐Ruiz (Molecular Ecology, 2003)
The genetic variation within and between wild apple samples ( Malus sylvestris ) and cultivated apple trees was investigated with amplified fragment length polymorphisms (AFLP) and microsatellite markers to develop a conservation genetics programme for the endangered wild apple in Belgium. In total, 76 putative wild apples (originating from Belgium and Germany), six presumed hybrids and 39 cultivars were typed at 12 simple sequence repeats (SSR) and 139 amplified fragment length polymorphism (AFLP) loci. Principal co‐ordinate analysis and a model‐based clustering method classified the apples into three major gene pools: wild Malus sylvestris genotypes, edible cultivars and ornamental cultivars. All presumed hybrids and two individuals (one Belgian, one German) sampled as M. sylvestris were assigned completely to the edible cultivar gene pool, revealing that cultivated genotypes are present in the wild. However, gene flow between wild and cultivated gene pools is shown to be almost absent, with only three genotypes that showed evidence of admixture between the wild and edible cultivar gene pools. Wild apples sampled in Belgium and Germany constitute gene pools that are clearly differentiated from cultivars and although some geographical pattern of genetic differentiation among wild apple populations exists, most variation is concentrated within samples. Concordant conclusions were obtained from AFLP and SSR markers, which showed highly significant correlations in both among‐genotypes and among‐samples genetic distances.

Analysis of DNA methylation in Arabidopsis thaliana based on methylation-sensitive AFLP markers - M.-T. Cervera; L. Ruiz-García; J. Martínez-Zapater (Molecular Genetics and Genomics, 2003)

Quantitative Inoculations of Poplars with Melampsora Larici-populina - M.H. Pei; C. Ruiz; J. Harris; T. Hunter (European Journal of Plant Pathology, 2003)

Analysis of DNA methylation in Arabidopsis thaliana based on methylation-sensitive AFLP markers - M.-T. Cervera; L. Ruiz-García; J. Martínez-Zapater (Molecular Genetics and Genomics, 2002)

First Report of Urinary Tract Infection due to Pichia ohmeri - J. Puerto; P. García-Martos; A. Saldarreaga; J. Ruiz-Aragón; R. García-Agudo; S. Aoufi (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Establishment of a Non-Permanent GPS Network to Monitor the Recent NE-SW Deformation in the Granada Basin (Betic Cordillera, Southern Spain) - A. J. Gil; G. Rodríguez-Caderot; M. C. Lacy; A. M. Ruiz; C. Sanz de Galdeano; P. Alfaro (Studia Geophysica et Geodaetica, 2002)

Mexican native trouts: a review of their history and current systematic and conservation status - Dean A. Hendrickson; Héctor Espinosa Pérez; Lloyd T. Findley; William Forbes; Joseph R. Tomelleri; Richard L. Mayden; Jennifer L. Nielsen; Buddy Jensen; Gorgonio Ruiz Campos; Alejandro Varela Romero; Albert van der Heiden; Faustino Camarena; et al. (Reviews in Fish Biology and Fisheries, 2002)

Distribution of intrachromosomal telomeric sequences (ITS) on Macaca fascicularis (Primates) chromosomes and their implication for chromosome evolution - A. Ruiz-Herrera; F. García; C. Azzalin; E. Giulotto; J. Egozcue; M. Ponsà; M. Garcia (Human Genetics, 2002)

Comparative Trial of the Effect of Pneumococcal Vaccine on Viral Load and CD4+ Lymphocytes in Asymptomatic and Antiretrovirally Naïve HIV-Infected Patients - Santos J.; Palacios R.; Ruiz J.; González M.; Márquez M. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Improvement of DNA transfection with cationic liposomes - A. Rocha; S. Ruiz; J. M. Coll (Journal of Physiology and Biochemistry, 2002)

Genes for mevalonate biosynthesis in Phycomyces - J. Ruiz-Albert; E. Cerdá-Olmedo; L. Corrochano (Molecular Genetics and Genomics, 2002)

Fragile Sites in Human and Macaca Fascicularis Chromosomes are Breakpoints in Chromosome Evolution - A. Ruiz-Herrera; M. Ponsà; F. García; J. Egozcue; M. García (Chromosome Research, 2002)

A comparative study of molecular and morphological methods of describing relationships between perennial ryegrass (Lolium perenne L.) varieties - I. Roldán-Ruiz; F.A. van Euwijk; T. J. Gilliland; P. Dubreuil; C. Dillmann; J. Lallemand; M. De Loose; C. P. Baril (Theoretical and Applied Genetics, 2001)

Verapamil sensitisation to alkaloids on colchicine-selected human colon adenocarcinoma cells - M. J. Ruiz Gómez; A. Souviron; L. Gil; M. Martínez Morillo (Journal of Physiology and Biochemistry, 2001)

Influence of fitness on the integrated neuroendocrine response to aerobic exercise until exhaustion - A. M. de Diego Acosta; J. -C. García; V. J. Fernández-Pastor; S. Perán; M. Ruiz; F. Guirado (Journal of Physiology and Biochemistry, 2001)

Molecular characterization of a novel recombinant strain of human astrovirus associated with gastroenteritis in children - J. E. Walter; J. Briggs; M. L. Guerrero; D. O. Matson; L. K. Pickering; G. Ruiz-Palacios; T. Berke; D. K. Mitchell (Archives of Virology, 2001)

A negative regulator of light-inducible carotenogenesis in Mucor circinelloides - E. Navarro; J. Lorca-Pascual; M. Quiles-Rosillo; F. Nicolás; V. Garre; S. Torres-Martínez; R. Ruiz-Vázquez (Molecular Genetics and Genomics, 2001)

The Leishmania genome project: new insights into gene organization and function - Peter J. Myler; Stephen M. Beverley; Angela K. Cruz; Deborah E. Dobson; Alasdair C. Ivens; Paul D. McDonagh; Rentala Madhubala; Santiago Martinez-Calvillo; Jeronimo C. Ruiz; Alka Saxena; Ellen Sisk; Susan M. Sunkin; et al. (Medical Microbiology and Immunology, 2001)

Multicenter Study of a Commercial, Automated Polymerase Chain Reaction System for the Rapid Detection of Mycobacterium tuberculosis in Respiratory Specimens in Routine Clinical Practice - M. Bogard; J. Vincelette; R. Antinozzi; R. Alonso; T. Fenner; J. Schirm; D. Aubert; C. Gaudreau; E. Sala; M. Ruiz-Serrano; H. Petersen; L. Oostendorp; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

Regulation of the hydrogenase system in Rhizobium leguminosarum - T. Ruiz-Argüeso; J. M. Palacios; J. Imperial (Plant and Soil, 2001)

Phytoplankton biomass in the sub-Antarctic area of the Straits of Magellan (53°S), Chile during spring-summer 1997/1998 - José Luis Iriarte; A. Kusch; J. Osses; M. Ruiz; José Luis Iriarte (Polar Biology, 2001)

Estimating above-ground biomass and production in mangrove communities of Biscayne National Park, Florida (U.S.A.) - Michael S. Ross; Pablo L. Ruiz; Guy J. Telesnicki; John F. Meeder (Wetlands Ecology and Management, 2001)

Chromosomal location and evolution of a satellite DNA family in seven sturgeon species - M. Lanfredi; L. Congiu; M. A. Garrido-Ramos; R. dela Herrán; M. Leis; M. Chicca; R. Rossi; J. Tagliavini; C. Ruiz Rejón; M. Ruiz Rejón; F. Fontana (Chromosome Research, 2001)

Symbiotic efficiency and infectivity of an autochthonous arbuscular mycorrhizal Glomus sp. from saline soils and Glomus deserticola under salinity - J. M. Ruiz-Lozano; Rosario Azcón (Mycorrhiza, 2000)

P-glycoprotein, glutathione and glutathione S-transferase increase in a colon carcinoma - M. J. Ruiz-Gómez; A. Souviron; M. Martínez-Morillo; L. Gil (Journal of Physiology and Biochemistry, 2000)

NOTE: Spatial Structure and Gene Flow from Biochemical Markers in the “Pyrenean Brown” Breed, a Rare Cattle Race in Catalonia (Spain) - M. Ruiz-Garcia; J. Jordana (Biochemical Genetics, 2000)

Prognostic Factors for Pneumococcal Bacteremia in a University Hospital - C. Fariñas Alvarez; M. C. Fariñas; J. D. García-Palomo; M. González-Ruiz; C. Fernández Mazarrasa; J. A. Parra; J. González-Macías (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

The evolution of the ribosomal loci in the subgenusLeopoldia of the genusMuscari (Hyacinthaceae) - N. Cuñado; R. De la Herrán; J. L. Santos; C. Ruiz Rejón; M. A. Garrido-Ramos; M. Ruiz Rejón (Plant Systematics and Evolution, 2000)

Fish and ships: relating dispersal frequency to success in biological invasions - M. J. Wonham; J. T. Carlton; G. M. Ruiz; L. D. Smith (Marine Biology, 2000)

Chromosomal homologies between humans and Cebus apella (Primates) revealed by ZOO-FISH - F. García; C. Nogués; M. Ponsà; A. Ruiz-Herrera; J. Egozcue; Montserrat Garcia Caldés (Mammalian Genome, 2000)

Coat protein sequence comparisons of three Mexican isolates of papaya ringspot virus with other geographical isolates reveal a close relationship to American and Australian isolates - L. Silva-Rosales; N. Becerra-Leor; S. Ruiz-Castro; D. Téliz-Ortiz; J. C. Noa-Carrazana (Archives of Virology, 2000)

Transfer of PLRV resistance fromSolanum verrucosum Schlechdt to potato (S. tuberosum L.) by protoplast electrofusion - A. Carrasco; J. I. Ruiz de Galarreta; A. Rico; E. Ritter (Potato Research, 2000)

A SWACROP-based potato root water-uptake function as determined under tropical conditions - Angel Utset; Maria Elena Ruiz; J. Garcia; R. A. Feddes (Potato Research, 2000)

Multidrug resistance increment in a human colon carcinoma cell line by colchicine - M. J. Ruiz Gómez; L. Gil; A. Souviron; M. Martínez Morillo (Journal of Physiology and Biochemistry, 2000)

Improved activity and stability of an immobilized recombinant laccase in organic solvents - Annia I. Ruiz; Adriel J. Malavé; Claus Felby; Kai Griebenow (Biotechnology Letters, 2000)

Genes involved in resistance to powdery mildew in barley differentially modulate root colonization by the mycorrhizal fungus Glomus mosseae - J. M. Ruiz-Lozano; S. Gianinazzi; V. Gianinazzi-Pearson (Mycorrhiza, 1999)

Age and sources of the ore at Tharsis and Rio Tinto, Iberian Pyrite Belt, from Re-Os isotopes - R. Mathur; J. Ruiz; F. Tornos (Mineralium Deposita, 1999)

Growth modification of human colon adenocarcinoma cells exposed to a low-frequency electromagnetic field - M. J. Ruiz Gómez; J. M. Pastor Vega; L. de la Peña; L. Gil Carmona; M. Martínez Morillo (Journal of Physiology and Biochemistry, 1999)

Fully Automated Liquid Culture System Compared with Lwenstein-Jensen Solid Medium for Rapid Recovery of Mycobacteria from Clinical Samples - J. Ferro; N. Ruiz Palma; P. Prendes; H. Villar; J. J. Palacios; J. Rodrguez; M. D. Macas; J. M. Garca (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Evolution of Resistance among Clinical Isolates of Acinetobacter over a 6-Year Period - J. Ruiz; M. L. Núñez; J. Pérez; E. Simarro; L. Martínez-Campos; J. Gómez (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Stability of xylanases in the presence of methanol and its evaluation on the bleaching capacity - J. Ruiz; R. Angelo; J. Freer; J. Baeza; C. Aguirre; E. Curotto; N. Durán (Biotechnology Letters, 1999)

Metabolic and hormonal changes during aerobic exercise in distance runners - V. J. Fernández-Pastor; M. Ruiz; A. M. Diego-Acosta; C. Avila; J. C. García; F. Pérez; F. Guirado; N. Noguer (Journal of Physiology and Biochemistry, 1999)

Invasion Pressure to a Ballast-flooded Estuary and an Assessment of Inoculant Survival - L. David Smith; Marjorie J. Wonham; Linda D. McCann; Gregory M. Ruiz; Anson H. Hines; James T. Carlton (Biological Invasions, 1999)

Evaluation of Methods for Isolation of Salmonella Species using Modified Semisolid Rappaport-Vassiliadis Medium and Salmonella-Shigella Agar - J. Ruiz Gomez; I. Lorente Salinas; J. Perez Salmerón; E. Simarro Cordoba; L. Martinez Campos (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Comparison of the Ligase Chain Reaction with Solid and Liquid Culture Media for Routine Detection of Mycobacterium tuberculosis in Nonrespiratory Specimens - J. J. Palacios; J. Ferro; N. Ruiz Palma; S. G. Roces; H. Villar; J. Rodríguez; P. Prendes (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Effect of RU486 injected on proestrous morning on LHRH, LH and 17β-estradiol secretion during the estrous cycle in rat - M. Tébar; A. Ruiz; D. González; G. Hernández; R. Alonso; J. E. Sánchez-Criado (Journal of Physiology and Biochemistry, 1998)

Micropropagation of 21 species of Mexican cacti by axillary proliferation - Eugenio Pérez Molphe Balch; Martha E. Pérez Reyes; Enrique Villalobos Amador; Ernestina Meza Rangel; Leticia del Rocío Morones Ruiz; Hugo J. Lizalde Viramontes (In Vitro Cellular & Developmental Biology - Plant, 1998)

WildSolanum species as resistance sources against different pathogens of potato - J. I. Ruiz de Galarreta; A. Carrasco; A. Salazar; I. Barrena; E. Iturritxa; R. Marquinez; F. J. Legorburu; E. Ritter (Potato Research, 1998)

α-MeGlc and D-glucose transport by hepatopancreatic brush border membrane vesicles from prawn - J. A. Blaya; C. M. Vázquez; F. J. G. Muriana; V. Ruiz-Gutiérrez; J. Bolufer (Journal of Physiology and Biochemistry, 1998)

Seed germination in wild clovers ( Trifolium, Leguminosae ) from Southwestern Europe (Spain) - J. A. DEVESA; T. RUIZ; P. RODRIGUEZ (Plant Biosystems, 1998)

Dissipation and Distribution of Atrazine, Simazine, Chlorpyrifos, and Tetradifon Residues in Citrus Orchard Soil - M. J. Redondo; M. J. Ruiz; G. Font; R. Boluda (Archives of Environmental Contamination and Toxicology, 1997)

Variation and classification of B low-molecular-weight glutenin subunit alleles in durum wheat - M. T. Nieto-Taladriz; M. Ruiz; M. C. Martínez; J. F. Vázquez; J. M. Carrillo (Theoretical and Applied Genetics, 1997)

Toxicity Assessment of Pesticides Using the Microtox Test: Application to Environmental Samples - M. J. Ruiz; L. López-Jaramillo; M. J. Redondo; G. Font (Bulletin of Environmental Contamination and Toxicology, 1997)

Cryptic invasions of the crab Carcinus detected by molecular phylogeography - J. B. Geller; E. D. Walton; E. D. Grosholz; G. M. Ruiz (Molecular Ecology, 1997)
Coastal marine ecosystems world‐wide are threatened by invasions of nonindigenous species. The ubiquity of marine sibling species identifiable only by genetic analysis suggests that many invasions are cryptic and therefore undetected, causing an underestimation of the actual number and impacts of invading species. We test this hypothesis with European crabs in the genus Carcinus that have invaded five regions globally. Partial 16S ribosomal RNA gene sequences confirm sibling species status of morphologically similar Atlantic C. maenas and Mediterranean C. aestuarii . Based on 16S rRNA haplotypes, crabs from California, New England and Tasmania were all C. maenas . However, we report the cryptic multiple invasion of both species in Japan and South Africa, where only C. aestuarii and C. maenas , respectively, were previously recognized.

Evaluation and improvement of the energy efficiency of nitrogen fixation in Lotus corniculatus nodules induced by Rhizobium loti strains indigenous to Uruguay - J. Monza; P. Diaz; O. Borsani; T. Ruiz-Argu¨eso; J.M. Palacios (World Journal of Microbiology and Biotechnology, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Morphometric and genetic analysis as proof of the existence of two sturgeon species in the Guadalquivir river - M. A. Garrido-Ramos; M. C. Soriguer; R. de la Herrán; M. Jamilena; C. Ruiz Rejón; A. Domezain; J. A. Hernando; M. Ruiz Rejón (Marine Biology, 1997)

RESEARCH: Managing Mountainous Degraded Landscapes After Farmland Abandonment in the Central Spanish Pyrenees - M. Molinillo; T. Lasanta; J. M. García-Ruiz (Environmental Management, 1997)

Lipid and fatty acid composition of muscle and internal organs from Ruvettus pretiosus - V. Ruiz‐Gutierrez; M. C. Perez‐Zarza; F. J. G. Muriana; L. Bravo (Journal of Fish Biology, 1997)
The lipid composition of different muscular areas (dorsal, ventral, subcutaneous, periosteum) and organs (liver, gall bladder, testes) of a gempylid fish Ruvettus pretiosus was examined. Waxes were the main lipid fraction in muscular areas, while the liver and testes were quite enriched in triglycerides and phospholipids. Oleic acid and fatty acids of n‐3 family were the most frequently found in total lipids.

Δ9-tetrahydrocannabinol increases activity of tyrosine hydroxylase in cultured fetal mesencephalic neurons - Maria L. Hernández; Lucía García-Gil; Fernando Berrendero; Jose A. Ramos; J. Javier Fernández-Ruiz (Journal of Molecular Neuroscience, 1997)

A marine bacterial strain effective in producing antagonisms of other bacteria - C. M. Ruiz; G. Romn; J. L. Snchez (Aquaculture International, 1996)

Suspended particulate matter dynamics in the shallow mesotidal urdaibai estuary (Bay of Biscay, Spain) - A. Ruiz; J. Franco; E. Orive (Aquatic Ecology, 1994)

Morphogenesis of African swine fever virus in monkey kidney cells after reversible inhibition of replication by cycloheximide - O. Arzuza; A. Urzainqui; J. R. Díaz-Ruiz; E. Tabarés (Archives of Virology, 1992)

Nitrite uptake in Azotobacter chroococcum - María T. Ruiz; María C. Muñoz-Centeno; Francisco J. Cejudo; Antonio Paneque (Archives of Microbiology, 1992)

Effect of divalent cations on the short-term NH 4 + inhibition of nitrogen fixation in Azotobacter chroococcum - María T. Ruiz; Francisco J. Cejudo; Antonio Paneque (Archives of Microbiology, 1990)

Self-assembly properties of the proteinaceous coat secreted by the ?slime? variant of Neurospora crassa - M. Casanova; J. P. Martinez; M. L. Gil; R. Sentandreu; J. Ruiz-Herrera (Archives of Microbiology, 1989)

Characterization of a proteinaceous extracellular coat synthesized by the ?slime? variant of Neurospora crassa - J. P. Martinez; M. L. Gil; M. Casanova; M. Rico; R. Sentandreu; J. Ruiz-Herrera (Archives of Microbiology, 1989)

Amplified expression of ribulose bisphosphate carboxylase/oxygenase in pBR322-transformants of Anacystis nidulans - H. Daniell; J. A. Torres-Ruiz; A. Inamdar; B. A. McFadden (Archives of Microbiology, 1988)

Inhibition of the yeast-mycelial transition and the phorogenesis of Mucorales by diamino butanone - M. Martinez-Pacheco; G. Rodriguez; G. Reyna; C. Calvo-Mendez; J. Ruiz-Herrera (Archives of Microbiology, 1988)

Separation of chitosomes and secretory vesicles from the ?slime? variant of Neurospora crassa - J. Ruiz-Herrera; J. P. Martinez; M. Casanova; M. L. Gil; R. Sentandreu (Archives of Microbiology, 1987)

Activation of chitin synthetase from Phycomyces blakesleeanus by calcium and calmodulin - G. Martinez-Cadena; J. Ruiz-Herrera (Archives of Microbiology, 1987)

Accumulation and distribution of hydrocarbons, polychlorobyphenyls, and DDT in tissues of three species of Anatidae from the Ebro Delta (Spain) - G. A. Llorente; A. Farran; X. Ruiz; J. Albaigs (Archives of Environmental Contamination and Toxicology, 1987)

Stabilization of chitin synthetase and purification of chitosomes from several mycelial Mucorales - G. Martinez-Cadena; E. Lopez-Romero; I. Acosta; C. Gonzales; J. Ruiz-Herrera (Antonie van Leeuwenhoek, 1987)

An examination of factors affecting the instability of Saccharomyces cerevisiae glucan synthetase in cell free extracts - F. Leal; J. Ruiz-Herrera; J. R. Villanueva; G. Larriba (Archives of Microbiology, 1984)

Nucleotide sequence relationships among thirty peanut stunt virus isolates determined by competition hybridization - J. R. Daz-Ruiz; J. M. Kaper (Archives of Virology, 1983)

Correlation between extracellular polysaccharide composition and nodulating ability inRhizobium trifolii - Miguel A. Caviedes; Manuel Megias; Antonio M. Gil; Antonio J. Palomares; Francisco Ruiz-Berraquero (Archives of Microbiology, 1982)

Proteins specified by African swine fever virus - E. Tabarés; J. Martinez; F. Ruiz Gonzalvo; C. Sánchez-Botija (Archives of Virology, 1980)

Characteristics of the H2 oxidizing system in soybean nodule bacteroids - Toms Ruiz-Argeso; David W. Emerich; Harold J. Evans (Archives of Microbiology, 1979)

Hydrogen production and uptake by pea nodules as affected by strains of Rhizobium leguminosarum - Tomas Ruiz-Argeso; Joe Hanus; Harold J. Evans (Archives of Microbiology, 1978)

Properties of ?-glucan synthetase from Saccharomyces cerevisiae - E. Lpez-Romero; J. Ruiz-Herrera (Antonie van Leeuwenhoek, 1978)

Synthesis of chitin by particulate preparations from Aspergillus flavus - E. Lpez-Romero; J. Ruiz-Herrera (Antonie van Leeuwenhoek, 1976)

A physiological study of formate dehydrogenase, formate oxidase and hydrogenlyase fromEscherichia coli K-12 - J. Ruiz-Herrera; A. Alvarez (Antonie van Leeuwenhoek, 1972)

Induction of isoenzymes of alcohol dehydrogenase in ?flor? yeast - M.a J. Fernndez; C. Gmez-Moreno; M. Ruiz-Amil (Archives of Microbiology, 1972)

Cellular distribution of yeast pyruvate decarboxylase, and its induction by glucose - M. Ruiz-Amil; Ma. J. Fernndez; L. Medrano; M. Losada (Archives of Microbiology, 1966)

Virus multiplication and interferon production at different temperatures in adult mice infected with Coxsackie B 1 Virus - J. Ruiz-Gomez; J. Sosa-Martinez (Archives of Virology, 1965)

Condensation of ?-ketobutyrate and acetyl-CoA in baker's yeast - J. L. Canovas; M. Ruiz-Amil; M. Losada (Archives of Microbiology, 1965)